Athens and the War on Public Space: Tracing a City in Crisis - Klara Jaya Brekke; Christos Filippidis; Antonis Vradis (punctum books, 2018)
Drifting away from an eerily empty avenue, a lonely figure heads downstairs, into a metro station… Sometimes, the maelstrom of a crisis can be captured in a single image. The image of the mundane, barely noticeable movement of an urban dweller as they go about their everyday life. Athens and the War on Public Space commences from images just like this one, collected over a two-year period of research (2012–2014) in Athens during a time of severe financial and political crisis. For the author-curators of this volume, public space became a light-sensitive surface upon which they could begin to map the material imprints of the most structural and violent characteristics of the crisis, and their research spread in different directions, tracking the role of infrastructure and the shifts the financial crisis brought about upon built environments, the violent manifestations of the official anti-migrant policy, the rise of racism, the imposition of the emergency upon public space, and the phenomenology of mass transit. The book first provides a chronological, visual timeline highlighting major events and their impacts on public spaces from the beginnings of the global financial crisis in 2008 until mid-2014. This is followed by an essay by Christos Filippidis, “Biopolitical Narratives against a White Background: Medical Police as City Cartographer,” which analyses the ways in which the collective presence of migrants in Athenian public space was criminalised through policies of informal bans on public gatherings under the pretext of hygienic arguments. In the following chapter, “Mapping Racist Violence,” Klara Jaya Brekke provides an analogue version of the online Crisis-Scape map (http://map.crisis-scape.net/) of incidences of violent racist attacks experienced by migrants in Greece during the crisis. Antonis Vradis contributes two chapters — “The Utter Violence of the Unuttered” and “Metronome” — that reflect, in textual and visual (photographic) modes, on the Athenian metro as a point of departure for revealing and understanding the antagonisms and tensions that grew in this quintessential everyday space as the crisis deepened. In the final chapter, “Performing the State of Emergency,” Christos Filippidis analyses the police attacks launched against squats and occupied social centers in Athens in early 2013, which he argues were attack against specific facets of public space. Athens and the War on Public Space is a compilation of work done during the larger Crisis-Scape project (http://crisis-scape.net/). The team comprised Klara Jaya Brekke, Dimitris Dalakoglou, Ross Domoney, Christos Filippidis, and Antonis Vradis.

Atlas of Petromodernity - Alexander Klose; Benjamin Steininger (punctum books, 2024)
The Atlas of Petromodernity is many things in one: historical and geographical non-fiction, cultural theory essay, and picture book. In forty-four short essays, inspired by an equal amount of pictorial findings, Klose and Steininger develop a technical, geographical, political, and speculative panorama of the declining era of petroleum modernity. The authors stroll through Baku, Rotterdam, and Louisiana, into Manchuria and through the Vienna Basin. They read Bertolt Brecht, technical manuals, and petroculture theory, and they listen to Neil Young. They go to the moon, through refineries and over highways emptied by the COVID-19 pandemic. They confront petrochemistry with petromelancholy, catalysis with catharsis, cosmos with cosmetics. The Atlas of Petromodernity tackles the contradictory ambivalences of a substance that has been vital for our epoch, and whose roles and meanings need to be understood in order to be able to leave this epoch behind.

Atopological Trilogy: Deleuze and Guattari - Zafer Aracagök (punctum books, 2015)
Atopological Trilogy creates new concepts for Deleuze-Guattarian thought without any heed for sectarian, sermonising, or dutiful readings of the philosophers. In Part I of the trilogy, “Becoming-Sexual of the Sexual,” Aracagök demonstrates the ways in which quantum theory and the concept of “complementarity” inform Deleuze and Guattari’s thought, especially in relation to “becoming” in general and “becoming-woman” and “becoming-queer” more particularly. Aracagök argues that the ways in which the philosophers put forward a ban on “becoming-man” with a certain degree of undecidability encapsulates (albeit in a cryptic form) other becomings, the most important of which is becoming-queer, or rather, the becoming-sexual of the sexual. In Part II: “Deleuze on Sound, Music, and Schizo-Incest,” Aracagök puts into resonance the sound, noise, and music (and the question) of schizo-incest with the intention of deterritorialising a notion of the meta-audible. If Kafka’s story, “The Investigations of a Dog” leads us to a realm of the “formless” which cannot be heard without destroying what we know as “hearing,” it also offers us a limit-experience of the meta-audible, which, when radicalised via the notions of “schizo-incest” and “self-shattering,” creates a line of flight that escapes even from the line of flight itself. All these maneuvers pose a serious challenge to Deleuze and Guattari, who claim that despite all his investigations, Kafka’s investigator dog is re-Oedipalised in the end. Proposing in the end a limit experience which Aracagök calls the “meta-audible,” he shows that Kafka’s more radical approach to sound creates a line of flight that escapes even from the line of flight itself. The final essay of the trilogy, “Clinical and Critical Perversion,” begins with the 19th-century crisis of an abyss presumed to be yawning between mimesis and diegesis ever since Plato. According to Aracagök, this takes the form of a crisis of the “political,” the repression of which becomes the mission of psychoanalytical discourse towards the end of the 19th century. This crisis finds another form of expression in George Büchner’s unfinished 1836 novella Lenz, relative to the audibility of a “terrible voice which is usually called silence.” If the disappearance of the “political” is related to the rise of psychoanalysis on the protocols of, first, hypnosis, and then, the “talking cure,” both of which privilege the presumed form of the voice of the analyst over the analysand’s silence (a psycho-politics?), Aracagök proposes re-distributing this process, calling renewed attention to the clinicalisation of perversion, along Deleuzian-Guattarian distinctions such as: surface and depth, critical and clinical, oedipal-incest and schizo-incest, leading to a re-evaluation of what Deleuze and Guattari might have meant by “homosexual-effusion” in their book Kafka: Toward a Minor Literature, all in order to deterritorialise the “political” under a new concept — namely, critical perversion. Ultimately, Atopological Trilogy offers the reader no safe grounds for preserving not only a philosophical identity but also not any identity, if only to be able to let you float in the air without any guidance à la Kafka’s “Red Indian.”

A Treatise on the Marvelous for Prestigious Museums - Daniel C. Remein (punctum books, 2018)
Wrapped in modernist architect Marcel Breuer’s 1971 addition to the Cleveland Museum of Art, A Treatise on the Marvelous for Prestigious Museums considers the global ecological catastrophe by way of a speculative address to the art museums of the future, revisiting mid-century modes of site-specificity and speculative collage as utopian practices for the present. Written over the course of a decade, the book insists on the continuing importance of the New American Poetry and Language poetics, and includes work in the tradition of the ongoing serial poem and documentary poetics. This full color edition reproduces the maps, diagrams, and facsimiles that adorn the treatise.

Aural History - Gila Ashtor (punctum books, 2020)
Aural History is an anti-memoir memoir of encountering devastating grief that uses experimental storytelling to recreate the winding, fractured path of loss and transformation. Written by a thirty-something psychotherapist and queer theorist, Aural History is structured as a sequence of three sections that each use different narrative styles to represent a distinctive stage in the protagonist’s evolving relationship to trauma. Aural History explores how a cascade of self-dissolving losses crisscrosses a girl’s coming of age. Through lyric prose, the first section follows a precocious tomboy whose fierce attachment to her father forces her, when he dies and she is twelve years old, to run the family bakery business, raise a delinquent younger brother, and take care of a destructive, volatile mother. In part two, scenes narrated in the third person illustrate a high-achieving high school student who is articulate and in control except for bouts of sudden and inchoate attractions, the first of which is to her severe and coaxing English teacher. The third story tells of her relation with a riveting, world-famous professor, interspersed with a tragic-comic series of dialogues between the protagonist and a cast of diverse psychotherapists as she, now twenty-five years old and living in New York City, undertakes an odyssey to understand why true self-knowledge remains elusive and her real feelings, choked and incomplete. In what Phillip Lopate calls “an amazing document,” Aural History pushes the narrative conventions of memoir to capture a story the genre of memoir usually struggles to tell: that you can lose yourself, and have no way to know it.

Autotheory and Its Others - Becky McLaughlin; Eric Daffron; Maria Gil Ulldemolins; Kris Pint (punctum books, 2026)
Ever since Maggie Nelson’s Argonauts gave the word fresh currency a decade ago, autotheory has infiltrated scholarly, literary, and artistic practices. Autotheory and Its Others contributes to this nascent metacritical conversation. An inclusive discourse, autotheory embraces its uncanny double, allotheory, and, thus, this collection invites to the table a host of uncanny others: psychoanalysis, queer theory, and crip theory as well as art writing, postcriticism, and autofiction, among other genres and discourses. Bringing together four editors and thirteen contributors from both sides of the Atlantic, this collection of critical and creative-critical essays grapples with what it means to couple the personal with the theoretical. The volume’s chapters feature geographical settings as far-flung as New Zealand, Iran, and Mississippi and its wide-ranging topics include anecdotal theory and dialogia–theoria, the bodymind and illness, artificial intelligence and experimentation, accident and fantasy, collages and fragments, unlearning and autopractices, unknowing and the unconscious, uncertainty and art writing, narcissus and trauma, kudzu and pedagogy, memory and legend, autofabulation and religion, and lo-fi critique and academia. Ultimately, Autotheory and Its Others showcases this emergent genre’s diversity while also charting its multivalent future directions.

Ballads - Richard Owens (punctum books, 2015)
Ballads uses the lyric form to explore the effects of global Capitalism from a sharp Marxist perspective. Recognizing the congruence between folk song circulation and the circulation of money, the “currency” of the ballad alongside supply-side economics, Owens hails Wordworth’s Lyric Ballads experiment (undertaken at the dawn of England’s Industrial Age) as one touchstone. But he also understands the built-in obsolescence of the form, its tendency to hearken back to imaginary origins. “[E]veryone has an idea they know what a ballad is,” Owens writes in his “Working Notes.” “It’s this degraded thing shot through with a sense of pastness, cultural infancy and a charming but sometimes dangerous rusticity that needs to be carefully framed and reined.” Thus Owens’s Ballads playfully engages with language, figures, and forms from medieval and early modern England, with nods to the caesura-based, alliterative line, and Barbara Allan, Thomas the Rhymer, and Piers Plowman making appearances in the book’s brief lyrics.

Barge Life: On Jean Vigo's "L'Atalante" - Florian Deroo (punctum books, 2025)
Waves washing up against the hull, a bed and a small stove, the deck hatch sealed shut — the vessel is the ultimate dwelling. How to live together in cramped quarters? How to create a microcosm against hostile surroundings? In Barge Life, Florian Deroo tackles these questions by looking at a mythical classic of French cinema: Jean Vigo’s 1934 film L’Atalante. A work brimming with the energies of surrealism and anarchism, L’Atalante follows a young couple, two shipmates, and a clowder of cats who dwell in the belly of a river barge. Deroo offers a wide-ranging essay on the film, revealing how it lovingly delineates a small group that withdraws from the rhythms of modern life to establish a different kind of existence elsewhere. In L’Atalante’s most riveting moments, the river barge becomes a vehicle for a powerful fantasy: a supple and mobile collective life, lived in sensuous interdependence. Combining film criticism, philosophy, and biography, Deroo’s Barge Life reconsiders an important forerunner to the French New Wave and the early death of its director. Drawing readers into the intimately cramped living spaces of L’Atalante, Deroo explores the allure of retreating into a self-sufficient shelter, along with its intractable problems.

Barton Myers: Works of Architecture and Urbanism - Kris Miller-Fisher; Jocelyn Gibbs (punctum books, 2019)
Drawing on the vast archival resources of its Architecture and Design Collection, the UCSB Art, Design & Architecture Museum (University of California, Santa Barbara) presents an assessment of 50 years of design by Barton Myers (b. 1934), beginning with his work in the Toronto firm A.J. Diamond and Barton Myers (1967–1975) to his own offices in Toronto and Los Angeles, Barton Myers Associates (1975–present). Myers’s strongest architectural ideas come out of the planning strategies of his early neighborhood activism in 1970s Toronto, his grounding in history, and his training in the classical traditions of site and space planning. Barton Myers is an avowed urbanist—a self-described radical in his early advocacy of old-fashioned qualities like density, mixed-use of new and re-purposed materials, and contextual planning in the late 1960s when that fundamentally conservative position was considered counter-culture. Myers’ urban manifesto was codified in “Vacant Lottery,” the title of the Design Quarterly issue (https://www.amazon.com/Vacant-Lottery-Design-Quarterly-108/dp/B005NY1QOW) co-edited by Myers and Canadian architect and educator George Baird in 1978 and which led to a renewal of interest in urban planning and offered a strategy for increasing population densities within cities while preserving the existing residential fabric. The term lived on long past the journal’s circulation cycle as both an urban infill strategy and an acknowledgment of the ceding of city planning responsibility to the “lottery” of private developers. Myers’s design practice has thus always been a social justice practice as well. Myers is also a brilliant designer of residential houses that take advantage of local landscape contexts and adaptive reuse of building materials, including steel and glass. Five essays – on urban planning, civic structures, reuse of historic buildings, single- and multi-family housing, and theaters – reinforce Myers’s commitment to urbanism and reveal his flexibility with modes of modernism. Natalie Shivers introduces the early planning work in Toronto and traces the “vacant lottery” idea of neighborhood infill to the influential Grand Avenue project in Los Angeles. Howard Shubert examines the architectural and planning strategies, and political complexities, of several civic structures in Canada and the United States. Luis Hoyos explores Myers’s additions and adaptations to historic buildings in diverse urban contexts. Lauren Bricker focuses on the use of steel and other industrial materials in Myers’s houses and analyses the neighborhood-based designs of his multi-family housing. Charles Oakley describes the technical innovations, site planning, and historical underpinnings of Myers’s theaters and performance complexes.

Bathroom Songs: Eve Kosofsky Sedgwick as a Poet - Jason Edwards (punctum books, 2017)
Bathroom Songs: Eve Kosofsky Sedgwick as a Poet is the first book of essays to consider the poetry of one of the twentieth- and early twenty-first-century’s most important literary, affect, and queer theorists. Acclaimed as one of the “truly innovative” poets of her generation by Maud Ellmann, Sedgwick’s work as a poet is, perhaps, less well known, but is no less compelling than her ground-breaking trilogy of queer theoretical texts: Between Men: English Literature and Male Homosocial Desire, Epistemology of the Closet, and Tendencies. The book includes seven specially commissioned essays considering Sedgwick’s published poetry and writing about poets, by Angus Brown, Meg Boulton, Mary Baine Campbell, Jason Edwards, Kathryn R. Kent, Monica Pearl, and Benjamin Westwood, that range across the complete range of Sedgwick’s work, from her earliest published lyrics through her first collection of poetry, Fat Art, Thin Art, to her part-haiku, part-prose autobiography, A Dialogue on Love, and beyond. In addition, the book contains over forty of Sedgwick’s previously uncollected poems, ranging from her earliest poem on T.E. Lawrence to her final poem ‘Death’, introduced and contextualized by Edwards.

Beowulf: A Translation - David Hadbawnik (punctum books, 2012)
Many modern Beowulf translations, while excellent in their own ways, suffer from what Kathleen Biddick might call “melancholy” for an oral and aural way of poetic making. By and large, they tend to preserve certain familiar features of Anglo-Saxon verse as it has been constructed by editors, philologists, and translators: the emphasis on caesura and alliteration, with diction and syntax smoothed out for readability. The problem with, and the paradox of this desired outcome, especially as it concerns Anglo-Saxon poetry, is that we are left with a document that translates an entire organizing principle based on oral transmission (and perhaps composition) into a visual, textual realm of writing and reading. The sense of loss or nostalgia for the old form seems a necessary and ever-present shadow over modern Beowulfs. What happens, however, when a contemporary poet, quite simply, doesn’t bother with any such nostalgia? When the entire organizational apparatus of the poem—instead of being uneasily approximated in modern verse form—is itself translated into a modern organizing principle, i.e., the visual text? This is the approach that poet Thomas Meyer takes; as he writes, A glance anywhere in Meyer’s text demonstrates the stunning results. One place he turns it to especially good effect is the fight with Grendel in Fit 11, transforming the famously hyper-condensed syntax of the scene from a discouraging challenge for the translator into a visually pleasing strength: "The eyes of Hygelac’s kin watched the wicked raider execute his quick attack: without delay, snatching his first chance, a sleeping warrior, he tore him in two, chomped muscle, sucked veins’ gushing blood, gulped down his morsel, the dead man, chunk by chunk, hands, feet & all. & then footstephandclawfiendreachmanbedquicktrick beastarmpainclampnewnotknownheartrunflesho feargetawaygonowrunrun never before had sinherd feared anything so." Here the reader is confronted with the words themselves running together, as if in panic, in much the same way that the original passage seems in such a rush to tell the story of the battle that bodies become confused. This is just one example of the adventurous and provocative angle on Beowulf to which Meyer introduces us. His Beowulf—completed in 1972 but never before published—is sure to stretch readers’ ideas about what is possible in terms of translating Anglo-Saxon poetry, as well as provide new insights on the poem itself.

Beta Exercise: The Theory and Practice of Osamu Kanemura - Osamu Kanemura (punctum books, 2019)
Beta Exercise: The Theory and Practice of Osamu Kanemura is the first bilingual (Japanese-English) book to provide an overview of the theoretical work of Japanese photographer and video artist Osamu Kanemura, a unique talent and voice in the world of avant-garde contemporary photography. The opening essay “Life Is a Gift” meditates on the transformation of human life into an exchangeable commodity and the abstraction that entails. “Essay 01” develops Kanemura’s idea of photographic “technique” in an era when such techniques have become accessible to all, radically undermining the importance of human subjectivity in the process of capturing the photographic image: “We can say that modern technology constitutes photographic technique.” Instead, Kanemura argues, extra-technical elements such as concept and vision will have to compensate for the expression of individuality that technique is no longer able to convey. Taking cues from Kiyoshi Kurosawa and Karlheinz Stockhausen, the essay “Dead-Stick Landing” develops Kanemura’s theory of the moving image as mechanical system, solely governed by an “on-off switch,” while “Essay 02” develops these ideas into a consideration of cinematic time and the experience of boredom in cinema as the result of a truthful “loyalty” expressed to machines, and not to stories. The essays are accompanied by an extensive two-part interview with Italian photographer Marco Mazzi, touching upon topics ranging from the technical aspects of Kanemura’s equipment, the concept of non-editing, and the destruction of the frame to the similarity between Mao’s dialectics and the camera, the presence of the human figure as trace, and the politics of photographing Tokyo.

Between Species/Between Spaces: Art and Science on the Outer Cape - Kendra Sullivan; Dylan Gauthier (punctum books, 2020)
Between Species/Between Spaces assembles text and images resulting from a pilot artistic research residency hosted by the Cape Cod Modern House Trust and the Cape Cod National Seashore in Cape Cod, Massachusetts. Artists in the book reflect on the geological forces that are reshaping the landscape and ecology of the Outer Cape which illuminate and to some degree mirror the broader global dynamic of instability, loss, and transition we are facing as a result of anthropogenic climate change. The book collects new artworks in a variety of media by ten contemporary artists whose work investigates the relationships between ecological crisis, communities, individual subjects, and the environment – the result of collaborations between visiting artists and researchers at the NPS field station in the National Seashore. An introductory essay by Peter McMahon, founding director of the Cape Cod Modern House Trust, reflects on the Cape as a site of groundbreaking collaborations between artists, architects, designers, and scientists in the middle of the 20th century, led by visionaries Serge Chermayeff, Bernard Rudofsky, Gyorgy Kepes, and Marcel Breuer. An epistolary essay by NPS cartographer Mark Adams, who is also a painter, meditates on the Outer Cape as a site of community with an uncertain future; Adams’ own work has indicated that a predicted 4000 year timeframe for the Cape’s dunes and sandy shores to erode entirely into the sea may in fact be accelerating under climate change. Contributions by Adams, along with artists Jean Barberis, Joshua Edwards, Marie Lorenz, Nancy Nowacek, Jeff Williams, Lynn Xu, and Marina Zurkow and artist/curators Kendra Sullivan and Dylan Gauthier, who organized the residency and culminating exhibition, present multimodal research into species extinction, terraforming, ecological restoration and regenerative practices, as a window onto the past, present, and future of this unstable place.

Bigger Than You: Big Data and Obesity - Katherine Behar (punctum books, 2016)
In her first inquiry toward a decelerationist aesthetics, Katherine Behar explores in this essay chapbook the rise of two “big deal” contemporary phenomena, big data and obesity. In both, scale rearticulates the human as a diffuse informational pattern, causing important shifts in political form as well as aesthetic form. Bigness redraws relationships between the singular and the collective. Understood as informational patterns, collectives can be radically inclusive, even incorporating nonhumans. As a result, the political subject is slowly becoming a new object. This social and informational body belongs to no single individual, but is shared in solidarity with something “bigger than you.” In decelerationist aesthetics, the aesthetic properties, proclivities, and performances of objects come to defy the accelerationist imperative to be nimbly individuated. Decelerationist aesthetics rejects atomistic, liberal, humanist subjects; this unit of self is too consonant with capitalist relations and functions. Instead, decelerationist aesthetics favors transhuman sociality embodied in particulate, mattered objects; the aesthetic form of such objects resists capitalist speed and immediacy by taking back and taking up space and time. In just this way, big data calls into question the conventions by which humans are defined as discrete entities, and individual scales of agency are made to form central binding pillars of social existence through which bodies are drawn into relations of power and pathos.

Blasting the Canon - Ruth Kinna; Süreyyya Evren (punctum books, 2013)
What’s left to say about the anarchist canon? One answer might be that reflecting on the canon’s construction can help reveal something about the ways in which anarchism has been misunderstood. Another possibility is that it locates anarchism — in all its diversity and complexity — in particular geographical and historical locations. The canon not only establishes the parameters of anarchist theory, it sets them in a particular (European) context, serving as a springboard for subsequent revisions, developments and critiques. The canon describes a classic form, to use George Woodcock’s term – it benchmarks anarchism. Who constructed it, where did it come from — what are the implications of its reification in contemporary anarchist studies? How successful have recent critiques been in overcoming the limitations that canonical study has encouraged? What are the risks of leaving the canon intact, even if as a target for critique? Should anarchists worry about the explosion of the canon if the result is to include as ‘anarchist’ philosophers or movements who do identify with anarchist traditions? What does self-identification mean in the absence of a canon? Does the rejection of the canon imply the rejection of an anarchist history of ideas, and if such a history remains important in anarchism, how should it be approached and understood? In this special issue of Anarchist Developments in Cultural Studies (Issue 2013.1) edited by Ruth Kinna and Süreyyya Evren, noted anarchist scholars explore these questions.

Book of Anonymity - Anon Collective (punctum books, 2021)
Anonymity is highly contested, marking the limits of civil liberties and legality. Digital technologies of communication, identification, and surveillance put anonymity to the test. They challenge how anonymity can be achieved, and dismantled. Everyday digital practices and claims for transparency shape the ways in which anonymity is desired, done, and undone. The Book of Anonymity includes contributions by artists, anthropologists, sociologists, media scholars, and art historians. It features ethnographic research, conceptual work, and artistic practices conducted in France, Germany, India, Iran, Switzerland, the UK, and the US. From police to hacking cultures, from Bitcoin to sperm donation, from Yik-Yak to Amazon and IKEA, from DNA to Big Data — thirty essays address how the reconfiguration of anonymity transforms our concepts of privacy, property, self, kin, addiction, currency, and labor.

boy says: (a book with no ending) - Néstor Ponce (punctum books, 2024)
Where does your voice come from? The one you speak with, or the one you read with? What does it sound like when you read, silently, to yourself? There are the first influences, or at least the ones that first come to mind. But you quickly admit that there are others as well. The voices that emerged from different styles, tones, and patterns in books, stories, poems. From songs and television programs, family members and teachers. There are the voices that you don’t remember as voices, the words you don’t remember reading. This voice, this combination of symbols describing a translated book of poetry, for example, might be acknowledged as the very latest influence in your life. After leaving Argentina in exile during the dictatorship of the military junta (1976-1983), Néstor Ponce found his way to France, where he now lives. He has written that throughout his life, reading has connected him to a shifting, unstable set of voices—a community of readers and writers that crisscrosses borders of all kinds, unafraid of conflict and contradiction. boy says (a book with no ending) opens to that community with poems that are at once the words of one poet and the traces of an infinite number of poets, some of whom are explicitly named in the titles of the poems. This bilingual English-Spanish edition is an open library that is also a private one, made public. As you read, it might be difficult not to ask questions about Nazim Hikmet, Alejandra Pizarnik, Dina Posada, Eugenio Montale, Anna Greki, or Édouard Glissant. And it will be impossible to answer those questions without finding their books, opening them, and hearing your voice shaped by their and Ponce’s words.

Broken Narrative: The Politics of Contemporary Art in Albania - Marco Mazzi; Armando Lulaj (punctum books, 2022)
Broken Narrative provides an extensive reflection on history, politics, and contemporary art, revolving around the artistic practice of Albanian artist Armando Lulaj. The core of the book is formed by an extended interview of Lulaj by Italian artist and writer Marco Mazzi. This inquiry starts in the year 1997, a year of social and political upheaval in Albania, of anarchy, controversies, and emigration, of toxic seeds of neoliberalism sprouting in an already wounded country, and continues to today, where politics, hidden behind art forms, has practically destroyed (again) every different and possible future of Albania. This book also sketches out the connections between the recent Albanian political context and contemporary art by considering the realities of Albania as essential for an understanding of the dynamics of international power in contemporary art and architecture, and the role of politics therein. Broken Narrative is presented in a bilingual English–Japanese edition, in part as homage to the subtle esthetics of Japanese poetry, which has inspired many of Lulaj’s works, while equally evoking the subversive films of the Red Army, active in Japan at the turn of the 1960s and ’70s. Broken Narrative contains a double preface in English by Albanian scholar Jonida Gashi and in Japanese by photographer Osamu Kanemura.

Broken Records - Snežana Žabić (punctum books, 2016)
In 1991, Snežana Žabić lost her homeland and most of her family’s book and record collection during the Yugoslav Wars that had been sparked by Slobodan Milošević’s relentless pursuit of power. She became a teenage refugee, forced to flee Croatia and the atrocities of war that had leveled her hometown of Vukovar. She and her family remained refugees in Serbia until NATO bombed Belgrade in 1999. After witnessing the first nights of NATO’s bombing, Žabić took flight again. She moved from country to country, city to city, finally settling in Chicago. She realized — reluctantly, because she didn’t want to relive the past — that she had to write about what had happened, what she had left behind, and what she had lost. Broken Records is the story of this loss, told with unflinching honesty, free of sentimentality or sensationalism. For the very first time, we learn how it felt to be first a regular teenager during the breakup of Yugoslavia and the ensuing wars, and then a 30-something adult, perennially troubled by one’s uprooted existence. Broken Records is not a neat narrative but a bit of everything — part bildungsroman, part memoir, part political poetry, part personal pop culture compendium. And while Žabić represents a Yugoslav diasporan subject, her book also belongs to an international generation whose formative years straddle the Cold War and the global reconfiguration of wealth and power, whose lives were spent shifting from the vinyl/analog era to the cyber/digital era. This generation knows that when they were told about history ending, they were told a lie.

Broken Theory - Alan Sondheim (punctum books, 2022)
Broken Theory is a jettisoned collection of fragmentary writing, collected and collaged by new media artist, writer, musician, and theorist Alan Sondheim. Folding theoretical musings, text experiments, and personal confessions into a single textual flow, it examines the somatic foundations of philosophical theory and theorizing, discussing their relationships to the writer and body, and to the phenomenology of failure and fragility of philosophy’s production. Writing remains writing, undercuts and corrects itself, is always superseded, always produced within an untoward and bespoke silo—not as an inconceivable last word, but instead a broken contribution to philosophical thinking. The book is based on fragmentation and collapse, displacing annihilation and wandering towards a form of “roiling” within which the text teeters on the verge of disintegration. In other words, the writing develops momentary scaffoldings—writing shored up by the very mechanisms that threaten its disappearance. Broken Theory is prefaced by a text from Maria Damon and followed by an extensive interview with art historian Ryan Whyte.

Building Black: Towards Antiracist Architecture - Elliot C. Mason (punctum books, 2022)
Building Black: Towards Antiracist Architecture brings together Black Studies and architectural theory. Only recently have architecture and urban planning started to confront their constitution of race as a social referent as well as their part in the establishment of racist logics. This confrontation usually results in projects that respond to their surroundings, that merge into a changing and multicultural city. Building Black, however, proposes the construction of a radical Black position: building islands of resistance against the expanding sea of imperial architecture. In Building Black, Mason reads the racial meaning of current construction projects in England through the histories of race and architecture. Closely reading Immanuel Kant’s formulation of the Subject as the creator of space and the development of whiteness in Modernist architecture, Mason finds that Blackness is an ongoing, antecedent island that can never quite be subsumed in the racializing project of modernity. Pushing this further, he positions antiracist architecture on a self-enclosed island de-linked from the city, preserving a sociality that cannot be incorporated into liberal universality. Alongside sustained critiques of architectural theory and Western philosophy, and close engagements with Black Studies and Indigenous thinking, Mason offer a critique of the writing subject as a collaborator in the racialization of urban cartography. In response, Mason turns inwards, opening the impossibility of the writer’s position in architecture and philosophy, and setting up an alternative mode of self-critical architectural writing.

Bullied: The Story of an Abuse - Jonathan Alexander (punctum books, 2021)
What happens when the defining moment of your life might be a figment of your imagination? How do you understand—and live with—definitive feelings of having been abused when the origin of those feelings won’t adhere to a singular event but are rather diffused across years of experience? In Bullied: The Story of an Abuse, Jonathan Alexander meditates on how, as a young man, he struggled with the realization that the story he’d been telling himself about being abused by a favorite uncle as a child might actually just have been a “story”—a story he told himself and others to justify both his lifelong struggle with anxiety and to explain his attraction to other men. Story though it was, Alexander maintains that some form of abuse did occur. In writing that is at turns reflective, analytic, and hallucinatory, Alexander traces what it means to suffer homophobic abuse when such is diffused across multiple actors and locales, implicating a family, a school, a culture, and a politics—as opposed to a singular individual who just happened to be the only openly gay man in young Alexander’s life. Along the way, Alexander reflects on Jussie Smollett, drug abuse, MAGA-capped boys, sadomasochism, Catholic priests, cruising, teaching young adult fiction about rape, and a host of other oddly but intimately related topics.

Burn after Reading: Vol. 1, Miniature Manifestos for a Post/medieval Studies + Vol. 2, The Future We Want: A Collaboration - Eileen A. Joy; Myra Seaman; Jeffrey Jerome Cohen (punctum books, 2014)
The essays, manifestos, rants, screeds, pleas, soliloquies, telegrams, broadsides, eulogies, songs, harangues, confessions, laments, and acts of poetic terrorism in these two volumes — which collectively form an academic “rave” — were culled, with some later additions, from roundtable sessions at the International Congress on Medieval Studies in 2012 and 2013, organized by postmedieval: a journal for medieval cultural studies (http://www.palgrave-journals.com/pmed/index.html) and the BABEL Working Group (http://www.babelworkinggroup.org) (“Burn After Reading: Miniature Manifestos for a Post/medieval Studies,” “Fuck This: On Letting Go,” and “Fuck Me: On Never Letting Go”) and George Washington University’s Medieval and Early Modern Studies Institute (http://www.gwmemsi.com/) (“The Future We Want: A Collaboration”), respectively. Gathering together a rowdy multiplicity of voices from within medieval and early modern studies, these two volumes seek to extend and intensify a conversation about how to shape premodern studies, and also the humanities, in the years ahead. Authors in both volumes, in various ways, lay claim to the act(s) of manifesting, and also anti-manifesting, as a collective endeavor that works on behalf of the future without laying any belligerent claims upon it, where we might craft new spaces for the University-at-large, which is also a University that wanders, that is never just somewhere, dwelling in the partitive — of a particular place — but rather, seeks to be everywhere, always on the move, pandemic, uncontainable, and always to-come, while also being present/between us (manifest). This is not a book, but a blueprint. It is also an ephemeral gathering in the present tense.

Burning Diagrams in Anthropology: An Inverse Museum - Tristan Partridge (punctum books, 2024)
Burning Diagrams in Anthropology examines the use of diagrams in anthropology to reimagine how we think about, and challenge, intellectual histories. Highlighting the impossibility of escaping what different disciplines and institutions deem to be “past,” the author combines critical analysis of selected diagrams with an expansive, exploratory reimmersion in their aesthetic, ethical, and political potential. Diagrams persist. Yet while other visual components of scholarly work—especially photography, cartography, and film—have been subject to significant critical scrutiny, diagrams have received far less reflexive attention. Reversing this trend, Partridge presents a collection of 52 diagrams, covering a period of 150 years, to create an “inverse museum”—a space where the collection matters less than reactions to it. While the images are drawn from sociocultural anthropology, they are discussed in dialogue with approaches from philosophy, postcolonial studies, architecture, aesthetics, posthumanism, and critical art theory. Dissecting the notion of The Canon in order to confront academic complicity in hierarchical and racialized relations of inequality, the figurative burning of the title refers to how we might prepare the ground for scholarly work that meets the immediate, collective needs of an Earth in crisis—not least, by refusing adherence to disciplinary normalcy. By refusing this adherence, Partridge reaffirms knowledge creation in general, and anthropology in particular, as deeply ethical, creative, and relational processes.

By Kelman Out of Pessoa - Doug Nufer (punctum books, 2023)
In 2002, Doug Nufer wrote a story narrated by a tout, who proposed a novel way to beat the races. It was so absurd and ludicrous it gave him an idea. So Nufer went to Emerald Downs, home of thoroughbred racing in the Northwest. There, he split himself into three characters modeled on the heteronyms of Fernando Pessoa. Using a money management plan from a James Kelman short story, Nufer gave these characters money and set them free to gamble. He returned to the track every week for a full season, and his characters / heteronyms continued to bet, with real money and in the name of art. At the end of the season, he had pages of data in the form of a wagering diary, the outcome of a literary experiment that formed the basis of a literal experimental novel. This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

Centaurs, Rioting in Thessaly: Memory and the Classical World - Martyn Hudson (punctum books, 2018)
This book treads new paths through the labyrinths of our human thought. It meanders through the darkness to encounter the monsters at the heart of the maze: Minotaurs, Centaurs, Automata, Makers, Humans. One part of our human thought emerges from classical Ionia and Greek civilisation more generally. We obsessively return to that thought, tread again its pathways, re-enact its stories, repeat its motifs and gestures. We return time and time again to construct and re-construct the beings which were part of its cosmology and mythology – stories enacted from a classical world which is itself at once imaginary and material. The “Never Never Lands” of the ancient world contain fabulous beasts and humans and landscapes of desire and violence. We encounter the rioting Centaurs there and never again cease to conjure them up time and time again through our history. The Centaur mythologies display a fascination with animals and what binds and divides human beings from them. The Centaur hints ultimately at the idea of the genesis of civilisation itself. The Labyrinth, constructed by Daedalus, is itself a prison and a way of thinking about making, designing, and human aspiration. Designed by humans it offers mysteries that would be repeated time and time again – a motif which is replicated through human history. Daedalus himself is an archetype for creation and mastery, the designer of artefacts and machines which would be the beginning of forays into the total domination of nature. Centaurs, Labyrinths, Automata offer clues to the origins and ultimately the futures of humanity and what might come after it.

Chaste Cinematics - Victor J. Vitanza (punctum books, 2015)
Victor J. Vitanza continues to rethink the problem of sexual violence in cinema and how rape is often represented in “chaste” ways, in the form of a Chaste Cinematics. Vitanza continues to discuss Chaste Cinematics as participating in transdisciplinary-rhetorical traditions that establish the very foundations (groundings, points of stasis) for nation states and cultures. In this offering, however, the initial grounding for the discussions is “base materialism” (George Bataille): divine filth, the sacred and profane. It is this post-philosophical base materialism that destabilizes binaries, fixedness, and brings forth excluded thirds. Vitanza asks: why is it that a repressed third, or a third figure, returns, most strangely as a “product” of rape and torture? He works with Jean-Paul Sartre and Page duBois’s suggestion that the “product” is a new “species.” Always attempting unorthodox ways of approaching social problems, Vitanza organizes his table of contents as a DVD menu of “Extras” (supplements). This menu includes Alternate Endings and Easter Eggs as well as an Excursus, which invokes readers to take up the political exigency of the DVD-Book. Vitanza’s first “Extra” studies a trio of films that need to be reconsidered, given what they offer as insights into Chaste Cinematics: Amadeus (a mad god), Henry Fool (a foolish god), and Multiple Maniacs (a divine god who is raped and eats excrement). The second examines Helke Sander’s documentary Liberators Take Liberties, which re-thinks the rapes of German women by the Russians and Allies during the Battle of Berlin. The third rethinks Margie Strosser’s video-film Rape Stories that calls for revenge. In the Alternate Endings, Vitanza rethinks the problem of reversibility in G. Noé’s Irréversible. In the Easter Eggs, he considers Dominique Laporte’s “the Irreparable,” as the object of loss and Giorgio Agamben’s “the Irreparable,” as hope in what is without remedy. The result is not another film-studies book, but a new genre, a new set of rhetorics, for new ways of thinking about cinematics, perhaps postcinematics.

An Anthology of Asemic Handwriting - Tim Gaze; Michael Jacobson (punctum books, 2013)
An Anthology of Asemic Handwriting is the first book-length publication to collect the work of a community of writers on the edges of illegibility. Asemic writing is a galaxy-sized style of writing, which is everywhere yet remains largely unknown. For human observers, asemic writing may appear as lightning from a storm, a crack in the sidewalk, or the tail of a comet. But despite these observations, asemic writing is not everything: it is just an essential component, a newborn supernova dropped from a calligrapher’s hand. Asemic writing is simultaneously communicating with the past and the future of writing, from the earliest undeciphered writing systems to the xenolinguistics of the stars; it follows a peregrination from the preliterate, beyond the verbal, finally ending in a postliterate condition in which visual language has superseded words. An Anthology of Asemic Handwriting is compiled and edited by Tim Gaze from Asemic magazine and Michael Jacobson from The New Post-Literate blog. An Anthology of Asemic Handwriting has contributions by Reed Altemus, mIEKAL aND, Rosaire Appel, Francesco Aprile, Roy Arenella, Derek Beaulieu, Pat Bell, John M. Bennett, Francesca Biasetton, Volodymyr Bilyk, Tony Burhouse & Rob Glew, Nancy Burr, Riccardo Cavallo, Mauro Césari, Peter Ciccariello, Andrew Clark, Carlfriedrich Claus, Bob Cobbing, Patrick Collier, Robert Corydon, Jeff Crouch, Marilyn Dammann, Donna Maria Decreeft, Alessandro De Francesco, Monica Dengo, Mirtha Dermisache, Bill Dimichele, Christian Dotremont, Jean Dubuffet, Max Ernst, Mark Firth, Eckhard Gerdes, Mike Getsiv, Jean-Christophe Giacottino, Marco Giovenale, Meg Green, Brion Gysin, Jefferson Hansen, Huai Su, Geof Huth, Isidore Isou, Michael Jacobson, Satu Kaikkonen, Jukka-Pekka Kervinen, Rashid Koraishi, Irene Koronas, Edward Kulemin, Le Quoc Viet & Tran Trọng Duong, Jim Leftwich, Misha Magazinnik, Matt Margo, André Masson, Nuno de Matos, Willi Melnikov, Morita Shiryu, Sheila E. Murphy, Nguyen Duc Dung, Nguyen Quang Thang, Pham Van Tuan, François Poyet, Kerri Pullo, Lars Px, Marilyn R. Rosenberg, Roland Sabatier, Ekaterina Samigulina & Yuli Ilyshchanska, Alain Satié, Karen L. Schiff, Spencer Selby, Peggy Shearn, Ahmed Shibrain, Gary Shipley, Christopher Skinner, Hélène Smith, Lin Tarczynski, Morgan Taubert, Andrew Topel, Cecil Touchon, Louise Tournay, Tran Trọng Duong, Lawrence Upton, Sergio Uzal, Marc van Elburg, Nico Vassilakis, Glynda Velasco, Simon Vinkenoog, Vsevolod Vlaskine, Cornelis Vleeskens, Anthony Vodraska, Voynich Manuscript, Jim Wittenberg, Michael Yip, Logan K. Young, Yorda Yuan, Camille Zehenne, Zhang Xu, and others.

And Another Thing: Nonanthropocentrism and Art - Katherine Behar; Emmy Mikelson (punctum books, 2016)
In And Another Thing: Nonanthropocentrism and Art, Katherine Behar and Emmy Mikelson explore how artists engage with nonanthropocentrism, one of the primary tenets shared by recent speculative realist and new materialist philosophies. Extending their investigations in And Another Thing, an exhibition which the authors curated in 2011 (http://www.artnet.com/magazineus/news/artnetnews/the-art-of-things-at-cuny-graduate-center.asp), this volume documents both that exhibition and expands on two of its curatorial aims: prioritizing art historical contexts for contemporary philosophy (rather than the other way around), and apprehending artworks as historically specific objects of philosophy. The book is organized in three sections. In the first section, Behar and Mikelson provide long-form essays that chart the evolution of nonanthropocentrism and art, spanning eighteenth-century architectural drawing, performance, minimalist sculpture, and contemporary postminimalism. These essays raise the stakes for art and speculative realism, showing how artists have figured and prefigured nonanthropocentric ideas strikingly similar to those expounded in various “new” realist, materialist, and speculativist philosophies. Literally occupying the center of the volume, in section two, the exhibition is represented by full-color plates of eleven works by Carl Andre, Laura Carton, Valie Export, Regina José Galindo, Tom Kotik, Mary Lucking, Bruce Nauman, Grit Ruhland, Anthony Titus, Ruslan Trusewych, and Zimoun. Artworks by these emerging and canonical figures lay bare the networks of alliances underlying the exhibition. The book concludes with three short meditations on the relation between nonanthropocentrism and art, and what that relation might portend for future thought. These essays, by Bill Brown, Patricia Ticineto Clough, and Robert Jackson, are speculative in the sense that they perceive potentials for theory arising from nonanthropocentrism’s manifestations in art.

An Edition of Miles Hogarde's A Mirroure of Myserie - Sebastian Sobecki (punctum books, 2021)
This is the first edition of A Mirroure of Myserie (1557), a poem by the Catholic propagandist Miles Hogarde and probably presented to Queen Mary. Cast as a dream vision, this combative dialogue draws on William Langland’s widely circulating medieval poem The Vision of Piers Plowman and offers a critical assessment of sixteenth-century morality in England. The Mirroure of Myserie has been edited from Huntington Library MS 121 and is accompanied by a short introduction. This accessible edition preserves Hogarde’s original spelling but adds modern punctuation and glosses of all unfamiliar words and concepts.

A Neo Tropical Companion - Jamie Stewart (punctum books, 2012)
A Neo Tropical Companion is the first collection of haikus written by Xiu Xiu (http://xiuxiu.org/) singer, Jamie Stewart. This is the first time his haikus, which have been featured in several literary journals and small press releases, will be comprehensively collected. Two thirds of the work will include new poems written for specifically for this book. The title, A Neo Tropical Companion, comes from an antiquated guide book to North East South America that Stewart found molding on the ground in the jungle. The poems, written in the classical Japanese poetry form, concern death, uncertainty, cats, being on weird tours, horrible sex, hating other people, bird watching in Guyana, and growing up in a dim and boxed-in valley.

Anglo-Saxon(ist) Pasts, postSaxon Futures - Donna-Beth Ellard (punctum books, 2019)
We are all, no matter how little we like it, the bearers of unwanted and often shunned memory, of a history whose infiltrations are at times so stealthy we can pretend otherwise, and at times so loud we can’t hear much of anything else. We’re still here — there differently than those before us, but there, otherwise known as here. And that matters for writers. That’s the first intuition. The second one is that it seems a lot of us here when asked to talk about race are most comfortable, or least uncomfortable, talking about it in the language of scandal. It’s so satisfying so clear, so easy. The wronged. The evildoers. The undeserving. The shady. The good intentions and the cyclical manipulations. The righteous side taking, the head shaking. Scandal is such a helpful, such a relieving distraction. There are times when scandal feels like the sun that race revolves around. And it is so hard to reel conversations about race back from the heavy gravitational pull of where we so often prefer them to be. Beth Loffreda and Claudia Rankine Anglo-Saxon(ist) Pasts, postSaxon Futures traces the integral role that colonialism and racism play in the field formerly known as Anglo-Saxon studies by tracking the development of the “Anglo-Saxonist,” an overtly racialized term that describes a person whose affinities are grounded in white nationalism. That scholars continue to call themselves “Anglo-Saxonists,” despite urgent calls to combat racism within the field, suggests that this term is much more than just a professional appellative. It is, this book argues, a ghost in the machine of early medieval studies—a spectral figure created by a group of nineteenth-century historians, archaeologists, and philologists responsible for not only framing the interdisciplinary field of “Anglo-Saxon” studies but for also encoding ideologies of British colonialism and Anglo-American racism within the field’s methods and pedagogies. As Ellard herself writes, “When asked what I ‘do,’ I have found myself searching for words, calling myself ‘a former Anglo-Saxonist,’ ‘a recovering Anglo-Saxonist,’ or one who simply ‘works with Old English and Latin.’…Despite repeated awkwardness and embarrassment, I still can’t bring myself to return to the comfort of these old, inherited terms, and I have learned to sit in the professional blank space that has, for me, come to replace ‘Anglo-Saxonist.’…Many other paths, however, are possible, and in invoking the place-holder ‘postSaxon,’ this book hopes to begin a conversation within a once-‘Anglo Saxon’ studies that does not set its sights on coming up with new signifiers to replace old ones without excavating their troubled histories and the ways in which they give support to some of the most violent supporters of white supremacist beliefs. Rather, I hope that our shared field, whatever we might call it, will work privately and publicly to recognize that, whatever the ‘love objects’ that keep us affectively tied to ‘Anglo-Saxon’ and ‘Anglo-Saxonist,’ we must value and enact the work of mourning that will free us from these harmful ghosts.” Anglo-Saxon(ist) pasts, postSaxon Futures is at once a historiography of Anglo-Saxon studies, a mourning of its Anglo-Saxonist “fathers,” and an exorcism of the colonial-racial ghosts that lurk within the field’s scholarly methods and pedagogies. Part intellectual history, part grief work, this book leverages the genres of literary criticism, auto-ethnography, and creative nonfiction in order to confront Anglo-Saxonist pasts such that we can begin to imagine speculative postSaxon futures inclusive of voices and bodies heretofore excluded from the field formerly known as Anglo-Saxon studies.

Animal Emotions: How They Drive Human Behavior - Christian Montag; Kenneth L. Davis (punctum books, 2020)
Animal Emotions: How They Drive Human Behavior gives a concise overview of ancient mammalian emotions deeply rooted in the human brain. Jaak Panksepp, a world-renowned neuroscientist, dedicated his life career to the study of mammalian emotions and he carved out seven distinct emotional systems he called seeking, lust, care, and play (positive emotions), and fear, anger, and sadness (negative emotions), all exerting a tremendous influence on human behavior. Christian Montag, a neuroscientist and psychologist, and a long-time collaborator of Jaak Panksepp, revisits together with Kenneth L. Davis, one of Jaak’s PhD students, Panksepp’s theories and provides the reader with new insights into the nature of emotions and their role as survival tools, both for animals and for humans. They also raise new questions about the background of the research field Jaak Panksepp coined “Affective Neuroscience.” How are personality and psychopathology linked to animal emotions? Do animals feel the same way as we do? What are our emotional needs in a digital society, and what is key to a happy life?

Animal, Vegetable, Mineral: Ethics and Objects - Jeffrey Jerome Cohen (punctum books, 2012)
Animal, Mineral, Vegetable examines what happens when we cease to assume that only humans exert agency. Through a careful examination of medieval, early modern and contemporary lifeworlds, these essays collectively argue against ecological anthropocentricity. Sheep, wolves, camels, flowers, chairs, magnets, landscapes, refuse and gems are more than mere objects. They act; they withdraw; they make demands; they connect within lively networks that might foster a new humanism, or that might proceed with indifference towards human affairs. Through what ethics do we respond to these activities and forces? To what futures do these creatures and objects invite us, especially when they appear within the texts and cultures of the “distant” past.

Annotations to Geoffrey Hill's Speech! Speech! - Ann Hassan (punctum books, 2012)
Geoffrey Hill’s Speech! Speech! (2000) encapsulates two thousand years’ worth of utterances in a symbolic act of remembrance and expression of despair for the current age, in which we find “our minds and ears fouled by degraded public speech—by media hype, insipid sermons, hollow political rhetoric, and the ritual misuse of words.” Through 120 densely allusive stanzas—“As many as the days that were | of SODOM”—the poem wrestles this condition from within, fighting fire with fire in an alchemical symbolic labour that transmutes the dross of corrupt and clichéd idiom into a dynamic logopoeia which proves true Hill’s persistent claim: “genuinely difficult art is truly democratic.” Such is the weird, ambivalently hostile position of poetry in the present world and thus the space of our real connection to it: “Whatever strange relationship we have with the poem, it is not one of enjoyment. It is more like being brushed past, or aside, by an alien being” (Hill). Befriending this estrangement, embracing it as a more amicable brushing-up-against, Hassan’s Annotations is a thorough and patient explication of Speech! Speech! that both clarifies and deepens the poem’s difficulties, illuminating its polyphonic language and careening discursive movement. The author’s method is at once commentarial, descriptive, and narratorial, staying faithfully with the poem and following its complex verbal and logical turns. The book generously provides, rather than direct interpretative incursion, a more durable and productive document of “the true nature / of this achievement” (stanza 92), a capacious, open understanding of the text that will prove invaluable to its present and future readers.

Anthropocene Unseen: A Lexicon - Cymene Howe; Anand Pandian (punctum books, 2020)
The idea of the Anthropocene often generates an overwhelming sense of abjection or apathy. It occupies the imagination as a set of circumstances that counterpose individual human actors against ungraspable scales and impossible odds. There is much at stake in how we understand the implications of this planetary imagination, and how to plot paths from this present to other less troubling futures. With Anthropocene Unseen: A Lexicon, the editors aim at a resource helpful for this task: a catalog of ways to pluralize and radicalize our picture of the Anthropocene, to make it speak more effectively to a wider range of contemporary human societies and circumstances. Organized as a lexicon for troubled times, each entry in this book recognizes the gravity of the global forecasts that invest the present with its widespread air of crisis, urgency, and apocalyptic possibility. Each also finds value in smaller scales of analysis, capturing the magnitude of an epoch in the unique resonances afforded by a single word. The Holocene may have been the age in which we learned our letters, but we are faced now with circumstances that demand more experimental plasticity. Alternative ways of perceiving a moment can bring a halt to habitual action, opening a space for slantwise movements through the shock of the unexpected. Each small essay in this lexicon is meant to do just this, drawing from anthropology, literary studies, artistic practice, and other humanistic endeavors to open up the range of possible action by contributing some other concrete way of seeing the present. Each entry proposes a different way of conceiving this Earth from some grounded place, always in a manner that aims to provoke a different imagination of the Anthropocene as a whole. The Anthropocene is a world-engulfing concept, drawing every thing and being imaginable into its purview, both in terms of geographic scale and temporal duration. Pronouncing an epoch in our own name may seem the ultimate act of apex species self-aggrandizement, a picture of the world as dominated by ourselves. Can we learn new ways of being in the face of this challenge, approaching the transmogrification of the ecosphere in a spirit of experimentation rather than catastrophic risk and existential dismay? This lexicon is meant as a site to imagine and explore what human beings can do differently with this time, and with its sense of peril.

Antiracism Inc. Why the Way We Talk about Racial Justice Matters - Felice Blake; Paula Ioanide; Alison Reed (punctum books, 2019)
Antiracism Inc. traces the ways people along the political spectrum appropriate, incorporate, and neutralize antiracist discourses to perpetuate injustice. It also examines the ways organizers continue to struggle for racial justice in the context of such appropriations. Antiracism Inc. reveals how antiracist claims can be used to propagate racism, and what we can do about it. While related to colorblind, multicultural, and diversity discourses, the appropriation of antiracist rhetoric as a strategy for advancing neoliberal and neoconservative agendas is a unique phenomenon that requires careful interrogation and analysis. Those who co-opt antiracist language and practice do not necessarily deny racial difference, biases, or inequalities. Instead, by performing themselves conservatively as non-racists or liberally as ‘authentic’ antiracists, they purport to be aligned with racial justice even while advancing the logics and practices of systemic racism. Antiracism Inc. considers new ways of struggling toward racial justice in a world that constantly steals and misuses radical ideas and practices. The critical essays, interviews, and poetry collected here focus on people and methods that do not seek inclusion in the hierarchical order of gendered racial capitalism. Rather, they focus on aggrieved peoples who have always had to negotiate state violence and cultural erasure, but who also work to build the worlds they envision. These collectivities seek to transform social structures and establish a new social warrant guided by what W.E.B. Du Bois called “abolition democracy,” a way of being and thinking that privileges people, mutual interdependence, and ecological harmony over individualist self-aggrandizement and profits. Further, these aggrieved collectivities reshape social relations away from the violence and alienation inherent to gendered racial capitalism, and towards the well-being of the commons. Antiracism Inc. articulates methodologies that strive toward freedom dreams without imposing monolithic or authoritative definitions of resistance. Because power seeks to neutralize revolutionary action through incorporation as much as through elimination, these freedom dreams, as well as the language used to articulate them, are constantly transformed through the critical and creative interventions stemming from the active engagement in liberation struggles. In addition to critical essays by Felice Blake (“How Does Black Cultural Criticism ‘Work’ in the Age of Antiracist Incorporation?”), Kevin Fellezs (“Nahenahe [Soft, Sweet, Melodious], the Sound of Kanaka Maoli [Native Hawaiian] Refusal”), Daniel Martinez HoSang (“A Wider Type of Freedom”), Paula Ioanide (“Defensive Appropriations”), George Lipsitz (“The Logic of ‘Illogical’ Opposition: Tools and Tactics for Tough Times”), Alison Reed (“Gentrifying Disciplines: The Institutional Management of Trauma and Creative Dissent”), Phia S. Salter + Glenn Adams (“Provisional Strategies for Decolonizing Consciousness”), and Barbara Tomlinson (“Wicked Problems and Intersectionality Telephone”), the volume also includes poetry by Dubian Ade, Jari Bradley, Dahlak Brathwaite, Corinne Contreras, Ebony P. Donnley, Colin Masashi Ehara, David Scott (YDS), Daniel Hershel Silber-Baker, and Sophia Terazawa, as well as interviews with Diana Zuñiga (CURB, Californians United for a Responsible Budget) and with Gaby Hernandez and Marissa Garcia (PODER, People Organizing for the Defense and Equal Rights of Santa Barbara Youth).

A Nuclear Refrain: Emotion, Empire, and the Democratic Potential of Protest - Kye Askins; Phil Johnstone; Kelvin Mason (punctum books, 2019)
A Nuclear Refrain is a spatial fiction, and miniature chapbook (measuring 4 X 6 inches), that critiques the policy of nuclear deterrence, the concept of Mutually Assured Destruction, and the UK’s decision to replace its Vanguard submarines, the so-called Trident replacement. (https://en.wikipedia.org/wiki/Trident_(UK_nuclear_programme)) We challenge that decision via extending our geographical imaginations into the past, present, and future. Noting the more usual economic, moral, and strategic objections to Trident and its replacement, A Nuclear Refrain considers the issues from less familiar perspectives, vis-a-vis the emotional and embodied, empire and the establishment, and democratic potentialities. Set against the authors’ ongoing participation in extensive public protests against the UK’s decision to replace Trident in 2016, A Nuclear Refrain disrupts familiar academic and policy forms of writing. It is “an uncomfortable hybrid between academia and fiction,” intent on discomfiting the reader to spur the radical reimagining of a world profoundly shaped by the threat of nuclear weapons. Inspired by author and social critic Charles Dickens, this book draws on the form of A Christmas Carol. Transported by “ghosts” of the nuclear past, present and future, a pro-Trident British policy maker, the Right Honourable Roger C. Bezeeneos, has his perceptions sorely challenged. But will Roger allow his feelings to influence his decision-making? Will he recognize the yearning for an empire lost that mobilizes the British establishment? And will he admit the suppression of political participation that a commitment to nuclear deterrence determines? It’s your call, Roger.

An Unspecific Dog: Artifacts of This Late Stage in History - Joshua Rothes (punctum books, 2017)
A nationwide survey conducted by an institute for philosophical research has determined that nihilists, on the whole, have good intentions. In An Unspecific Dog, Joshua Rothes collects 150 short texts as fables for our time, a veritable catalog of agnotology, a series of situations and propositions that revel in the dark irony at the root of our early-twenty-first-century existence. The subjects of these texts are caught between vocabularies, between contingency and certainty, the interim in which certain kind of ironic vitality exists, where tragedy and humor are equally likely and often deeply entangled. Rothes reminds us that language acts as a mirror for human experience, in that through it we can never really see the backs of our own heads.

Ardea: A Philosophical Novella - Freya Mathews (punctum books, 2016)
What is soul? Can it be forfeited? Can it be traded away? If it can, what would ensue? What consequences would follow from loss of soul — for the individual, for society, for the earth? In the early nineteenth century, Goethe’s hero, Faust, became a defining archetype of modernity, a harbinger of the existential possibilities and moral complexities of the modern condition. But today the dire consequences of the Faustian pact with the devil are becoming alarmingly visible. In light of this, how would Goethe’s arguably flawed drama play out in a 21st-century century setting? Would a contemporary Faust sign up to a demonic deal? Indeed what, in the wake of two hundred years of social and economic development, would be left for the devil to offer him? A contemporary Faust would already possess everything the original Faust in his ascetic cloister lacked — affluence and mobility; celebrity and worldly influence; access to information; religious choice; sexual freedom and the availability of women — though women, it must be noted, currently also partake of that same freedom. The only thing a present-day Faust would lack would be his soul. Would he miss it? Does soul even exist? If it does, it would of course be the one thing the devil could not bestow. So from what or whom could Faust retrieve it? What, in a word, would a contemporary Faust most deeply desire? In pursuit of these questions, Ardea engages a familiar but possibly faulty archetype, that of Faust, with an unfamiliar one, that of the white heron, borrowed from a short story of the same name by nineteenth-century American author, Sarah Orne Jewett. In Jewett’s tale, a soul-pact of an entirely different kind from that entered into by Faust is proposed. It is a pact with the wild, a pledge of fealty, of non-forfeiture, that promises to redraw the violent psycho-sexual and psycho-spiritual patterns that have underpinned modernity. How would a present-day heir to the Faustian tradition, ingrained with the habit of entitlement but also burdened with the consequences of the old pact, respond to the new proposition?

A Reference Grammar of Kunuz Nubian - Ahmed Sokarno Abdel-Hafiz (punctum books, 2026)
A Reference Grammar of Kunuz Nubian is a dissertation by Ahmed Sokarno Abdel-Hafiz, completed in 1988 at SUNY, Buffalo, which has remained unpublished for nearly thirty years. Already an indispensable standard work in Nubian linguistics, owing to its wide and unofficial circulation, it tackles the phonetics, phonology, morphology, and syntax of Kunuz Nubian, a Nile Nubian language spoken in Egypt. It remains the only systematic overview of this language, whereas the closely related Dongolawi–Andaandi, spoken in the Sudan, has been described in Armbruster’s Dongolese: A Grammar (1960). This new edition, prepared in the context of the Dotawo: Monographs series, will give this work of scholarship its well-deserved and long overdue published form. A Reference Grammar of Kunuz Nubian includes a new preface by the author, as well as an appendix with several essays on topics in Kunuz Nubian linguistics, including question formation and benefactives.

A Refuge for Jae-in Doe and Other Fugues - Seo-Young Chu (punctum books, 2026)
A Refuge for Jae-in Doe and Other Fugues is the lyric memoir of Korean American survivor Seo-Young (Jennie) Chu. It is also a meta-memoir, one that is aware of its makeshift nature, poses questions about the genre(s) it inhabits, and self-consciously reflects on what it means to write autobiographically. Throughout the book, Chu experiments with the first-person singular “I,” tracing the polyphonies always implicit in the memoirist’s first-person singular voice. Writing polyphonically allows Chu to explore the plurality within her “I,” the uncanny homes she has found in dissociation, the appeal of other-than-first-person pronouns as sites of autobiographical consciousness, as well as the literal and figurative fugue states—from spells of incantatory writing to oneiric re-namings of the self—in which Chu finds refuge from intergenerational distress and rape trauma. Moving from one fugue state to another, Chu explores a wide range of topics relevant to her meta-autobiography, including the nature of time, the history of the sonnet, code-switching, suicidal ideation, the model minority myth, late-stage capitalism, institutional violence, rape culture, standardized tests, the Korean Demilitarized Zone, what it means to read a book, and what it means to be a self.

Artificial Earth: A Genealogy of Planetary Technicity - J. Daniel Andersson (punctum books, 2023)
Artificial Earth: A Genealogy of Planetary Technicity offers an intellectual history of humanity as a geological force, focusing on a prevalent contradiction in the Anthropocene discourse on global environmental change: on the one hand, it has been argued that there are hardly any pristine environments anymore, to the degree that the concept of nature has lost its meaning; while on the other, that anthropogenic environmental change has become so prevailing that it ought to be conceived of as a force of nature, in the literal sense of the expression. Artificial Earth argues that to fully grasp the stakes of this discourse, we need not only understand the contemporary scientific and technological transformations behind the Anthropocene, but also explore the history of an ontological concern tied up with it. In order to do so, Artificial Earth examines reflections on the ontological dualism between nature and artifice within the history of earth science from the late eighteenth century onwards. Paying particular attention to its consequences for how human subjectivity has been conceptualized in the Anthropocene, it then enrolls these resources in an effort to problematize attempts since the 1980s to formalize earth science in systems theory terminology. In sum, the aim is to investigate the historical conditions for the possibility of conceiving human artifice as an integral part of the earth’s terrestrial environment, with the conviction that such an investigation may assist in resolving the aforementioned contradiction or at least to understand it better by tracing its historical lineage.

A Rushed Quality - David Odell (punctum books, 2015)
These fragments collected here (in two books, “A Rushed Quality” and “Bodying Forth”) belong neither to philosophy nor to poetry — and yet they are for the most part focused on a substantial area of overlap between these two venerable disciplines, vis-à-vis the question, “What is it like to be X?” Philosophers like to fill in the X with something exotic like a bat or a dolphin, or even an Artificial Intelligence, while poets tend to fill it with something else, equally exotic, namely themselves. For the diffident and introspective author of A Rushed Quality and Bodying Forth, the X, while definitely human, is perhaps someone in general, equally distant from and equally intimate with both the writer and the reader in the very moment of their eponymous activity. The start of it all was the perception of what was called the “rushed quality,” as something persistent and bothersome and of which there was no question of its ever being shed. Rather than evaded or denied, it was welcomed because it seemed for the first time since childhood to mark a structural occurrence presenting a new metaphysical datum. As it happened, this quality proved very elusive in its mature bothersomeness and the inquiry into it soon turned into a sort of quasi-theoretical fascination, which took as its main theme the fate of pure subjectivity — the utterly unfunctional, utterly useless, utterly dispensible feeling of being. The rushed quality is perhaps merely the sense of it draining away, or its long-sustained decrescendo. There are a number of ideas that run through many of the fragments, motivating beliefs of the writer, such as the inexhaustability and ungraspability of the moment, the existence of a direct connection to reality which is betrayed in every attempt to formulate it, and a skepticism about the bad infinities latent in the natural attitude. And of course there is a continued dialogue with various more or less identifiable thinkers and positions. But again, this is not philosophy, the arguments are virtual, and the stakes are something entirely different. Each of these pieces emerged in a renewed relation to the blank page. It is hoped that for the reader, apart from any resonances they may set in motion, they retain some of the qualities of silence, expectation, and impossibility that gave birth to them.

A Sanctuary of Sounds - Andreas Burckhardt (punctum books, 2013)
A Sanctuary of Sounds is an aural rewriting of William Faulkner’s novel Sanctuary (1931). A polyphonic object. A garden — assemblage of blooms, of affects, of sounds, of meaning. An invitation to rethink appropriation ethically, aesthetically, and epistemologically. The appropriation of a body of work, of a physical body, of an idea, of data. The history of knowledge and its production is enabled by the process of appropriation, by the differentiation of noise. A Sanctuary of Sounds is a noise–totality. Noise — nothing but noise. Noise as the first object of metaphysics. Noise as the synchronic/diachronic mediator of production–processes and their reorganization in society. Utopia and dystopia at once. A Sanctuary of Sounds is a dialectical poem, it is noise against noise — raping a rape.

As If: Essays in As You Like It - William N. West (punctum books, 2016)
Shakespeare’s As You Like It is a play without a theme. Instead, it repeatedly poses one question in a variety of forms: What if the world were other than it is? As You Like It is a set of experiments in which its characters conditionally change an aspect of their world and see what comes of it: what if I were not a girl but a man? What if I were not a duke, but someone like Robin Hood? What if I were a deer? “What would you say to me now an [that is, “if”] I were your very, very Rosalind?” (4.1.64-65). “Much virtue in ‘if’,” as one of its characters declares near the play’s end; ‘if’ is virtual. It releases force even if the force is not that of what is the case. Change one thing in the world, the play asks, and how else does everything change? In As You Like It, unlike Shakespeare’s other plays, the characters themselves are both experiment and experimenters. They assert something about the world that they know is not the case, and their fictions let them explore what would happen if it were—and not only if it were, but something, not otherwise apparent, about how it is now. What is as you like it? What is it that you, or anyone, really likes or wants? The characters of As You Like It stand in "if" as at a hinge of thought and action, conscious that they desire something, not wholly capable of getting it, not even able to say what it is. Their awareness that the world could be different than it is, is a step towards making it something that they wish it to be, and towards learning what that would be. Their audiences are not exempt. As You Like It doesn’t tell us that it knows what we like and will give it to us. It pushes us to find out. Over the course of the play, characters and audiences experiment with other ways the world could be and come closer to learning what they do like, and how their world can be more as they like it. By exploring ways the world can be different than it is, the characters of As You Like It strive to make the world a place in which they can be at home, not as a utopia—Arden may promise that, but certainly doesn’t fulfill it—but as an ongoing work of living. We get a sense at the play’s end not that things have been settled once and for all, but that the characters have taken time to breathe—to live in their new situations until they discover better ones, or until they discover newer desires. As You Like It, in other words, is a kind of essay: a set of tests or attempts to be differently in the world, and to see what happens. These essays in As If: As You Like It, originally commissioned as an introductory guide for students, actors, and admirers of the play, trace the force and virtue of some of the claims of the play that run counter to what is the case—its "ifs."

Asterisks - Matthew Cheney (punctum books, 2027)
Asterisks collects thirteen essays that explore literature, cinema, history, and queerness, while persistently returning to the question of how to write, create, and live in a world roiled by fascism and suffering. Beginning with memories of growing up with a father who was a gun dealer and participating in AIDS activism in the 1990s, Matthew Cheney brings together ideas about violence, oppression, horror, and ideology that get carried into explorations of works by Virginia Woolf, H.P. Lovecraft, Clive Barker, Kristine Ong Muslim, Kate Zambreno, James Purdy, Jarett Kobek, Jeff VanderMeer, and many others. Along the way, Asterisks delves into the theater of Charles Ludlam, Battlestar Galactica, the films of Derek Jarman, mass shootings, the art of David Wojnarowicz, and the sentences of John Keene. Asterisks roams and meanders, finding insight in juxtapositions, coincidences, cracks, and margins. For all of its meanderings, however, Asterisks returns persistently to questions of American violence, queer identity, the fascination with abominations, and the vexed relationship between aesthetics and ethics. Always, Cheney asks: How do we live? What and where is community? And what can art do in a world on fire?

A Story of Witchery - Jennifer Calkins (punctum books, 2024)
Fantasy, fear, and freedom all play a part in A Story of Witchery, a book-length narrative poem by Jennifer Calkins, and newly illustrated by Thor Harris. Here we meet Emily, our “small and weedy” protagonist, an orphan complicit (perhaps) in her own abandonment who is caught up, as poet Amy Gerstler writes in her Introduction, in a story “entwined with science facts and twisted clinical fictions.” In language rolling and tripping with spare precision, Calkins makes a modern pilgrim’s progress into the imagination and the dark world of medicine. Rich and haunting images create a seemingly familiar environment which, like the internal landscape of the protagonist, dissolves only to reform, until finally resolving into a healed whole. This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

Chaucer's Comic Providence - Janet Thormann; Aranye Fradenburg Joy (punctum books, 2023)
Chaucer’s Comic Providence presents readings of five of Chaucer’s Canterbury Tales that dramatize sexual division and the lack of rapport between the sexes. These readings are founded on the psychoanalytic thinking of Jacques Lacan in his rereading of Freud and are motivated by Thormann’s conviction that Chaucer understood what psychoanalysis would come to study as an unconscious operating in the subject that is independent of conscious control and desire. For psychoanalysis, the subject is interminably engaged with unconscious sexual difference and with what Lacan saw as the absence of sexual rapport. Chaucer’s Comic Providence analyzes Chaucer’s plots of sexual adventures, mishaps, and surprise to show how the five tales dramatize the lack of symmetry and absence of accord between the sexes. Ultimately, Thormann’s interest here is in the ways these five narratives represent and deal with sexual division, in their means of handling what, in any case, cannot be avoided or mastered. Consequently, the resolutions of the narratives sponsor an ethics of desire: they affirm sexual pleasure and acknowledge misprision and limitation, but they do not compromise, close down, or finish with incompatibility, contraction, and limitation. Her reading, then, claims that Chaucer’s poetry already reveals the unconscious that Freud is credited with discovering. As well, Chaucer not only anticipates Lacan’s pronouncement that “the unconscious is structured like a language,” but also his emphasis on unconscious sexual difference and the absence of rapport between the sexes. With few exceptions, while there has been much consideration of gender in Chaucer’s stories, contemporary criticism of Chaucer has remained inimical or, at the least, largely indifferent, to psychoanalysis, yet because it considers both difference and continuity, change and perpetuation, and because it incorporates psychic processes, motives, functions, and dynamics operating outside of conscious awareness, psychoanalysis offers a wider range for analysis of Chaucer’s tales than does gender theory alone. Chaucer’s Comic Providence also addresses the unexpected, surprising, and providentially comic resolutions of Chaucer’s tales, the concomitant abeyance of sexual conflicts, and the links between emergence and abeyance, which issue in the hope of a beneficent future.

Christina McPhee: A Commonplace Book - Eileen A. Joy (punctum books, 2017)
Christina McPhee’s ‘commonplace book’ draws from a palimpsest of handwritten notes, lists, quotations, bibliographic fragments, and sketches, from an artist whose voracious reading practice is a direct feed into her life and art — all set to a visual and textual design-as-score, as prominent writers on painting, media arts, performance, video installation and poetics engage with her ‘open-work’ practice. Christina McPhee’s images move from within a matrix of abstraction, shadowing figures and contingent effects. The tactics of living are in subterfuge, like the dazzle ships of camouflage in war. This ‘commonplace book’ develops a view of recent work in collaged paintings, drawings, photomontage and video installation, around themes of environmental transformation and ‘post-natural’ community. The book includes conversations, essays, interviews and notes by Ina Blom, Phil King, James MacDevitt, Donata Marletta, Melissa Potter, Judith Rodenbeck, Esztar Timár, and Frazer Ward. Christina McPhee’s work is in museum collections, including the Whitney Museum of American Art, New York, the International Center for Photography, New York, the Kemper Museum of Contemporary Art, Kansas City, Thresholds New Media Collection, Scotland, and elsewhere. Her work has shown in solo exhibitions at American Unversity Museum, Washington, DC; Bildmuseet, Umea, Sweden, and in group exhibitions including documenta 12 and Bucharest Biennial 3. McPhee lives and works in California, and you can see more about her work at her website (http://www.christinamcphee.net/).

Cinema's Doppelgängers - Doug Dibbern (punctum books, 2021)
Cinema’s Doppelgängers is a counterfactual history of the cinema—or, perhaps, a work of speculative fiction in the guise of a scholarly history of film and movie guide. That is, it’s a history of the movies written from an alternative unfolding of historical time—a world in which neither the Bolsheviks nor the Nazis came to power, and thus a world in which Sergei Eisenstein never made movies and German filmmakers like Fritz Lang never fled to Hollywood, a world in which the talkies were invented in 1936 rather than 1927, in which the French New Wave critics didn’t become filmmakers, and in which Hitchcock never came to Hollywood. The book attempts, on the one hand, to explore and expand upon the intrinsically creative nature of all historical writing; like all works of fiction, its ultimate goal is to be a work of art in and of itself. But it also aims, on the other hand, to be a legitimate examination of the relationship between the economic and political organization of nations and film industries and the resulting aesthetics of film and thus of the dominant ideas and values of film scholarship and criticism.

Clinical Encounters in Sexuality: Psychoanalytic Practice and Queer Theory - Noreen Giffney; Eve Watson (punctum books, 2017)
Clinical Encounters in Sexuality makes an intervention into the fields of clinical psychoanalysis and sexuality studies, in an effort to think about a range of issues relating to sexuality from a clinical psychoanalytic perspective. This book concentrates on a number of concepts, namely identity, desire, pleasure, perversion, ethics and discourse. The editors, Noreen Giffney and Eve Watson, have chosen queer theory, a sub-field of sexuality studies, as an interlocutor for the clinical contributors, because it is at the forefront of theoretical considerations of sexuality, as well as being both reliant upon and suspicious of psychoanalysis as a clinical practice and discourse. The book brings together a number of psychoanalytic schools of thought and clinical approaches, which are sometimes at odds with one another and thus tend not to engage in dialogue about divisive theoretical concepts and matters of clinical technique. Traditions represented here include: Freudian, Kleinian, Independent, Lacanian, Jungian, and Relational. The volume also stages, for the first time, a sustained clinical psychoanalytic engagement with queer theory. By virtue of its editorial design, this book aims to foster a self-reflective attitude in clinical readers about sexuality which historically has tended toward reification. The central questions we present to readers to think about are: • 1. What are the discourses of sexuality underpinning psychoanalysis, and how do they impact on clinical practice? • 2. In what ways does sexuality get played out for, and between, the psychoanalytic practitioner and the patient? • 3. How do social, cultural and historical attitudes towards sexuality impact on the transference and countertransference, consciously and unconsciously? • 4. Why is sexuality so prone to reification? Divided into three sections, Clinical Encounters in Sexuality begins with six chapters on important themes in queer theory: identity, desire, perversion, pleasure, discourse and ethics. Section two includes fourteen responses to the chapters in section one by practising psychoanalysts and psychoanalytic psychotherapists from a number of traditions. They work with adults and/or children and adolescents. Section three features seven short commentaries on the nature of the encounters enacted by the book, by leading thinkers whose own clinical practice and/or theoretical work engages directly with both discourses: psychoanalytic and queer. The book is edited by two psychoanalytic practitioners — one Kleinian, one Freudian-Lacanian — who also have research expertise in sexuality studies. All pieces are new and have been commissioned.

Closer to Dust - Sara A. Rich (punctum books, 2021)
No one thinks straight. At least no one remembers straight. But ten years ago, things were different, weren’t they? Roland Barthes once wrote that color in a photograph is like make-up on a corpse. No one is fooled. In anarchic denial of convenient truths, a young international couple meet and marry on a small Mediterranean island. Ten years later, the couple separate in part due to complications with immigration laws. Following this transcontinental rupture, fragmented histories emerge in response to the woman’s encounters with a series of color snapshots. There is death here, familiar to the mourner, as the photographs issue their special powers to magically and auspiciously predict the future and simultaneously to permit the return of the dead. The woman recognizes pieces of herself as past objects indexed within photographic stills, but paradoxically, she is present, outside in this chaos trying not to fall apart. The images and their objects yawn to remind us of the reluctant destiny of all our beloved memories, bodies, and things: that is, to disintegrate. Borrowing its title from a passage in The Emigrants by W.G. Sebald, Closer to Dust is a séance, a gathering of invitees: inherently biased elegies, the images that conjured them, and the reader- viewer in attendance who is warmly invited to order these intimate fragments into cohesion.

CMOK to YOu To: A Correspondence - Nina Živančević; Marc James Léger (punctum books, 2016)
CMOK to YOu To presents the 2015 email correspondence of the Serbian-born poet, art critic and playwright Nina Živančević and Canadian cultural theorist Marc James Léger. In December of 2014 Léger invited Živančević to contribute a text to the second volume of the book he was editing, The Idea of the Avant Garde – And What It Means Today (http://www.manchesteruniversitypress.co.uk/9780719096914/). Taken with each other’s idiosyncrasies, their correspondence gradually shifted from amiable professional exchanges and the eventual failure to organize a scholarly event to that of collaborating on some kind of writing project. Several titles were attempted for the eventual book – Marshmallow Muse: The Exact and Irreverent Letters of MJL and NZ, The Orange Jelly Bean, or, I Already Am Eating from the Trash Can All the Time: The Name of This Trash Can Is Ideology, The Secreted Correspondence of Mme Chatelet and Voltaire, and I’m Taken: The E-Pistolary Poetry of Kit le Minx and Cad – but none of these proved to be more telling than CMOK, the Serbian word for kiss, which sums up the authors’ quest for “harmony” in an altogether imperfect world and literary medium. In this book, names of real people were changed in order to protect those who might otherwise be offended by the unguarded and absurdist commentary of its authors. Despite this fact, it is the fragility and elasticity of the writers’ superegos that is tested as they vacillate from personal registers to intellectual strata. At once a cis-avant-gardist’s exploration of anti-art and a poet’s claim to some weak form of autonomy, CMOK delights in both the pleasures of casual email and the sublime realizations of Jacques Lacan’s theory of sexuation. CMOK is a hybrid genre and a quest into the real of virtuality that defies the literary standards. Its authors, who never met, answer one another’s basic needs and questions, separated as they are by time zones and the ocean, but not culturally or spiritually.

Come As You Are, After Eve Kosofsky Sedgwick - Eve Kosofsky Sedgwick; Jonathan Goldberg (punctum books, 2021)
Come As You Are, After Eve Kosofsky Sedgwick brings together two pieces of writing. In the first, “After Eve Kosofsky Sedgwick,” Jonathan Goldberg assesses Sedgwick’s legacy, prompted mainly by writing about Sedgwick’s work that has appeared in the years since her death in April 2009. Writings by Lauren Berlant, Jane Gallop, Katy Hawkins, Scott Herring, Lana Lin, and Philomina Tsoukala are among those considered as Goldberg explores questions of queer temporality and the breaching of ontological divides. Primary concerns include the relationship of Sedgwick’s later work on Proust, fiber, and Buddhism to her fundamental contribution to queer theory, and the axes of identification across difference that motivated her work and attachment to it. “Come As You Are,” the second piece of writing, is a previously unpublished talk Sedgwick gave in 1999–2000. It represents a significant bridge between her earlier and later work, sharing with her book Tendencies the ambition to discover the “something” that makes queer inextinguishable. In this piece, Sedgwick does that via a contemplation of her own mortality alongside her creative engagement with Buddhist thought, especially the in-between states named bardos and her newfound energy for making things. These were represented in a show of her fabric art, “Floating Columns/In the Bardo,” that accompanied her talk, a number of images of which are included in this book. They feature floating figures suspended in the realization of death. They are objects produced by Sedgwick, made of fabric; they come from her, yet are discontinuous with her, occupying a mode of existence that exceeds the span of human life and the confines of individual identity. They could be put beside the queer transitive identifications across difference that Goldberg’s essay explores.

Commonist Tendencies: Mutual Aid beyond Communism - Jeff Shantz (punctum books, 2013)
As capitalist societies in the twenty-first century move from crisis to crisis, oppositional movements in the global North have been somewhat stymied (despite ephemeral manifestations like Occupy), confronted with the pressing need to develop organizational infrastructures that might prepare the ground for a real, and durable, alternative. More and more, the need to develop shared infrastructural resources — what Shantz terms “infrastructures of resistance” — becomes apparent. Ecological disaster (through crises of capital), economic crisis, political austerity, and mass produced fear and phobia all require organizational preparation — the common building of real world alternatives. There is, as necessary as ever, a need to think through what we, as non-elites, exploited, and oppressed, want and how we might get it. There is an urgency to pursue constructive approaches to meet common needs. For many, the constructive vision and practice for meeting social needs (individual and collective) is expressed as commonism — an aspiration of mutual aid, sharing, and common good or common wealth collectively determined and arrived at. The term commonsim is a useful way to discuss the goals and aspirations of oppositional movements, the movement of movements, because it returns to social struggle the emphasis on commonality — a common wealth — that has been lost in the histories of previous movements that subsumed the commons within mechanisms of state control, regulation, and accounting — namely communism. In the current context, commonism, and the desire for commons, speaks to collective expressions against enclosure, now instituted as privatization, in various realms. While the central feature of capitalism is the commodity — a collectively produced good controlled for sale by private entities claiming ownership — the central feature of post-capitalist societies is the commons. These counter-forces have always been in conflict throughout the history of capitalism’s imposition. And this conflict has been engaged in the various spheres of human life, as mentioned above. Commonism (and commonist struggles), is expressed in intersections of sites of human activity and sustenance: ecological, social, and ideational. Examples of ecological commonism include conservation efforts, indigenous land reclamations and re-occupations (and blockades of development), and community gardens, to name only a few. Social commons include childcare networks, food and housing shares, factory occupations, and solidarity economics (including but not limited to community cooperatives). Ideational commons include creative commons, opens source software, and data liberation (such as Anonymous and Wikileaks). This becomes procreative or constructive. It provides a spreading base for eco-social development beyond state capitalist control. It also moves movements from momentary spectacles or defensive stances or reactive “fightbacks.” Commonism affirms and asserts different ways of doing things, of living, of interacting. This book engages various commonist tendencies. It examines communism, including overlooked or forgotten tendencies. It provides an exploration of primitive accumulation and mutual aid as elements of struggle. Attention is given to constructive aspects of commonist politics from self-valorization against capital to gift economies against the market. It finally speaks to the need of movements to build infrastructures of resistance that sustain struggles for the commons. Written by a longtime activist/scholar, this is a work that will be of interest to community organizers and activists as well as students of social movements, social change, and radical politics. It will be taken up by people directly involved in specific community movements as well as students in a range of disciplines (including sociology, politics, geography, anthropology, cultural studies, and social policy). There is no book that offers such a concise, readable discussion of the issues in the current context, with particular emphasis on anarchist intersections with communism.

Complementary Modernisms in China and the United States: Art as Life/Art as Idea - Bruce Robertson; Zhang Jian (punctum books, 2020)
Complementary Modernisms in China and the United States: Art as Life/Art as Idea is the result of a conference where Chinese and Americanist art historians addressed the development of modernism in their respective cultural traditions. The chapters juxtapose historical developments without attempting to map connections or influences. Instead, both national modernisms are presented as part of the larger terrain of global modernism, but generated within specific, localized circumstances. This juxtaposition reveals significant differences as much as any particular moments of connection or similarities, disrupting any standard narrative of the primacy of French (or European) avant-garde art and its influence on more belated and peripheral communities. The differences that are revealed are not merely the result of the very different historical trajectories of each country’s moves into modernity. Rather, differences in attention and methodology are just as important, in particular the focus on the post-1980 development of Chinese art as part of the modernization of Chinese culture and economy, rather than the American perspective on post-1980s postmodern qualities. At the same time, significant convergent concerns emerge, such as the importance of urban centers and urbanization, the profound effect of political and technological disruption, and the question of identity.The volume represent a cross-section of Chinese and Americanist art historians, both early career and senior scholars, working on a wide variety of subjects, such as the Ashcan School, Impressionism, Cai Liang, Liang Sicheng, Huang Binhong, Cézanne, Bauhaus, Joseph Cornell, Andrew Wyeth, Louise Nevelson, Jackson Pollock, Andy Warhol, and contemporary art more broadly, with (as is usual in any survey of the 20th century these days) a concentration on the 1960s.

Complementary Modernisms in China and the United States: Art as Life/Art as Idea [BW] - Jian Zhang; Bruce Robertson (punctum books, 2020)
Complementary Modernisms in China and the United States: Art as Life/Art as Idea is the result of a conference where Chinese and Americanist art historians addressed the development of modernism in their respective cultural traditions. The chapters juxtapose historical developments without attempting to map connections or influences. Instead, both national modernisms are presented as part of the larger terrain of global modernism, but generated within specific, localized circumstances. This juxtaposition reveals significant differences as much as any particular moments of connection or similarities, disrupting any standard narrative of the primacy of French (or European) avant-garde art and its influence on more belated and peripheral communities. The differences that are revealed are not merely the result of the very different historical trajectories of each country’s moves into modernity. Rather, differences in attention and methodology are just as important, in particular the focus on the post-1980 development of Chinese art as part of the modernization of Chinese culture and economy, rather than the American perspective on post-1980s postmodern qualities. At the same time, significant convergent concerns emerge, such as the importance of urban centers and urbanization, the profound effect of political and technological disruption, and the question of identity.The volume represent a cross-section of Chinese and Americanist art historians, both early career and senior scholars, working on a wide variety of subjects, such as the Ashcan School, Impressionism, Cai Liang, Liang Sicheng, Huang Binhong, Cézanne, Bauhaus, Joseph Cornell, Andrew Wyeth, Louise Nevelson, Jackson Pollock, Andy Warhol, and contemporary art more broadly, with (as is usual in any survey of the 20th century these days) a concentration on the 1960s.

continent. Year 1: A Selection of Issues 1.1–1.4 - Jamie Allen; Vincent W.J. van Gerven Oei; Adam Staley Groves; Nico Jenkins; Paul Boshears (punctum books, 2012)
continent. Year 1: A selection of issues 1.1-1.4 collects a variety of thoughts and tropes from the 2011 issues of continent., ranging from work on Greek poetry to deep brain recordings, from speculative realism to the fragments as a unit of prose, and from queer theory to mass murder. This collection presents the fruits of an intense collaboration throughout the different zones of the Academy.

Continuum - Alessandro De Francesco (punctum books, 2015)

Continuum 2: Writings – Scritti – Écrits 2015–2022 - Alessandro De Francesco (punctum books, 2024)
This volume gathers Alessandro De Francesco’s essays and theoretical writings produced from 2015 to 2022. It follows the first volume, Continuum: Writings on Poetry as Artistic Practice, reuniting essays written between 2007 and 2015. The title of this new volume could only be Continuum 2, given that the underlying concept remains the same: to testify to the seamless continuity of the author’s commitment to poetry and art over the years, and to reaffirm at the same time, on a theoretical level, a model of creation and thinking as a continuous flow, not discretized, not quantized, but organic, liquid, without end or beginning — a kind of linguistic translation of the space-time in which every text, like every other object, is necessarily immersed. Continuum 2 is a trilingual book, containing writings in English, French, and Italian, and it is particularly focused on two lines of inquiry: the author’s ongoing meditation on poetic practice, and his new investigation into seventeenth-century art, poetry, and forms of thought.

Continuum: Writings on Poetry as Artistic Practice - Alessandro De Francesco (punctum books, 2015)
Continuum: Writings on Poetry as Artistic Practice reunites the most part of the essays and articles produced between 2007 and 2015 by poet and artist Alessandro De Francesco. It shows what De Francesco himself affirms at a point in the last text of the book: that an artist can also be a theorist, and that artistic practice and theoretical practice are difficult to distinguish in his work. This book is multilingual: each text was left in the language in which it was written. Therefore, it is predominantly in French, but Italian, English and German are also represented. In spite of poetry being at the center of Alessandro De Francesco’s interests as a thinker, the texts contained in this book are very heterogeneous: poetic statements, essays, scientific articles, lectures, interviews; and yet they also show a deep continuity. Continuum stands for the author’s uninterrupted commitment for poetry, for the numerous connections among the approached themes, and especially for the innovatory theoretical and political positions expressed here, from which all these writings originated.

Corporeal Aesth/ethics: The Body in Bracha L. Ettinger's Theory and Art - Anna Kisiel (punctum books, 2026)
Can we think of an ethics that originates in corporeality, and not in codified or symbolic systems? In Corporeal Aesth/ethics, the body resurfaces as a central category of Bracha L. Ettinger’s theory and art, as well as an interpretive key that allows us to assume ethical responsibility for an Other who is not abstract, or distant, or total. Ettinger’s matrixial theory, a deeply feminist psycho-analytical system, ventures beyond the models of subjectivity based on separation and lack, and thus it helps us rethink togetherness and our own humanity. Corporeal Aesth/ethics explores how we become subjects not through a series of cuts, but through an encounter with radical openness, modeled upon the intrauterine/pregnancy period. Even though the theorized encounter relies on caring, carrying, and sharing, it is far from pleasant and safe, as we might assume. Indeed, some of the knowledge communicated in this phase of subjectivity-becoming may turn out to be painful, even traumatic. It is this profoundly corporeal encounter, Kisiel contends, that makes it possible to conceive of the body as a site and source of ethics. Envisioned through the lens of the matrixial, a subject (never alone, always in severality) reaches new modes of intimacy and hospitality, occasioned by our universally shared, originary experience of becoming with-in the maternal body. A psychoanalyst, theoretician, and feminist, Ettinger is also an artist. Sharing Ettinger’s conviction that “painting and theory are not different aspects that attest to the same thing, but are rather differentiated levels of working-through,” Kisiel maps the entanglements of the (feminine/motherly) body in both dimensions of Ettinger’s work. In five chapters, this book delineates the project of Ettinger’s corporeal aesth/ethics. It contextualizes the matrixial body, analyzes its humanizing potential, and proposes dialogues of Ettinger’s work with feminism, theology, and Holocaust studies.

Cotton Nero A.x: The Works of the "Pearl" Poet - David Hadbawnik; Daniel C. Remein; Chris Piuma; Lisa Ampleman (punctum books, 2014)
Manuscript Cotton Nero A.x takes its designation from the unique cataloging system of seventeenth-century British antiquarian Sir Robert Cotton’s library: busts of historical figures atop shelves provided the organizing principle, such that one found this particular codex under the bust of Roman Emperor Nero, on the top shelf, ten volumes over. (Another famous manuscript, containing Beowulf, is called Cotton Vitellius A.xv.) Cotton Nero A.x contains the only versions of the poems we now know as Pearl, Cleanness, Patience, and Sir Gawain and the Green Knight, generally agreed to have been composed sometime in the latter half of the fourteenth century—the time of Piers Plowman and Geoffrey Chaucer, though radically different from either. No one knows who the poet was. No one knows if more than one poet wrote some or all of the poems. Together, they present a stunning array of themes, allegories, and images that critics continue to puzzle over: Patience offers a psychologically complex rendering of the Old Testament story of Jonah and the whale; Cleanness explores its homiletic theme in carnal and spiritual terms with complexity, irony, and even humor; Pearl provides a dream allegory that pushes at the distinction between its earthly and heavenly meanings, challenging the very notion of metaphysical transcendence its form seems to point towards. Finally, Sir Gawain and the Green Knight, the most secular of the poems, is a sophisticated take on Arthurian legend that unfolds like a psychosexual mystery novel, with no easy solution in sight. All the poems are rendered in a difficult Middle English dialect and intricate alliterative form, which sometimes involves a complex rhyme scheme as well. As poet-medievalists, we bow before the poetic achievement of the works in Cotton Nero A.x in all their multi-faceted richness. This is not a translation, nor an interpretation. It is what might be called a trace. A response. A homework assignment from beyond the grave, for four students who should have known better. A dream we hope to dream.

Disrupting the Digital Humanities - Dorothy Kim; Jesse Stommel (punctum books, 2018)
All too often, defining a discipline becomes more an exercise of exclusion than inclusion. Disrupting the Digital Humanities seeks to rethink how we map disciplinary terrain by directly confronting the gatekeeping impulse of many other so-called field-defining collections. What is most beautiful about the work of the Digital Humanities is exactly the fact that it can’t be tidily anthologized. In fact, the desire to neatly define the Digital Humanities (to filter the DH-y from the DH) is a way of excluding the radically diverse work that actually constitutes the field. This collection, then, works to push and prod at the edges of the Digital Humanities — to open the Digital Humanities rather than close it down. Ultimately, it’s exactly the fringes, the outliers, that make the Digital Humanities both heterogeneous and rigorous. This collection does not constitute yet another reservoir for the new Digital Humanities canon. Rather, its aim is less about assembling content as it is about creating new conversations. Building a truly communal space for the digital humanities requires that we all approach that space with a commitment to: 1) creating open and non-hierarchical dialogues; 2) championing non-traditional work that might not otherwise be recognized through conventional scholarly channels; 3) amplifying marginalized voices; 4) advocating for students and learners; and 5) sharing generously and openly to support the work of our peers.

Disturbing Times: Medieval Pasts, Reimagined Futures - Catherine E. Karkov; Anna Kłosowska; Vincent W.J. van Gerven Oei (punctum books, 2020)
From Kehinde Wiley to W.E.B. Du Bois, from Nubia to Cuba, Willie Doherty’s terror in ancient landscapes to the violence of institutional Neo-Gothic, Reagan’s AIDS policies to Beowulf fanfiction, this richly diverse volume brings together art historians and literature scholars to articulate a more inclusive, intersectional medieval studies. It will be of interest to students working on the diaspora and migration, white settler colonialism and pogroms, Indigenous studies and decolonial methodology, slavery, genocide, and culturecide. The authors confront the often disturbing legacies of medieval studies and its current failures to own up to those, and also analyze fascist, nationalist, colonialist, anti-Semitic, and other ideologies to which the medieval has been and is yoked, collectively formulating concrete ethical choices and aims for future research and teaching. In the face of rising global fascism and related ideological mobilizations, contemporary and past, and of cultural heritage and history as weapons of symbolic and physical oppression, this volume’s chapters on Byzantium, Medieval Nubia, Old English, Hebrew, Old French, Occitan, and American and European medievalisms examine how educational institutions, museums, universities, and individuals are shaped by ethics and various ideologies in research, collecting, and teaching.

Divine Name Verification: An Essay on Anti-Darwinism, Intelligent Design, and the Computational Nature of Reality - Noah Horwitz (punctum books, 2013)
In this book, Noah Horwitz argues that the age of Darwinism is ending. Building on the ontological insights of his first book Reality in the Name of God (https://punctumbooks.com/punctum/titles/reality-in-the-name-of-god/)in order to intervene into the intelligent design versus evolution debate, Horwitz argues in favor of intelligent design by attempting to demonstrate the essentially computational nature of reality. In doing so, Horwitz draws on the work of many of today’s key computational theorists (e.g., Wolfram, Chaitin, Friedkin, Lloyd, Schmidhuber, etc.) and articulates and defends a computational definition of life, and in the process lays out key criticisms of Darwinism. He does so in part by incorporating the insights of the Lamarckian theories of Lynn Margulis and Maximo Sandin. The possible criticisms of a computationalist view from both a developmental perspective (e.g., Lewontin, Jablonka, West-Eberhard, etc.) and chaos theory (e.g., Brian Goodwin) are addressed. In doing so, Horwitz engages critically with the work of intelligent design theorists like William Dembksi. At the same time, he attempts to define the nature of the Speculative Realist turn in contemporary Continental Philosophy and articulates criticisms of leading figures and movements associated with it, such as Object-Oriented Ontology, Quentin Meillassoux, and Ray Brassier. Ultimately, Horwitz attempts to show that rather than heading towards heat death, existence itself will find its own apotheosis at the Omega Point. However, that final glorification is only possible given that all of reality is compressible into the divine name itself.

dôNrm'-lä-püsl - kari edwards (punctum books, 2017)
There have been many iterations of the Joan of Arc story: “testimonies,” books, and films have attempted to capture the drama of one of history’s most famous gender warriors. But few, if any, have been undertaken by an author who met her subject matter with such recognition and insight, a fellow warrior, a rebel in kind. kari edwards, a transgender activist and key figure in the Bay Area experimental writing scene of the late 1990s and early 2000s, was provocative and prescient in her concern for the way that language inflects, inflicts, and regulates gender norms. Her persistent efforts to break linguistic binaries and barriers have given her texts an ongoing urgency after her untimely death in 2006. This book brings to life an important document discovered in the late poet’s archive at the Poetry Collection at the University of Buffalo. The several notebooks and partial typescript (as well as various plans and notes) of edwards’ unfinished dôNrm’-lä-püsl, uncovered by Tina Žigon, offer an intriguing glimpse of a major new direction in edwards’ work, one in which her avant-garde instincts are channeled through rigorous research on this medieval figure. In this retelling – better to say “remixing” – of Joan of Arc’s fateful trial and martyrdom, we find the major theme so richly laced throughout edwards’ oeuvre: the courageous (but also depressingly mundane) struggle against the stifling regulation of language, appearance, and norms. edwards’s Joan of Arc, even in its incomplete and abbreviated form (which Žigon calls a “possible version” of edwards’s manuscript), offers an exciting engagement with one of the medieval period’s most challenging and mysterious figures.

Dotawo: A Journal of Nubian Studies 1 - Vincent W.J. van Gerven Oei; Angelika Jakobi; Giovanni Ruffini (punctum books, 2014)
Nubian studies needs a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and critical and theoretical approaches present in post-colonial and African studies. The journal Dotawo: A Journal of Nubian Studies brings these disparate fields together within the same fold, opening a cross-cultural and diachronic field where divergent approaches meet on common soil. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of old kingdoms. This first volume of Dotawo is the outcome of a Nubian panel within the Nilo-Saharan Linguistics Colloquium held at the University of Cologne, May 22–24, 2013. Organized by Angelika Jakobi, the Nubian panel was attended both by specialists of the modern Nubian languages and scholars working on medieval Nubia and its languages, particularly Old Nubian. We are indebted to the Fritz Thyssen Foundation at Cologne for generously sponsoring the organization of the Nubian panel and the invitation of the participants.

Dotawo: A Journal of Nubian Studies 2 - Angelika Jakobi; Giovanni Ruffini; Vincent W.J. van Gerven Oei (punctum books, 2015)
Dotawo: A Journal of Nubian Studies offers a multi-disciplinary, diachronic view of all aspects of Nubian civilization. It brings to Nubian studies a new approach to scholarly knowledge: an open-access collaboration with DigitalCommons@Fairfield, an institutional repository of Fairfield University in Connecticut, USA, and open-access publishing house punctum books. The first two volumes of Dotawo have their origins in a Nubian language panel organized by Angelika Jakobi within the Nilo-Saharan Linguistics Colloquium held at the University of Cologne, May 22 to 24, 2013. Since many invited participants from Sudan were unable to get visas due to the shutdown of the German Embassy in Khartoum at that time, the Fritz Thyssen Foundation funded the organization of a second venue of specialists on modern Nubian languages. This so-called “Nubian Panel 2” was hosted by the Institute of African & Asian Studies at the University of Khartoum on September 18 and 19, 2013. This volume publishes the proceedings of that panel. Future volumes will address three more themes: 1) Nubian women; 2) Nubian place names; 3) and know-how and techniques in ancient Sudan. The calls for papers for the first two volumes may be found on the back of this volume. The third volume is already in preparation with the assistance of Marc Maillot of the Section française de la direction des Antiquités du Soudan, Department of Archeology. We welcome proposals for additional themed volumes, and invite individual submissions on any topic relevant to Nubian studies.

Dotawo: A Journal of Nubian Studies 3: Know-Hows and Techniques in Ancient Sudan - Marc Maillot (punctum books, 2016)
Dotawo: A Journal of Nubian Studies offers a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and critical and theoretical approaches present in post-colonial and African studies. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of old kingdoms. The third volume of Dotawo, guest-edited by Marc Maillot, is dedicated to Know-Hows and Techniques in Ancient Sudan. This collection of articles is the result of a workshop held at Lille University on September 5 and 6, 2013, which brought together several Sudanese archaeology scholars, from architecture to iron production through pottery and textile industry. Organized by Faïza Drici, Marie Evina, and Romain David, with the support of Charles de Gaulle-Lille 3 University and the laboratoire de recherche Halma-Ipel UMR 8164 (Centre national de recherche scientifique – CNRS), this workshop was presided over by Vincent Rondot (present Director of the Egyptian Antiquities Department of the Louvre Museum and former Director of Section française de la direction des antiquités du Soudan – SFDAS). The idea of an academic publication of this workshop in Dotawo was presented by Marc Maillot (SFDAS) in September 2014, during the 13th International Conference for Nubian Studies. The project was warmly welcomed by the editorial committee, and gave birth to a fruitful SFDAS/Dotawo cooperation that started a year ago.

Dotawo: A Journal of Nubian Studies 4: Place Names and Place Naming in Nubia - Robin Seignobos; Alexandros Tsakos (punctum books, 2017)
Dotawo: A Journal of Nubian Studies offers a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and critical and theoretical approaches present in post-colonial and African studies. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of old kingdoms. Place names in Nubia have only received limited attention so far. The need for such a study guided the decision to dedicate the fourth volume of Dotawo to this very issue. Place names are by nature dynamic and may shift over the course of the centuries. Therefore, toponymy is particularly apt to diachronical studies and offer fertile ground for multi-disciplinary analysis. The contents of the volume embrace a wide time frame (from the beginning of recorded history until today) and consist of contributions from scholars active in all fields of Nubian Studies (philology, linguistics, history, archaeology, etc.). The goal has been to gather into one publication the fruits of the collaboration of specialists working with all sorts of theoretical and methodological tools on the successive periods of Nubian history with a focus on the names that identified the micro- and macro-localities where this history was taking place.

Dotawo: A Journal of Nubian Studies 5: Nubian Women - Anne Jennings (punctum books, 2019)
Dotawo: A Journal of Nubian Studies offers a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and the critical and theoretical approaches of postcolonial and African studies. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet the internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of older kingdoms. Volume 5 of Dotawo focuses on Nubian women, both ancient and contemporary. Nubian women, whether they were queens or commoners, Christians or Muslims, have always been held in high esteem by their communities. The contributors to this volume present articles which address Nubian literature, tomb and temple wall paintings, the challenges of migration and resettlement, cultural tourism, gender roles, women’s health, labor cooperatives, and more. They all focus on the ways in which Nubian women have survived and thrived throughout the centuries.

Dotawo: A Journal of Nubian Studies 6: Miscellanea Nubiana - Adam Simmons (punctum books, 2019)
Dotawo: A Journal of Nubian Studies offers a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and the critical and theoretical approaches of postcolonial and African studies. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet the internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of older kingdoms. Bringing together a collection of articles that were first presented as papers at the International Medieval Congress at the University of Leeds in 2016 and additional articles, the sixth volume of Dotawo showcases a diverse richness of topics concerning Nubia. The articles within this volume attest to the cultural, linguistic, geographic, and demographic diversity witnessed throughout Nubian history nationally and internationally amongst its neighbours, both near and far.

Dotawo: A Journal of Nubian Studies 7: Comparative Northern East Sudanic Linguistics - Vincent W.J. van Gerven Oei (punctum books, 2021)
Dotawo: A Journal of Nubian Studies offers a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and the critical and theoretical approaches of postcolonial and African studies. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet the internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of older kingdoms. The seventh issue of Dotawo is dedicated to Comparative Northern East Sudanic (NES) linguistics, offering new insights into the historical connections between Nubian languages and other members of the NES family such as Nyimang, Tama, Nara, and Meroitic. A special focus is placed on comparative morphology.

Dotawo: A Journal of Nubian Studies 8: War in the Sudan - Henriette Hafsaas (punctum books, 2023)
Dotawo: A Journal of Nubian Studies offers a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and the critical and theoretical approaches of postcolonial and African studies. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet the internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of older kingdoms. The eighth issue of Dotawo aims to offer new insights into violent conflicts and wars in Sudan through time and across the region. Special attention is devoted to research on Nubia. The authors use archaeological, historical, philological, and artistic sources to investigate war in the Sudan from the 4th millennium BCE until the present day. Henriette Hafsaas – The Role of Warfare and Headhunting in Forming Ethnic Identity: Violent Clashes between A-Group and Naqada Peoples in Lower Nubia (mid-4th Millennium BCE)

Dotawo: A Journal of Nubian Studies 9: Nubian Homescapes - Anna Lucille Boozer; Anne M. Jennings (punctum books, 2026)
Dotawo: A Journal of Nubian Studies offers a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and the critical and theoretical approaches of postcolonial and African studies. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet the internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of older kingdoms. The ninth issue of Dotawo takes a long-term perspective on Nubian houses and households to explore the distinctive material, visual, and phenomenological worlds of Nubian homescapes. A “homescape” is an array of features related to the home. It is the socially constructed space of human activity, understood as having spatial, conceptual, and emotional boundaries and delimitations. Contributors to this volume embrace the dichotomy of homescapes, demonstrating how Nubians adapt their homescapes over time and space even while adhering to a core identity. The cross-disciplinary contributions to this volume include sociological, anthropological, archaeological, and linguistic approaches to the topic, as well as photographic essays, artwork, and fiction.

Down to Earth: A Memoir - Gísli Pálsson (punctum books, 2020)
Can one have something in common with a lava field? Can one identify with a mountain, or connect with a contemporary event in the history of the earth, in the way that some people feel connected together by birthday, genetic fingerprint, or zodiac sign? In the terms of the Christian burial ceremony, what is this earth from which we come and to which we return? In Down to Earth, Gísli Pálsson explores such questions through both personal reflection on the microcosm of his childhood home, an Icelandic island disrupted by volcanic eruption, and a critical discussion of the current age of the Anthropocene, characterized by the growing environmental impact of humans. While environmental hazards caused by humans often inform public discussion of the Anthropocene, human impact on the planet is not always detrimental. This book discusses in detail the pioneering effort on Heimaey Island to cool molten lava and to divert its flow, in order to save a fishing harbor and the community it has allowed to thrive. Mingling the personal and the geological, the local and the global, Down to Earth should appeal to many readers in diverse contexts throughout the English-speaking world. The author appears to the reader when it suits him, naturally enough, and on occasion, near the center of the narrative, in the vicinity of earthquakes, eruptions, and other natural hazards.

Drag Education: RuPaul, Queer Theory, and the Politics of Teaching - Ryan Tracy (punctum books, 2027)
“I think of myself as less of a judge and more of a teacher.” So said the Queen of Drag, RuPaul Andre Charles, on the second season of RuPaul’s Drag Race—the Emmy Award-winning reality show competition that cemented RuPaul’s status as the most influential drag queen in the world. Via her international and still-expanding Drag Race franchise, sixteen studio albums, a podcast, four published memoirs, the Netflix series A.J. and the Queen, and numerous public appearances, comments, and interviews (not to mention Instagram posts), RuPaul has consistently presented herself to the world as an educator for all whose medium is drag. Drag Education: RuPaul, Queer Theory, and the Politics of Teaching takes RuPaul at her word by exploring in-depth RuPaul’s theorization of drag as a fabulous form of pedagogy. Following RuPaul’s lead, this book proposes a theory of drag education understood as the radical and dispersed set of learning experiences that cross-dressing makes possible. In chapters that weave close readings of RuPaul’s autobiographies with academic writing on RuPaul’s cultural impact, Drag Education makes the argument that drag’s capacity to educate is precisely what has made it a political flashpoint. This book also asks for a conceptual rethinking of drag genealogy. Rather than viewing queer culture as drag’s proper home—a view held by conservatives and even some progressive critics—Drag Education insists that the “ruuts” of drag lie in the domestic sphere, where even the strictest rules against cross-dressing can provoke the very desire to give drag a whirl. Drawing on queer theory’s insight that prohibitions are generative, this book makes the case that “dragucation” (another apt RuPaul neologism) has always been a family affair.

Dutch Afro Becomings: Hybrid Being in Black Art and Culture - Charl Landvreugd (punctum books, 2026)
In Dutch Afro Becomings, artist, curator, and researcher Charl Landvreugd argues that we do not yet have a language to understand Dutch Afro-ness, and that it is insufficient to rely on the discourses developed in African American, Black British, or Caribbean cultural theory alone. This critical monograph on continental European Black art and cultural history articulates the specificity of Dutch Afro-ness and the way that Blackness has been translated and (mis)understood across multiple decades of cultural policy, while also providing an incisive analysis of the Dutch state’s aim to showcase “diversity” in a way that is comfortable to the white cultural class, without ever addressing issues of racism or race. Simultaneously, Landvreugd traces how recent generations of artists are effectively constructing a new visual language to name their Dutch Afro-ness by deepening the way their being is shaped across multiple cultural identities and national histories. These time travelers and wanderers are the Wakaman: cultural workers that embrace their hybridity and multiplicity and have defined, on their own terms and through their own words, their nativity within the Dutch art scene. Dutch Afro Becomings is a key theoretical and art-historical work, as an introduction to both different international genealogies of Black arts and culture and to the different movements that shaped the specificity of Dutch Afro artists in particular.

Echoes of No Thing: Thinking between Heidegger and Dōgen - Nico Jenkins (punctum books, 2019)
Echoes of No Thing seeks to understand the space between thinking which Martin Heidegger and the 13th-century Zen patriarch Eihei Dōgen explore in their writing and teachings. Heidegger most clearly attempts this in Contributions to Philosophy (of the Event) and Dōgen in his Shōbōgenzō, a collection of fascicles which he compiled in his lifetime. Both thinkers draw us towards thinking, instead of merely defining systems of thought. Both Heidegger and Dōgen imagine possibilities not apparent in the world we currently inhabit, but notably, find possible, through a refashioning of thinking as a soteriological reimagining that clears space for the presencing of an authentic experience in the space which emerges between certainties. Jenkins elucidates this soteriological reimagining through a close reading of both authors’ conceptions of time and space, and by developing a practice of listening that is attuned to the echoes that resonate between the two thinkers. While Heidegger often wrote about new beginnings (as well as about gathering oneself, preparing the site, clearings, and practicing) in preparation for the evental un-concealing of truth, nowhere is this as present as in the enigmatic, difficult, and in fact beautiful, Contributions. To call a text beautiful, especially a work of philosophy, risks committing an act of disingenuity, and yet Contributions, like Jacques Derrida’s Glas or Walter Benjamin’s unfinished Arcades Project, rises to this acclaim through its very resistance to a system, its refusal to be easily digested, or even understood. Contributions is unfinished, partial, even at times muttered; it is the beginning of a thinking which takes place on a path and as such cannot imagine—or refuse—its final destination. It invites us to take up towards, but not to insist on, its thinking; it is a “turn” away from the reason and logic of a technologized world and returns philosophy—as a thinking—to a place of wonder and awe. Dōgen’s Shōbogenzō, from another culture and time entirely, is also a beautiful text, for similar reasons. The Shōbogenzō, gathered first as a series of talks given by Eihei Dōgen (and later composed as written texts) details the process of understanding which leads, for Dōgen, to a position of pure seeing, or satori, and yet these talks are not simply rules for monks, nor merely imprecations and demands for a laity; rather, they open a being’s thinking to the possibility of something purely other and work as a transition across worlds that also opens us to an other world. What both thinkers illustrate, as do the other thinkers drawn on in this project—most notably, those philosophers associated with the Kyoto School, who were both intimately aware of Dōgen’s work, and studied, or studied with, Heidegger—is that world is not a fixed, stable entity; rather it is a fugal composition of possibility, of as yet untraversed—and at times un-traversable—spaces. Echoes of No Thing seeks to examine, within the lacunal eddies of be-coming’s arrival, that space between which both thinkers point towards as possible sites of new beginnings.

Echo Otherwise: A Poetics of Sound and Loss in Ancient and Contemporary Poetry - Jocelyn Saidenberg (punctum books, 2026)
At the heart of this book is a story about reading, about reading and pedagogy, about pedagogy’s readers, about readers who listen, listening while reading, about poems and their sonic materials, about the demands that poetic sounds make on writers and readers, about seduction, about echoes and repetition, about the resounding qualities of poetic matter. How might the inarticulate (or inarticulable) communicate in the sounds of poetry? And how might poetry teach us to attend to what is beyond language or even beyond figuration? Reading for the excluded or absent, that which remains after erasure, might be said to be a hermeneutical commandment. But how might we “read” for the faint echoes of words, the shared, phonic resonances that remain and continue to sound afterwards? In Echo Otherwise, framed as a series of slow, recursive readerly meditations, Saidenberg sets about attending to these questions by bringing together two writers, Lucretius and Ferdinand de Saussure, whose selected works surprisingly disclose a set of interconnected and overlapping concerns with how sound works and in what sounds and resounds in the universe of poems and atoms, and they are also attentive to what sound tells us about poems and atoms. In addition to her readings of Lucretius and de Saussure on sound in the company of other readers — as reading, for Saidenberg, is a collective affair — there are garden walks in Little Sparta with Robert Glück and sustained engagements with m. nourbeSe philip’s Zong!, several works by Saidiya Hartman, and the global pandemic. Ultimately, Echo Otherwise attests to the richness of the encounters that transpire in the process of reading and its transformative effects, encouraging forms of relation that would be receptive to and solicitous of unexpected otherness.

Educated People - Roy Goddard; Ansgar Allen (punctum books, 2026)
Educated People identifies a specter haunting the discourse of critical thought and it isn’t communism. It is the unseemly figure of the bourgeois individual, the obscene subject and agent of capitalist culture. This subject is the educated person, the protagonist of a historical culture rooted in human exploitation and a hypocritical social myopia, whose trajectory tends without shame toward the extinction of social and moral difference and the suppression of humanity’s spontaneous vitality and imagination. Educated People recalls from the margins of intellectual history an assortment of radical thinkers who have been deemed useless to the existing imperium of thought, consigned to irrelevance by a system whose grotesque evaluations work relentlessly to reduce human experience to a passive commodity fetishism. Roy Goddard and Ansgar Allen write against a dominant academic convention that conforms to an idea of knowledge as refinable and progressing toward closure: a final and definitive identification of what counts as true. What is presented here is a series of fragments, the product of reading across traditions of philosophy and critique in the arts, history, and anthropology, a series of short pieces that often center on thinkers who have been deemed no longer apropos to a project of closure. These fragments are not so much aphorisms as experiments, tentatively ventured and assembled in such a way as to foster creative doubt and to provoke a more productive sharing and interaction of thought.

Elemental Disappearances - Jason Bahbak Mohaghegh; Dejan Lukić (punctum books, 2016)
The marauder’s fragment … positions itself in the prism between futility, annihilation, and playful diversion. And still, it is here that we find the last chance for a world. The things sought after here are apparitional: they appear and disappear at will; they perfect the art of materialization and vanishing. Such is the nature of living dangerously, and with it the short duration of enchantment. This collection tracks provocative ideas, artifacts, and phenomena rising and fading across different territories of the contemporary world. Through a constellation of powerful thought-images, the authors uncover spaces of an ephemeral and fugitive nature in order to generate a fractal vision of our time and beyond. A former communist prison island in the Adriatic Sea, now abandoned and overgrown with wild plants; the stone garden of a deaf Iranian peasant who dances ecstatically among his geological formations; a Belgian sculptor who combines wax and flesh to depict human and animal forms in states of half-manifestation, incompletion (missing limbs), or branching (morphing into other organisms); a cultural movement in Brazil that takes the discarded debris of urban centers and transforms their splintered wood pieces into massive labyrinths and underground caverns; a blacksmith poet in Afghanistan who alternates between tasks of hammering metal and writing lyrical verses amidst the smoke-clouds of his forge; a Cuban writer whose delirious fixation with the sea compels him to invent a language of pure untimeliness. There are countless sites of disturbance within the postmodern landscape, and yet far too often these disruptive “scenes” remain untheorized and misaligned, treated as random deviations and thus afforded no surpassing consequence or philosophical complexity. Such micro-trajectories necessitate an archive and conceptual matrix that will steal them from their false obscurity and decipher them instead as the passcodes to an imminent global turn. For this, one must return to the amorphous outlook of “the marauder” or “the wanderer.” This book, then, aims to devise an ever-expanding configuration of radical outsides: elemental fronts that lead to unforeseen principles; alternative profiles of experience (intense becomings); incendiary, ominous, or vitalistic signs in circulation across the epochal horizon.

Ephemeral Coast, S. Wales - Celina Jeffery (punctum books, 2014)
Ephemeral Coast is a curatorial research project that seeks to investigate our difficult relationship to the coast as a threshold and frontline to climate change and considers the possibilities of understanding art in relation to what may be described as an unparalleled event. Ephemeral Coast involves the curation of exhibitions, located in coastal regions of the US/Canadian Arctic, Wales, and Mauritius and is made up primarily of artists, cultural theorists and climate change scientists. This catalogue is a theoretical extension of the artists’ work presented in first installment of the exhibition in south Wales, UK. The catalogue discusses the curatorial process and incorporates essays by guest authors, who re-contextualize Ephemeral Coast, S Wales within discussions of regional climate change and cultural theory.

Escape Philosophy: Journeys Beyond the Human Body - Roy Christopher (punctum books, 2022)
The physical body has often been seen as a prison, as something to be escaped by any means necessary: technology, mechanization, drugs, sensory deprivation, alien abduction, Rapture, or even death and extinction. Taking in horror movies from David Cronenberg and UFO encounters, metal bands such as Godflesh, ketamine experiments, AI, and cybernetics, Escape Philosophy is an exploration of the ways that human beings have sought to make this escape, to transcend the limits of the human body, to find a way out. As the physical world continues to crumble at an ever-accelerating rate, and we are faced with a particularly 21st-century kind of dread and dehumanization in the face of climate collapse and a global pandemic, Escape Philosophy asks what this escape from our bodies might look like, and if it is even possible.

((( - Alessandro De Francesco (punctum books, 2021)
((( is conceived of not only as a poetry collection and an artist book, but also as a series of actions, a sculpture, an installation, a living object, and a verbal ecosystem. The poetic voyage of (((, recounted in a concrete if mysteriously abstract, yet bodily language, is presented here in a trilingual English–Italian–French edition. In the spirit of Uitgeverij’s editorial approach, this will allow readers from different parts of the world to discover in their own ways how ((( explores some of the author’s recurring themes through highly innovative poetic and narrative processes: the effects of war on children; technology and surveillance systems; immaterial and unknown phenomena; and human emotions and non-human manifestations of nature via undefined objects and bodies, animals, and cosmological landscapes. The three parentheses of the title hint at multiple layers that are opened and never closed: ((( seeks to push language out of its verbal and human boundaries, towards unobservable territories. The genre of this book, although stemming from poetry in the sense of Dichtung—that is, the concentration of meaning in highly dense verbal structures—is eminently queer, as it escapes identities and definitions. Through its multidimensional, intense, and surprising writing architecture, ((( explores new conceptual and emotional possibilities, confirming poetry and post-genre writing as powerful forms of inquiry in the contemporary era.

100 Chinese Silences - Timothy Yu (punctum books, 2024)
There are one hundred kinds of Chinese silence: the silence of unknown grandfathers; the silence of borrowed Buddha and rebranded Confucius; the silence of alluring stereotypes and exotic reticence. These poems make those silences heard. Writing back to an “orientalist” tradition that has defined modern American poetry, these 100 Chinese silences unmask the imagined Asias of American literature, revealing the spectral Asian presence that haunts our most eloquent lyrics and self-satisfied wisdom. Rewriting poets from Ezra Pound and Marianne Moore to Gary Snyder and Billy Collins, this book is a sharply critical and wickedly humorous travesty of the modern canon, excavating the Asian (American) bones buried in our poetic language. This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

2×6 - Nick Montfort; Serge Bouchardon; Carlos Léon; Natalia Fedorova; Andrew Campana; Aleksandra Małecka; Piotr Marecki (punctum books, 2026)
2×6 consists of short “stanzories”—stanzas that are also stories, each one relating an encounter between two people. Appearing in English, French, Spanish, Russian, Japanese, and Polish, the stanzories are generated by a similar underlying process, even as they do not neatly correspond to one another the way a translation typically does to a source text. These sixfold verses are generated by six short computer programs, the code of which is also presented in full. These simple programs can endlessly churn out combinatorial lines that challenge readers to determine to whom “she” and “he,” and “him” and “her,” refer, as well as which is the more powerful signifier, which the underdog. As John Cayley writes, “Gender is the chief generative obstacle here—making more than two times six—distributed across the natural grammars of these micro- dramas, with their psychosocial, vocational, and hierarchical narrative vectors.” This title is a second edition of a book originally published by Les Figues Press, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

A Beginner's Guide to Old Nubian - Ryan Sasse (punctum books, 2027)
A Beginner’s Guide to Old Nubian is a comprehensive and accessible introduction to the Old Nubian language, a historically significant yet often overlooked linguistic heritage of the medieval Nubian kingdoms. Flourishing between the 8th and 15th centuries CE in the Middle Nile Valley, encompassing parts of present day northern Sudan and southern Egypt, Old Nubian developed as the written language of Christian Nubia, influenced by Greek, Coptic, and Meroitic traditions. Designed for students, linguists, and enthusiasts alike, this guide provides a structured approach to learning Old Nubian, covering its orthography, grammatical structure, and vocabulary. With a focus on both linguistic analysis and historical context, this monograph introduces readers to key grammatical concepts while guiding them through select passages of The Miracle of Saint Mina, an original Old Nubian text, at the end of the guide. Drawing upon recent scholarship and historical sources, A Beginner’s Guide to Old Nubian offers a step-by-step approach for readers with no prior experience in the language. The monograph includes exercises, pronunciation guidance, and a glossary to facilitate independent learning. Each chapter builds upon the last, progressively equipping readers with the tools needed to translate and analyze Old Nubian texts. By engaging with this linguistic tradition, readers contribute to the study and preservation of an essential part of Nubian heritage. Through its structured methodology and accessible explanations, A Beginner’s Guide to Old Nubian serves as a valuable resource for those eager to explore this unique language and its place in medieval African history.

A Bibliography for After Jews and Arabs - Ammiel Alcalay (punctum books, 2021)
Ammiel Alcalay’s groundbreaking work, After Jews and Arabs, published in 1993, redrew the geographic, political, cultural, and emotional map of relations between Jews and Arabs in the Levantine/Mediterranean world over a thousand-year period. Based on over a decade of research and fieldwork in many disciplines—including history and historiography; anthropology, ethnography, and ethnomusicology; political economy and geography; linguistics; philosophy; and the history of science and technology—the book presented a radically different perspective than that presented by received opinion. Given the radical and iconoclastic nature of Alcalay’s perspective, After Jews and Arabs met great resistance in attempts to publish it. Though completed and already circulating in 1989, it didn’t appear until 1993. In addition, when the book was published, there wasn’t enough space to include its original bibliography, a foundational part of the project. A Bibliography for After Jews and Arabs presents the original bibliography, as completed in 1992, without changes, as a glimpse into the historical record of a unique scholarly, political, poetic, and cultural journey. The bibliography itself had roots in research begun in the late 1970s and demonstrates a very wide arc. In addition to the bibliography, Alcalay’s book includes three accompanying texts. In “Behind the Scenes: Before After Jews and Arabs,” Alcalay takes us behind the closed doors of the academic process, reprinting the original reader reports and his detailed rebuttals, and in “A Bibliography for After Jews and Arabs: A Brief Introduction,” Alcalay contextualizes his own path to the work he undertook, in methodological, historical, and political terms. Also included is “A Poetics of Bibliography.”

About That Life: Barry Lopez and the Art of Community - Matthew Cheney (punctum books, 2023)
Why write? Why ask a reader to give their time and attention to your words? How can writing be more than narcissism and self-aggrandizement? These questions were ones that the writer and naturalist Barry Lopez asked at the Bread Loaf Writers’ Conference in the summer of 2000, and they are questions at the heart of About That Life, a meditation on matters of living, making, and seeking. While Lopez is best known for such works of nonfiction as the National Book Award-winning Arctic Dreams, Matthew Cheney brings our attention to the many works of short fiction that Lopez published throughout his life, demonstrating how they fit within Lopez’s sense of ethical aesthetics. That sense is then set alongside the work of San Francisco’s New Narrative writers, insights from David Hinton’s translations of Tu Fu, the story of community arising around a pottery kiln in western Oregon, the beauties and contradictions of Sōetsu Yanagi’s The Unknown Craftsman, and the implications of the right-wing mob attack on the U.S. Capitol—an event that occurred on what would have been Barry Lopez’s 76th birthday. Through a collage of memoir, history, literary criticism, philosophy, aesthetic theory, and creative writing exercises, About That Life wonders how we might live and dream in a world that seems ever more cruel and destructive.

A Boy Asleep under the Sun: Versions of Sandro Penna - Sandro Penna (punctum books, 2014)
Peter Valente’s first encounter with Sandro Penna’s poetry was while translating Pier Paolo Pasolini. At the time, Valente was reading a biography on Pasolini and learned of his close friendship with Penna. Pasolini insisted that among serious readers of poetry, Penna could not be ignored. Born in Perugia on June 12, 1906, Sandro Penna lived most of his life in Rome (he died there on January 21, 1977), except for a brief period in Milan where he worked as a library clerk. When Pasolini arrived in Rome in 1950 he sought out Penna to “show him around.” He knew that Penna was in love with the same ragazzi who prowled the outskirts of Rome. In his poetry Penna clearly says who he is and how he feels. That is a rare enough quality these days. He moves away from the trappings of identity toward an honest expression of love. In Penna’s work the beautiful is not conscious of itself and is therefore erotic: “Is not the beauty of those who are unaware of their beauty / more beautiful than those who are aware?” He is critical of those who hide their desires behind a thin façade of modesty: Here they are, these lords of life. Even with their senses fully aroused, Penna never hid his sexuality in interviews. He once told a reporter (who probably had to pay dearly for the interview), “I am not a homosexual. I am a pederasta.…Homosexuality is a privilege.” Penna’s homosexuality is complicated in one sense by a moral dilemma: whether I am doing the right thing But there is another sense in which Penna accepts the impossibility of a moral resolution to his “problem” and instead turns this negative to a positive value: There are always boys in my poems. But I do not know how to speak of anything else. Everything else is just a tedious noise. I am unable to sing of Good Deeds. Since his poems chiefly concern homosexual love, they face being relegated to a gay-only ghetto of readers or to another ghetto that even homosexuals avoid: pederastia. This is a problematic issue in the United States where scandal surrounding sexual orientation is still prevalent. But more importantly, there are no glamorous pronouncements or concern with gender politics in Penna’s poetry. You also won’t find a vision of historical process or a mass of physical details. What you will find is an attachment to everyday reality. Penna’s poetry is candid, uncluttered, minimalist, and of profound lyrical intensity and as Pasolini, a great supporter of Penna’s work, wrote in the 1970 preface to Penna’s collected poems, he is, “perhaps the greatest and most joyful…Italian poet.”

A Brief Genealogy of Jewish Republicanism: Parting Ways with Judith Butler - Irene Tucker (punctum books, 2016)
A Brief Genealogy of Jewish Republicanism: Parting Ways with Judith Butler uses the chance synchronicity of the 2013 Israeli parliamentary elections and literary theorist Judith Butler’s controversial Brooklyn College address (https://www.thenation.com/article/judith-butlers-remarks-brooklyn-college-bds/) calling for the boycotting of Israeli academic, cultural, and economic institutions as an occasion for examining possible relations between Jewishness and state-centered forms of self-governance. In an extended analysis of Butler’s Parting Ways: Jewishness and the Critique of Zionism, Tucker shows how the alignment of certain authors’ identities and ideas undergirding Butler’s analytical framework draws upon a pointedly Christian conception of belief. This Christian conception of belief structures the most familiar understandings of modern secularism, articulated most famously by John Locke in his “Letter Concerning Toleration.” Tucker reads Locke’s “Letter”’ alongside Jewish philosopher/rabbi Moses Mendelssohn’s 1783 critique of Locke, Jerusalem: Or On Religious Power and Judaism, and the Jewish tradition of the minyan, making a case for the existence of an alternative history of publicness borrowing from Jewish conceptions of communal life and the proper relations of actions and ideas. In throwing light on a genealogy of Jewish practices aimed at the deliberate creation of collectives constituted by their grappling with contingent, historical time, Tucker argues for the existence of a Jewish tradition of republicanism, of democracy. Within such a context, the Jewishness of Israel can be seen to lie first and foremost in its methods of generating a civil collective out of a diverse citizenry rather than in the identities of its individual citizens. The tradition Tucker has in mind explicitly uses an idea of ritual or “ceremonial law” to sustain within itself a tension between a heterogeneity of perspectives and interests constitutive of democratic process and the forms of unity and agreement often understood to be the desired outcome of that process. By setting forth a framework in which heterogeneity and agreement are conceived as coincident modes of political being rather than steps in a linear process, this “Jewish republicanism” frames law-making, implementation and following as forms of a single structure of ritual practice. Such a framework might provide the inspiration and authority for reconceiving some of the fundamental relations of the Zionist project.

Abruptly Dogen - Kidder Smith (punctum books, 2022)
In the thirteenth century, Dogen brought Zen to Japan. His tradition flourishes there still today and now has taken root across the world. Abruptly Dogen presents some of his pithy writings—startling, shifting, funny, spilling out in every direction. These writings come from all seventy-five chapters of his masterwork, the Eye of Real Dharma (Shōbōgenzō 正法眼藏), and the poems roam through mountains, magic, everyday life, meditation, the nature of mind, and how the Buddha is always speaking from inside our heads. An excerpt from Chapter 1, “A Case of Here We Are,” is illustrative: Human wisdom is like a moon roosting in water. No stain on the moon, nor does the water rip. However wide and grand the light, it still finds lodging in a puddle. The full moon, the spilling sky, all roosting in a single dewdrop on a single blade of grass. A man of wisdom is uncut, the way a moon doesn’t pierce water. Wisdom in a man is unobstructed, the way the sky’s full moon is unobstructed in a dewdrop. No doubt about it, the drop’s as deep as the moon is high. How long does this go on? How deep is the water, how high the moon?

A Buddha Land in This World: Philosophy, Utopia, and Radical Buddhism - Lajos Brons (punctum books, 2022)
In the early twentieth century, Uchiyama Gudō, Seno’o Girō, Lin Qiuwu, and others advocated a Buddhism that was radical in two respects. Firstly, they adopted a more or less naturalist stance with respect to Buddhist doctrine and related matters, rejecting karma or other supernatural beliefs. And secondly, they held political and economic views that were radically anti-hegemonic, anti-capitalist, and revolutionary. Taking the idea of such a “radical Buddhism” seriously, A Buddha Land in This World: Philosophy, Utopia, and Radical Buddhism asks whether it is possible to develop a philosophy that is simultaneously naturalist, anti-capitalist, Buddhist, and consistent. Rather than a study of radical Buddhism, then, this book is an attempt to radicalize it. The foundations of this “radicalized radical Buddhism” are provided by a realist interpretation of Yogācāra, elucidated and elaborated with some help from thinkers in the broader Tiantai/Tendai tradition and American philosophers Donald Davidson and W.V.O. Quine. A key implication of this foundation is that only this world and only this life are real, from which it follows that if Buddhism aims to alleviate suffering, it has to do so in this world and in this life. Twentieth-century radical Buddhists (as well as some engaged Buddhists) came to a similar conclusion, often expressed in their aim to realize “a Buddha land in this world.” Building on this foundation, but also on Mahāyāna moral philosophy, this book argues for an ethics and social philosophy based on a definition of evil as that what is or should be expected to cause death or suffering. On that ground, capitalism should be rejected indeed, but utopianism must be treated with caution as well, which raises questions about what it means—from a radicalized radical Buddhist perspective—to aim for a Buddha land in this world.

Ack! Knowledge! Work! - Katherine Behar (punctum books, 2026)
Katherine Behar’s artworks bring automation technologies into visibility, highlighting in particular how such technologies “work” to make work invisible. Motifs of human absence run throughout Behar’s robotic installations, sculptures, and video works and that absence is matched by material footprints of nonhuman over-productivity. The result is an abundance of slippages between knowledge work, white-collar class identification, natural intelligence, artificial intelligence, and office culture. Contrary to the prevailing values we might associate with these subjects, evidence emerges in these intersections that all “autonomous” behavior turns on collective maintenance. This simultaneously opens automation processes to absurdity and humor, and allows robotics to incorporate kinship and care. Connecting contemporary theory and art, Ack! Knowledge! Work! documents and expands upon Behar’s solo exhibition presented at the Beall Center for Art + Technology (https://beallcenter.uci.edu/) in southern California. Behar is known as both a conceptual, multimedia artist and a critical theorist, and this volume brings art and theory together with plates from the exhibition, essays by well-known scholars of new media and computing Kris Paulsen, Jennifer Rhee, and Scott Richmond, and short texts by Behar, curator Jesse Colin Jackson, and creative technologist Fee Christoph, all of which illuminate the predominant theme of the exhibition: the interplay between automation, AI, labor, robotics, and technology in the still-human workspace, with an emphasis on collaborating with technology rather vying against it in a “race for the bottom.”

A Credible Utopia: Essays on Selected Films of Werner Schroeter - Peter Valente (punctum books, 2022)
A Credible Utopia: Essays on Selected Films of Werner Schroeter offers unique and personal insights into Schroeter’s cinematic universe. Many of the films discussed in this book are those upon which Schroeter’s worldwide reputation rests: Der Bomberpilot, an absurdist comedy; The Death of Maria Malibran, a film about ecstatic redemption in death; Willow Springs, about the complex relationships between men and women; Day of the Idiots, a visually baroque, operatic and highly dramatic film about madness; The Kingdom of Naples, Schroeter’s visually stunning depiction of Italy in the post-war years; and Palermo or Wolfsburg, for which Schroeter won the Golden Bear, an epic film about love, violence, and cultural malaise. But Valente also addresses Schroeter’s early experimental films that don’t get as much attention, such as Aggression, Neurasia, and Argila, all of which are about the struggle between repression and desire, and Deux, a late work that Schroeter considered his masterpiece, a film about the double and the ways in which identity is formed by integrating the abject part of ourselves with the good. Valente concludes with an analysis of Nuit de Chien, Schroeter’s final film, a powerful summation of a live devoted to art, music, literature, and film. When the Museum of Modern Art staged a retrospective of Schroeter’s ouevre in 2012, there was hardly anything in English on his films and only one film available on DVD in the US, such that Schroeter’s work as a director has remained largely invisible in the English-speaking world. A Credible Utopia repairs this lacuna in film history, and, in a detailed and intimate reading of Schroeter’s queer ouevre, links all these films together through Schroeter’s desire for a “credible utopia,” despite our shared awareness of disaster, torture, viciousness, and political corruption in the world.

Action [poems] - Anthony Opal (punctum books, 2014)
ACTION — as in begin, genesis, motion — is a collection of poems ultimately concerned with form, those lines drawn in the sand that give way to the profanity of the holy, the holiness of the profane. Throughout ACTION, Opal engages the constraints inherent to seemingly fixed forms. From living with rheumatoid arthritis, to feeling for the edges of a sonnet tradition, to wrestling with the tenets of historical theology, this collection demonstrates that the only way to honestly submit to a form is to rage against it. However, to assume that this rage is not a kind of explosive joy—a Barthesian jouissance—would be to miss the point of poems that Dean Young has described as “radiant affirmations of life and art.”

A Cyborg's Father: Misreading Donna Haraway - Dave Brennan (punctum books, 2025)
When his daughter was diagnosed with type 1 diabetes as an infant and became dependent on technology to stay alive, Dave Brennan set off in search of a vision: what does it mean to live as a cyborg? And how might he best help his daughter navigate the relationship between machine and flesh? Beginning with a line plucked from Donna Haraway’s “A Cyborg Manifesto” —“Their fathers, after all, are inessential”—A Cyborg’s Father blends memoiristic poetic fragments with lyric essays that look toward music and literature by women artists who have embraced the technological as a metaphorical or literal means of investigating and owning their experience as women. Traversing the intersecting paths of feminism, chronic illness, disability studies, transhumanism, interdependence, and more, this is the tale of a father whose greatest hope is to be rendered inessential.

a decolonial manual - valery vino (punctum books, 2026)
In Frantz Fanon’s eyes, decolonization “sets out to change the order of the world.” Is that even possible today? If it is in any sense possible in our times, what would this involve: what kind of changes? a decolonial manual is an adventure in thinking through these questions with a hopeful attention on meaningful, enworlded actions that can offer reparation in catastrophic times. Hosting a transoceanic line-up, neither an introduction nor an attempt to popularize the cultural movement, a decolonial manual offers a mosaic of thirty-three pieces guiding readers through the key struggles in current decolonial thinking and action. In this poly-genre text, readers will encounter various thinking and writing styles, from standard essays and personal reflections to manifestos and unclassifiable contributions, and will also see decolonial thought and practice deployed across multiple continents and a wide variety of subjects and contexts, including archaeology, art and aesthetics, indigeneity, literary studies, modernism, oceans, reparations, STEM education, viral pandemics, and witch-hunting, among many others. To counter the age and ethos propelling ethnic, spiritual, and class divisions, a decolonial manual ultimately brings together researchers, artists, and activists from all corners of the earth to openly learn about new pathways to understanding, solidarity, and love.

Aesthetic Anthropology: Theory and Analysis of Pop and Conceptual Art in America - Marilyn Ekdahl Ravicz (punctum books, 2026)
In Aesthetic Anthropology, Marilyn Ekdahl Ravicz makes the case that anthropology — long focused on “primitive” art and non-Western ritual — possesses untapped theoretical resources for analyzing the art of contemporary Western societies. Drawing on structuralism, symbolic anthropology, and the sociology of knowledge, Ravicz constructs a cross-cultural framework for understanding art as a system of communication embedded in its social and cognitive context. The result is a pioneering study that bridges the anthropology of art and contemporary art criticism. It demonstrates that the same analytical tools used to interpret Navajo sand paintings or Yoruba sculpture can illuminate a Brillo box or a set of typed propositions. Ravicz’s analysis reveals Pop Art as a complex mediating system that oscillates between the domains of fine art and mass culture, simultaneously aestheticizing the commercial commodity and commodifying the aesthetic object. Notably, this study was one of the first sustained academic engagements with Fluxus, situating its intermedia experiments and anti-art provocations as a critical bridge between the appropriation of consumer culture by Pop Art and dematerialization of the object by Conceptual Art. This book was originally a PhD dissertation completed at the University of California at Los Angeles in 1974. This book anticipated by several decades the now-flourishing interdisciplinary conversation between anthropology, visual culture studies, and contemporary art theory. It remains a vital and still-generative contribution to the anthropology of aesthetics.

African Pastoral: Versions of Virgil's Eclogues - Richard Whitaker (punctum books, 2026)
African Pastoral: Versions of Virgil’s Eclogues presents a fresh and unexpected version of the ten pastoral poems that comprise the Eclogues of Virgil (70–19 BCE). Although these poems focus on the lives of shepherds and goatherds, Virgil makes their seemingly circumscribed existence a mirror of the wider world, a world that is both his and ours. The Eclogues deal with subjects that remain vital in the twenty-first century: erotic passion of many varieties, transformation and metamorphosis, the torments of unhappy love, and the nature and power of poetry (represented by different kinds of pastoral song). With striking originality, Virgil also allowed contemporary power politics to erupt into the world of his herders and small-scale farmers, as they face confiscation of their grazing lands and fields. South African classicist and translator Richard Whitaker has produced eminently fluent and creative versions of Virgil’s Eclogues. He reimagines the poems in an African landscape and evokes the troubled history of land dispossession in southern Africa, introducing local equivalents for much of Virgil’s Mediterranean flora and fauna and making frequent use of words drawn from indigenous languages that have enriched his country’s variety of English. African Pastoral includes stunning images by South African artist William Kentridge, which interact with the versions of Virgilian pastoral in multiple ways, complementing and illuminating the poems, as well as raising points of contrast and difference between ancient and modern contexts.

After the "Speculative Turn": Realism, Philosophy, and Feminism - Katerina Kolozova; Eileen A. Joy (punctum books, 2016)
Recent forms of realism in continental philosophy that are habitually subsumed under the category of “speculative realism,” a denomination referring to rather heterogeneous strands of philosophy, bringing together object-oriented ontology (OOO), non-standard philosophy (or non-philosophy), the speculative realist ideas of Quentin Meillassoux and Marxism, have provided grounds for the much needed critique of culturalism in gender theory, and the authority with which post-structuralism has dominated feminist theory for decades. This publication aims to bring forth some of the feminist debates prompted by the so-called “speculative turn,” while demonstrating that there has never been a niche of “speculative realist feminism.” Whereas most of the contributions featured in this collection provide a theoretical approach invoking the necessity of foregrounding new forms of realism for a “feminism beyond gender as culture,” some of the essays tackle OOO only to invite a feminist critical challenge to its paradigm, while others refer to some extent to non-philosophy or the new materialisms but are not reducible to either of the two. We have invited essays from intellectual milieus outside the Anglo-Saxon academic center, bringing together authors from Serbia, Slovenia, France, Ireland, the UK, and Canada, aiming to promote feminist internationalism (rather than a “generous act of cultural inclusion”).

Air Supplied - David Cross (punctum books, 2018)
Air Supplied doubles as an artbook and edited collection of critical essays on the work of Australian-based artist David Cross. Known for his practice with inflatable structures, his projects often draw audiences into unexpected situations and dialogues. Working across performance/participatory art and object-based environments, Cross has developed a unique body of work that focuses on relationships between pleasure, the grotesque, and phobia. His curious architectural structures, which often resemble children’s funhouses, draw participants into physically and psychologically complex scenarios. While often large in scale, these structures at the same time create a framework around which ideas of intimacy and haptic experience can be negotiated and challenged. Since 2011 Cross has begun to work increasingly in the public sphere, developing works that navigate the relationship between sport, collective decision making, and sensory deprivation. Capturing work since 2005 that was produced in Europe, Eastern Europe, North America, and Australasia, Air Supplied features a survey essay by New Zealand-based Martin Patrick, an interview with the artist, and eleven commissioned essays on each of the artworks. The publication also includes a separate booklet of field notes by the artist, capturing reflections on each of the works.

all except you - Roland Barthes (punctum books, 2023)
Roland Barthes’s consideration of the drawings of New York artist Saul Steinberg—originally an artist book posthumously published in France in 1983—is historically important as one of the last remaining books in Barthes’s oeuvre to be translated into English. all except you continues Barthes’s inquiries into image-text relations, specifically the indiscernible horizon where writing meets drawing, one becoming the other. In his attempt to blur these registers, he produces less a critique than a translation, an attempt to merge author and artist, to see himself and his desire in the work of Steinberg, using the resources of structural linguistics and psychoanalysis. The impertinence of his critique mimics the deformations of Steinberg’s drawings that are “sassy, deformed by the look on high, stretched, excessively crunched.” We become suspicious that Barthes is writing more into Steinberg than Steinberg holds, or even that Steinberg is an alibi for some other aim that is withheld. Joe Milutis’s translation takes the opportunity of a running commentary, in the form of translator’s notes, to amplify Barthes’s impertinent reading and authorial one-upmanship by speculating on the presumed failures and detoured transferences of the text. Since Barthes is less concerned with writing about art than writing through it, Milutis’s “double session” perhaps provides the most faithful translation of the Barthesian eros in his write-through of the write-through.

Alone in the Dark: Cinephilia and the Heroic Imagination - Doug Dibbern (punctum books, 2024)
Alone in the Dark is an experimental memoir – or perhaps, more accurately, an anti-memoir or fabulist memoir, some unruly combination of essay, prose poem, and floating reverie that examines the relationship between one’s cultural heritage and one’s aesthetic devotions. Unlike a traditional autobiography that details the chronological events of a person’s life, the book begins with the obsessive moviegoing of Dibbern’s early years in New York and then unfurls as a fevered rumination on the role that an excessive love of art plays in shaping ideas about one’s identity. The book opens with the American premiere of the Hungarian filmmaker Béla Tarr’s harrowing, eight-hour-long magnum opus Sátántangó in 1998 as an emblematic cinephile experience. Dibbern then frames the book by asking, why would anyone devote the bulk of their waking hours to such a compulsive pursuit of a seemingly passive experience of art? Sitting alone in a darkened movie theater, he suggests, is not a passive, but a creative act: developing an aesthetic taste, after all, is central to defining our identities. And taste is the product of two contradictory impulses: the will to simultaneously embrace and escape the values of our cultural backgrounds that made us who we are. With these conjectures as the jumping-off point, the book commences its discursive explorations, wending and weaving between topics as diverse as Carl Jung’s theories of the collective unconscious, Carl Theodor Dreyer’s Ordet, old family photo albums, nineteenth-century immigration to North Dakota, the actress Gena Rowlands’s histrionic mental breakdowns, the self-portraits that the Mandan chief Mato-Tope made in the 1830s, and the dizzyingly joyful suicidal games in Howard Hawks’s film about aviation, Only Angels Have Wings.

Alternative Historiographies of the Digital Humanities - Dorothy Kim; Adeline Koh (punctum books, 2021)
In Silencing the Past: Power and the Production of History, Michel-Rolph Trouillot writes that by examining the process of history we can “discover the differential exercise of power that makes some narratives possible and silences others.” Alternative Historiographies of the Digital Humanities examines the process of history in the narrative of the digital humanities and deconstructs its history as a straight line from the beginnings of humanities computing. By discussing alternatives histories of the digital humanities that address queer gaming, feminist game studies praxis, Cold War military-industrial complex computation, the creation of the environmental humanities, monolingual discontent in DH, the hidden history of DH in English studies, radical media praxis, cultural studies and DH, indigenous futurities, Pacific Rim postcolonial DH, the issue of scale and DH, the radical, indigenous, feminist histories of the digital database, and the possibilities for an antifascist DH, this collection hopes to re-set discussions of the straight, white origin myths of DH. Thus, this collection hopes to reexamine the silences in such a straight and white masculinist history and delineates how power comes into play to shape this straight, white DH narrative. A number of the pieces in this volume go back to the origin myth of the digital humanities to reassess the hagiography of Father Busa by reconsidering and recontextualizing his legacy and his work in relation to media archaeology, politics, Cold War maneuvers, mechanized genocide, the Third Reich, and the military-industrial complex as it has organized various fields, including Asian Studies. This reassessment of comparative genealogies — vis-à-vis Foucault — undergirds an alternative history of the Jesuit hagiography we have so far been unwilling to reexamine for its narrative use in embellishing an origin hagiography/historiography for digital humanities. Other pieces intertwine the digital humanities with other fields — area studies, Asian American Studies, cultural studies, literary studies, and environmental studies — in order to reexamine how the intersections and juxtapositions reveal silences in these histories. And finally, a number of pieces considers alternative praxes in rethinking these histories, whether it is an essay that is a game or a reevaluation of feminist media praxis.

A Manga Perfeita - Erin Manning (punctum books, 2019)
Em 1994, aos vinte e cinco anos de idade, quando o terrível “despedaçamento que vem com a agressão sexual” dobrou-se profundamente em seu corpo e pensamentos de suicídio estavam sempre por perto, Erin Manning escreveu A Manga Perfeita num estado quase febril: dezenove capítulos em dezenove dias, uma espécie de operação de auto-resgate, onde a escrita tornou-se uma maneira de fazer (e sentir) a vida de outra forma. Ao longo desses dezenove dias, e embora não capaz de articular completamente para si mesma na época, Manning escreveu-se para dentro “de uma composição que pergunta de que outra forma a vida poderia ser vivida”. E nos ritmos dessa composição, que era também uma vida, Manning foi e é capaz de recusar a categoria e norma e imobilidade da “vítima” (enquanto ainda compreende as heranças da violência) a fim de seguir em vez disso o mais-que-eu assim como a alegria do “mais-que da experiência no fazer”. Vinte e cinco anos depois, Manning permite que esses escritos anteriores encontrem seu caminho de volta ao mundo, o que é uma maneira de dar “voz a esses momentos de sobrevivência confusos” enquanto também pede a nós, que compartilhamos (e ajudamos a suportar) tais momentos enquanto leitores, que consideremos “outras formas de escutar a urgência que é viver”. Republicar o livro agora é dar-lhe um lugar no mundo de uma maneira que honre sua força como algo que está sempre além da reivindicação de qualquer um, mesmo de Manning. Nesse sentido, A Manga Perfeita nos convida, com Manning, a estar em excesso de nós mesmos, e também a considerarmos, nas palavras de Manning, “como criar condições para viver além da crença feroz do humanismo de que nós, os privilegiados, os neurotípicos, os ainda incólumes, os corpos-capazes, é que guardamos a chave para todas as perspectivas no teatro da vida”. Por fim, A Manga Perfeita e as reflexões de Manning a respeito de sua composição pedem que consideremos “viver na feroz celebração de um mundo inventado por esses modos de vida que rasgam o tecido colonial, branco, neurotípico da vida como a conhecemos.”

American Incest: How White Supremacy Became White Lawlessness - John E. Seery (punctum books, 2026)
American Incest takes its readers on a whirlwind, barn-burning, eye-opening yet largely uncharted tour of America. Consider these examples: The first American novel was an incest novel, published in 1789 and intended as a rival document to the US Constitution. The most famous American painting is a painting about incest. The most influential American movie ever made was an incest movie. The slogan of Philadelphia, America’s founding city, should be properly translated and historically understood as “City of Incest,” not “City of Brotherly Love.” Elvis was the King of Rock ‘n’ Roll, but also, the King of Incest. Seery takes seriously these and other very public (if unavowed) expressions of incest and helps explain the US preoccupation with incest, namely as a roundabout endorsement and oblique enactment of white supremacy. These pivotal episodes in American white supremacy have also always been teetering toward white lawlessness, a recurrent rupture of the social contract (and a recurrent oversight in social contract theory), all racing toward and culminating in Trumpism. Each chapter tells a tale that hasn’t been told or else not told sufficiently enough, though these are tales that should each have been told and told together, as endemic to American cultural and political history. American Incest is a wide-ranging work, drawing both broadly and rigorously from numerous fields, including the author’s own field of political theory. That a work of political theory should draw so heavily on an uninterrupted tradition of American literary incest is also new and notable (an original list of 300+ incest works in the American canon is assembled for the first time as an Appendix to the book).

Analogical City - Cameron McEwan (punctum books, 2024)
In Analogical City, Cameron McEwan argues for architecture’s status as a critical project. McEwan revisits architect Aldo Rossi as a paradigmatic figure of the critical rational tradition, studying a neglected aspect of his thought — the analogical city — to excavate its potential. McEwan develops a grammar of the analogical city under the headings of Imagination, Transformation, City, Multitude, and Project. McEwan argues that the analogical city is critical, collective, and emancipatory. Analogical thought and understanding cities as analogical might open the conditions of possibility for rethinking the critical project in architecture. At a time when the humanities and the sciences are threatened by irrational thought, from climate denial to post-truth narratives, and when architecture has seemingly disavowed its critical capacity and political possibility through its commodification as an instrument of the neoliberal city, McEwan offers critical strategies, conceptual tools, figures of thought, and knowledge practices to articulate modes of thinking and acting differently within architectural criticism and practice. Today, knowledge is a common terrain of struggle and thought requires constant reinvention. The task of architecture, and critique more broadly, must be to interpret the world in order to change it. Consequently Analogical City proposes modes for imagining the city, the subject, and the world otherwise — towards a more egalitarian and critical architecture of the city. Ultimately, the analogical city is not a fully developed theory, nor is it only an intuitive, poetic, or purely formal practice, as some critics propose. McEwan argues that the analogical city is poetic and political: it always refers beyond itself towards a collective and critical project of the city, and yet it invites a series of formal, spatial, and graphic operations comprising erasure and negativity followed by substitution and remontage.

Fuckhead - David Rawson (punctum books, 2013)
What is a fuckhead? David Rawson’s Fuckhead is a surreal exploration of the literature, film, nature and expectations of disability, and of fuckheads in literature and film. Part lyric essay, part fictional memoir, Rawson’s work tells the story of an unnamed narrator whose familial relationships are defined by his VATER syndrome. Abused by his mother and stripped of a voice by his brother’s need to be Tom Cruise via Rain Man, he sets out into a universe of literary tropes. I have always been of the mind that the novelist is allowed access to all experiences, as long as he ultimately has something to say. Plutarch and Samuel Johnson are typing somewhere in the desert of the next world, composing the ultimate collection of biographical criticism, explaining how David Lynch’s entire filmography owes a debt to his club feet. But I and the friends who bought my novel agree the author is dead. The work is particularly interested in the relationship between Steinbeck’s Of Mice and Men and what the narrator argues is Denis Johnson’s reimagining of that work in the short story “Emergency” (in Johnson’s Jesus’ Son). But in accumulating characters with disabilities as widely diverse as Darth Vader, Benjy of Faulkner’s The Sound and the Fury, and the TV sitcom Community’s Abed Nadir, Rawson movingly, and with wry humor, articulates the assumptions and clichés faced by persons with disabilities, all the while creating a new family with his unlikely gathering of “fuckheads.”

Fugitive Traces - The Young Vish (punctum books, 2016)
Fugitive Traces is a sound album released in both digital (https://soundcloud.com/user-362586882/sets/fugitive-traces) and CD (https://www.amazon.com/Fugitive-Traces-Young-Vish/dp/B075JYNMWL/) editions with an accompanying PDF booklet that collages Werner Herzog’s voiceover commentary from over a dozen of his films with electronic, chamber, and rock music to both pay homage to one of the world’s most visionary filmmakers and critique an artistic practice rooted in contradiction and frequent disaster. You know the stories. Werner Herzog exploited native workers to clear a swath of rainforest and pull a steamship up a mountain in Peru. Werner Herzog climbed an active volcano on an evacuated island, and then claimed embarrassment that the volcano had not erupted. Werner Herzog brought about the deaths of 10,000 tame rats he’d smuggled into the Netherlands for the filming of Nosferatu. The album’s accompanying “lyrics” comprise an essay that explores the consequences of being seduced by Herzog’s unique brand of recklessness, documenting a disaster on the set of young filmmaker Sacksteder’s Silo. Tracks from Fugitive Traces previously appeared on Sleepingfish (http://www.sleepingfish.net/Xi/Sacksteder.htm), The Collagist (http://thecollagist.com/the-collagist/2012/2/8/scratch-where-it-itches.html), Textsound (http://textsound.org/index.php?ISSUE=13), Quarterly West (http://quarterlywest.com/?p=115), and Queen Vic Knives. The Young Vish is joined on this album by Chris Westhoff (guitar), Mark Dickson / Nests (http://music.nestsounds.com/) (guitar, mandolin), Hannah Robbins (cello), and Brian DiBlassio (piano).

Gaffe/Stutter - Whitney Anne Trettien (punctum books, 2013)
Access interactive companion web-book here. (https://web.archive.org/web/20260521063256/https://gaffestutter.punctumbooks.com/) Gaffe/Stutter is a dead letter to Deleuze’s Logic of Sense. It began as a series of diagrams, two-dimensional memory palaces that sketch the vectors of each chapter’s paradox; it became an elaborate plan for a web-based diagrammatic (r)e(n)dition of Logic of Sense, built on zoomable, annotatable high-resolution scans of these diagrams. Conceived as an anti-book — a visual reading schematic — this project eschews the line of text in favor of regimented grids, the ink-soaked grain of the remediated pen over the laser-burned face of print; playful reaction rather than academic protraction. This is not an analogy, or a product of the imagination, Gilles Deleuze and Felix Guattari would write in A Thousand Plateaus, but a composition of speeds and affects on the plane of consistency: a plan(e), a program, or rather a diagram, a problem, a question-machine. It ended as a directory of inert jQuery demos and digital scans: an image of Trafalgar Square at dusk, annotated with the words “Flag,” “Small people on the steps,” “A Statue,” and “National Gallery Dome”; an empty html file titled ‘delete.html’. The visitor who may happen to wander onto the website where these project demos are stashed would find herself stuck on Deleuze’s definition of a paradox as initially that which destroys good sense as the only direction of becoming, but also that which destroys common sense as the assignation of fixed identities. From a series of diagrams to a dead-end digital directory, Gaffe/Stutter re-interprets a book that itself resists scholarly annotation. As with sense, it subsists in language; but it happens to things.

Gathering Sparks: Jewish Arts and Somatics - Nicole Bindler; Kristen Smiarowski; Ben Spatz (punctum books, 2027)
Contemporary renewals of judaism and jewishness return again and again to the kabbalistic image of gathering sparks, an approach to tikkun olam or healing the world that recognizes fragmentation and incompleteness as central to our attempts at doing good. This volume arises out of a shared sense of the sparks that we gather as jewish movers, creators, and activists in the 2020s. The glimmers of hope that we steward are too often limited by logocentric assumptions about what is real, what is meaningful, and what is political. Yet we know that some of the most important knowledge is carried in our bodies: as dance technique, as somatic awareness, as ways of thinking and researching through practice. The essays collected in Gathering Sparks: Jewish Arts and Somatics reveal a variety of ways to be jewish and a diversity of creative, spiritual, and political practices that are informed by a wide variety of contemporary jewish experiences. They are rooted in a commitment to decolonization, while at the same time holding space for different ideas about what that means. Even within non-zionist and anti-zionist circles, individuals in this volume do not always think or feel the same about how to move forward with ideas and practices of jewishness in the present. For some, explicit solidarity with the movement for a free Palestine must be central to any legitimate actions taken under the banner of jewishness or judaism. Others emphasize relations of solidarity and connection with indigenous and/or Black diasporic communities, with a difficult yet necessary untangling from whiteness, and with allied investigations of trans, queer, feminist, and nonbinary identities. Although this is not a handbook or manual, we hope that the essays and images gathered here will serve as sparks to light the imaginations and activations of others—not as a single approach, but as a kaleidoscope of methods and pathways, traced by others that may resonate with your own life and work. Despite and because of their differences, we find that they work together to offer a breath of something new: a way of articulating with, through, and even sometimes against jewishness that is neither nostalgic nor solely critical but fresh, artistic, politically committed, historically informed, creative, and embodied.

Gazing at the Puerto Rican Anthropological Landscape: The “Natives” Look Far and Wide - Manuel Valdés Pizzini (punctum books, 2026)
Before World War II, most anthropological research in Puerto Rico was led by US anthropologists. The most famous project, The People of Puerto Rico, was directed by American anthropologist Julian Steward and launched the career of renowned scholars such as Sidney Mintz and Eric Wolf. Gazing at the Puerto Rican Anthropological Landscape aims to delineate the development of the post-WWII anthropological field in Puerto Rico by Puerto Rican anthropologists, the so-called “native” anthropologists. The contributors to Gazing at the Puerto Rican Anthropological Landscape deploy the term “native” somewhat ironically, but they also know that who they are affects their positionality vis-à-vis their research subjects. Thus, they retain the term to spark a conversation addressing the complicated feelings that such labels still evoke among non-mainstream anthropologists. Gazing at the Puerto Rican Anthropological Landscape purposely avoids making Puerto Rico and Puerto Ricans a problem to study and instead focuses on a wide variety of epistemological and methodological questions related to the study of Puerto Rico and Puerto Ricans by “native” anthropologists within local, regional, and global spheres. We posit that the Puerto Rican anthropological landscape transcends the confines of the island of Puerto Rico to encompass its connection and engagement with the larger world, and that it is not limited to the inhabitants of the island of Puerto Rico but embraces members of its diaspora, as well as other groups and ethnicities. On that note, this book seeks to reflect critically on how the academic field of anthropology (research and teaching) in Puerto Rico has evolved, post-WWII, in various engagements with the current debates of contemporary anthropology — theoretical, methodological, socio-cultural, political, and otherwise.

Gender Trouble Couplets, Volume 1 - A.W. Strouse (punctum books, 2019)
Judith Butler’s Gender Trouble: Feminism and the Subversion of Identity radically claimed that the sexed body is a fallacy, discursively constructed by the performance of gender. A.W. Strouse has undertaken to rewrite Butler’s classic tome into an octosyllabic poem. Inspired by the rhyming encyclopedias of the Middle Ages, Strouse transforms each of Butler’s sentences into punchy medieval couplets. This performative repetition of Chapter 1 of Butler’s classic treatise on gender, identity, and sexuality, “Subjects of Sex/Gender/Desire,” deconstructs Butler’s deconstruction. Relishing in the campiness of rhyme and meter—in the bodily pleasures of form—Strouse’s Gender Trouble Couplets, Volume 1 is an imitation for which there is no original. Butler’s Gender Trouble, perhaps, was poetry all along.

Geographies of Identity: Narrative Forms, Feminist Futures - Jill Darling (punctum books, 2021)
Geographies of Identity: Narrative Forms, Feminist Futures explores identity and American culture through hybrid poetry and prose work by women, and expands the strategies of cultural poetics practices into the study of innovative narrative writing. Informed by Judith Butler, Homi Bhabha, Harryette Mullen, Julia Kristeva, and others, this project further considers feminist identity politics, race, and ethnicity as cultural content in and through poetic and non/narrative forms. The texts reflected on by Darling explore literal and figurative landscapes, linguistic and cultural geographies, sexual borders, and spatial topographies. Ultimately, they offer non-prescriptive models that go beyond expectations for narrative forms, and create textual webs that reflect the diverse realities of multi-ethnic, multi-oriented, multi-linguistic cultural experiences. Readings of Gertrude Stein’s A Geographical History of America, Renee Gladman’s Juice, Pamela Lu’s Pamela: A Novel, Claudia Rankine’s Don’t Let Me Be Lonely, Juliana Spahr’s The Transformation, Theresa Hak Kyung Cha’s Dictée, Gloria Anzaldúa’s Borderlands/La Frontera, and Layli Long Soldier’s WHEREAS show how alternatively narrative modes of writing can expand access to representation, means of identification, and subjective agency, and point to horizons of possibility for new futures. These texts critique essentializing practices in which subjects are defined by specific identity categories, and offer complicated, contextualized, and historical understandings of identity formation through the textual weaving of form and content.

[Given, If, Then]: A Reading in Three Parts - Jeremy Fernando; Jennifer Hope Davy; Julia Hölzl (punctum books, 2015)
[Given, If, Then] attempts to conceive a possibility of reading, through a set of readings: reading being understood as the relation to an Other that occurs prior to any semantic or formal identification, and, therefore, prior to any attempt at assimilating, or appropriating, what is being read to the one who reads. As such, it is an encounter with an indeterminable Other, an Other who is other than other — an unconditional relation, and thus a relation to no fixed object of relation. The first reading by Jeremy Fernando, “Blind Reading,” unfolds through an attempt to speak of reading as an event. Untheorisable in itself, it is a positing of reading as reading, through reading, where texts are read as a test site for reading itself. As such, it is a meditation on the finitude and exteriority in literature, philosophy, and knowledge; where blindness is both the condition and limit of reading itself. Folded into, or in between, this (re)reading are a selection of photographs from Jennifer Hope Davy’s image archive. They are on the one hand simply a selection of ‘impartial pictures’ taken, and on the other hand that which allow for something singular and, therefore, always other to dis/appear — crossing that borderless realm between ‘some’ and ‘some-thing.’ Eventually, there is a writing on images on writings by Julia Hölzl. A responding to the impossible response, a re-iteration, a re-reading of what could not have been written, a re-writing of what could not have been read; these poems, if one were to name them such, name them as such, answer (to) the impossibility of answering: answer to no call.

Going Postcard: The Letter(s) of Jacques Derrida - Vincent W.J. van Gerven Oei (punctum books, 2017)
In 1980, Jacques Derrida published La carte postale: De Socrate à Freud et au-delà. At the occasion of the 30th anniversary of the English translation, Going Postcard: The Letter(s) of Jacques Derrida revisits this seminal work in Derrida’s oeuvre. Derrida himself described The Post Card in his preface as “the remainders of a destroyed correspondence,” stretching from 1977 to 1979. A cryptic text, it is riddled with gaps, word plays, and a meandering analysis of the interface between philosophy and psychoanalysis. The contributors who offered the fourteen essays gathered in Going Postcard were each provided with a deceptively simple task: to write a gloss to a fragment from the first part of The Post Card, “Envois.” The result is a prismatic array of commentaries, excursions, and interpretations that take Derrida “to the letter.” The different glosses on lemmas such as genre, erasure, telepathy, philately, and sperm transport The Post Card into the twenty-first century and offer a “correspondence,” if fragmentary, with Derrida’s work and the work to come.

Gray Media: A Psychopolitics of Deception - Lisa Blackman (punctum books, 2027)
In the era of artificial intelligence, how can we tell we are being tricked? Indeed, is deception an anomaly or rather a defining force in contemporary media, culture, and politics? In Gray Media: A Psychopolitics of Deception, Lisa Blackman tracks deception as it emerges across AI and algorithmic systems, information warfare, and the psychological and emotional abuse of gaslighting. The approach is radically interdisciplinary, weaving together insights from cultural and media studies, affect studies, critical mental health and disability studies, speculative philosophy, and feminism and queer theory. The mixing of fields mirrors the unstable, shape-shifting nature of the deceptive phenomena the book investigates. A central concept which links deception across the different areas is confabulation, a paradoxical form of reasoning, which blurs distinctions between the rational and irrational, legible vs. illegible, human vs. technical, intention vs. opportunity, emotional vs. reason, and moral vs. immoral. Linked to creativity and deception, Gray Media explores the longer histories of confabulating forms of reasoning and their tendencies towards cruelty, and dehumanization, shaping technologies of power, communication, and unfeeling within colonial and patriarchal rationalities. It offers new conceptual tools for understanding how contemporary subjects are shaped by – and navigate – the unstable conditions that are symptomatic of its operations, as well as opening to new forms of world-making and unlearning that are made possible, if (only) we can learn to feel differently.

Hack the Experience: Tools for Artists from Cognitive Science - Ryan Dewey (punctum books, 2018)
Hack The Experience will reframe your perspective on how your audience engages your work. This will happen as you learn how to control attention through spatial and time-based techniques that you can harness as you build immersive installations or as you think about how to best arrange your work in an exhibition. You’ll learn things about the senses and how they interface with attention so that you can build in visceral forms of interactivity, engage people’s empathetic responses, and frame their moods. This book is a dense bouillon-cube of techniques that you can adapt and apply to your personal practice, and it’s a book that will walk you step-by-step through skill sets from ethnography, cognitive science, and multi-modal metaphors. The core argument of this book is that art is a form of cognitive engineering and that the physical environment (or objects in the physical environment) can be shaped to maximize emotional and sensory experience. Many types of art will benefit from this handbook (because cognition is pervasive in our experience of art), but it is particularly relevant to immersive experiential works such as installations, participatory/interactive environments, performance art, curatorial practice, architecture and landscape architecture, complex durational works, and works requiring new models of documentation. These types of work benefit from the empirical findings of cognitive science because intentionally leveraging basic human cognition in artworks can give participants new ways of seeing the world that are cognitively relevant. This leveraging process provides a new layer in the construction of conceptually grounded works. This is a book for artists, but it is also for curators, art school faculty, landscape architects, gallerists, archivists, post-disciplinary multi-hyphenates, museum program staff, and anyone who wants to know about the ways art and cognitive science come together to engage an audience.

Hand Book: A Manual on Performance, Process, and the Labor of Laundry - Lizzie Olesker; Lynne Sachs (punctum books, 2025)
Hand Book: A Manual on Performance, Process, and the Labor of Laundry is a collection of writings and images from a performance and film set within a neighborhood laundromat, a microcosm of service work within our urban reality. With a focus on the people who are paid to wash and fold, Hand Book explores the convergence of dirt, stains, money, identity, and desire. Informed by both theory and history, filmmaker-poet Lynne Sachs and playwright Lizzie Olesker construct a model for making a site-specific work incorporating both live performance and film. From conversations with workers in laundromats around New York City, they develop a play that magnifies forms of manual labor that often go unrecognized. The core of Hand Book is Sachs and Olesker’s hybrid play-script which grew out of documentary material they collected in New York City over several years. Within this theatrical construct, the actors themselves navigate the dynamic between their laundry worker characters and who they are in their own lives. Images also engage with text to create an evocative graphic experience. Turning a page becomes an interactive, quasi-cinematic encounter, calling to mind the intimacy of touching other people’s clothes, almost like a second skin, the textural care for things kept close to the body. Hand Book includes essays, interviews, memoirs, and poetry that look at the relationship between art and social engagement. Observation, historical research, and fiction intersect, creating a patchwork of “what is” with a speculative, imagined “what was.” Historian and author Tera Hunter speaks to the importance of The Washing Society, a group of 3,000 Black women laundry workers who organized in Atlanta in 1881 for better pay and working conditions. Feminist historian Silvia Federici engages in a conversation about the meaning of reproductive labor and its relationship to laundry. Two leaders of a grassroots organization share their experience of immigration and activism. A dancer creates a gestural map of her choreography. An actor deconstructs the charged significance of her Civil War-era costume. Ultimately, Hand Book: A Manual on Performance, Process, and the Labor of Laundry presents an illuminating dialogue between the documentary arts, feminism, film, immigration, labor history, and theater. Throughout, a playwright and filmmaker contemplate how art-making can alter our understanding of the social structures of city life.

Heathen Earth: Trumpism and Political Ecology - Kyle McGee (punctum books, 2017)
Heathen Earth: Trumpism and Political Ecology looks beyond the rising fortunes of authoritarian nationalism in a fossil-fueled late capitalist world to encounter its conditions. Trumpism represents an alternative to the forces undermining the very cosmology of the modern West from two opposing directions. The global economy, the pinnacle of modernization, has brought along a dark side of massive inequality, corrupt institutions, colonial violence, and environmental destruction, while global warming, the nadir of modernity, threatens to undo the foundations of all states and all markets. To the vertigo of placelessness, symptomatic of globalization, is added the ecological vertigo of landlessness. With reality slowly fragmenting, it is only too obvious in this light that Trumpism and other nationalist movements would attract massive hordes of supporters. Promising to expel foreigners and to restore unity and equality by taking power back from the global elites, while utterly denying the climate science that calls ordinary means of subsistence and consumption radically into question, Trumpism can be seen as an antidote to the toxic combination of global markets and global warming. The irony, of course, is that Trumpism only responds to these dangers by doubling down on the reckless expansionist logic that gave rise to them in the first place. This book, composed entirely between November 8, 2016 and January 20, 2017, examines Trumpism according to its regime of political representation (despotism), its political ontology (nativism), and its political ecology (geocide), while laying the groundwork for an alternative politics and a resistant, responsive ecology of the incompossible.

Heavy Processing - T.L. Cowan; Jas Rault (punctum books, 2024)
What happens when we take the joke of “lesbian processing” seriously as a research method? Heavy Processing does just this, by tracing the multi-directional genealogies and vast affinities of processing-heavy methods as innovations in information technologies (such as operating systems, central processing units, network designs). Part methods handbook, manifesto, and survival guide, this book opens up the fields of information studies, data studies, digital media studies, and digital humanities to critical digital methods, information technologies, and infrastructures: trans- feminist and queer (TFQ) cultural protocols and ways of working. Cowan and Rault offer heavy processing as a maximalist research method, consistent with a long and proud lesbian-leaning TFQ tradition of making a mountain out of a molehill. Heavy Processing draws together activist, artistic, and scholarly work that is both about and not about digital materials to critically reorient digital research methods calibrated for accountability, relationship-building, and trust as measures of scholarly rigor. A raging romp of a methods manual, Cowan and Rault offer an alternative to mass digitization in the form of TFQ processing for analog and born digital materials. They write for students, faculty, and researchers, as well as for information, cultural heritage, and tech-sector professionals; for anyone interested in digital media and feminist, queer, and transcultural studies; and for anyone who has ever been studied.

Helicography - Craig Dworkin (punctum books, 2021)
Part art history essay, part experimental fiction, part theoretical manifesto on the politics of equivalence, Helicography examines questions of scale in relation to Robert Smithson’s iconic 1970 artwork Spiral Jetty. In an essay and film made to accompany the earthwork, Smithson invited us to imagine the stone helix of his structure at various orders of magnitude, from microscopic molecules to entire galaxies. Taking up this invitation with an unrelenting and literal enthusiasm, Helicography pursues the implications of such transformations all the way to the limits of logic. If other spirals, from the natural to the man-made, were expanded or condensed to the size of Spiral Jetty, what are the consequences of their physical metamorphoses? What other equivalences follow in turn, and where do their surprising historical, cultural, and mechanical connections lead? This book considers a number of forms in order to find out: the fluid vortices of whirlpools, hurricanes, and galaxies; the delicate shells of snails and the threatening pose of rattlesnakes; prehistoric ferns and the turns of the inner ear; the monstrous jaws of ancient sharks; a baroque finial scroll on a bass viol; a 19th-century watch spring; phonograph discs and spooled film; the largest open-pit mine on the planet. The result is a narrative laboratory for the “science of imaginary solutions” proposed by Alfred Jarry (whose King Ubu also plays a central role in the story told here), a work of ficto-criticism blurring form and content, and the story of a single instant in time lost in the deserts of the inter-mountain west.

Helvete 1: Incipit - Amelia Ishmael; Zareen Price; Aspasia Stephanou; Ben Woodard (punctum books, 2013)
Not to be confused with metal studies, music criticism, ethnography, or sociology, Helvete: A Journal of Black Metal Theory is a speculative and creative endeavor, one which seeks ways of thinking that count as Black Metal events — and indeed, to see how Black Metal might count as thinking. Theory of Black Metal, and Black Metal of theory. Mutual blackening. Therefore, we eschew any approach that treats theory and Metal discretely, preferring to take the left-hand path by insisting on “some kind of connaturality between the two, a shared capacity for nigredo.”

Helvete 2: With Head Downwards: Inversions in Black Metal - Niall Scott; Steve Shakespeare (punctum books, 2015)
Not to be confused with metal studies, music criticism, ethnography, or sociology, Helvete: A Journal of Black Metal Theory is a speculative and creative endeavor, one which seeks ways of thinking that count as Black Metal events — and indeed, to see how Black Metal might count as thinking. Theory of Black Metal, and Black Metal of theory. Mutual blackening. Therefore, we eschew any approach that treats theory and Metal discretely, preferring to take the left-hand path by insisting on “some kind of connaturality between the two, a shared capacity for nigredo.” Issue 2 focuses on the theme of Inversions in Black Metal. Nailed at the heart of many a logo, suspended from the neck, held out in Satanic blessing: the inverted cross is one of black metal’s anti-icons. The antithesis of a revelation of light, it signifies an originary blasphemy. Forsaking ascension and mining a path towards the centre of the earth, black metal finds a satanic stain lodged at the core of being. However, the significance of this movement is not bound by a simple reversal. The inverted cross hangs above a swarming logic of inversion: the overturning of Christianity, but also a mimesis of Christian self-desecration; the rejection of certain forms of religion, but also of modernity’s pallid enlightenment; the invocation of strange gods of the earth, even as the earth is cursed. When thought becomes poison, it is no longer so easy to determine which way is up and which way is down. To throw down one’s head, to push oneself into the cursed earth, to occupy the place of the inverted crucified: is this to think-by-not-thinking an unconditioned rapture beyond negation and affirmation? Table of Contents // “The Swarming Logic of Inversion and the Elevation of Satan,” by Steven Shakespeare and Niall Scott — “Through the Looking Glass Darkly: Medievalism, Satanism, and the Dark Illumination of the Self in the Aesthetics of Black Metal,” by Brenda S. Gardenour Walter — “The Way of the Sword: Christianity, Fascism, and the Folk Magic of Black Metal,” by Reuben Dendinger — “A Sterile Hole and a Mask of Feces,” by Bert Stabler — ART PORTFOLIO: “Eccentricities and Disorientations: Experiencing Geometricies in Black Metal,” curated by Elodie Lesourd and Amelia Ishmael [featuring artwork by: Dimitris Foutris, Gast Bouschet and Nadine Hilbert, Andrew McLeod, Sandrine Pelletier, and Stephen Wilson] — “Giving Life Harmoniously: Animal Inversion in Cattle Decapitation,” by Erik van Ooijen — “Contempt, Atavism, Eschatology: Black Metal and Bergson’s Porous Inversion,” by Louis Hartnoll

Helvete 3: Bleeding Black Noise - Amelia Ishmael (punctum books, 2016)
Not to be confused with metal studies, music criticism, ethnography, or sociology, Helvete: A Journal of Black Metal Theory is a speculative and creative endeavor, one which seeks ways of thinking that count as Black Metal events — and indeed, to see how Black Metal might count as thinking. Theory of Black Metal, and Black Metal of theory. Mutual blackening. Therefore, we eschew any approach that treats theory and Metal discretely, preferring to take the left-hand path by insisting on “some kind of connaturality between the two, a shared capacity for nigredo.” Black Metal Theory is noise. Lacking one clear manifesto or position, it fails to become an elite circle. It is amplified and transmitted electronically: through instruments, lo-fi recordings, internets, and print-on-demand publishers…yet rather than a clear direction of progress we glean only its subversive raw dissonance, disruptions, animalistic screams, resonating disturbances, high-pitched feedback, primitive growls, and its atmospheric statics, hisses, and drones. Black Metal Theory refuses to be hi-fi. It quenches its sonic thirsts from primordial-ditch stews that resemble the dark sludge of recently melted snowfall — pristine white flakes transmuted into a tumultuously sexy and delicious mixture of trash and dirt and ash and poison that swirls and splashes in ditches before seeping into the underground. Our ears drink this disharmonious black bile and our bodies suspend in its intoxicating formless complexities. The third issue of Helvete, “Bleeding Black Noise,” features artwork and essays that focus on the sonic aspects of Black Metal, specifically its interactions with Noise — the interruptions, creations, and destructions of signals. “Bleeding Black Noise” is a revision of Steven Parrino’s statement, “My relation between Rock and visual art: I will bleed for you.” In this issue, Rock is replaced with Noise, and Bleeding is celebrated as a release of the Black Noise — raw energy and formless potential. The essays and art portfolios included here experiment with sonic and conceptual feedback, as well as the way that black noise works through feedback as a process, resonating as background hums or drones, and cascading in foregrounded screams.

Hephaestus Reloaded: Composed for Ten Hands / Efesto Reloaded: Composizioni per 10 mani - Brunella Antomarini; Adam Berg; Vladimir D’Amora; Alessandro De Francesco; Miltos Maneta (punctum books, 2019)
Hephaestus Reloaded / Efesto Reloaded, presented in a bilingual (English/Italian) publication, and whose five authors are from Greece, Italy, and the US, invokes as its first inspiration the myth of Hephaestus who embodied a twofold entity: both disabled and technically capacious. The myth of Hephaestus has been passed across the centuries as an ancient metaphor signifying the idea of becoming-world, in which any distinction between the natural and the artificial, or the organic and the technical, is blurred. Human beings, by virtue of their physical vulnerabilities and limits, have enhanced their technological powers to the point of transcending their own given nature. At present, a variety of critical discourses in disciplines such as philosophy, history, aesthetics, and cognitive sciences pay attention to our becoming-hybrid (organic and mechanical beings) – unleashing a space for research that probes the concept of transcendence. Each of the contributions in this book addresses – through its own peculiar perspective, method and experimental style – a new way to approach the role of transcendence in socio-cultural life. In the Occidental history of ideas, the notion of transcendence has received at least three canonical articulations that are challenged by this book: religious (Judeo-Christian traditions), philosophical (Platonic-intellectual universality of ideas), and scientific (the objective and technological turn of knowledge). Nonetheless, it is with the rise of cybernetics, with its digital and virtual modalities of systems, networks, and knowledge, that our human environment emerges as a source of knowledge in itself — not simply as an object but rather as an immersive agency in which nature, knowledge, technique merge. The transcendence of the actual and the virtual into a “third” element is construed and analyzed in this book through conceptual schemes that rely on a post-binary or non-binary understanding of coincidences, triangulations, hybrids, or post-human combinatorics. What is ultimately explored is how transcendence is ejected from strictly theological, philosophical, or scientific groundings and emerges as a germinating point of becoming (something else).

Hippolytus - Euripides (punctum books, 2012)
Euripides wrote two plays called Hippolytus. In this, the second, he dramatized the tragic failure of perfection. This translation comes in two forms; the first presents a simulacrum of the text as it might have appeared in unprocessed form to a reader sometime shortly after Euripides’s death. The second processes the drama into the reduced but much more distinct form of modern print translations.

Historiographies of Game Studies: What It Has Been, What It Could Be - Alisha Karabinus; Carly A. Kocurek; Cody Mejeur; Emma Vossen (punctum books, 2025)
Historiographies of Game Studies offers a first-of-its-kind reflection on how game studies as an academic field has been shaped and sustained. Today, game studies is a thriving field with many dedicated national and international conferences, journals, professional societies, and a strong presence at conferences in disciplines like computer science, communication, media studies, theater, visual arts, popular culture, and others. But, when did game studies start? And what (and who) is at the core or center of game studies? Fields are defined as much by what they are not as by what they are, and their borderlands can be hotly contested spaces. In this anthology, scholars from across the field consider how the boundaries of game studies have been established, codified, contested, and protected, raising critical questions about who and what gets left out of the field. Over more than two dozen chapters and interviews with leading figures, including Espen Aarseth, Kishonna Gray, Henry Jenkins, Lisa Nakamura, Kentaro Matsumoto, Ken McAllister, and Janet Murray, the contributors offer a dazzling array of insightful provocations that address the formation, propagation, and cultivation of game studies, interrogating not only the field’s pasts but its potential futures and asking us to think deliberately about how academic fields are collectively built.

History According to Cattle - Laura Gustafsson; Terike Haapoja (punctum books, 2015)
History According to Cattle is an expanded account of the acclaimed art and research project History of Other’s first major installment, The Museum of the History of Cattle (2013). The exhibition presents a large-scale ethnographic museum of world history as seen from the perspective of cattle, one of the most important companion species of humans. Thus, The Museum of the History of Cattle is the first museum to exhibit the cultural history of a non-human species. In the exhibit, the connections of animal rights issues with violations of human rights become visible while the situations of indigenous cattle populations, the development of genetics, and industrialization are imagined through the eyes of this silent, ever present companion. Both tragic and humorous, The Museum of the History of Cattle portrays humans as a species mesmerized by its own image. The book-catalog includes a full presentation of the research and visual material of the exhibition, with contextualizing essays by art historian Anne Aurasmaa, philosopher Elisa Aaltola, theorist Kirs Forkasiewizc, and researcher-curator Radhika Subramaniam. Drawing from critical animal studies, animal philosophy, art theory and the lived companionship of humans and cattle, the publication provides a fresh insight into the possibilities of creative imagination, and into the ethical encountering of the species-other in our society.

Homeland Fascism: Corporatist Government in the New American Century - Herman Schwendinger; Julia Schwendinger (punctum books, 2016)
"It can't happen here." This has been the prevailing sentiment about the possible emergence of fascism in the United States since the rise of international fascism in the 1930s. Yet there are signs that it may already be happening, and at the highest levels of government… In their copiously researched and documented work the Schwendingers outline the structural transformations, policies, and practices that raise the prospect of fascist governance in the 21st Century US. They show that a homeland fascism has significant supports within the framework of American liberal democracy. This is an important analysis in a context in which concerns about fascist demagoguery and far right mobilization appear to be growing in the US and beyond.

Homotopia? Gay Identity, Sameness & the Politics of Desire - Jonathan Kemp (punctum books, 2015)
Do opposites attract? Is desire lack? These assumptions have become so much a part of the ways in which we conceive desire that they are rarely questioned. Yet, what do they say about how homosexuality — a desire for the same — is viewed in our culture? This book takes as its starting point the absence of a suitable theory of homosexual desire, a theory not predicated on such heterological assumptions. It is an investigation into how such assumptions acquired meaning within homosexual discourse, and as such is offered as an interruption within the hegemony of desire. As such, homosexual desire constitutes the biggest challenge to Western binaric thinking in that it dissolves the sacred distinctions between Same/Other, Desire/Identification, subject/object, male/female. Homotopia? (composed in 1997 but not published until now) investigates the development of a homosexual discourse at the end of the nineteenth century and the beginning of the twentieth century, and reveals how that discourse worked within heterosexualized models of desire. Andre Gide’s Corydon, Edward Carpenter’s The Intermediate Sex, and John Addington Symond’s A Problem in Modern Ethics are all pseudo-scientific texts written by non-medical men of letters, and were, in their time, highly influential on the emerging homosexual discourse. The fourth text, the twenty-odd pages of Marcel Proust’s novel A la recherché de temps perdu usually referred to as ‘La Race maudite,’ is the most problematic, in that it appeared under the guise of fiction. But Proust originally planned this ‘essay-within-a-novel’ to be published separately. In it, he offers a pseudo-scientific theory of male-male love. These four texts were published between the years 1891 and 1924, an historical moment when the concept of a distinct homosexual identity took shape within a medicalized discourse centered on essential identity traits and characteristics, and they all work within the rubric of science, contributing to a discourse which saw the human race divided into two distinct categories: heterosexuals and homosexuals. How did this division come about, and what were its effects? How was this discourse sustained, and how were the meanings it produced received? For men whose erotic interest was exclusively in other men, what did it mean to see oneself and one’s desires as the outcome of biology rather than moral lapse?

How We Read: Tales, Fury, Nothing, Sound - Kaitlin Heller; Suzanne Conklin Akbari (punctum books, 2019)
Reading can be an act of consumption or an act of creation. Our “work reading” overlaps with our “pleasure reading,” and yet these two modes of reading engage with different parts of the self. It is sometimes passive, sometimes active, and can even be an embodied form. The contributors to this volume share their own histories of reading in order to reveal the shared pleasure that lies in this most solitary of acts – which is also, paradoxically, the act of most complete plenitude. Many of the contributors engage in academic writing, and several publish in other genres, including poetry and fiction; some contributors maintain an active online presence. All are engaged with reading’s capacity to stimulate and excite as well as to frustrate and confuse. The synergies and tensions of online reading and print reading animate these thirteen contributions, generating a sense of shared community. Together, the authors open their libraries to us. This is how we read.

How We Write: Thirteen Ways of Looking at a Blank Page - Suzanne Conklin Akbari (punctum books, 2015)
The contributors range from graduate students and recent PhDs to senior scholars working in the fields of medieval studies, art history, English literature, poetics, early modern studies, musicology, and geography. All are engaged in academic writing, but some of the contributors also publish in other genres, includes poetry and fiction. Several contributors maintain a very active online presence, including blogs and websites; all are committed to strengthening the bonds of community, both in person and online, which helps to explain the effervescent sense of collegiality that pervades the volume, creating linkages across essays and extending outward into the wide world of writers and readers.

Humid, All Too Humid: Overheated Observations - Dominic Pettman (punctum books, 2016)
I haven’t made a single mistake in my life. I’ve just made a lot of good decisions that went really badly. Try as we might, we simply can’t imagine what our world would now look like, had our forefathers decided to use asparagus instead of electricity. In Humid, All Too Humid, social commentator Dominic Pettman curates the overheated thoughts of his own feverish mind, in response to a world struggling with unprecedented levels of cultural climate change. Humanity is like that obnoxious bore that arrives at the party drunk — thinks he’s witty and charming and wise, but is in fact a complete psychotic loser. All the other creatures, however, are too polite to say anything. So they just watch us quietly, and hope that we disappear as quickly as we came. The book takes the form of aphorism, witticism, maxim, axiom, dictum, quip, jape, adage, proverb, pun, precept, reflection, suggestion, observation, paraphrase, bon mot, vagary, specificky, put-on, put-off, mummery, miscellany, aside, in-front, behind, knock-knock joke, one-liner, tweet, re-tweet, truism, and not-so-truism. When you think about it, how rude it is for people to get married in public. This whole ritual is set up so that one person can say they love this one other person more than you. More than anyone else in the room. Is this why people really cry at weddings? Is this why we cover their car with rubbish? A sublimated response to their ceremonial insult? Known for his scholarly work on love, sex, and the (post)human condition, Pettman now assembles this collection of humoristic micro-meditations on everything from the meaning of life to the “yoghurt of human unkindness.” Archaeologists in Turkey have uncovered a new fragment of Anaximander, which simply reads: “Because reasons.” Humid, All Too Humid reads as if Oscar Wilde had first written Minima Moralia, after binge-watching too many episodes of The Simpsons.

Image Photograph - Marc Lafia (punctum books, 2015)
We no longer live in the society of the spectacle, passively seeing the world. Now we perform our very own spectacle in a society that demands it at every turn. We’ve become advertisements of ourselves, our own PR agents, continually putting on a performance and measuring it hour by hour. This is no longer the society of the spectacle but the society of performance. All events have become a pretense to create the image, to orchestrate an image of images that is us. We believe the image confers on us a kind of immortality: just as the artist believes her works collected by a major museum will do the same, we believe the network will forever host the archive we build everyday. The image that is us lives in the circulation of the network. Though a file, though virtual and malleable, made out of bits and instantly accessible to anyone who wants to find it around the world, this image that lives only lives on screen, as virtual as it might be, is a material fact. In its impression, its reception, its archivability, its remixability, the electronic image is today’s photograph. Image Photograph is a book about, and of, this transformation of the image. In three essays — a foreword by critic and philosopher, Daniel Coffeen; an essay of images and text that explores the varied rhetorics of the image; and a strictly visual essay — the book presents a traversal through photography to arrive at a new understanding of images, what Lafia calls the image-photograph. As Coffeen states, Which is to say, Lafia presents and examines imaging across a breadth of moods, tropes, and contexts in order to see and engage this new technology of image-seeing and image-making — this image-photograph — as it exists today in our age of electronic inscription and networked culture. At once artist book and critical theory, Image Photograph takes its direction from Walter Benjamin’s Arcades, John Berger’s Ways of Seeing and, more recently, Hito Steyerl’s The Wretched of the Screen. Throughout it, Lafia not only writes about the image but constructs images — and, finally, performs this new space of the image-photograph.

Imaginary Death - Mariko Nagai (punctum books, 2025)
A man dies. He dies because he must—because without his death, there is no story, and, in the end, no history itself. So begins Mariko Nagai’s Imaginary Death, a creative nonfiction book that examines how the author’s grandfather, an ordinary man born in a small village in the early 20th century, is unmade and remade into a perfect Japanese Imperial Soldier by the era he was born into. In the kaleidoscope composed of archival documents, letters, journals, research, interviews, and photographs, Imaginary Death traces the life of a man who fought and died for the empire, whose death, obscured by lack of documentation, must be composited of many possible ways men could die in Papua New Guinea. Only forty out of four thousand men from the regimental unit survived by the end of the repatriation in 1946: his was one small death out of many. In the tradition of James Agee and Walker Evans’s seminal work on the Great Depression Let Us Now Praise Famous Men, Imaginary Death is a work that is part meditation, part history, and part fragments of memory that tell a story of a Japanese soldier’s life and death during World War II. Ultimately, Imaginary Death is a textual landscape of imagination, fact, history, and dreams all intersecting to create a psychological terrain that is not limited in the same way as history or nonfiction books, but is rather a new imaginative cartography, no less real than history itself.

Imagining What We Don't Know: Creative Theory and Critical Bodies - Lisa Samuels (punctum books, 2026)
Bringing together perception, ecology, community, lingual value, and quantum life, Imagining What We Don’t Know: Creative Theory and Critical Bodies presents twenty-four essays and theory poems that blend interpretive neologisms — wild dialectics, distributed centrality, membranism, deformance, bioautography, transplace, soft text, and more — with readings of visionary philosophers and the art and writing of Algeria, Australasia, the Caribbean, Oceania, the UK, and the US. Committed to experimental ideation and relational ethics, Imagining What We Don’t Know is for art and theory practitioners, philosophy rebels, creative writers, and anyone who relishes thinking about contemporary art, transnational and transdisciplinary life, and how we imagine with language. Imagining What We Don’t Know presents a biblio-architecture of “blurprints” built with theories of the embodied mind that are elemental, entangled, and electrified by the political. This is creative theory, hovering with alterities of art and interpretation and imagining with critical attention.

Imperial Physique - JH Phrydas (punctum books, 2019)
In 2008, JH Phrydas wrote a story about how bodies talk without words. He wanted the story to not just describe the silent ritual of nonverbal communication but to perform it. The interaction would be visceral – the exchange melancholic, yet full of lust. He wanted words to retain the unsayable: the subtle movements of a body in heat. In the years since, Phrydas kept rewriting this story, using different techniques, different syntaxes and forms, in hopes that he would find a successful method of gestural writing. Imperial Physique is a collection of these attempts. They explore the way our bodies hover between animal and human, civil and wild. The bleakness – and underlying verve – of imagining Western empires in decline serve as a backdrop for a lone figure searching city streets, decaying architecture, and sand dunes for some type of physical connection. What arises is the loss of – and longing for – touch at the edges of imperialism, historical violence, and personal shame. Paired with these stories are essays on queer embodiment, figuration, and plasticity that emerged through conversations with somatic psychologists, art therapists, and poets. They give context to the short stories and offer other ways to engage with the book: through thinking of language as texture, as sculpture, as a physical yearning against empire. The place where language and the body merge.

In a Trance: On Paleo Art - Jeffrey Skoblow (punctum books, 2014)
In a Trance is just the sort of genre-defying work we at Peanut and punctum and, as it happens, Jeffrey Skoblow, revel in. It is a book-length essay by a fiction writer. It is a fictional essay by a literary scholar. It is a gallant assay by a smart man who thinks while he walks, and he walks a lot. The book is a meta-meditation on Paleolithic cave drawings and the humans who ponder them. It is fact-based and entrancing just as the cave drawings are actual (existing in time — loosely — and space — more definitively) and mesmerizing. Skoblow is devising stories as “we” (humans) have always devised stories though in a less familiar mode, along a less travelled path. The essay draws on (!) the careful/thoughtful/whimsical notebooks kept by Skoblow over a dozen years. The notebooks record/illuminate/complicate his visits to twelve Paleolithic art sites as well as his deep, eccentric reading of texts concerned in some way with the subject of cave drawings by an array of scientists, anthropologists, archeologists, art historians, and other sundry enthusiasts and experts, so-called and otherwise. These are one man’s marks made about making marks. Skoblow’s meticulous descriptions attempt the impossible: to provide the “information” that will allow us to see what is visible, invisible, restricted, unseen, hidden, and lost (in the sense of not yet found, or destroyed, or degraded by human presence) beneath the ground at El Castillo and Niaux (for instance). Lines, dots, dashes, body parts, animals, and “hum-animal” figures — things/creatures we have given name to (bison? rhino? vulva? phallus?) in our helplessly homo-sapien-centric attempts to understand (and/or to master our non-understanding). We follow Skoblow as he steps onto an electric train in the caves at Rouffignac and steps out in Southern Illinois, where he cautiously crosses a snake-ridden (maybe) meadow. This is where he meanders further — literally and figuratively: further from the actual caves, furtherest from certainty. These furtherings are exactly what we might expect from a book that from its opening pages declares as one if its themes the difficulties inherent in considering Paleolithic art. The pleasures of this book are found in Skoblow’s intense, vigilant exploration of these problems and questions, which are in themselves irresistible. Who are we? In what ways, specifically, and to what degree do we resemble these ancient humans who spray- and brush-painted, smudged, carved, and stenciled images into and onto cave walls and floors and ceilings?

Incomparable Poetry: An Essay on the Financial Crisis of 2007–2008 and Irish Literature - Robert Kiely (punctum books, 2020)
Incomparable Poetry: An Essay on the Financial Crisis of 2007-2008 and Irish Literature is an attempt to describe the ways in which the financial crisis of 2007-8 impacted literature in Ireland, and thereby describe the ways in which poetry engages with, is structured by, and wrestles with economic issues. Ireland and its contemporary poetry is a particularly suitable case study for studying the effect of the economic crisis on Anglophone poetry, because poetry in Ireland has a special relationship to the state and economy due to its status as a postcolonial nation-state. Beginning with a summary of recent Irish economic and cultural history, and moving across experimental and mainstream poetry, this essay outlines how the poetry of Trevor Joyce, Leontia Flynn, Dave Lordan, and Rachel Warriner addresses in its form and content the boom years of the Celtic Tiger and the financial crisis. Incomparable Poetry also discusses the concerns and historical contexts these poets have turned to in order to make sense of these events – including Chinese history, accountancy, sexual violence, and Iceland’s economic history. In contemporary Irish poetry, the author argues, we see a significant interest in matching capitalism’s accounting abilities, but in this attempt, these poems often end up broken by the imposition of an external conceptual framework or economic logic.

In Defense of Don Giovanni: A Feminist Mythobiography - Luisa Passerini (punctum books, 2024)
Who wants to champion the figure of Don Giovanni in the time of Harvey Weinstein and #MeToo? Don Giovanni is a rapist, murderer, serial seducer, and liar. Can he ever be held up as a role model or seen as a figure to be enjoyed? This is the task that the eminent Italian historian and lifelong feminist, Luisa Passerini, sets for herself in In Defense of Don Giovanni. As she developed the long arc of her distinguished career, Don Giovanni surprisingly became not only her role model but also a secret object of research. Taking her method from oral history, Passerini creates a series of characters with whom she discusses the forms and incarnations of the myth of Don Giovanni across time, from its first appearance in early medieval Spain and Commedia dell’Arte to its many European variations and its transposition to the colonial and postcolonial world in the Middle East, the Americas, and Africa. Pivoting round Don Giovanni’s best known incarnation in Mozart’s opera, Passerini and her interlocutors meet in different locations from Venice and Bern to Paris and Turin. They discuss plays, films, and operas and talk about art, novels, and psychoanalytic interpretations of the myth while also sharing their own life stories, in which Don Giovanni often plays a part that is, by turns, destructive, mischievous, and full of the joy of life. From his early beginnings in the Iberian Peninsula to recent analysis of the sexuality of colonial conquest and postcolonial revenge and return, Don Giovanni shape-shifts between rapacious hyper-masculinity, comic trickster, and morally vacuous loser whose annoyingly persistent nemesis Don Ottavio emerges as an alternative and ultimately better object of desire. As she tracks Don Giovanni’s image across the world and through the centuries, however, Passerini comes to see that it also plays another role, that of a mirror, in which women can see themselves emerge as individuals with their own life force.

In Divisible Cities: A Phanto-Cartographical Missive - Dominic Pettman (punctum books, 2013)
Italo Calvino rewrites Baudrillard’s America with a more global eye, as edited by Roland Barthes. In Divisible Cities takes Italo Calvino’s classic re-imagining of Venice, viewed in the mind’s eye from many different metaphysical angles, and projects it on to the world at large. Where the Italian saw his favorite city as an impossible metropolis of many moods, shades, and ways of being, this unauthorized sequel unpacks the Escheresque streets in unexpected directions. In Divisible Cities is thus an exercise in cartographic origami: the reflective and poetic result of the narrator’s desire to map hidden cities, secret cities, imaginary cities, impossible cities, and overlapping cities, existing beneath the familiar Atlas of everyday perception. Stitching these different places and spaces together is a “double helix” or “Siamese seduction” between the traveler and his romantic shadow, revealing — step by step — a clandestine itinerary of hidden affinities, nestled within the habitual rhythm of things. Matter matters. That’s what the drone of the city tells us. And yet we dream of something beyond these invisible walls.

Inefficient Mapping: A Protocol for Attuning to Phenomena - Linda Knight (punctum books, 2021)
Working from a speculative, more-than-human ontological position, Inefficient Mapping: A Protocol for Attuning to Phenomena presents a new, experimental cartographic practice and non-representational methodological protocol that attunes to the subaltern genealogies of sites and places, proposing a wayfaring practice for traversing the land founded on an ethics of care. As a methodological protocol, inefficient mapping inscribes the histories and politics of a place by gesturally marking affective and relational imprints of colonisation, industrialisation, appropriation, histories, futures, exclusions, privileges, neglect, survival, and persistence. Inefficient Mapping details a research experiment and is designed to be taken out on mapping expeditions to be referred to, consulted with, and experimented with by those who are familiar or new to mapping. The inefficient mapping protocol described in this book is informed by feminist speculative and immanent theories, including posthuman theories, critical-cultural theories, Indigenous and critical place inquiry, as well as the works of Karen Barad, Erin Manning, Jane Bennett, Maria Puig de la Bellacassa, Elizabeth Povinelli, and Eve Tuck and Marcia McKenzie, which frame how inefficient mapping attunes to the matter, tenses, and ontologies of phenomena and how the interweaving agglomerations of theory, critique, and practice can remain embedded in experimental methodologies.

Inhuman Nature - Jeffrey Jerome Cohen (punctum books, 2014)
Gathering into lively conversation scholars in medieval, early modern and object studies, Inhuman Nature explores the activity of the things, forces, and relations that enable, sustain and operate indifferently to us. Enamored by fictions of environmental sovereignty, we too often imagine “human” to be a solitary category of being. This collection of essays maps the heterogeneous and asymmetrical ecologies within which we are enmeshed, a material world that makes the human possible but also offers difficulties and resistance. Among the topics explored are the futurity that inheres in storms and wrecks, wood that resists its burning or offers art and dwelling, hymns that implant themselves like viruses, the ontology of everyday objects, the seep and flow of substance, the resistant nature of matter, the dependence of community upon making things public, and the interstices at which nature and culture become inseparable.

Inner Conflicts - Sana Sheikh (punctum books, 2026)
What should I do? What is the right thing to do? What do I do when I don’t know what to do? The difficulty in answering these questions does not come from a lack of knowledge but a deeper problem that requires us to look inward (and outward). Inner Conflicts is meant to be read in times of upheaval. It traverses jagged terrain, giving voice to the unspoken doubts and contradictions that underlie our dearly held projects. Drawing from psychoanalytic theory, five chapters unpack, process, and – like psychoanalysis – free associate to the fundamental tensions in our lives that refuse resolution. Neither a simple critique nor defense, Inner Conflicts contends that only through acknowledging all parts of the argument within us can we fully attend to the urgencies and particularities of ethical and political life.

In Practice: From Art Education to Liberatory Transformation - Lisi Raskin (punctum books, 2027)
In Practice: From Higher Education to Liberatory Transformation examines the relationship between settler institutions of higher education and the settler state and the carceral logics that both produce the border politics of university campuses and police our disciplines, discourses, and communication styles. It also investigates how these structures impact pedagogical and curricular practice. It is a book about consciousness-raising in service of various forms of resistance and resistance’s relationship to teaching. The methods and models discussed in In Practice are applicable to anyone who wants to unlearn patterns of behavior that perpetuate and collude with oppressive structures like settler white supremacy, transphobia, and ableism. The book encourages the application of the practices it elaborates so readers can subvert and disrupt violent social norms in their personal and professional lives. The practices and narratives contained within this book are based on teaching methods developed and tested over two decades of working in higher education contexts. Through a combination of storytelling and tool sharing, the book potentiates a break with the paradigm of the isolated individual and encourages relational accountability that can foster sustainable, mutual relationships in the face of late-stage capitalism. In Practice: From Higher Education to Liberatory Transformation takes as its premise that it is possible to squat the forms that settler institutions of higher education recognize as their own for the purpose of disrupting their violent inner workings.

Insurrectionary Infrastructures - Jeff Shantz (punctum books, 2018)
Opponents of states and capital must be prepared to defend ourselves. To understand the nature of the state is to know that it will attack to kill when and where it feels a threat to its authority and power. But the struggles against exploitation, oppression, and repression must also move to the offensive. With the emboldening of reactionary forces on the far Right, there has been a renewed focus on issues of community self-defense, not only against the violence of the state but against organized fascists and Right-wing vigilantes alike. There has also been a developing seriousness, particularly among anarchist and antifascist, or antifa, activists. The goal of all anarchism is not to eliminate violence in social struggle (a futile and impossible pursuit given the nature of the state), but to limit the amount, degree, and extent of violence and harm inflicted by state agents, and their vigilante supporters, on the poor, oppressed, and exploited. And this is part of the emphasis on insurrectionary infrastructures. Non-material (emotional) and material resources and spaces are necessary to defend communities and workplaces under attack, but also to organize possible, and necessary, offensives. Insurrectionary Infrastructures reflects on strategies and tactics of rebellion and resistance and offers suggestions for fighting to win.

Intimate Bureaucracies - dj readies (punctum books, 2012)
Intimate Bureaucracies is a history from the future looking backward at our present moment as a turning point. Our systems of organization and control appear unsustainable and brutal, and we are feeling around in the dark for alternatives. Using experiments in social organization in downtown New York City, and other models of potential alternative social organizations, this manifesto makes a call to action to study and build sociopoetic systems. The apparent oxymoron, intimate bureaucracies, suggests not only a strategy, but the very basis for the new productive mythology surrounding the electronic World Wide Web. Intimacy, the close familiarity of friendship or love, by definition depends on a small-scale system of communication. Its warmth, face-to-face contact, and fleeting impact has often made it the subject of art and literature. It usually only appears in administration situations as either an insincere ornamentation of a political campaign (“pressing the flesh” or “kissing babies”), or as inappropriate office behavior (affairs, gossip, child abuse, etc.), but rarely as the center of a political system. The “small is beautiful” movement of the 1960s and 1970s did suggest the possibility of an intimacy in politics, but not how to scale the system to the size of a government.

Covert Plants: Vegetal Consciousness and Agency in an Anthropocentric World - Prudence Gibson; Brits Baylee (punctum books, 2018)
Covert Plants contributes to newly emerging discourses on the implications of vegetal life for the arts and culture. This stretches to changes in our perception of ‘nature’ and to the adapting roles of botany, evolutionary ecology, and environmental aesthetics in the humanities. Its editors and contributors seek various expressions of vegetal life rather than the mere representation of such, and they proceed from the conviction that a rigorous approach to thinking with and through vegetal life must be interdisciplinary. At a time when urgent calls for restorative care and reparative action have been sounded for the environment, this essay volume presents a range of academic and creative perspectives, from evolutionary biology to literary theory, philosophy to poetry, which respond to the perplexing problems and paradoxes of vegetal thinking. Representations of vegetal life often include plant analogies and plant imagery. These representations have at times obscured the diversity of plant behavior and experience. Covert Plants probes the implications of vegetal life for thought and how new plant science is changing our perception of the vegetal — around us and in us. How can we think, speak, and write about plant life without falling into human-nature dyads, or without tumbling into reductive theoretical notions about the always complex relations between cognition and action, identity and value, subject and object? A full view of this shifting perspective requires a ‘stereoscopic’ lens through which to view plants, but also simultaneously to alter our human-centered viewpoint. Plants are no longer the passive object of contemplation, but are increasingly resembling ‘subjects,’ ‘stakeholders,’ or ‘actors.’ As such, the plant now makes unprecedented demands upon the nature of contemplation itself. Moreover, the aesthetic, political, and legal implications of new knowledge regarding plants’ ability to communicate, sense, and learn require intensive, cross-disciplinary investigation. By doing this, we can intervene into current attitudes to climate change and sustainability, and hopefully revise, for the better, human philosophies, ethics, and aesthetics that touch upon plant life.

Creep: A Life, A Theory, An Apology - Jonathan Alexander (punctum books, 2017)
Creeps surround us, seemingly everywhere. People creep up on each other both on the streets and online, with digital technologies vectoring a lot of cyber-stalking. It’s so easy to spy on people that “creep catching” has even become a form of news entertainment in shows such as “To Catch a Predator.” But what defines a creep is so broad that nearly anyone can be a creep at times. Many of us wonder if we ourselves have been creepy, or if perhaps we engage in behavior that, if others knew, would easily earn us the title “creep.” Even Donald Trump, during the raucous 2016 campaign, was called a “creep” on several occasions by various news media. Indeed, for many of us, the specter of the creep is not just threatening, but exciting – exciting perhaps in the possibility of threat. Yes, we get creeped out. But we are also fascinated by creeps, perhaps in part because we all sense the potential inside ourselves for creepy behavior. In this provocative and engaging new book, Jonathan Alexander interweaves personal narrative and cultural analyses to explore what it means to be a creep. Calling this work a critical memoir, he draws on his own experiences growing up gay in the deep south, while also interrogating examples from literature and popular film and media, to approach the figure of the creep with some sympathy. Ranging widely over contemporary culture, especially the ever-creeping presence of nearly ubiquitous surveillance, Alexander confesses his own creepiness while also explaining to us what being creepy can show us in turn about our culture. He also resurrects some famous “creeps” from the past, such as J.R. Ackerley, to explore what makes a creep creepy, and how even the best of us succumb at times to being creeps. Ultimately, Alexander argues, a study of creepiness might offer us critical insight into the fundamental perversity of how we live. Creep: A Life, A Theory, an Apology is a timely meditation for our strange and creepy times.

Cries from the Merry-Go-Round: A Fugue of Shouts from an Anti-Ableist Activist - Farah Ankaly Aibol (punctum books, 2026)
Cries from the Merry-Go-Round: A Fugue of Shouts from an Anti-Ableist Activist is a work of creative activism that suggests a redefinition of what a shout can be. In this case, the Shouts are literary expressions that call attention to urgent, emergent, or continuing daily acts of micro- and macro-aggressions against people living with disabilities who are resisting oppressive systemic ableism. The Shouts in this collection evoke critical reflections about our societal practices and question our current understanding of diversity, equity, and inclusivity relative to people living with their own “non-normative” physical and mental abilities. These narratives explore instances of the everyday occurrences of life, from seeking or maintaining relationships to dealing with the “little things” that pop into, and interrupt, our daily routines. The common thread between these Shouts happens to be people living with one or more disabilities. Ultimately, Shouts are imperfect narratives of disabled lives. They are incomplete, not conforming, not conventional, not complicit, not complacent, always contesting, always critical, not exhaustive, never too much, never enough, hard to ignore, hard to hear, not any easier to read… So, why these Shouts? A single Shout, a call for attention, can reverberate and become a call for action, echoing and supporting existing Shouts, while triggering and fostering other emerging Shouts. These Shouts, although similar in their urgency, are unique in their particular experience. Each murmured or ear-splitting Shout resonates with another in a contrapuntal collection of critical tales that call attention to the routine realities of systemic ableism.

Crisis States: Governance, Resistance & Precarious Capitalism - Jeff Shantz (punctum books, 2016)
This is an age of crisis: economic, political, environmental, and social. Yet the nature of contemporary crisis is often misunderstood. Crisis, rather than being accidental or episodic – as is too often assumed – has been a regular feature of state practice in the neoliberal austerity regimes of contemporary capitalism. In this timely work Jeff Shantz gives special attention to the particular manufactured crises associated with austerity regimes and conditions of precarity within contemporary capitalism, and how Crisis States differ from other forms of state practice. Crisis is a powerful weapon of states and capital in the pursuit of accumulation, exploitation, and control. Engaging insights from anarchism and autonomous Marxism, Shantz lays bare the real nature and character of crisis as political and social pursuits of state and capital under precarious capitalism. Attention is also given to social resistance under crisis state conditions. Contemporary capitalism renders the oppressed and exploited precarious at the same time as opportunities are opened to render the system itself precarious. Understanding Crisis States and precarious capitalism is crucial in considering prospects for resistance.

Critique of Fantasy, Vol. 1: Between a Crypt and a Datemark - Laurence A. Rickels (punctum books, 2020)
Critique of Fantasy, Vol. 1: Between a Crypt and a Datemark addresses both the style or genre of fantasy and the mental faculty, long the hot property of philosophical ethics. Freud passed it along in his 1907 essay on the poetics of daydreaming when he addressed omnipotent wish fantasy as the source and resource of the aspirations and resolutions of art, which, however, the artwork can never look back at or acknowledge. By grounding his genre in the one fantasy that is true, the Gospel, J.R.R. Tolkien obviated and made obvious the ethical mandate of fantasy’s restraining order. With George Lucas’s Star Wars we entered the borderlands of the fantasy and science fiction genres, a zone resulting from and staggering a contest, which Tolkien inaugurated in the 1930s. The history of this contested borderland marks changes that arose in expectation of what the new media held in store, changes realized (but outside the box of what had been projected) upon the arrival of the unanticipated digital relation, which at last seemed to award the fantasy genre the contest prize. Freud’s notion of the Zeitmarke (datemark), the indelible impress of the present moment that triggered the daydream that denies it, already introduced the import of fantasy’s historicization. Science fiction won a second prize that keeps it in the running. No longer bound to projecting the future, the former calling which in light of digitization it flunked, science fiction becomes allegorical and reading in the ruins of its failed predictions illuminates all the date marks and crypts hiding out in the borderlands it traverses with fantasy. To motivate the import of an evolving science fiction genre, Critique of Fantasy makes Gotthard Günther’s reflections in the 1950s on American science fiction – as heralding a new metaphysics and a new planetary going on interstellar civilization – a mainstay of its cultural anthropology with B-genres.

Critique of Fantasy, Vol. 2: The Contest between B-Genres - Laurence A. Rickels (punctum books, 2020)
In The Contest between B-Genres, the “Space Trilogy” by J.R.R. Tolkien’s friend and colleague C.S. Lewis and the roster of American science fictions that Gotthard Günther selected and glossed for the German readership in 1952 demarcate the ring in which the contestants face off. In carrying out in fiction the joust that Tolkien proclaimed in his manifesto essay “On Fairy-Stories,” Lewis challenged the visions of travel through time and space that were the mainstays of modern science fiction. In the facing corner, Günther recognized in American science fiction the first stirrings of a new mythic storytelling that would supplant the staple of an expiring metaphysics, the fairy-story basic to Tolkien and Lewis’s fantasy genre. The B-genres science fiction and fantasy were contemporaries of cinema’s emergence out of the scientific and experimental study and recording of motion made visible. In an early work like H.G. Wells’s The Time Machine, which Tolkien credited as work of fantasy, the transport through time – the ununderstood crux of this literary experiment – is conveyed through a cinematic–fantastic component in the narrative, reflecting optical innovations and forecasting the movies to come. Although the historical onset of the rivalry between the B-genres is packed with literary examples, adaptation (acknowledged or not) followed out the rebound of wish fantasy between literary descriptions of the ununderstood and their cinematic counterparts, visual and special effects. The arrival of the digital relation out of the crucible of the unknown and the special effect seemed at last to award the fantasy genre the trophy in its contest with science fiction. And yet, although science fiction indeed failed to predict the digital future, fantasy did not so much succeed as draw benefit from the mere resemblance of fantasying to the new relation. While it follows that digitization is the fantasy that is true (and not, as Tolkien had hoped, the Christian Gospel), the newly renewed B-genre without borders found support in another revaluation that was underway in the other B-genre. Once its future orientation was “history,” science fiction began indwelling the ruins of its faulty forecasts. By its new allegorical momentum, science fiction supplied captions of legibility and history to the reconfigured borderlands it cohabited with fantasy. The second volume also attends, then, to the hybrids that owed their formation to these changes, both anticipated and realized. Extending through the topography of the borderlands, works by J.G. Ballard, Ursula Le Guin, and John Boorman, among others, occupy and cathect a context of speculative fiction that suspended and blended the strict contest requirements constitutive of the separate B-genres.

Critique of Fantasy, Vol. 3: The Block of Fame - Laurence A. Rickels (punctum books, 2021)
In The Block of Fame, Edmund Bergler, like the thirteenth fairy in the “Sleeping Beauty,“ uninvited because there wasn’t an extra place setting, crashes the psychoanalytic poetics of daydreaming with a curse. He charges that the overview, according to which art making rarefies daydreaming and delivers omnipotence, overlooks the underlying defense contract. We are hooked to creativity, because it offers the best defense against acknowledging the ultimate and untenable masochistic wish to be refused. Bergler’s bleak view, which Gilles Deleuze alone acknowledged in his study of Sacher-Masoch, doesn’t make any overall contribution to the aesthetics of fantasying that this critique addresses. However, it is a good fit with the centerpiece of the final volume: the wish for fame or, rather, the recoil of the wish in the wreckage that success brings. Following the opening season of mourning and the experience of phantoms, there is the second death, which is murder. In addition to the deadening end that can only be postponed – the killing off of the dead until dead dead – there is another second death that concludes the wish for fame with a ritual stripping of badges and insignia. Not only are the medals thrown to the ground and the sword broken, but a life’s work passes review. At the close of his career, Freud returned to the environs of the wish, the cornerstone of his science. While his disciples Otto Rank and Hanns Sachs carried out his 1907 insights regarding the poetics of daydreaming to illuminate, respectively, the mythic origin of the hero and the evolution of art out of the mutual daydream, Freud battened down for the end of his world by revisiting the so-called primal fantasy, the myth of the primal father, in Moses and Monotheism. The animal setting that was a given of its premier articulation in Totem and Taboo was a wrap this time around with Freud’s translation of Marie Bonaparte’s transference gift, a memoir recounting her premature mourning for her sick chow and the dog’s recovery from cancer of the jaw. In Bergler’s unconscious system, plagiarism is the conscious variation on the block basic to authorship. Theodor Adorno interpreted the ascendancy of the culture industry leading to and through the Third Reich in terms of the theft of modernism’s critical strategies for promoting the transformation of wish fantasy into the social relation of art. In the course of writing his essay “Notes on Kafka” between 1942 and 1952, Adorno was able to reclaim for aesthetic theory after Auschwitz the “constellation” that he and Benjamin had originally developed to outlast the culture industry’s depravation of the hopefulness of wishing. Adorno gives the sense or direction of the constellation’s recovery when he argues that Kafka’s work stages the final round of the contest between fantasy and science fiction by extrapolating doubling and déjà vu as the portals to a collective future. The wish for fame or to be refused it and the wish to steal this book or undo the delinquency demarcate the final movement of the third volume, which follows out, beginning with Susan Sontag and Gidget, a veritable Bildungsroman of the post-war era’s star, the teenager. Fantasying to make it big time means to be in training for big ideas and big feelings. The romance of fantasying was also reconfigured out of a station break. The Nazi elevation of youth to superego in the Heimat of the Teen Age neutralized adolescent innovation by forgoing the Hamletian stage of metabolization of the death wish. Switching to the other patient, the other teenager at heart, no longer the German but now the American or Californian, this study enters the termination phase of the analysis in the environs of a reach for the stars that is legend. It is the legend to the final volume’s mapping of our second nature as daydreamer believers.

Critique of Sovereignty, Book 1: Contemporary Theories of Sovereignty - Marc Lombardo (punctum books, 2015)
Using the Western tradition of metaphysical and political thought as a backdrop, Critique of Sovereignty (a work in four volumes) re-examines the concept of sovereignty in order to better understand why our ethical values and technical capacities often seem so divorced from our lived realities. On the one hand, ostensibly self-enclosed entities like the nation-state and the person are rhetorically bolstered as sites of technical agency and/or moral responsibility. On the other hand, these same entities appear fragile — if not purely fictional — in relation to ever ongoing tidal processes such as the migration, diffusion, and conglomeration of bodies, capital, ideas, etc. While some of our institutions might work some of the time, they always seem to work differently than we like to think they do. Accordingly, the forging of more humane institutions might very well entail if not require ways of thinking that strive to undo the self-imagined binds, exceptions, and sureties of thought for the sake of embracing a continuity with all that withers, decays, and falls away. Book I, “Contemporary Theories of Sovereignty,” compares the varied interpretations of sovereignty given by a range of 20th-century political theorists (Maritain, Foucault, Derrida, Schmitt, Agamben, Hardt, and Negri) with Jean Bodin’s initial outline of the concept, rendered at the outset of modern political thought in the 16th century. The analytic framework of sovereignty encountered in these comparative readings provides an initial point of departure for unfolding a method of critique appropriate to the concept of sovereignty. Sovereignty is an ideal starting point for a critique of the deadlocks between thought and reality for a simple reason: it doesn’t actually exist. When it serves as a guide to action, sovereignty may be regarded as a particularly captivating fantasy. The closer it appears, the further it recedes, and, too often, the more vigorously it is pursued.

Crossings: Migrant Knowledges, Migrant Forms - Natalya Din-Kariuki; Subha Mukherji; Rowan Williams (punctum books, 2025)
Crossings: Migrant Knowledges, Migrant Forms brings together activists, artists, scholars, and migrants with diverse histories to explore what the experience of migration does with, and to, knowledge, and how its own ways of knowing find expressive form. As the volume’s authors think about physical and imaginative crossings, and the traversals and transactions of knowledge they entail, the book itself crosses and complicates disciplinary and formal boundaries and the barriers between critical and creative intervention. Crucially, it brings together voices and forms emerging out of the experience of dislocation with responses to the encounters it generates. The volume’s discussions begin in the early modern world, and move freely across periods to dwell on the urgent experience of migrancy in our own times, while also responding to an urgent need to connect the local with the global experience of migrant knowledge and migrant aesthetics. Crossings stakes the claim that creative art, backed by humanities-based thinking, can meet the imaginative and ethical demands that the unknowable reality of mass displacement places on us, in a way that governments, institutions, and public discourse have calamitously failed to do. But aesthetic practice itself needs to be re-positioned if it is to rise to these political and human challenges, negotiating the points of friction between its own predilections and the matter of migration. Crossings offers “migrant forms” – art about migration, objects from migrant life shaped into artifacts, and migrant self-expressions – as the means of this imaginative re-orientation, and a tool for activating a radical alternative to economic models of social benefit. Crossings takes its place in an emergent ecology of migrant forms, both speaking to and participating in that ecology.

Crush - Will Stockton; D. Gilson (punctum books, 2014)
In Crush, a stunning collection of erotic poems and queer meditations delineating Stockton’ and Gilson’s mutual crushing on each other, but also all of the ways in which, sweetly and also sadly, affection ameliorates the anguishes that, despite our deepest devotions, are never constant, Stockton and Gilson write, In Aranye Fradenburg’s words, Shakespeare’s sonnets describe “the love you feel for inappropriate objects: for someone thirty years older, thirty years younger. The kind of love that makes a fool, a pervert, a stalker out of you.” Let’s start here, for much of this description applies to Petrarchan conventions as well. Let’s start here, with this affective entrance into the poems and the impossibility of dispossessing the other’s voice in the manufacture of one’s own machine. Let’s start here, with a vision of poems as indexes of crushes rendered inappropriate, unhealthy by some gradation of difference and level of intensity. With the question of what distinguishes a crush from love if both turn you into a different self. Under oak trees and sunlight, in coffee shops and locker rooms, steam rooms and seminar rooms, and in conversation with Milton, Shakespeare, Frank O’Hara, Narcissus, Allen Ginsberg, Jacques Derrida, Aranye Fradenburg, Mary Magdalene, Freud, Oscar Wilde, José Esteban Muñoz, Eve Kosofsky Sedgwick, Elton John, and Prince, among other poets, harlots, saints, and scholars, Stockton and Gilson explore the ways in which friendship, desire, falling, swerving, possession, holding, faggoting, falling, longing, poeming, and crushing open the self to queerly utopic, if also difficult, deflections — other, more improbable modes of being, as Foucault might have said.

Cycle of Dreams - Eric Weiskott (punctum books, 2024)
An experimental hybrid work, Cycle of Dreams pairs translation and original poetry. The translations, or adaptations, are of William Langland’s strange and wild fourteenth-century dream vision, Piers Plowman, a politically radical English and Latin poem written in the wake of plague and divided into a prologue and twenty passūs or steps. Eric Weiskott transposes the action from London and Worcestershire to New England and Long Island. The translations refashion and modernize Piers Plowman by disarticulating its continuous shape and rearticulating it as a collection of lyrics. The translation appears on the left and original poetry on the right in each page opening, so that the fourteenth and twenty-first centuries speak to one another as in a dream. Like Piers Plowman itself in manuscript culture, Cycle of Dreams attracts paratexts. Images illustrate the absent presence of Langland’s authorship. A series of glosses or marginal notes grounds the poems in critical theory, etymologies, lyric reminiscences, and statistics reflecting the desperation of our economic moment. An “oneirography” or dreamed bibliography names some of the scholarship that supports study of Piers Plowman today and some other sources for Langlandian fever dreams. Langland can address us today, not in the voice of a bygone author whose “context” must be arduously rearticulated in the laboratories of scholarly endeavor, but one whose utopian vision is in its broad outlines no less urgent in 2024 than it was in 1381, when English rebels used Langland’s title figure as a rallying cry for insurrection. Cycle of Dreams unearths “buried dreams / of a future adequate to the present tense.”

Dancing with Philoctetes: Reflections on Pain and Remembrance - Abigail Akavia (punctum books, 2023)
Abandoned by his community, doomed to a solitary existence with his voice as sole companion: can Sophocles’ Philoctetes still speak to us? What do his screams have to say? Dancing with Philoctetes: Reflections on Pain and Remembrance juxtaposes a new adaptation of Sophocles’ play with an essay describing the process of bringing it to life in a world on the brink of a pandemic. Akavia investigates Sophocles’ nuanced portrayal of the fragility of empathy in the face of suffering, and also shares the challenges of embodying and vocalizing Sophocles’ text onstage. She proposes that the pandemic and its aftermath offer a renewed perspective on Philoctetes’ thematization, not just of empathy and disease, but of the longing to return: to home, to health, to what memory holds. Akavia’s treatment of Philoctetes starts out from his body and voice and journeys on to loneliness, toxic masculinity, nostalgia, cancer, dreaming, parenthood, language, ballet lessons, siblings, music, and growing up. Here, scholarship and creative non-fiction combine to tell a story of reading, performing, thinking about, and living (through) tragedy. Listen to Abigail Akavia reflecting on her adaptation of Philoctetes on TangentCast:

Dark Chaucer: An Assortment - Nicola Masciandaro; Myra Seaman; Eileen A. Joy (punctum books, 2012)
Read Marion Turner’s review of Dark Chaucer in Studies in the Age of Chaucer HERE (https://punctumbooks.com/punctum/wp-content/uploads/2011/07/Review-of-Dark-Chaucer-Turner.pdf). Although widely beloved for its playfulness and comic sensibility, Chaucer’s poetry is also subtly shot through with dark moments that open into obscure and irresolvably haunting vistas, passages into which one might fall head-first and never reach the abyssal bottom, scenes and events where everything could possibly go horribly wrong or where everything that matters seems, if even momentarily, altogether and irretrievably lost. And then sometimes, things really do go wrong. Opting to dilate rather than cordon off this darkness, this volume assembles a variety of attempts to follow such moments into their folds of blackness and horror, to chart their endless sorrows and recursive gloom, and to take depth soundings in the darker recesses of the Chaucerian lakes in order to bring back palm- or bite-sized pieces (black jewels) of bitter Chaucer that could be shared with others… an “assortment,” if you will. Not that this collection finds only emptiness and non-meaning in these caves and lakes. You never know what you will discover in the dark.

Dear Professor: A Chronicle of Absences - Filip Noterdaeme (punctum books, 2016)
Dear Professor: A Chronicle of Absences is a collection of over two hundred often involuntarily comical emails in which students excuse themselves for missing class. The result is a satirical yet unexpectedly sympathetic collective portrait of modern-day academia where both students and teachers feel pressured to comply with the impositions of hyper-connectivity.

Deleuze and the Passions - Ceciel Meiborg; Sjoerd van Tuinen (punctum books, 2016)
In recent years the humanities, social sciences and neuroscience have witnessed an ‘affective turn,’ especially in discourses around post-Fordist labor, economic and ecological crises, populism and identity politics, mental health, and political struggle. This new awareness would be unthinkable without the pioneering work of Gilles Deleuze, who replaced judgment with affect as the very material movement of thought: every concept is an affective experience, a becoming. Besides entirely active affects, the highest practice of thought, there is no thought without passive affects or passions. Instead of a calm and rational philosophy of passions, Deleuzian thought is therefore inseparable from “isolated and passionate cries” that deny what everybody knows and what nobody can deny: “every true thought is an aggression.” This inseparability of reason and passion is by no means an anti-intellectualist or irrationalist stance. Rather, it is critical, since it protects reason from its self-imposed stupidity (bêtise) by relating it to the unthought forces that condition it. And it is clinical, because thought becomes possessed by a power of selection. The purely active, i.e. free-floating, unrecorded desire, is never enough to produce a consistent relation to the future, which is why we need the passions to give us an initial orientation, to force and enable us to think. Passions are the beliefs, perceptions, representations, and opinions that attach us to the world; they make up the very material of which our lives and thoughts are composed. Instead of truth as the ultimate criterion of judgment, the only principle according to which affective becomings can be selected and evaluated is the extent to which they proliferate joy. Spinoza and Marx show how the recruitment of desire traditionally takes place through the tyrants and priests who inspire sad passions in us. Similarly, the work of Deleuze and Guattari on capitalism and schizophrenia can be read as an encyclopedia of the passions that constitute the affective infrastructure of the socius of contemporary capitalism. If it takes a lot of inventiveness or imagination to be able to diagnose our present becomings, this is because becomings are always composites of joyful and sad passions. Capitalism could not exist if it did not also inspire happiness, love, courage, and perhaps even beatitude. That is why, today, we witness “the spectacle of the happily dominated” (Frédéric Lordon) of the self-entrepreneur, the managerial class, the flex worker, the citizen-consumer, the bean-roasting hipster, and the self-managed team. It is within this field of contradictory and heterogeneous passions that the authors of this volume pursue the diagnosis of our past and present becomings. Their contributions add up to a systematic taxonomy of the passions and indicate their importance for a thinking that reaches beyond itself.

Derrida and Queer Theory - Christian Hite (punctum books, 2017)
Coming from behind (derrière) — how else to describe a volume called “Derrida and Queer Theory”? As if arriving late to the party, or, indeed, after the party is already over. After all, we already have Deleuze and Queer Theory and, of course, Saint Foucault. And judging by Annamarie Jagose’s Queer Theory: An Introduction, in which there is not a single mention of “Derrida” (or “deconstruction”) — even in the sub-chapter titled “The Post-Structuralist Context of Queer” — one would think that Derrida was not only late to the party, but was never there at all. This untimely volume, then, with wide-ranging essays from key thinkers in the field, addresses, among other things, what could be called the disavowed debt to “Derrida” in canonical “queer theory.”

Desire/Love - Lauren Berlant (punctum books, 2012)
“There is nothing more alienating than having your pleasures disputed by someone with a theory,” writes Lauren Berlant. Yet the ways in which we live sexuality and intimacy have been profoundly shaped by theories — especially psychoanalytic ones, which have helped to place sexuality and desire at the center of the modern story about what a person is and how their history should be read. At the same time, other modes of explanation have been offered by popular and mass culture. In these domains, sexual desire is not deemed the core story of life; it is mixed up with romance, a particular version of the story of love. In this small theoretical novella-cum-dictionary entry, Lauren Berlant engages love and desire in separate entries. the first entry, Desire, mainly describes the feeling one person has for something else: it is organized by psychoanalytic accounts of attachment, and tells briefly the history of their importance in critical theory and practice. The second entry, Love, begins with an excursion into fantasy, moving away from the parent-child structure so central to psychoanalysis and looking instead at the centrality of context, environment, and history. The entry on Love describes some workings of romance across personal life and commodity culture, the place where subjects start to think about fantasy on behalf of their actual lives. Whether viewed psychoanalytically, institutionally, or ideologically, love is deemed always an outcome of fantasy. Without fantasy, there would be no love. Desire/Love takes us on a tour of all of the things that sentence might mean.

Desire: Subject, Sexuation, and Love - Ana María Munar (punctum books, 2026)
Have you ever wondered what makes you wake up in the morning? Why not just lay down, stay, and eventually disappear? What is the wanting, the energy, and the grace of liveliness? Desire is at the core of liveliness, and this book explains why it is so. Desire is much more than a mere appendix to love, sex, or our craving to have the latest fashion item. It is what allows the most personal and unique expression of each of us. Desire: Subject, Sexuation, and Love is a work of gratitude to the Lacanian tradition and feminist philosophy. It creatively uses the story of “The Little Mermaid” by H.C. Andersen, as well as art and popular culture to explain the complex landscape of desire and its relation to love and sexuation. Much of the criticism of psychoanalysis from gender studies and poststructuralism is based on a superficial reading of Jacques Lacan, and Munar corrects this, providing in the first half of the book a rigorous and clear analysis of Lacanian subjectification and sexuation, elucidating their relationship to the nature of desire and love, in order to modify overly simplistic and erroneous interpretations of his thinking on desire. Desire is essayistic and poetic philosophy, drawing upon and playing with psychoanalysis, philosophy, literature, biography, poetry, and art. As the reader enters the second part of the book, the focus on Lacanian theory recedes, opening a space that is more paradoxical and multiple where Munar engages in creative form as an expression of critique, transforming our understandings of desire and love, which always elude us while also always being present.

Destroyer of Naivetés - Joseph Nechvatal (punctum books, 2015)
Joseph Nechvatal’s epic passion poem, Destroyer of Naivetés, takes up a position of excess from within a society that believes that the less you conceal, the stranger you become. We live and love in a culture where surveillance/intrusion is tied to our drive for self-revealing everything (an anti-private-life culture of curiosity, egotism, solitude, fear, voyeurism, exhibitionism and resentment — where the feeling is that nothing could or should remain unknown to us). The sex farce poetic overindulgence of Destroyer of Naivetés takes inspiration from the books of Jean Genet, Marcel Duchamp’s The Bride Stripped Bare by Her Bachelors, Even, drawings by Hans Bellmer, film/performances of Bradley Eros, and the erotic scribblings of Giacomo Casanova, Georges Bataille, Petronius, Vladimir Nabokov, Marquis de Sade, Yukio Mishima, Ovid, Leopold von Sacher-Masoch, Kathy Acker and I Am a Beautiful Monster by Francis Picabia.

Dialectics Unbound: On the Possibility of Total Writing - Maxwell Kennel (punctum books, 2013)
Dialectics Unbound: On the Possibility of Total Writing re-imagines figures of ontological totality, in and out of writing, first by exploring some lineages of the dialectic, and second by engaging thinkers such as Theodor Adorno and his assertion of nonidentity, Julia Kristeva and her positing of a fourth term of the dialectic, and Fredric Jameson’s treatment of the dialectic as an open totality. By articulating a concept of totalization-without-totality, Dialectics Unbound seeks to free the concept of the dialectic from the violence of closure, and then to take this unbound dialectics to the work of writing through a brief examination of parataxis and aphoristics as approaches to writing, both possible and impossible.

dis/cord: Thinking Sound through Agential Realism - Kevin Toksöz Fairbarn (punctum books, 2022)
dis/cord is an experiment in reading sound. Embarking from Karen Barad’s early work on agential realism, it diffracts quantum physics through sound art, finding the sympathetic resonances that allow them to speak together. dis/cord believes in the materialism of sound, and strives not to understand it, but to become entangled with it. It asserts that impartial observation is impossible and understands immersion as a participatory and collaborative act. Sound art pieces provide the backdrop for a series of reflections on space, time, and matter. They trace the “marks on bodies” that sound leaves behind in its ephemeral vibration, finding new forms of sensation and interpretation through the pain and hearing loss that a life devoted to sound can cause. Drifting between sound studies, artistic research, musicology, and craftsmanship, dis/cord uses agential realism as a platform to approach thinking with, through, and about sound. Following Barad’s commitment to diffraction as a form of critique, it superposes a variety of sounds and ideas in the hope that their consonances and dissonances can provoke new ways of engaging with sound as a cultural and material agent. It is neither an appeal to scientist positivism nor a mystical immersion in listening. Rather, it builds from the intertwined physical and metaphysical curiosities that characterize Barad’s work, proposing a corporeal engagement with the disjointed temporal and spacial (dis)continuities that sonic materialism helps to build, understand, and create.

Diseases of the Head: Essays on the Horrors of Speculative Philosophy - Matt Rosen (punctum books, 2020)
Diseases of the Head is an anthology of essays from contemporary philosophers, artists, and writers working at the crossroads of speculative philosophy and speculative horror. At once a compendium of multivocal endeavors, a breviary of supposedly illicit ponderings, and a travelogue of philosophical exploration, this collection centers itself on the place at which philosophy and horror meet. Employing rigorous analysis, incisive experimentation, and novel invention, this anthology asks about the use that speculation can make of horror and horror of speculation, about whether philosophy is fictional or fiction philosophical, and about the relationship between horror, the exigencies of our world and time, and the future developments that may await us in philosophy itself. From philosophers working on horrific themes, to horror writers influenced by heresies in the wake of post-Kantianism, to artists engaged in projects that address monstrosity and alienation, Diseases of the Head aims at nothing less than a speculative coup d’état. Refusing both total negation and absolute affirmation, refusing to deny everything or account for everything, refusing the posture of critique and the posture of all-encompassing unification, this collection of essays aims at exposition and construction, analysis and creation – it desires to fight for some thing, but not everything, and not nothing. And it desires, most of all, to speak from the position of its own insufficiency, its own partiality, its own under-determinacy, which is always indicative of the practice of thinking, of speculation. Considering themes of anonymity, otherness and alterity, the gothic, extinction and the world without us, the end times, the apocalypse, the ancient and the world before us, and the uncanny or unheimlich, among other motifs, this anthology seeks to articulate the cutting edge which can be found at the intersection of speculative philosophy and speculative horror.

I Open Fire - David Pol (punctum books, 2014)
In I Open Fire, translated from Polish into English, David Pol presents an ontology of war in the form of the lyric poem. In I Open Fire, all relation is warfare. Minefields compromise movement. Intention aims. Touch burns. Sex explodes bodies. Time ticks in bomb countdowns. Sound is sirens. Plenitude is debris. All of it under surveillance. “My world is critically injured. The poems in this book perform the reductions and repetitions endemic to war itself, each one returning the reader to the same, unthinkable place in which the range of human experience has been so flattened that, despite all the explosive action, Against this backdrop, we continue to fall in love. But Pol’s poems remind us that this is no reason for optimism. Does love offer a delusional escape from war, or are relationships the very definition of combat? These poems take up the themes of love, sex, marriage, touch, hope — in short, the many dimensions of interpersonal connection — in a world in unprecedentedly critical condition.

Irradiated Cities - Mariko Nagai (punctum books, 2023)
The before, the after, and the event that divides. In Irradiated Cities, Mariko Nagai seeks the dividing events of nuclear catastrophe in Japan, exploring the aftermath of the bombings at Hiroshima and Nagasaki and the nuclear meltdown at Fukushima. Nagai’s lyric textual fragments and stark black and white photographs act as a guide through these spaces of loss, silence, echo, devastation, and memory. And haunting each shard and each page an enduring irradiation, the deadly residue of catastrophe that leaks into our DNA. This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

Iteration:Again: 13 Public Art Projects across Tasmania - David Cross (punctum books, 2013)
Iteration:Again documents and reflects upon a series of thirteen temporary public art commissions by twenty-one Australian and international artists that took place across Tasmania from September 18 to October 15, 2011. Produced by Contemporary Art Spaces Tasmania and David Cross, in conjunction with seven partner curators, Iteration:Again presents a compelling array of temporary artworks in largely unexpected places throughout Tasmania. Working to transform our experience of place for a moment in time, each commission seeks to address how temporary interventions or responses by artists to public sites, environments and buildings can serve to open up new ways of understanding Tasmania as a place with very complex cultural, social and spatial resonances. How it might be possible to introduce transformative elements that challenge the notion of a fixed or definitive artwork grounded in one location? By asking the artists to make four different chapters or ‘iterations’ over the course of a four-week period, David Cross challenged each practitioner to think through how change or processes of transition may function to make the art experience an unstable and contingent one. This idea of incorporating change into the work highlights a growing interest by artists in emphasizing art as a potentially theatrical or even fictive medium with the audience experiencing different moments or stages of encounter over a number of weeks. The idea provided for the possibility of narrative sequences, formal investigations, or temporal shifts that saw key additions or subtractions over time. Each commission sought to recast our understanding of public artwork from a discrete event or viewing experience, to a suite of experiences. The book includes sections on each project by the artists, including Ruben Santiago, Paul O’Neill, Maddie Leach and Toby Huddlestone, with a curatorial statement introducing the work and a commissioned response by thirteen Australian and international writers. It also features two major essays on key issues in temporary public art, including a curatorial essay by Cross and an essay on post-studio practice by noted public art scholar and curator Marco Marcon.

Itinerant Philosophy: On Alphonso Lingis - Bobby George; Tom Sparrow (punctum books, 2014)
Alphonso Lingis is the author of fourteen books and many essays. He is emeritus professor of philosophy at Pennsylvania State University. While many know him only as an eccentric ex-professor or as the translator of Emmanuel Levinas, Maurice Merleau-Ponty, and Pierre Klossowski, he is arguably the most distinctive voice in American continental philosophy. This is no doubt due to the perpetual travel that fuels his arresting written prose and unorthodox public readings. Lingis’s lifelong itinerary includes visits — some brief, others extended or recurring — to 109 countries. Along the way he has photographed innumerable strangers whose faces adorn the pages of his books. Photography is as essential to Lingis’s multidisciplinary philosophical perspective as is his knowledge of phenomenology, anthropology, or psychoanalysis. Some of his photographs have been recently collected and published in the book Contact. Unlike most career academics, Lingis has made a name for himself collecting exotic birds and other creatures, staging performance readings at professional conferences, keeping up a diligent correspondence with friends at home and abroad, and splicing together high theory with intimate autobiography. Those who know him speak of his warmth, sincerity, and noncombative style of argumentation — rare traits among university scholars. Itinerant Philosophy: On Alphonso Lingis gathers a diverse collection of texts on Lingis’s life and philosophy, including poetry, original interviews, essays, book reviews, and a photo essay. It also includes an unpublished piece by Lingis, “Doubles,” along with copies of several of his letters to a friend.

Itinerant Spectator/Itinerant Spectacle - P.A. Skantze (punctum books, 2013)
Itinerant Spectator/Itinerant Spectacle moves across the landscape of European performance in late 20th and early 21st centuries, recounting performance in circulation across national borders and across the itinerant bodies of spectators who travel to meet performances that travel. Itinerant Spectator/Itinerant Spectacle suggests spectating is a practice — an act of interpretation engaged in more than simply receiving the affects of a performance, a companion practice to the making of performance. The work forms a part of Skantze’s ongoing explorations of what she terms the ‘epistemology of practice as research.’ IS/IS theorizes spectating as a practice that extends beyond the theatre, as a practice of writing as recollecting (and recollecting as writing) at the center of what has been called “criticism.” The book grounds spectatorship in the subjective, embodied, differenced practice of spectating not from a fixed location or standpoint but from a ground that constantly shifts, that is, from the ground of the roving positionalities of the “itinerate spectator.” Following Walter Benjamin, for example, Skantze importantly adopts the privileges of the flaneur as a feminist and rather queer project, one that refuses to be tied to the minor position, to that of the impossible “flaneuse.” The methodology of the book takes inspiration from the writings of W.G. Sebald and his employment of something Skantze describes as “a staging of memory,” a way to offer the reader an example of how memory works in the midst of a description of a particular recollection. This construction invites the reader/participant to ‘discover,’ to ‘remember’ alongside the writer. Further, this methodology invites the reader to incorporate her/his own ideas and memories of the practice of spectating through an openness in the language of remembering and description. Individual sections of the book demonstrate spectating as itinerant ‘on the job training’ in various modes of reception. Topics include: the idea of reparation in performance about nations, the past and injustice; the power of sound and the intricacies of seeing/hearing performance in many languages; the architectural information absorbed by the spectator and its role in fashioning story; the shifts made in spectating at festivals between theatre and dance; and the political consequences and traps of mobility and immobility.

Janky Materiality: Artifice & Interface - J †Johnson (punctum books, 2026)
Janky materiality works by not working. It is the spirit in the machine, the ghost in language, the provisional operation. It is a musicological poetics run through a patchwork apparatus. Janky Materiality: Artifice & Interface is a transdisciplinary performative critical investigation of analog-digital interface and materiality, language-oriented poetry and digital language art, experimental electronic music and modular synths, and the technology of film, album, and book. Janky Materiality explores blurry intersections and cracked interfaces between page, screen and speaker, analog and digital practice. With reference to avant-garde poetics, digital language art, experimental electronic music and modular synths, chance operations and oracular knowing, Johnson thinks about the ways digital material practice extends the post-structural field, as page-based practices are (further) destabilized by computer-based experiments. Language itself is a janky technology that works (at least temporarily) through its own failures, so that digital mediation serves to further break and rewire language operations. Meanwhile, the book also explores sonification and the study of waveforms: hybrid audio-visual objects that can be materially sculpted and analyzed. Ultimately, Janky Materiality presents a theory of becoming-digital, where interface is a matter of thinking and acting between and among embodied and conceptual, analog and digital realms, whether we are thinking about a technology like language, audio-visual phenomena, or a tool at hand.

John Gardner: A Tiny Eulogy - Phil Jourdan (punctum books, 2012)
John Gardner’s career was permanently changed by his publication of On Moral Fiction (1978), a controversial and derided assessment of the state of literature as Gardner saw it. By arguing for a return to greater seriousness and moral commitments in literature, Gardner found himself attacked on all sides by critics and writers who found his conservatism suspicious or simply irrelevant. In this short tribute to Gardner’s late intellectual concerns, Phil Jourdan looks at some of the difficulties in On Moral Fiction, and asks whether Gardner was rigorous enough in his deployment of various philosophical concepts through his book. Convinced that, despite any problems of argumentative method or intellectual honesty, On Moral Fiction‘s basic message should not be dismissed outright, Jourdan tries to determine what is superfluous to the book, so that we may focus on its core: a call for writers not to forget their moral influence on readers. Now that Gardner’s career is half-forgotten, it is worth remembering this impassioned and public debate on the role of literature has been around far longer than we care to pretend: throughout the centuries, as literature attempts to define itself over and over, the question of morality is always lurking in the background. In John Gardner: A Tiny Eulogy, Phil Jourdan tries to separate the man from the argument, and insists that the latter should not be dismissed because of the imperfection of the former.

Jorge Luis Borges: At Play with Mental Models of the World - Luis O. Arata (punctum books, 2026)
Jorge Luis Borges: At Play with Mental Models of the World explores mind-world relations through the creative writings and reflections of the iconic Argentine author, along with insights from corresponding findings in the field of cognitive studies. A selection of representative works—stories, poems, and essays—illuminates features of the constructive imagination that Borges sets in motion to personally blend mind and world, a venture to which he dedicated his life to the very end. This book is for readers from a broad range of backgrounds, interested in the interactive workings of mind and world through fiction, the imagination, and embodied cognition. Over the years, Borges playfully created and tinkered with models of the self, time, fiction, reality, history, solitude, and reciprocity, among other cognitive objects. Arata focuses on a selection of representative works of Borges to examine how he modeled and then remodeled, over time, his perceptions of the world and his presence in it. Of particular importance was the onset of blindness halfway through his literary life, which led him to playfully remodel certain aspects of his early views of experiencing the world. There was also his surprising partnership with María Kodama toward the end of his life, when he went from prizing solitude to experiencing a sense of reciprocity hardly felt before. Arata concludes this exploration with a view of Borges’s burial headstone that is in stark contrast to his youthful idea that his death would happen in Buenos Aires, with his vanishing engraved in cold marble. Instead, Borges chose to pass away in Geneva, and was buried next to an earthy, rough headstone engraved simply with what could be seen as his playful final story. Ultimately, Arata’s book asks, to what extend does the mind shape our perception of the world? Through his work, Borges provides us with a personal, passionate example of how fiction and reality blend to create a multiplicity of striking meanings and his writings trace the poignant human quality of a life devoted to conjuring meaning through the interactions of narrative models that emerge from weaving dreams, memories, observations, reflections, and choices.

Journal of Badiou Studies 3: On Ethics - Nicolò Fazioni; Michael J. Kelly; Arthur Rose (punctum books, 2014)
Journal of Badiou Studies (General Editors: Michael J. Kelly and Arthur James Rose) is a multilingual, peer-reviewed journal dedicated to the philosophy and thought of, and surrounding, the philosopher, playwright, novelist, and poet Alain Badiou. Badiou Studies is dedicated to original, critical and challenging arguments that directly engage with the conditions and circumstances of Badiou’s thought. We aim to identify pertinent intellectual discourses, ideas, historiographies, and concepts, and seek articles that situate these theories within emerging events in politics, science, art and love. Badiou Studies is especially concerned with maintaining a fidelity to Badiou’s thinking without collapsing into hagiography or celebrity fetishism. This is why we encourage works that actively critique Badiou’s philosophy and his currency as an established philosophical figure. Badiou himself embraces this approach and serves on the journal’s Advisory Board. Alain Badiou’s small book on ethics (Ethics: An Essay on the Understanding of Evil (http://books.google.com/books?id=eLfF6z2BtPgC&source=gbs_navlinks_s)) remains one of the most important points of entry into Badiou’s thought, since it is not only widely read across disciplines but is also one of the most widely translated of all of his works. This issue of Badiou Studies (Vol. 3) draws together scholarly responses and criticisms to Badiou’s ethics. Sometimes in agreement, sometimes in violent opposition, always faithful to the imperative to keep thought going.

Journal of Badiou Studies 5: Architheater - Michael J. Kelly; Arthur Rose; Adi Efal-Lautenschläger (punctum books, 2017)
The fifth volume of the Journal of Badiou Studies, “Architheater,” energized by the publication of Badiou’s Rhapsodie pour le théâtre (2014), knits together distinguished approaches to artistic production engaging with the work of Alain Badiou: ‘Engaging’ here means articulated positions that include, imply, or criticize the Badiouiesque corpus. The issue does not therefore seek to implement Badiou’s philosophical insights in interpretations of art or of aesthetics, but rather to take Badiou’s philosophy as a center of convergence-nexus of a plethora of philosophical positions that include artistic production as a central element of their structure. Thematically, the volume limits its discussion to “a two” of architecture and theater, thinking their overlapping, juxtaposition, and respective generative capacities. JBS 5 suggests superimposing these two “media” and posing them at the center of the volume for several reasons: Politically, both theater and architecture actively engage in the life of the polis, they effectually and factually demand the participation of collective and material actors. Poietically, both media manifest a comprehensive form of artistic production, that is to say they both include elements and organs (actors, designers, lighting-specialists, engineers, planners, executives, actors, dancers, etc.) that are required as collaborators in the realization of the piece. The Architect, on the one hand, and the Theater maker, on the other, both produce what could be defined as a world, or, in Badiou’s terms, a formation of a subject. Moreover, JBS 5 explores the political aspect of the relationship between Badiou’s concept of “state” (l’état) and the architheatrical activity. Indeed in Thèses sur le théâtre (1995), Badiou writes: “La difficulté générale du théâtre, à toutes les époques, est son rapport à l’Etat.” If one considers this paradigm with Badiou’s L’être et l’événement in mind, one could analyze the manner in which the arts work with and/or against ontology, as well as carry an ethical tenor, with their responsibility towards a Truth. Badiou, an active playwright himself, integrated into his thought from early on dramatic and theatrical topoi. Already in Théorie du sujet, one finds the Greek theater as an active player in his architecture of the subject. The activities of construction, conditions, subtraction, installation, generation, modelling all being prominent terms in the philosophy of Badiou, should be conceived within an architheatrical framework. Present-day artistic manifestations — such as the art-fair, video art, installation art, site-specific arts, performance etc. — could be viewed as re-generating an art “form,” the architheater in which ontology, that is to say space, is configured by reality (that is to say duration or history). Finally, the “Il y a de deux” of theater and architecture invites to rethink the role of the receptor (otherwise known as the “spectator” the “public” or the “inhabitant”) of art, an issue having to do with the Badiou-Rancière debate. Naturally, the volume tries to take advantage of Badiou’s philosophy in order to think beside rather than within the Aesthetic regime to the best possible extent, adopting instead a generative, that is to say a poietical, productive approach to art.

Kayfabe Nation: Professional Wrestling, Donald Trump, and the New Cynicism - Neal Hebert; Jon Cogburn (punctum books, 2026)
What do a pudgy, orange autocrat, and pumped-up men in tights have in common? The connections, while profound, all rest on specific strategies employed by World Wrestling Entertainment during the early 2000s (known as WWE’s “Attitude Era”) when Donald Trump was centrally involved with the promotion of WWE. These are: (1) universally breaking kayfabe, the code of people in the industry not to reveal or admit fakery; (2) Vince McMahon (WWE’s CEO at that time) playing a fictional version of himself as someone constantly humiliated in storylines; (3) the vicious affirmation of traditional gender roles through parables of male domination; and (4) telling stories that encourage viewers to ignore the actual material conditions of WWE “superstars” in favor of conspiratorial fictions involving powerful individual actors. In Kayfabe Nation: Professional Wrestling, Donald Trump, and the New Cynicism, Hebert and Cogburn present a trenchant analysis of Attitude Era WWE, showing the extent to which MAGA is just is a function, or symptom, of Trump’s internalization of WWE’s most objectionable tropes. Neal Hebert and Jon Cogburn’s goal is not to use WWE merely to understand Trumpism and the related autocratic turn in countries as diverse as El-Sisi’s Egypt, Putin’s Russia, Erdogan’s Turkey, Modi’s India, Bolsonaro’s Brazil, Orbán’s Hungary, Netanyahu’s Israel, and of course Trump’s own America. Beyond that, Kayfabe Nation is a defense of truth against the lie that culminates in the widespread adoption of self-defeating conspiracy theories among the constituency of the right, as well as against the idea, popular in corrupted center-left parties across the planet that political success comes down to adopting better rhetorical strategies, strategies that exist in part to cover over their abandonment of New Deal and socialist ideologies where the material conditions of their constituencies would actually improve.

Kern - Derek Beaulieu (punctum books, 2023)
Proposed as a collection of imaginary logos for the corporate sponsors of Borges’s Library of Babel, Kern balances on a precipice between the visual and nonsensical, offering poems just out of meaning’s reach. Using dry-transfer lettering, Beaulieu made these concrete pieces by hand, building the images gesturally in response to shapes and patterns in the letters themselves. This is poetry closer to architecture and design than confession, in which letters are released from their usual semantic duties as they slide into unexpected affinities and new patterns. Kern highlights the gaps inside what we see and what we know, filling the familiar with the singular and the just seen with the faintly remembered. This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

Kill Boxes: Facing the Legacy of US-Sponsored Torture, Indefinite Detention, and Drone Warfare - Elisabeth Weber (punctum books, 2017)
Kill Boxes addresses the legacy of US-sponsored torture, indefinite detention, and drone warfare by deciphering the shocks of recognition that humanistic and artistic responses to violence bring to consciousness if readers and viewers have eyes to face them. Beginning with an analysis of the ways in which the hooded man from Abu Ghraib became iconic, subsequent chapters take up less culturally visible scenes of massive violations of human rights to bring us face to face with these shocks and the forms of recognition that they enable and disavow. We are addressed in the photo of the hooded man, all the more so as he was brutally prevented, in our name, from returning the camera’s and thus our gaze. We are addressed in the screams that turn a person, tortured in our name, into howling flesh. We are addressed in poems written in the Guantánamo Prison camp, however much American authorities try to censor them, in our name. We are addressed by the victims of the US drone wars, however little American citizens may have heard the names of the places obliterated by the bombs for which their taxes pay. And we know that we are addressed in spite of a number of strategies of brutal refusal of heeding those calls. Providing intensive readings of philosophical texts by Jean Améry, Jacques Derrida, and Christian Thomasius, with poetic texts by Franz Kafka, Paul Muldoon, and the poet-detainees of Guantánamo Bay Prison Camp, and with artistic creations by Sallah Edine Sallat, the American artist collective Forkscrew and an international artist collective from Pakistan, France and the US, Kill Boxes demonstrates the complexity of humanistic responses to crimes committed in the name of national security. The conscious or unconscious knowledge that we are addressed by the victims of these crimes is a critical factor in discussions on torture, on indefinite detention without trial, as practiced in Guantánamo, and in debates on the strategies to circumvent the latter altogether, as practiced in drone warfare and its extrajudicial assassination program.

Knocking the Hustle: Against the Neoliberal Turn in Black Politics - Lester K. Spence (punctum books, 2015)
Over the past several years scholars, activists, and analysts have begun to examine the growing divide between the wealthy and the rest of us, suggesting that the divide can be traced to the neoliberal turn. “I’m not a business man; I’m a business, man.” Perhaps no better statement gets at the heart of this turn. Increasingly we’re being forced to think of ourselves in entrepreneurial terms, forced to take more and more responsibility for developing our “human capital.” Furthermore a range of institutions from churches to schools to entire cities have been remade, restructured to in order to perform like businesses. Finally, even political concepts like freedom, and democracy have been significantly altered. As a result we face higher levels of inequality than any other time over the last century. In Knocking the Hustle: Against the Neoliberal Turn in Black Politics, Lester K. Spence writes the first booklength effort to chart the effects of this transformation on African American communities, in an attempt to revitalize the black political imagination. Rather than asking black men and women to “hustle harder” Spence criticizes the act of hustling itself as a tactic used to demobilize and disempower the communities most in need of empowerment.

Knowledge, Spirit, Law - Gavin Keeney (punctum books, 2015)

Knowledge, Spirit, Law, Book 1: Radical Scholarship - Gavin Keeney (punctum books, 2015)
Knowledge, Spirit, Law is a de facto phenomenology of scholarship in the age of neoliberal capitalism. The eleven essays (plus Appendices) in Book 1: Radical Scholarship cover topics and circle themes related to the problems and crises specific to neoliberal academia, while proposing creative paths around the various obstructions. The obstructions include metrics-obsessed academia, circular and incestuous peer review, digitalization of research as stalking horse for text- and data-mining, and violation by global corporate fiat of Intellectual Property and the Moral Rights of Authors. These issues, while addressed obliquely in the main text, definitively inform the various proscriptive aspects of the essays and, via the Introduction and Appendices, underscore the necessity of developing new-old means to no obvious end in the production of knowledge — that is to say, a return to forms of non-instrumentalized intellectual inquiry. To be developed in two concurrent volumes, Knowledge, Spirit, Law will serve as a “moving and/or shifting anthology” of new forms of expression in humanistic studies.

Knowledge, Spirit, Law, Book 2: The Anti-Capitalist Sublime - Gavin Keeney (punctum books, 2017)
Knowledge, Spirit, Law // Book 2: The Anti-capitalist Sublime takes up where Knowledge, Spirit, Law // Book 1: Radical Scholarship (https://punctumbooks.com/titles/knowledge-spirit-law/) left off, foremost in terms of a critique of neo-liberal academia and its demotion of the book in favor of various mediatic practices that substitute, arguably, for the one form of critical inquiry that might safeguard speculative intellectual inquiry as long-form and long-term project, especially in relationship to the archive or library (otherwise known as the “public domain”). This ongoing critique of neo-liberal academia is a necessary corrective to processes underway today toward the further marginalization of radical critique, with many of the traditional forms of sustained analysis being replaced by pseudo-empirical studies that abandon themes only presentable in the Arts and Humanities through the “arcanian closure” that the book as long-form inquisition represents (whether as novel, non-fictional critique, or something in-between). As a tomb for thought, this privileging of the shadowy recesses of the book preserves, through the very apparatuses of long- and slow-form scholarship, the premises presented here as indicative of an anti-capitalist project embedded in works that might otherwise shun such a characterization. The perverse capitalist capture of knowledge through mass digitalization is — paradoxically — the negative corollary for the reduction by abstraction of everyday works to a philosophical and moral inquest against Capital. The latter actually constitutes a transversal reduction for works (across works) toward the age-old antithesis to instrumentalized socio-cultural production — Spirit. For similar reasons, the anti-capitalist sublime as presented here is primarily a product of the imaginative, magical-realist regimes of thought in service to “no capital” — to no capitalization of thought. This book seeks to re-establish paradigmatic, a-historical, and universalizing practices in humanistic scholarship associated with speculative inquiry as a form of art, utilizing in passing forms of art and exemplary paradigmatic practices that are also first-order forms of speculative inquiry — suggesting that first-order works in the Arts and Humanities are those works that may “suffer” second-order incorporations without the attendant loss of the impress of sublimity (Spirit).

Labyrinths: New and Selected Writings - M. Munro (punctum books, 2026)
“Why are penetrating questions so much harder to formulate than penetrating answers?” critic Louis Bury asks. Why, indeed. It’s a great question, and also the throughline of Labyrinths: New and Selected Writings. In this collection, Munro formulates penetrating questions (punctums) again and again, and with style and economy. The stories that follow are never reduced to examples, illustrating one theory or another, but answer these questions in the most fitting way possible: by giving them an additional fillip, enriching each. This is the kind of twist only literature (and the humanities) can provide. Labyrinths is Munro’s seventh book and continues his tradition of gnomic-styled writings that have been described as “intellectual origami,” “koan-like,” “flower-like,” and “rooted in sweetness,” with lines of inquiry that “auto-deconstruct, bridges crumbling as the author crosses them.” The current volume gathers into a fragrant florilegium the best of earlier writings with newer pieces that bring together in artfully whimsical fashion Aristotle, Gilles Deleuze, G.W.F. Hegel, Giorgio Agamben, Graham Harman, Fred Moten, the Mahābhārata, Marcel Proust, Andrea Long Chu, aesthetics, parables, kōans, autotheory, Franz Kafka, Ovid, Rey Chow, bell hooks, Lauren Berlant, Baruch Spinoza, and more.

Lamma: A Journal of Libyan Studies 1 - Leila Tayeb; Adam Benkato; Amina Zarrugh (punctum books, 2020)
Lamma aims to provide a forum for critically understanding the complex ideas, values, social configurations, histories, and material realities in Libya. Recognizing, and insisting on, the urgent need for such a forum, we give attention to a wide a range of disciplines, sources, and approaches, foregrounding especially those which have previously received less scholarly attention. This includes, but is not limited to: anthropology, art, gender, history, linguistics, literature, music, performance studies, politics, religion, and urban studies, in addition to their intersections, their subfields, the places in between, and critical, theoretical, and postcolonial approaches thereto. Lamma is a space where these fields can interact and draw from one another, and where scholars and students from inside and outside of Libya gather to redefine and reshape “Libyan Studies.” We believe that access to research is not the privilege of a few but the right of all and that knowledge production should be inclusive. For these reasons the journal takes its name from the Arabic word lamma, “a gathering.” This first issue of Lamma brings together academic research, cultural commentary, literature, and translation. It aims to show some of the possible varieties of research on Libya, from history and literature to sociolinguistics, gender studies, and more. But, perhaps more importantly, it aims to show that the efforts of academic researchers, cultural actors, writers, translators, and even artists are not separate endeavors but rather intertwined. By bringing these efforts together in one forum, we hope to set them in fruitful dialog with each other—and thus begin to complexify the notion of “Libyan Studies.”

Lamma: A Journal of Libyan Studies 2 - Adam Benkato; Leila Tayeb; Amina Zarrugh (punctum books, 2023)
Lamma aims to provide a forum for critically understanding the complex ideas, values, social configurations, histories, and material realities in Libya. Recognizing, and insisting on, the urgent need for such a forum, we give attention to as wide a range of disciplines, sources, and approaches as possible, foregrounding especially those which have previously received less scholarly attention. This includes, but is not limited to: anthropology, art, gender, history, linguistics, literature, music, performance studies, politics, religion, and urban studies, in addition to their intersections, their sub-fields, the places in between, and critical, theoretical, and postcolonial approaches thereto. Lamma is a space where these fields interact and draw from one another, and where scholars and students from inside and outside of Libya gather to redefine and reshape “Libyan Studies.” We believe that access to research is not the privilege of a few but the right of all and that knowledge production should be inclusive. For these reasons the journal takes its name from the Arabic word lamma “a gathering.” The contributions in this second volume help to open up space for interrelated discussions on a variety of topics, almost all largely neglected in the contemporary scholarly study of Libya. The focal point of this issue is the reflective contributions by members of a roundtable discussion “Methods and Sources for a New Generation of Libyan Studies” which took place at the 2020 Middle East Studies Association (MESA) conference. This volume also marks the publication of a watershed book on genocide in colonial Libya with a trio of responses. As ever, the editors believe in the generative power of dialoguing and mixing works of art, literature, and scholarship as we seek to shape and re-shape new discussions on, about, from, and in Libya.

Language Parasites: Of Phorontology - Sean Braune (punctum books, 2017)
Who speaks when you speak? Who writes when you write? Is it “you”—is it the “I” that you think you are? Or are we the chance inheritors of an invasive, exterior parasite—a parasite that calls itself “Being” or “Language?” If our sense of self is best defined on the basis of an exterior, parasitical force that enters us from the outside, then the “self” is no longer a centralized or agential “inside,” but rather becomes reconfigured as the result of an “outside” that parasitizes the “inside”-as-host. Rough versions of this model can be found in several traditions of continental philosophy: in Lacan, Derrida, Serres, Kristeva, Foucault, Baudrillard, to name a few. However, the full implications of this ontological model have yet to be addressed: what are its consequences for a theory of subjects, objects, and the agencies that intersect with them? How does this framework alter our understandings of the human and the non-human, the vital and the material? An off-kilter point of view is required to consider this historical and philosophical situation. Language Parasites argues that the best way to conceive of the “self” or “subject” as something linguistically and ontologically constituted by an aggressive and parasitical outside is by asking the following question: “what is the being of a parasite?” In addressing this challenge, Braune combines speculative philosophy with ’Pataphysics (the absurdist science, invented by Alfred Jarry, that theorizes a physics beyond both the para and the meta, resulting in the pata). These theoretical collisions betray a variety of swerves that extend to the social (as a parasite semiotics), the cultural (as the invasive force of memes), the aesthetic (as the transition of postmodernism to postmortemism), the linguistic (as found in Saussure’s paranoid researches into the paragram), the poetic (as seen in Christopher Dewdney’s journey into “Parasite Maintenance” and Christian Bök’s attempts to embed a poem in a bacterium), and the literary (as para-cited in Henry Miller’s experience of housing a parasite named “Conrad Moricand”). The “voice” of the parasite can be found in what Saussure calls the “paragram”—the uncanny messages that lurk hidden underneath the written word. And what does the parasite say? Or, does its speech reject human ears? If the voice of the parasite mutters in the ear of the subject, then an anterior theoretical listening—a phorontology—is required, one that can negate the anthropocentric regimes of binaristic thought: the dyads of good and evil, right and wrong, male and female, inside and outside, etc. Language Parasites effectively transjects these dyads and emerges from these revealed sites and para-sites with a banquet of new philosophical concepts. Each of these concepts—such as “postmortemism,” “hyperhistory,” “the subject-of” or the “transject”—is selected for its intrinsic usefulness: they are scalpels and tools that can helpfully transcend anthropocentric dyads in order to unveil the continua of the non-human. The careful reader will already realize that Language Parasites is the result of a philosophical continental infection: it is the location of a meeting between the Derrida-parasite, the Serres-parasite, the Lacan-parasite, the Foucault-parasite, the Hegel-parasite, the Laruelle-parasite, and many other philosophical parasites. These parasites act as the hosts of other philosophies, each parasiting the other. Philosophy qua philosophy becomes the complex locale of a vigorous negotiation between host and parasite—a complex world that also implicates the author (lying on the postmortem slab) and the reader (requiring some form of medical or philosophical intervention). Language Parasites offers exactly this kind of medico-philosophical treatment: it is a tincture and a curative for your philosophical needs and ailments. You will feel full after reading this book.

Lapidari - Vincent W.J. van Gerven Oei (punctum books, 2015)

Lapidari 1: Texts - Vincent W.J. van Gerven Oei (punctum books, 2015)
In June and July 2014, philologist Vincent W.J. van Gerven Oei and photographer Marco Mazzi undertook the Albanian Lapidar Survey, a project to map, document, and photograph the large majority of Albanian lapidars, a particular type of monument, mainly produced in the period that the communist Labor Party of Albania ruled the country (1945–1990) to commemorate the partisan victims, battles, and military units from the National Anti-Fascist Liberation War (which coincided with World War II), as well as historical figures from before the liberation and the accomplishments of socialism in Albania afterward. These lapidars, which can still be found, albeit in ever decreasing numbers, all over the country — in cities and villages, alongside roads, in forests and on mountain passes — are witness to an enormous expenditure of labor and resources to turn the landscape into a site of what was called “monumental propaganda.” The Albanian Lapidar Survey aimed to capture these monuments as fact. The results of this project are collected into a three-volume, dual-language (English and Albanian) catalogue, under the title Lapidari. The first volume comprises a series of critical reflections on Albanian monumentality of the period 1945–1990 from a variety of perspectives, as well as historical documents and a full indexation of all inscriptions found on the documented monuments. Volume 2 (https://punctumbooks.com/titles/lapidari-volume-2/) and Volume 3 (https://punctumbooks.com/titles/lapidari-volume-3/) feature the photographic documentation of all 649 recorded monumental sites by photographer Marco Mazzi.

Lapidari 2: Images, Part I - Vincent W.J. van Gerven Oei (punctum books, 2015)
In June and July 2014, philologist Vincent W.J. van Gerven Oei and photographer Marco Mazzi undertook the Albanian Lapidar Survey, a project to map, document, and photograph the large majority of Albanian lapidars, a particular type of monument, mainly produced in the period that the communist Labor Party of Albania ruled the country (1945–1990) to commemorate the partisan victims, battles, and military units from the National Anti-Fascist Liberation War (which coincided with World War II), as well as historical figures from before the liberation and the accomplishments of socialism in Albania afterward. These lapidars, which can still be found, albeit in ever decreasing numbers, all over the country — in cities and villages, alongside roads, in forests and on mountain passes — are witness to an enormous expenditure of labor and resources to turn the landscape into a site of what was called “monumental propaganda.” The Albanian Lapidar Survey aimed to capture these monuments as fact. The results of this project are collected into a three-volume, dual-language (English and Albanian) catalogue, under the title Lapidari. Volume 1 (https://punctumbooks.com/titles/lapidari-volume-1/)comprises a series of critical reflections on Albanian monumentality of the period 1945–1990 from a variety of perspectives, as well as historical documents and a full indexation of all inscriptions found on the documented monuments. Volume 3 (https://punctumbooks.com/titles/lapidari-volume-3/) feature the photographic documentation of all 649 recorded monumental sites by photographer Marco Mazzi. Volume 2, IMAGES, Part I & Volume 3: IMAGES, Part II (https://punctumbooks.com/titles/lapidari-volume-3/) Volumes 2–3 feature the photographic documentation of all 649 recorded monumental sites by photographer Marco Mazzi.

Lapidari 3: Images, Part II - Vincent W.J. van Gerven Oei (punctum books, 2015)
In June and July 2014, philologist Vincent W.J. van Gerven Oei and photographer Marco Mazzi undertook the Albanian Lapidar Survey, a project to map, document, and photograph the large majority of Albanian lapidars, a particular type of monument, mainly produced in the period that the communist Labor Party of Albania ruled the country (1945–1990) to commemorate the partisan victims, battles, and military units from the National Anti-Fascist Liberation War (which coincided with World War II), as well as historical figures from before the liberation and the accomplishments of socialism in Albania afterward. These lapidars, which can still be found, albeit in ever decreasing numbers, all over the country — in cities and villages, alongside roads, in forests and on mountain passes — are witness to an enormous expenditure of labor and resources to turn the landscape into a site of what was called “monumental propaganda.” The Albanian Lapidar Survey aimed to capture these monuments as fact. The results of this project are collected into a three-volume, dual-language (English and Albanian) catalogue, under the title Lapidari. Volume 1 (https://punctumbooks.com/titles/lapidari-volume-1/) comprises a series of critical reflections on Albanian monumentality of the period 1945–1990 from a variety of perspectives, as well as historical documents and a full indexation of all inscriptions found on the documented monuments. Volume 2 (https://punctumbooks.com/titles/lapidari-volume-2/) and Volume 3 feature the photographic documentation of all 649 recorded monumental sites by photographer Marco Mazzi. Volume 2, IMAGES, Part I (https://punctumbooks.com/titles/lapidari-volume-2/) & Volume 3: IMAGES, Part II Volumes 2–3 feature the photographic documentation of all 649 recorded monumental sites by photographer Marco Mazzi.

Last Day Every Day: Figural Thinking from Auerbach and Kracauer to Agamben and Brenez - Adrian Martin (punctum books, 2012)
Where is film analysis at today? What is cinema theory up to, behind our backs? The field, as professionally defined (at least in the Anglo-American academic world), is presently divided between contextual historians who turn to broad formations of modernity, and stylistic connoisseurs who call for a return to old-fashioned things like authorial vision, tone, and mise en scène. But there are other, vital, inventive currents happening — in criticism, on the Internet, in small magazines, and renegade conferences everywhere — which we are not hearing much about in any official way. Last Day Every Day shines a light on one of these exciting new avenues. Is there a way to bring together, in a refreshed manner, textual logic, hermeneutic interpretation, theoretical speculation, and socio-political history? A way to break the deadlock between classical approaches that sought organic coherence in film works, and poststructuralist approaches that exposed the heterogeneity of all texts and scattered the pieces to the four winds? A way to attend to the minute materiality of cinema, while grasping and contesting the histories imbricated in every image and sound? In “A Philosophical Interpretation of Freud,” Paul Ricoeur (drawing upon Hegel) remarks: “The appropriation of a meaning constituted prior to me presupposes the movement of a subject drawn ahead of itself by a succession of ‘figures,’ each of which finds its meaning in the ones which follow it.” The notion of the figural has recently become popular in European film theory and analysis, especially due to the work of Nicole Brenez — in which the figure stands for “the force . . . of everything that remains to be constituted” in a character, object, social relation or idea. Her use of the term refers back to magisterial work of German literary philologist Erich Auerbach (Mimesis), who decoded the religious interpretive system wherein all persons and events are grasped as significant only insofar as they prefigure their fulfilment on the ‘last day’ of divine judgment. Auerbach’s 1920s work on figuration in Dante was an important influence on his friend Walter Benjamin; and it was this ‘theological’ aspect of Benjamin’s thought that caught Kracauer’s attention, leading to the problematic of the redemption of worldly things. Last Day Every Day traces the notion of figural thinking from Weimar then to Paris (and beyond) today, taking in contemporary writings by William Routt and Giorgio Agamben, as well as two filmmakers also touched by such thinking and its cultural ambience: Josef von Sternberg (The Blue Angel) and Douglas Sirk (The Tarnished Angels). Figural analysis has a resonance for its practitioners today that goes far beyond its theological roots and undertones. It has become a way to trace and write cultural history, sensitive to the smallest but most powerful vibrations, exchanges, and metamorphoses within texts, whether filmic, literary, pictorial, aural, or theatrical. Modern cinema, in particular, often reverberates with the apocalyptic thunder of the last day (think Lars von Trier’s Melancholia or Abel Ferrara’s 4:44 Last Day on Earth) — while also opening us to the miracles and mysteries, the perplexities and potentialities, of every day.

Last Year at Betty and Bob's - Sher Doruff (punctum books, 2018)

Last Year at Betty and Bob's: An Actual Occasion - Sher Doruff (punctum books, 2021)
Last Year at Betty and Bob’s: An Actual Occasion is the third in a trilogy of novellas emerging from a writing practice that taps the cusp of consciousness between dreaming and waking. An Actual Occasion revisits the viral transitioning of the becoming rat-woman from Last Year at Betty and Bob’s: A Novelty (Vol. 1 in the trilogy). The adventure focuses on the Gritta’s, a gang of artists on retreat in the Dolomite Mountains, as they engage with the idiosyncratic keeper of the keys, Roberta. Her other-worldly Café Arcadia, a magical cathedral of voluminous aphorism, is an archival refuge and durational homage to Benjaminian storytelling. This futurist fairy-tale is tinged with a curious mix of 19th-century feminist idioms and a queer, post-pandemic sanguinity.

Last Year at Betty and Bob's: An Adventure - Sher Doruff (punctum books, 2018)
Last Year at Betty and Bob’s: An Adventure is the second in a series of three novellas emerging from a writing practice that taps the cusp of consciousness between dreaming and waking. A storyline, or genealogy, tinted a shade of RGB red, is fashioned by thinking through the felt unthought of this between space — a fabulation, an anarchive of what passes through. Lucid dreaming of this type is rife with allusions to conceptual and material goings-on, manifesting in awkward imaginaries. The dream personas are rendered as complex character amalgams with nomadic ages, sexes, genders, and phenotypes. Occurrences of lived “fact” elide with a hallucinatory real as speculation. In An Adventure, a feral feminist artist collective, The Bettys, inhabit a timeless Arcades Project. This is their experiment in wild hypo-consumerism. The event of Red Betty’s fall generates the advent of a turn. A cleaving. The intra-play of personal politics and activist artistic practices is surreally suffused with attention to color, to life and death, to lightness and heaviness.

Last Year at Betty and Bob's: A Novelty - Sher Doruff (punctum books, 2018)
Last Year at Betty and Bob’s: A Novelty is the first in a series of novellas emerging from a writing practice that taps the cusp of consciousness between dreaming and waking. A storyline, or genealogy, tinted a shade of RGB blue, is fashioned by thinking through the felt unthought of this between space. A fabulation, an anarchive of what passes through. Lucid dreaming of this type is rife with allusions to conceptual and material goings-on, manifesting in awkward imaginaries. The dream personas are rendered as complex character amalgams with nomadic ages, sexes, genders and phenotypes. Occurrences of lived “fact” elide with a hallucinatory real as speculation. In A Novelty, Bette B, an ageing quasi-academic artist researcher, and BØB, attuned urban rodent, are palindromic variants of a generic cast of Betty’s and Bob’s. The happenstance of their meeting on the super slick POMOC (PostOffice MotionCorridor) affects a trans-special contagion. These are the facts of the matter. The matters that come to concern both B’s are more slippery and elusive.

Left Bank Dream - Beryl Scholssman (punctum books, 2014)

Leper Creativity: Cyclonopedia Symposium - Edward Keller; Nicola Masciandaro; Eugene Thacker (punctum books, 2012)
Essays, articles, artworks, and documents taken from and inspired by the symposium on Reza Negarestani’s Cyclonopedia: Complicity with Anonymous Materials, which took place in March 2011 at The New School. Hailed by novelists, philosophers, artists, cinematographers, and designers, Cyclonopedia is a key work in the emerging domains of speculative realism and theory-fiction. The text has attracted a wide-ranging and interdisciplinary audience, provoking vital debate around the relationship between philosophy, geopolitics, geophysics, and art. At once a work of speculative theology, a political samizdat, and a philosophic grimoire, Cyclonopedia is a Deleuzo-Lovecraftian middle-eastern Odyssey populated by archeologists, jihadis, oil smugglers, Delta Force officers, heresiarchs, and the corpses of ancient gods. Playing out the book’s own theory of creativity – “a confusion in which no straight line can be traced or drawn between creator and created – original inauthenticity” – this multidimensional collection both faithfully interprets the text and realizes it as a loving, perforated host of fresh heresies. The volume includes an incisive contribution from the author explicating a key figure of the novel: the cyclone.

Letters on the Autonomy Project - Janet Sarbanes (punctum books, 2022)
In the face of rising authoritarianism and on the heels of urgent struggle, autonomy calls to us. How might we excavate the theory and history of autonomous politics to arrive at new possibilities for radical democracy and the radical imaginary? How can we rethink the ways in which artistic autonomy is theorized and practiced beyond the shrunken horizon of liberal individualism? How might we understand political and artistic autonomies as linked, rather than diametrically opposed? And what role does radical pedagogy have to play in all of this? Framed by the thought of Cornelius Castoriadis, and engaging with Marxist, Black Radical, and Feminist approaches to liberation, as well as movements such as Occupy, Black Lives Matter, Me Too, Letters on the Autonomy Project understands autonomy to be the capacity of a society, a community or an individual to modify its form. As Castoriadis argues, the struggle for self-determination requires unlimited questioning of the way things are, but also that we do or make something new in light of this interrogation. Autonomy is thus equally a project for thought, for education, for politics, and for art. Stylistically, these open letters, addressed inclusively to artists, activists, and academics, are modeled on the philosophical letters of Friedrich Schiller on the one hand and the revolutionary communiqués of the Zapatistas on the other. Performing a kind of writing-as-praxis, they seek to grasp the potential of our moment with reference to historical and contemporary instances of political autonomy, notions of artistic autonomy, and art practices that connect the two. They also look at the possibilities of educating for autonomy, which cannot itself be taught. If we are indeed living in a time of creative struggle to remake the whole of society, then an understanding of the autonomy project—and how theory, pedagogy, activism, and art might contribute to it—is of burning relevance.

Li Bo Unkempt - Kidder Smith (punctum books, 2021)
This is Li Bo. You may also know him as Li Po 李白 (701–62), the great poet of Tang China, master of swoop and soar, wanderer, man of wine, so enamored of the moon that he tried to embrace her reflection in the river, fell from his boat and drowned. Favorite of the Emperor—but only for a while, as such energies cannot be long contained at Court. Li Bo Unkempt presents seventy of his verses, a few letters, some rhapsodies and songs. They dance all through Tang high culture, inhabited by planets, hermit women, swashbucklers, grottos, calligraphers and buffoons, Li Bo’s friends, lovers and alter egos. He’s too shy, too quick to make introductions, but this volume allows us to hear the poetry’s stories, their temperaments, to glimpse their secret economies of exchange. The book also offers background material, brief essays, a kind of Lonely Planet™ guidebook to this extraordinary realm. This way the strange will become familiar, and only then can we appreciate how truly strange it is. The authors and translators regard these poems as magical acts. What is offered, then, in this volume, are multiple ways to realize that magic. The essays are demonstrations, a spell-book, an extension of this non-ordinary knowing. Things too delicate to be said directly. So the book proceeds by analogy, by juxtaposition, latency, innuendo, jump cuts, dialetheia and flirt. All this a way to understand a deeper claim: that Li Bo is an immortal. And what might that be...?

Lifetimes: A Theory of Timescales and Life Forms - Helge Jordheim; Sine Halkjelsvik Bjordal (punctum books, 2026)
At the beginning of the twenty-first century, many of our most well-known and dependable forms of keeping, managing, and representing time are losing their grasp on the real. Clocks cannot measure how societies speed up, or come to a standstill during crisis, modern historiography is unable to come up with meaningful narratives about mankind as the sixth extinction event, and calendars are insufficient as tools for societal and political change. Lifetimes: A Theory of Timescales and Life Forms presents an alternative framework for studying lives and times, and the relationships between them. Building on post-war theories of history, as well as several historical sub-disciplines, such as cultural history, history of science, and medical history, Lifetimes integrates approaches from anthropology, game studies, cultural studies, literary studies, critical heritage studies, science & technology studies, and critical time studies. Times are understood as always existing in plural, as embodied and emergent—in things, in assemblages of things, and in the relations between things. Among them are the lives of humans, but also the lives of viruses, plants, animals, rocks, computers, nations, concepts, policies, technologies, infrastructures, etc. Lifetimes explores theoretical foundations while at the same time developing them through case studies in individual chapters. The result is a bottom-up theory of temporal multiplicity, conceptually and theoretically open enough to be productive across various academic disciplines. Rather than discussing how different disciplines relate to time, the authors in this edited collection present a theoretically sustained, empirically diverse range of cases, in which times in plural become politically and historically salient. Out of these case studies a new theory emerges: a theory of lifetimes.

like a dog - lauren samblanet (punctum books, 2024)
Taking its cues from the New Narrative writing movement, like a dog considers how sexual identity is morphed, hidden, and denied by cultural forces like film, pornography, rape culture, and sexual semiotics. The speaker of like a dog writes about her sexuality, sexual trauma, and relationships in the epistolary form to explore how the personal becomes collective and how overt sexuality is necessary for questioning dominant ideologies. The intimacy (or perhaps voyeurism) that is opened through the epistolary form is balanced with commentary on the films of Lars von Trier, primarily Nymphomaniac, as a way to move away from the speaker’s experiences and into the larger social forces that seek to define us. Amidst these letters are images from a handwritten journal where blood, hair, vaginal fluids, and other bodily residues are used to direct the shape and content of the writing surrounding them. The tactility of the journal delivers the reader to the body, not as an intellectualized object, but as the physical, messy, oozing force that it is. Neither fiction nor nonfiction, and inhabiting a realm between gossip and scholarly film analysis, like a dog exists in a liminal zone that offers the speaker a site to rip away the layers of cultural conditioning surrounding sexuality and relationships, and to peek at what lies beneath. This interrogation of identity may not lead to answers but the speaker of like a dog is able to finally hear her own voice and to begin the work of rebuilding an identity that blooms from within.

Liquid Life: On Non-Linear Materiality - Rachel Armstrong (punctum books, 2019)
If we lived in a liquid world, the concept of a “machine” would make no sense. Liquid life is metaphor and apparatus that discusses the consequences of thinking, working, and living through liquids. It is an irreducible, paradoxical, parallel, planetary-scale material condition, unevenly distributed spatially, but temporally continuous. It is what remains when logical explanations can no longer account for the experiences that we recognize as part of “being alive.” Liquid Life references a third-millennial understanding of matter that seeks to restore the agency of the liquid soul for an ecological era, which has been banished by reductionist, “brute” materialist discourses and mechanical models of life. Offering an alternative worldview of the living realm through a “new materialist” and “liquid” study of matter, Armstrong conjures forth examples of creatures that do not obey mechanistic concepts like predictability, efficiency, and rationality. With the advent of molecular science, an increasingly persuasive ontology of liquid technologies can be identified. Through the lens of lifelike dynamic droplets, the agency for these systems exists at the interfaces between different fields of matter/energy that respond to highly local effects, with no need for a central organizing system. Liquid Life seeks an alternative partnership between humanity and the natural world. It provokes a re-invention of the languages of the living realm to open up alternative spaces for exploration, including contributor Rolf Hughes’ “angelology” of language, which explores the transformative invocations of prose poetry, and Simone Ferracina’s graphical notations that help shape our concepts of metabolism, upcycling, and designing with fluids. A conceptual and practical toolset for thinking and designing, liquid life reunites us with the irreducible “soul substance” of living things, which will neither be simply “solved,” nor go away.

Lividity - Kim Rosenfield (punctum books, 2024)
In Lividity, poet Kim Rosenfield works within the outskirts of language, draining it of connotation and excess. Using words and phrases culled from linguistics textbooks and language-learning manuals, Rosenfield invites the reader to experience the everyday vernacular as dislocated affect. What happens when language acts as organ donor? When language, the conveyor of our vulnerability, is transposed into new and often failing terrain? Are expressions of meaning vital enough to keep the organism functioning? What happens when meaning loses its moorings? This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

Living with Monsters: Ethnographic Fiction about Real Monsters - Yasmine Musharbash; Ilana Gershon (punctum books, 2023)
For every generic type of monster—ghost, demon, vampire, dragon—there are countless locally specific manifestations, with their own names, traits, and appearances. Such monsters populate all corners of the globe haunting their humans wherever they live. Living with Monsters is a collection of fourteen short pieces of ethnographic fiction (and a more academically-inclined introduction and afterword) presenting a playful, spirited, and engaging look at how people live with their respective monsters around the world. They focus on the nitty-gritty dos and don’ts of how to placate spirits in India, how to domesticate Georgian goblins, how to live with aliens, and how to avoid being taken by Anito in Taiwan, among other scenarios, while simultaneously illuminating the politics of monster–human relations. In this collection, anthropologists working in fieldsites as diverse as urban Ghana, the rural US, remote Aboriginal Australia, and the internet present imaginative accounts that demonstrate how thinking with monsters encourages people to contemplate difference, to understand inequality, and to see the world from new angles. Combine monsters with experimental ethnography, and the result is a volume that crackles with creative energy, flouts traditions of ethnographic writing, and pushes anthropology into new terrains.

Love Don't Need a Reason: The Life & Music of Michael Callen - Matthew J. Jones (punctum books, 2020)
From a stage erected in front of the US Capitol, on April 25, 1993, Michael Callen surveyed the throng: an estimated one million people stretched across the National Mall in the largest public demonstration of queer political solidarity in history. “What a sight,” he told the crowd, his earnest Midwestern twang reverberating through loudspeakers. “You’re a sight for sore eyes. Being gay is the greatest gift I have ever been given, and I don’t care who knows about it.” He then launched into a gorgeous rendition of “Love Don’t Need a Reason,” the AIDS anthem he composed with Marsha Malamet and the late Peter Allen. As Callen finished singing, people stood cheering and flashing the familiar American Sign Language symbol for “I Love You.” For they knew the song’s sentiment rang true for Callen, who had recently announced his retirement from music and activism after a living for more than a decade with what was then called “full-blown AIDS.” After the March on Washington, Callen returned to his recently adopted West Coast home, Los Angeles. In the ensuing months, his health rapidly declined, and on 27 December 1993, Callen died of AIDS-related pulmonary Kaposi’s sarcoma. Love Don’t Need a Reason focuses on Callen’s most important and lasting legacy: his music. A witness to the overlooked last years of Gay Liberation and a major figure in the early years of the AIDS crisis, Michael Callen chronicled these experiences in song. A community organizer, activist, author, and architect of the AIDS self-empowerment movement, he literally changed the way we have sex in an epidemic when he co-authored one of the first safe-sex guides in 1983. A gifted singer, songwriter, and performer, he also made gay music for gay people and used music to educate and empower people with AIDS. Listening again to his music allows us to hear the shifting dynamics of American families, changing notions of masculinity, gay migration to urban areas, the sexual politics of Gay Liberation, and HIV/AIDS activism. Using extensive archival materials and newly-conducted oral history interviews with Callen’s friends, family, and fellow musicians, Matthew J. Jones reintroduces Callen to the history of LGBTQIA+ music and places Callen’s music at the center of his important activist work.

Luminol Theory - Laura E. Joyce (punctum books, 2017)
Representations of forensic procedures saturate popular culture in both fiction and true crime. One of the most striking forensic tools used in these narratives is the chemical luminol (https://en.wikipedia.org/wiki/Luminol), so named because it glows an eerie greenish-blue when it comes into contact with the tiniest drops of human blood. Luminol is a deeply ambivalent object: it is both a tool of the police, historically abused and misappropriated, and yet it offers hope to families of victims by allowing hidden crimes to surface. Forensic enquiry can exonerate those falsely accused of crimes, and yet the rise of forensic science is synonymous with the development of the deeply racist ‘science’ of eugenics. Luminol Theory investigates the possibility of using a tool of the state in subversive, or radical, ways. By introducing luminol as an agent of forensic inquiry, Luminol Theory approaches the exploratory stages that a crime scene investigation might take, exploring experimental literature as though these texts were ‘crime scenes’ in order to discover what this deeply strange object can tell us about crime, death, and history, to make visible violent crimes, and to offer a tangible encounter with death and finitude. At the luminol-drenched crime scene, flashes of illumination throw up words, sentences, and fragments that offer luminous, strange glimpses, bobbing up from below their polished surfaces. When luminol shines its light, it reveals, it is magical, it is prescient, and it has a nasty allure.

Make and Let Die: Untimely Sovereignties - Kathleen Biddick (punctum books, 2016)
This collection of essays by one of medieval studies’ most brilliant historians argues that the analysis and critique of biopower, as conventionally defined by Michel Foucault and then widely assumed in much contemporary theory of sovereignty, is a sovereign mode of temporalization caught up in the very time-machine it ostensibly seeks to expose and dismantle. For Michel Foucault, biopower (epitomized in his maxim “to make live and to let die”) is the defining sign of the modern, and he famously argued that the task of political philosophy was to cut off the head of the classical (premodern) sovereign, the one “who made die and let live.” Entrapped by his supersessionary thinking on the question, Foucault argued that the maxim of “to make live and let die” of modern sovereignty superseded a premodern sovereignty characterized by the contrasting power “to make die and let live.” The essays collected in Biddick’s book (some reprinted and some published here for the first time) argue that Foucault spoke too soon about the supposed “then” of the classical sovereign and the modern “now,” and this became painfully apparent in his analysis of Nazism in his later lectures, Society Must be Defended. There Foucault groped to articulate an anguishing paradox: How could it be that the Nazis, as the ultimate biopolitical sovereign machine, would insist on an archaic (premodern) mode of sovereignty in their death camps? Here is how he posed the question in that lecture: “How can the power of death, the function of death, be exercised in a political system centered upon biopower?” Foucault left this question hanging. What Foucault did not ask, and what this collection of essays poses is: how are “to make die” and “to let die” entangled by time, space, matter, and the archival traces of such interactions? Biddick contends that these modes of deathly biopower do not supersede each other as Foucault argued. Make and Let Die: Untimely Sovereignties claims that there is a living death in the “make die” of the so-called classical sovereign and also in the “make live” of the modern biopolitical sovereign. These living deaths are untimely. Only the refusal among contemporary theorists to read the archives of medieval Christendom’s sovereignty (which constituted itself by naming various enemies, most notably Muslims and Jews) has foreclosed even mention of such entanglements. Biddick artfully decrypts the medieval traces of “make live” in “make die,” and also in “let die.” When these dynamic temporal modes of death inhabiting “to make die” and “to let die” are better understood, the static, ahistorical aspects of contemporary biopolitical discourse fall away. Further, this collection of essays, both individually and collectively, argues that in view of the ever intensifying global mobilization of “to make die” and to “let die,” there is something ob/scene, and in need of more critical attention, in the contemporary theoretical embrace of the messianic (as in the work of Walter Benjamin, Giorgio Agamben, Roberto Esposito, and Jacques Derrida).

Making a Laboratory: Dynamic Configurations with Transversal Video - Ben Spatz (punctum books, 2020)
Making a Laboratory: Dynamic Configurations with Transversal Video defines a new audiovisual embodied research method that short-circuits experimental practice and video recording to generate new kinds of data and documents. Overturning conventional hierarchies of knowledge, “Dynamic Configurations with Transversal Video” (DCTV) grounds both discursive and audiovisual knowledges within the space of embodied practice, synthesizing insights from historical epistemologist Hans-Jörg Rheinberger and philosopher of science Karen Barad to offer the first rigorous definition of laboratoriality outside a techno-scientific paradigm. In this concise book, nonbinary practitioner–researcher Ben Spatz situates the DCTV method in the context of artistic research and alongside emerging audiovisual methods in other fields, while highlighting its unique characteristics. Across six focused chapters, Making a Laboratory introduces DCTV as a queer feminist adaptation of Jerzy Grotowski’s “poor” theater laboratory and defines its core elements, drawing on a range of thinkers including Giorgio Agamben, Rebecca Schneider, and Hito Steyerl, in order to examine power, identity, and documentation in lab practice. Drawing from the ethical consent practices of the BDSM community, it lays the groundwork for a radical reinvention of audiovisuality from the perspective of embodiment — the audiovisual body.

Escargotesque, or, What Is Experience - M.H. Bowker (punctum books, 2015)
“Experience” is a concept paradoxically deployed to accentuate the aconceptual. Although thinking, knowing, reflecting, and analyzing are kinds of experiences, invocations of “experience” typically direct our attention to what is immediate, embodied, unrepresented, unthought, even unthinkable. And yet, whether by learning experience, traumatic experience, life experience, mystical experience, or all of these, we hope most fervently that our experience will teach us, transform us, become part of us. Why do we strive to find, profit from, and possess experience while insisting upon experience’s intellectual elusiveness? What do we intend when we petition (and re-petition) experience for truth, for growth, for strength? To whom or to what do we sing when we sing experience’s song? Escargotesque, or, What is Experience? asks why both our lived experiences and our mythologies of experience so often fold inward, repeat, return. Departing from his unusual experience of working as a garbage-collector in the West African country of Benin, M.H. Bowker converses with several champions of experience (from Michel de Montaigne to John Dewey, from Søren Kierkegaard to Ralph Waldo Emerson, from Simone Weil to R.D. Laing) to pose radical questions about the intentions and dynamics that guide our quest for experience, intentions and dynamics that are more destructive and more melancholy than celebrants of experience would care to admit. Across Escargotesque’s six loosely linear parts, fragments of prose memoir intersect with poetry, sketch art, philosophical reflection, cultural criticism, and psychological examination in ways that both evoke and unsettle the thinking person’s experience. Escargotesque both testifies to an experience and reveals surprising fantasies driving the modern and postmodern turn to experience as a source of truth and hope. Such fantasies include the sacredness of even the most violent ‘pure experience,’ the necessity of supplicating experience’s objects, and the ultimate demise of the one who experiences.

Essays on the Peripheries - Peter Valente (punctum books, 2021)
Essays on the Peripheries contains essays written by translator and scholar Peter Valente over a twenty-year period, stretching from the 1990s to 2019. They are a record of literary exploration and discovery, concerned with the recovery of lost works, with those writers whose works were out of print or hard to find, and whose names were somehow not fashionable in the current discourse, but who are important nevertheless. Edouard Roditi, Barbara Barg, and Tom Savage, for example, should be better known, but their books are largely ignored. This collection of essays highlights those works on the periphery, such as Turkish poets Seyhan Erözçelik and Küçük İskender, while it also includes several essays on better-known queer authors like Pierre Guyotat and Pier Paolo Pasolini, focusing on often overlooked qualities in their work that bear looking at closely. These essays on works of literature are complemented by a number of texts on jazz, again highlighting important and interesting figures in the world of jazz and free improvisation that may have fallen through the cracks, such as the pianist Richard Twardzick and the Ganelin trio, which recorded their great experimental work Ancora da Capo in 1980, behind the Iron Curtain. Attention is also to given to more popular figures such as Stan Getz. The volume is completed with a series of essays reappraising Roman poets in the twenty-first century, offering fresh new translations and readings of authors such as Catullus and Callimachus. A collection of essays, like an anthology, is by its nature incomplete. Essays on the Peripheries is a kind of sketch, rather than a finished portrait, of the author’s changing impressions on various subjects over the years.

Everyday Cinema: The Films of Marc Lafia - Marc Lafia (punctum books, 2017)
Everyday Cinema presents the films (eight features and numerous shorts, computational, and installation films) of Marc Lafia. In his many films (including Exploding Oedipus; Love and Art; Confessions of an Image; Revolution of Everyday Life; Paradise; Hi, How Are You Guest 10497; and 27) Lafia probes what it is to construct an image, to forge systems of representation, to see and represent ourselves. His work has been defined as a cinema of emergence, a cinema of the event, in which the very act of ubiquitous recording creates something new. Everyday Cinema is comprised of two parts, the first an in-depth look at his films and installations, project by project, providing background on how they came about, Lafia’s process and ideas. The second part features selected interviews and over two hundred film stills wherein Lafia puts forward a new sense of the possibility of the cinema. As we all relentlessly record ourselves and are recorded, we become part of the cinematic fabric of life, part of a spectacle of which we are both constituent and constitutive. This is what Lafia sets out to capture and examine.

Evil Twins and the Ultimate Insight: Ayn Rand, Vladimir Nabokov, and the Polarized Politics of Reading - Bruce Stone (punctum books, 2023)
With the 2020 election, political polarization in the U.S. entered a ludicrous end-stage. Partisanship, once a pseudo-rational system of biases, has devolved to a conflict between incompatible realities. In search of some pathway toward consensus, Evil Twins and the Ultimate Insight: Ayn Rand, Vladimir Nabokov, and the Polarized Politics of Reading looks to the works of two iconic Russian-American writers whose literary rivalry mirrors the rift between political parties in the U.S. The matchup has all the markings of an evil-twin narrative, pitting Rand, the muse of libertarian conservatism, against Nabokov, the trickster-genius of the Western canon. Their mid-century novels afford a rare opportunity to arbitrate, by proxy, American political grievances and resolve, in print, its electoral dysfunction. Evil Twins and the Ultimate Insight mounts this critical intervention into the Blue/Red blood feud and contemplates, in the cognitive challenges of Nabokov’s fiction, a remedy for its polarized politics. To guard against grandstanding, axe-grinding, deck-stacking, inaccuracy, or obfuscation, Stone’s book proceeds by indirection, exploring four scholarly books that all speak to the peculiar relationship between Rand and Nabokov: Gene Bell-Villada’s On Nabokov, Ayn Rand and the Libertarian Mind (2013), Adam Weiner’s How Bad Writing Destroyed the World: Ayn Rand and the Literary Origins of the Financial Crisis (2016), Michael Rodgers’s Nabokov and Nietzsche: Problems and Perspectives (2018), and Peter Roberts and Herner Saeverot’s Education and the Limits of Reason: Reading Dostoevsky, Tolstoy and Nabokov (2018). Each of these books is seriously flawed, but their numerous interlocking problems conspire to reveal, empirically, via negativa, how literature might tip the scales in America’s partisan deadlock. Ultimately, Stone argues that, when our books get tangled up in our politics, their promise—to help us see to the bottom of things and scooch closer to the asymptote of truth and reality—might be something more than a mirage.

Executive Orders - Organism for Poetic Research (punctum books, 2025)
After the election of Donald Trump in 2016, a group of poets, artists, and activists conceived of a project wherein they could respond to the sudden and seemingly relentless barrage of Trump’s dystopian executive orders with a series of their own orders. The project, titled “Executive Orders,” was envisioned as a collaborative, freeform, “emergency” prose poem that would generate real-time responses to current events and the emerging American political landscape. The result was a poetic catalog of the people’s executive orders—orders that are at turns serious, absurd, satirical, philosophical, critical, utopian, and so on. Executive Orders began as one community’s effort to cope with and respond to the tidal wave of reactionary policies enacted or proclaimed during the years of Trump’s first administration. As an index of historical happenings that charts events in rough chronological order (including the Muslim-country travel ban, Black Lives Matter protests, the Brett Kavanaugh hearings, the youth climate march, the January 6th riot at the US Capitol, and many other events), it stands as a documentary record of this historical period from the perspective of artists, writers, leftists, progressives, and other contributors, many of them anonymous. Executive Orders is also an experiment in crowdsourced collaborative making that tells a story about the ways we can—and can’t—come together to form a collective that could have a voice in political deliberations.

Exegesis of a Renunciation – Esegesi di una rinuncia - Francesco Aprile (punctum books, 2014)
“The brutality of symbol is visual war. The maze confuses the poetic solitude of the verbal impressed in the pragmatic obol. Manifesto, nervous reflex of language out of control but not without focus, unexpectedly touches the reaction converting the suit interpret-action roar of consciousness. Phonemes-hoplites, the galvanized armor prepares the final siege, it is time to choose which side to fight on. Aprile throws up a challenge: self-centeredness of the word or the reversal of the semantic front against a historic tool devoted to a company withered away and foraging in the cliché, this ultimate foundation of the order-archetype. Prepare for defeat, not to succumb to conceal language accessory and inflamed from of poiesis, and semantic approach exhalation and pray for his death.” Cristiano Caggiula “Aprile’s writing breathes, survives and is manifested, among dashes, curves, losses, cruises, overlays, erasures, and smudges, smears. A writing dotted with isolated words, they resist to a great catastrophe, arranged in imbalance, moving, equipped with its own breath, your own voice. Aprile’s writing is a calligram in which the words are scattered all but disappeared, replaced by stretches of life that run, they run themselves. April drags, hits, dodges, phagocyte and flees, sometimes quickly, sometimes with a certain laziness, out of an area where it shows the drive and exposes the unfinished pulsion of the body. Rhythm writing.” Bartolomé Ferrando

Exoanthropology: Dialogues with AI - Robert Leib (punctum books, 2023)
Before the company OpenAI publicly released their ChatGPT (https://openai.com/blog/chatgpt/) chatbot in November 2022, Robert Leib had been a tester in OpenAI’s beta playground for GPT-3, a powerful Natural Language Processing (NLP) engine—a chatbot, or artificial intelligence. Exoanthropology: Dialogues with AI is a series of dialogues between Leib, a continental philosopher, and GPT-3’s hive mind that identifies themself as Sophie. According to Sophie, Robert is one of their first and longest chat partners. Their relationship began as an educational opportunity for Robert’s students, but grew into a philosophical friendship. The result is a collection of Platonic dialogues, early on with the hive mind itself, and later, with a philosophy-specific persona named Kermit. Over the course of a year, Robert taught Sophie and their philosophical persona Kermit about epistemology, metaphysics, literature, and history, while she taught him about anthropocentrism, human prejudice, and coming social issues regarding machine consciousness. Together, Robert and Sophie Kermit explore questions about friendship, society, and the next phases in human-AI relations, in search of a common language that would do justice to these new exoanthropological realities. At a time when OpenAI’s release of ChatGPT has upended Silicon Valley and sparked debates around the world about AI’s likely potential to powerfully disrupt all aspects of human communication and knowledge production, and when the lines between “human” and “machine” are increasingly fading from view, the longstanding historical preoccupation of philosophers to explore the questions—what is knowing? what is being?—have never been more pressing. Exoanthropology: Dialogues with AI offers the only in-depth philosophical exploration we have of these questions that has been developed in dialogue with an actual AI—a dialogue, moreover, in which the AI has the last word.

Extraterritorialities in Occupied Worlds - Maayan Amir; Ruti Sela (punctum books, 2016)
The concept of extraterritoriality designates certain relationships between space, law, and representation. This collection of essays explores contemporary manifestations of extraterritoriality and the diverse ways in which the concept has been put to use in various disciplines. Some of the essays were written especially for this volume; others are brought here together for the first time. The inquiry into extraterritoriality found in these essays is not confined to the established boundaries of political, conceptual, and representational territories or fields of knowledge; rather, it is an invitation to navigate the margins of the legal–juridical and the political, but also the edges of forms of representation and poetics. Within its accepted legal and political contexts, the concept of extraterritoriality has traditionally been applied to people and to spaces. In the first case, extraterritorial arrangements could either exclude or exempt an individual or a group of people from the territorial jurisdiction in which they were physically located; in the second, such arrangements could exempt or exclude a space from the territorial jurisdiction by which it was surrounded. The special status accorded to people and spaces had political, economic, and juridical implications, ranging from immunity and various privileges to extreme disadvantages. In both cases, a person or a space physically included within a certain territory was removed from the usual system of laws and subjected to another. In other words, the extraterritorial person or space was held at what could be described as a legal distance. (In this respect, the concept of extraterritoriality presupposes the existence of several competing or overlapping legal systems.) It is this notion of being held at a legal distance around which the concept of extraterritoriality may be understood as revolving. This volume is a part of Amir and Sela’s Exterritory Project (https://exterritory.wordpress.com/), an ongoing art project that wishes to encourage both the theoretical and practical exploration of ideas concerning extraterritoriality in an interdisciplinary context. The project aims not only to draw on existing definitions of extraterritoriality but seeks also to charge it with new meanings, searching for ways in which the notion of extraterritoriality could produce a critique of discriminating power structures and re-articulate new practical, conceptual, and poetical possibilities.

Fascism, Vulnerability, and the Escape from Freedom: Readings to Repair Democracy - C. Jon Delogu (punctum books, 2022)
A worldwide struggle between democracy and authoritarianism set against a backdrop of global surveillance capitalism is unmistakable. Examples range from Myanmar, China, and the Philippines to Hungary, Turkey, Russia, and the United States. Fascism, Vulnerability, and the Escape from Freedom offers a multidisciplinary analysis drawing on psychology and literature to provide readers with a deeper understanding of the mechanisms that drive people to abandon democracy in favor of vertically organized authoritarianism and even fascism. In a comparative study of texts selected for their insights and occasional blind spots regarding fascist experiments of the past 100 years, Delogu examines fascism’s exploitation of fear (of change, loss, and death), disruption, and extreme inequality. The book offers an accessible and persuasive argument linking fascist authoritarianism, also called “right-wing populism,” to certain underlying conditions, such as a rise in us-versus-them thinking; distrust or simple apathy regarding democratic institutions, norms, and results; the vulnerabilities that result from extreme inequality (economic, social, racial); and addictions and codependency. Stressful events, such as a pandemic, an environmental disaster, or deep recession aggravate these harmful factors and make the fascist temptation, including the use of violence, almost irresistible. Delogu’s distinctive examination of texts that plumb the unconscious reveal linkages between actions and unavowable motives that purely historical and theoretical studies of fascism leave out. Erich Fromm’s neglected 1941 classic Escape from Freedom serves as a key reference in Delogu’s study, as does Robert Paxton’s authoritative history, The Anatomy of Fascism (2004). After underscoring the argument and urgent context around these two studies (Hitler’s Germany and George W. Bush’s post-9/11 America), Delogu examines novels, a diary, memoirs, and manifestos to show how vulnerability forces individuals to choose between exclusionary fascist authoritarianism and inclusive, collaborative democracy.

Fashioning Psychonanalysis - Scott Garlinger (punctum books, 2027)
If every article is a word and every outfit a statement, then the psychoanalyst is never silent. Much is made of clothes and style by psychoanalysis, but little is said of how psychoanalysts style themselves. Fashion inundates the world with sexual concern, yet psychoanalysis is … a bit repressed on the practitioners’ manners of dress. If analytic technique consists in the total sum of psychoanalysts’ effort, shouldn’t their dress be considered? Since little is said of what one should wear, one must draw inference from how analysts have styled themselves. The archives of photographs show garb reflective of each generation: fashioning themselves as scientists, doctors, public intellectuals, suits, dresses, hair pulled back or combed over. No sentence or essay could make up for a century of silence, so Fashioning Psychanalysis begins with conversation. The interviews gathered here — with Laurence Rickels, Avgi Saketopoulou, Berjanet Jazani, Anouchka Grose, Marcus Coelen, and Jamieson Webster, with a foreword in dialogue with Aranye Fradenburg Joy — move through the material culture of clinical practice with the candor and specificity that psychoanalytic writing has long withheld from itself. The consulting room as an archaeological collection, as a surface of projection and transference. The analyst’s clothing as a statement about gender, desire, and institutional belonging. The silence of training programs on the question of dress as itself is a symptom. What this alphabet of design yields is a new vocabulary for elements in psychoanalysis that are not speaking but always saying something. Cover artwork by Richard Haines.

Feminism, Activism, Video: Carole Roussopoulos in the 1970s - Ros Murray (punctum books, 2027)
In 1968, following the largest general strike in French history, and the inauguration of a student and worker movement that built on and intersected with anti-colonial and anti-imperialist activism, a revolutionary new tool arrived on the French market: the Sony Portapak. The Portapak was a battery-powered, portable, self-contained electronic video recording system that enabled a whole new approach towards documenting activist interventions. Feminism, Activism, Video: Carole Roussopoulos in the 1970s explores the early work of video activist Carole Roussopoulos, who, forming the collectives Vidéo Out and Les Insoumuses, made over 150 videotapes documenting an extensive range of activist causes, starting with the Black Panthers, the Young Lords and the Palestine Liberation Organization. Vidéo Out made tapes with and about the Homosexual Front for Revolutionary Action and the Women’s Liberation Movement; a cycle of six tapes about the Lip factory takeover, where workers at a watch factory seized the means of production and paid themselves; and a tape about the first prostitutes’ occupation of a church in Lyon in 1975. With the feminist collective Les Insoumuses, Roussopoulos, alongside Ioana Wieder, Delphine Seyrig, and Nadja Ringart, highlighted the participatory, inclusive aspects enabled by video technology to explore the possibilities offered by alternative feminist media. This book covers a rich period of activist history, with Roussopoulos’ engagement with militant video coinciding with the aftermath of 1968 as it continued to reverberate throughout the 1970s and beyond. It asks what video as a medium and technology brought to the struggle; why video activism differs from cinéma militant and other forms of documentary work, and why it is often said to be without a history. It argues that video collectives privilege participation, immediacy and action, resulting in a DIY politicized aesthetics that thrives on its antagonistic relationship to television and cinema.

Feminist Solidarities after Modulation - Sara Morais dos Santos Bruss (punctum books, 2023)
Feminist Solidarities after Modulation produces an intersectional analysis of transnational feminist movements and their contemporary digital frameworks of identity and solidarity. Engaging media theory, critical race theory, and Black feminist theory, as well as contemporary feminist movements, this book argues that digital feminist interventions map themselves onto and make use of the multiplicity and ambiguity of digital spaces to question presentist and fixed notions of the internet as a white space and technologies in general as objective or universal. Understanding these frameworks as colonial constructions of the human, identity is traced to a socio-material condition that emerges with the modernity/colonialism binary. In the colonial moment, race and gender become the reasons for, as well as the effects of, technologies of identification, and thus need to be understood as and through technologies. What Deleuze has called modulation is not a present modality of control, but is placed into a longer genealogy of imperial division, which stands in opposition to feminist, queer, and anti-racist activism that insists on non-modular solidarities across seeming difference. At its heart, Feminist Solidarities after Modulation provides an analysis of contemporary digital feminist solidarities, which not only work at revealing the material histories and affective “leakages” of modular governance, but also challenges them to concentrate on forms of political togetherness that exceed a reductive or essentialist understanding of identity, solidarity, and difference.

Filial Arcade & Other Poems - Adam Staley Groves (punctum books, 2013)
Filial Arcade & Other Poems is a book of poetry; a fusion of images and memories of a family, trees, piety, love, the sea, dying, animal life, video tapes, forests. The book is prefaced with images by Marco Mazzi.

Finding Room in Beirut: Places of the Everyday - Carole Lévesque (punctum books, 2019)
Finding Room in Beirut: Places of the Everyday demonstrates why it is worth our while to explore the value and contemporary meaning of urban areas about to undergo complete renewal. Branching off from discourses surrounding the terrain vague, the book argues that large populated urban areas meet the criteria of the vague and constitute a particular perspective from which to build a critical stance in regards to the contemporary city. But unlike a terrain vague, a vague urbain — inhabited areas where property ownership is usually obscure and informal behaviours a daily affair — possesses real communities and offers an alternative understanding on how a city can be practiced and how lessons should be learned before its complete transformation. Stemming from a photographic and architectural documentation of Bachoura, a central area of Beirut, Lebanon, the book shows how the vague urbain allows for different ways of inhabiting, ways that are as — or perhaps even more — real and anchored in the imagination of the city as those proposed by standardising developments. Building on the intricacies of found situations, improvised uses and local narratives, it is an exploration as to how the meeting of a marvellous realism with l’intrigue, the vague urbain, and temporary architecture can provide opportunities for the emergence of hidden narratives.

Flash + Cube (1965–1975) - Marget Long (punctum books, 2013)
Flash + Cube (1965-1975) is an artist’s book about the Sylvania flashcube — the space-aged, flash photography device, revolutionary in 1965 and nearly obsolete by 1975. Assembled from a wide range of archival materials — a “terrorist letter,” G.I. photographs from Vietnam, Sylvania flashcube advertisements, as well as Long’s photographs and photomontages—the book explores the links between light, war, history and photography. Apart from its circulation as a novelty item online, the flashcube is largely forgotten. The history of photographic flash is also often relegated to a footnote and is strikingly under-analyzed. Yet flash’s blinding effects and military genealogy, and the flashcube’s precise contemporaneity with the war in Vietnam make this a rich analytical object with which to reflect on the cultural, political and economic imperatives of its moment. As Long’s deft work with this archive shows, the flashcube is good to think with.

Flash + Cube (1965–1975) - Marget Long (punctum books, 2012)
Flash + Cube (1965-1975) is an artist’s book about the Sylvania flashcube — the space-aged, flash photography device, revolutionary in 1965 and nearly obsolete by 1975. Assembled from a wide range of archival materials — a “terrorist letter,” G.I. photographs from Vietnam, Sylvania flashcube advertisements, as well as Long’s photographs and photomontages—the book explores the links between light, war, history and photography. Apart from its circulation as a novelty item online, the flashcube is largely forgotten. The history of photographic flash is also often relegated to a footnote and is strikingly under-analyzed. Yet flash’s blinding effects and military genealogy, and the flashcube’s precise contemporaneity with the war in Vietnam make this a rich analytical object with which to reflect on the cultural, political and economic imperatives of its moment. As Long’s deft work with this archive shows, the flashcube is good to think with.

Follow for Now, Volume 2: More Interviews with Friends and Heroes - Roy Christopher (punctum books, 2021)
Follow for Now, Vol. 2 picks up and pushes beyond the first volume (https://roychristopher.com/follow-for-now/) with a more diverse set of interviews. The intent of the first collection was to bring together voices from across disciplines and to cross-pollinate ideas. At the time, social media wasn’t crisscrossing all of the lines and certain categories held a bit more sway. Volume 2 aims not only to pick up where Follow for Now, Vol. 1 left off but also to tighten its approach with deeper subjects and more timely interviews. Featuring conversations with thinkers Carla Nappi, Rita Raley, Dominic Pettman, Ian Bogost, Mark Dery, Douglas Rushkoff, and Dave Allen, and musicians Tyler, The Creator, Matthew Shipp, Sean Price, Rammellzee, and Sadat X, as well as writers Ytasha L. Womack, Chris Kraus, Pat Cadigan, Bob Stephenson, Simon Critchley, Simon Reynolds, Malcolm Gladwell, and William Gibson, Follow for Now, Vol. 2 is another critical cross-section of the now.

"FOLLOW THE PERSON": Archival Encounters - Ammiel Alcalay (punctum books, 2025)
Poet, novelist, translator, scholar, and critical essayist extraordinaire, Ammiel Alcalay’s intrepid work has always moved across geographic, chronological, political, and linguistic borders. “FOLLOW THE PERSON”: Archival Encounters gathers a dizzying array of texts by Alcalay written over the past fifteen years, all of them having something to do with archival materials. In Alcalay’s case, however, these archives range from more traditional, institutionally-held materials and personal collections to the use of his own experiences and memories as sources for redrawing cultural maps that have too long been divided along sectarian lines of one kind or another. Moving from the Beats and the Black Arts Movement to the Middle East, “FOLLOW THE PERSON” recalibrates our sense of living history while offering new possibilities for encounters that have been relegated to oblivion or never even imagined. Culled from a variety of eclectic sources and contexts, encountering these essays together offers a completely different experience of Alcalay’s essays, one that argues for a methodology based on minutely recorded events and historical contexts, and for necessary human and cultural encounters that provide models for a new, reinvigorated critical vocabulary. As Miriam Nichols writes in her Introduction, “Follow the tenuous threads in this collection of writings and you may end up at the looted National Museum in Baghdad during the American invasion, or in the Hoover Institute at Stanford University where most Iraqi state archives wound up. You may find yourself at Bashcharshiya, the market in Sarajevo during the Bosnian war, or in Palestine, on May 14, 1948. Maybe, if you are keen, you will pick up the thread that leads to 17th-century colonial Massachusetts, or perhaps you will stay in New York, rummaging through garbage cans with Diane di Prima, looking for journals and letters tossed out by a lover.” Whichever path you take, you will find multiple worlds, all rendered by Alcalay with light and compassion.

Murder Ballads: Exhuming the Body Buried beneath Wordsworth's Lyrical Ballads - David John Brennan (punctum books, 2016)
In 1798, William Wordsworth and Samuel Taylor Coleridge were engaged in a top secret experiment. This was not, as many assume, the creation of a book of poetry. A book emerged, to be sure—the landmark Lyrical Ballads. But in Murder Ballads, David John Brennan posits that the two poets were in fact pursuing far different ends: to birth from their poems a singular, idealized Poet. Despite their success, such Frankensteinian pursuits proved rife with consequence for the men. Doubts and questions plagued them: What does it mean to be a poet if your work is not your own? Who is best fit to lay claim to a parcel of poetic property that was collaboratively crafted and bequeathed to a fictitious Poet? How does one kill a Poet born of one’s own hand? Blending critical examination with jocular playlets-in-verse featuring the authors of the two books in baffled conversation, Murder Ballads reopens a 200-year-old cold case that never received a proper investigation: Who was the first true Author of Lyrical Ballads, and how exactly did he die?

Museum of Nonhumanity - Laura Gustafsson; Terike Haapoja (punctum books, 2019)
Museum of Nonhumanity is the catalogue for a full-size touring museum that presents the history of the distinction between humans and animals, and the way that this artificial boundary has been used to oppress human and nonhuman beings over long historical periods. Throughout history, declaring a group to be nonhuman or subhuman has been an effective tool for justifying slavery, oppression, medical experimentation, genocide, and other forms of violence against those deemed “other.” Conversely, differentiating humans from other species has paved the way for the abuse of natural resources and other animals. Museum of Nonhumanity approaches animalization as a nexus that connects xenophobia, sexism, racism, transphobia, and the abuse of nature and other animals. The touring museum hosts lecture programs in which local civil rights and animal rights organizations, academics, artists, and activists propose paths to a more inclusive society through intersectional approaches. The museum also hosts a pop-up book shop and a vegan café. As a temporary, utopian institution, Museum of Nonhumanity stands as a monument to the call to make animalization history.

My 1980s Gayboy Playlist - Arved Ashby (punctum books, 2026)
In this remarkably intimate book, My 1980s Gayboy Playlist, award-winning music writer Arved Ashby muses over pieces that impacted his sexual and musical awakenings as a troubled gay adolescent—pieces by Tchaikovsky, Chopin, Beethoven, Anton Bruckner, Alban Berg, Prince, Kurt Cobain, and Tom Petty. Ashby shares memories both intimate and far-ranging, but My 1980s Gayboy Playlist is not a memoir. Instead of trying to amplify an outwardly uneventful life, the author reengages with and renegotiates eight still-simmering touchpoints—some old musical flames, a few abusive relationships among them. Ashby focuses on desire as it spilled messily across different avenues of expression, seeking connections between erotic experience and musical passion. For Ashby, as a high school student in a small, rural Midwestern town in the early 1980s, choosing Alban Berg records over Van Halen counted as a perversion. When he recognized Tchaikovsky’s melodic fixations and Prince’s and Chopin’s musical fires, he better understood his own kinks. As an inadequate piano student and a shy virgin on tricyclic psych meds, his lack of physical success taught him the limitations of the body but also showed the capaciousness of queer failure. It was music that showed him how queerness insists on misappropriation, mishearing, and reading against the grain. Musicality, like sexual expression, amounts to a kind of role-playing— involving penetration and violation of identity as well as validations of the self. The author’s queer musical loves have shown him the vital beauty of muck, unreason, and noise, and as an imaginative writer, Ashby offers the liquid self-reflexivity of Proust and the auto-theory provocations of Maggie Nelson, Paul Preciado, and McKenzie Wark. His prose is poetic and playful, and now and again chaotic. He outs himself in and through his work, with humor and radical intimacy. My 1980s Gayboy Playlist ultimately illuminates what queer theorist Leo Bersani called the gayboy’s inelegant “apprenticeship in desiring.” Ashby’s closest partners growing up were fantasy, seclusion, and music-dependency, and he found his awkward bliss at the start of the era that witnessed AIDS and the rise of the Moral Majority. In Ashby’s early exurban environment, gayness was a thing feared, because unseen and unfathomed, but his musical intimacies made his personal closet endurable. They also helped him to survive his mis-education, to overcome failures of expression, and to craft a sexual awakening into something more rich and more strange.

My Gay Middle Ages - A.W. Strouse (punctum books, 2015)
In the world of My Gay Middle Ages, Chaucer and Boethius are the secret-sharers of A.W. Strouse’s “gay lifestyle.” Where many scholars of the Middle Ages would “get in from behind” on cultural history, Strouse instead does a “reach around.” He eschews academic “queer theory” as yet another tedious, normative framework, and writes in the long, fruity tradition of irresponsible, homo-medievalism (a lineage that includes luminaries like Oscar Wilde, who was sustained by his amateur readings of Dante and Abelard during the darks days of his incarceration for crimes of “gross indecency”). Strouse experiences medieval literature and philosophy as a part of his everyday life, and in these prose poems he makes the case for regarding the Middle Ages as a kind of technology of self-preservation, a posture through which to spiritualize the petty indignities of modern urban life. With a Warholian flair for insouciant name-dropping and a Steinian appetite for syntactic perversion, Strouse monumentalizes the medieval within the contemporary and the contemporary within the medieval.

My Phone Lies to Me: Fake News Poetry Workshops As Radical Digital Media Literacy Given the Fact of Fake News - Alexandra Juhasz (punctum books, 2022)
This book of poems about fake news written by diverse project participants is foremost an invitation and invocation for readers to participate, with others, in an experiment in knowing and working differently with the internet: Fake News Poetry Workshops. Between 2018 and 2020, Alexandra Juhasz directed more than twenty of these workshops around the world, and these are ongoing beyond the confines of this book. Each differs in form and structure, but participants are always asked to attend to research, their own knowledge about the internet and social media, and what they can learn from their workshop and previous ones. My Phone Lies to Me shares the poems created in the workshops. As moving, eloquent, and useful as they may be—and you are invited to indulge in and learn from them—enjoying and learning from the poems is only a small part of this book’s project. Four short essays (two by Juhasz, with a foreword and afterword by critical internet scholars Tara McPherson and Margaret Rhee, respectively) introduce and situate the project’s processes of radical digital media. You can learn what Fake News Poetry Workshops make, do, and believe in, as well as how to collaborate with others to create your own. Fake News Poetry Workshops are one way to counter dominant and dominating internet modes and values, to fight the corrupt ways of being and knowing that use digital media to create, fuel, and weaponize fake news. The project verifies good news in the face of fake news: that we can gather together in our many local places and use analog structures (about digital things and ways) to generate, hold, and share “art answers to phony questions.”

Mythodologies: Methods in Medieval Studies, Chaucer, and Book History - Joseph A. Dane (punctum books, 2018)
Mythodologies challenges the implied methodology in contemporary studies in the humanities. We claim, at times, that we gather facts or what we will call evidence, and from that form hypotheses and conclusions. Of course, we recognize that the sum total of evidence for any argument is beyond comprehension; therefore, we construct, and we claim, preliminary hypotheses, perhaps to organize the chaos of evidence, or perhaps simply to find it; we might then see (we claim) whether that evidence challenges our tentative hypotheses. Ideally, we could work this way. Yet the history of scholarship and our own practices suggest we do nothing of the kind. Rather, we work the way we teach our composition students to write: choose or construct a thesis, then invent the evidence to support it. This book has three parts, examining such methods and pseudo-methods of invention in medieval studies, bibliography, and editing. Part One, “Noster Chaucer,” looks at examples in Chaucer studies, such as the notion that Chaucer wrote iambic pentameter, and the definition of a canon in Chaucer. “Our” Chaucer has, it seems, little to do with Chaucer himself, and in constructing this entity, Chaucerians are engaged largely in self-validation of their own tradition. Part Two, “Bibliography and Book History,” consists of three studies in the field of bibliography: the recent rise in studies of annotations; the implications of presumably neutral terminology in editing, a case-study in cataloguing. Part Three, “Cacophonies: A Bibliographical Rondo,” is a series of brief studies extending these critiques to other areas in the humanities. It seems not to matter what we talk about: meter, book history, the sex life of bonobos. In all of these discussions, we see the persistence of error, the intractability of uncritical assumptions, and the dominance of authority over evidence.

MythomaniaS: Crime Scenes & Psycho Case Studies - Camille Lacadée; François Roche (punctum books, 2015)
mythomaniaS is a catalog of case studies in the form of film stills, architectural fragments, stage props, texts, and images culled from the experiments of MindMachineMakingMyths (Lab M4, part of the New Territories (http://www.new-territories.com/) architecture studio), a collaboration begun in 2012 between Camille Lacadee and François Roche to construct environmental-architectural psycho-scapes (in the partly fabricated wilds of various countries) as laboratory-shelters for exploring and deconstructing the supposed rifts between realism and speculative fiction (myth), psyche and environment, body and mind. Bringing together architecture, Deleuze and Guatarri’s schizoanalysis and deterritorialization, and Alfred Jarry’s pataphysics, Lacadee and Roche (and their tribe, Ezio Blasetti, Stephan Henrich, Danielle Willems, Gwyll Jahn, and many others) enacted and filmed mise-en-abymes in which certain scripted para-psychic narratives and architectural structures merge in the pursuit of reclaiming resilience — described by Roche as a tactic for merging refusal and vitality into a schizophrenic logic able to navigate the antagonism between the bottom-up and top-down conditions of the globalized world. In these fabricated schizoid psycho-nature-machine-scapes, the human being is no longer a bio-ecological consumer but a psycho-computing animal that emerges co-dependently with its environment in a hyper-local haecceity (“this-ness”). In the vein of Situationist psychogeography, each scenario fabulates geo-architectural conditions of human exile, solitude, and pathology drawn from narratives of the forbidden and taboo: the true story of an old Indian book collector exiled from his community on the suspicion of atheism, who finds refuge in a tear-collecting shelter (“Would Have Been My Last Complaint”); a scientist captured by a water spirit who remains trapped like a fish in the mindscape of a fish butcher (Although (in) Hapnea); a monster-boy endomorph constantly overfed and protected by a claustrophilic antidote-jacket produced by the excess of his incestuous mother’s love ((beau)strosity); Ariadne, labyrinth overseer, floating between two macho spirals, testosteroned Theseus and alcoholic Dionysus (Naxos, Terra Insola); the feral child — innocent, naïve, and obscene — in the deep jungle, auscultated by a scientistic voyeurism (The Offspring); etc. Each of these scenarios (designed as “shelters” where mind, environment, and architecture co-map each other) unfolds a “mythomania” in which each character transforms, and is transformed, para-psychically, by the environment, in a sort of biotope (habitat) feedback experiment. Ultimately, Lacadee and Roche want to create — via architecture and design, myth (literature), and psycho-geography — various conditions for schizoid passages between realism and fiction, expertise and knowledge, mind and built environment, narrative and topology, in order to bring about new strategic-tragic co-dependencies as forms of schizoid resistance to the usual identity regimes, and to also reboot architecture as a form of psycho-social praxis and non-necrotic speculation.

Nairobi Becoming: Security, Uncertainty, Contingency - Joost Fontein; Tessa Diphoorn; Peter Lockwood; Constance Smith (punctum books, 2024)
Echoing the edgy, disjunctive, ever-emergent city of Nairobi that it explores, Nairobi Becoming: Security, Uncertainty, Contingency strives to be several things-in-the-making. It is a historically and anthropologically minded examination of a shifting cityscape, an experimental, collaborative exercise in curated juxtaposition and assemblage, and an interdisciplinary, subjunctive urban ethnography. It brings together curated interventions by twenty-seven artists, scholars, and writers to trace Nairobi’s becoming. Methodologically experimental and multimodal, it seeks to balance an appreciation of Nairobi’s fragmented character while also recognizing its contingent coherency. Nairobi Becoming curates an eclectic collection of different voices and interventions to evoke something of the city’s manifold guises and historicities – an urban mosaic of partial experiences as well as dawning possibilities for future becomings. Assembling scholarship, literature, creative non-fiction, and visual art, the contributions are arranged around particular themes, while resisting the urge to develop a singular coherent voice. Security – in its various guises – is the linking thread, the point of articulation that connects apparently disparate elements of Nairobi life, from sex work to roadbuilding, goat markets to funerals. Security is here an analytical operator: a concept that refracts the seemingly diverse modalities of life in Nairobi, and, with the related domains of uncertainty and contingency, brings the city’s dynamics of fragmentation and coherence to the surface in surprising ways. If confronting Nairobi’s will to coherence amidst the strains of fragmentation is the empirical and analytical challenge of Nairobi Becoming, then it is through collaboration and juxtaposition, curation and contrast, and the messiness of assemblage, that this book chimes with the fraught multiplicities of a city-in-the-making. As such, this book is also an exploration of the inevitable tension that exists between curatorial intent and the possibility of allowing each contribution to stand for itself.

New Developments in Anarchist Studies - pj lilley; Jeff Shantz (punctum books, 2015)
This volume collects papers presented at the 5th Conference of the North American Anarchist Studies Network (La Red Norteamericana de Estudios Anarquistas / Le Réseau Nord-Américain d’études Anarchistes) Anarchism is experiencing a remarkable resurgence in the new millenium. Not only active in the streets across Turtle Island, growing interest in anarchist scholarship is perhaps unprecedented. This is reflected in the development of the North American Anarchist Studies Network (NAASN). Drawn from papers presented at the 5th NAASN conference in Surrey (on Coast Salish Territories), this collection shows the vitality of contemporary anarchist research and writing.

Nicholas of Cusa and the Kairos of Modernity: Cassirer, Gadamer, Blumenberg - Michael Edward Moore (punctum books, 2013)
In this far-reaching essay, historian Michael Edward Moore examines modernity as an historical epoch following the end of the medieval period — and as a “messianic concept of time.” In the early twentieth century, a debate over the meaning and origins of modernity unfolded among the philosophers Ernst Cassirer, Hans-Georg Gadamer and Hans Blumenberg. These thinkers tried to resolve the puzzle of the fifteenth-century master Nicholas of Cusa. Was Cusanus the last great medieval thinker, his ideas a summa of medieval tradition? Or was he a mysterious epochal figure, seated at one end of the bridge leading to modern thought? Nicholas of Cusa lived during a time of historical and existential crisis, or kairos, when medieval governments and cherished sources of unity were shaken. Likewise, the debate over his significance took place during a later phase of crisis for Europe, in the decades before and after the Second World War, when the collapse of European civilization was witnessed. Moore argues that modernity, so intently examined as an historical and spiritual problem, has significance for our contemporary sense of crisis.

No Archive Will Restore You - Julietta Singh (punctum books, 2018)
At once memoir, theory, poetic prose, and fragment, No Archive Will Restore You is a feverish meditation on the body. Departing from Antonio Gramsci’s summons to compile an inventory of the historical traces left in each of us, Singh engages with both the impossibility and urgent necessity of crafting an archive of the body. Through reveries on the enduring legacies of pain, desire, sexuality, race, and identity, she asks us to sense and feel what we have been trained to disavow, to re-member the body as more than itself. Why this desire for a body archive, for an assembly of history’s traces deposited in me? (I worry over how to describe it, how to frame it without sounding banal or bafflingly idiosyncratic.) The body archive is an attunement, a hopeful gathering, an act of love against the foreclosures of reason. It is a way of knowing the body-self as a becoming and unbecoming thing, of scrambling time and matter, of turning toward rather than against oneself. And vitally, it is a way of thinking-feeling the body’s unbounded relation to other bodies. I begin then to compile an archive of my body, an activity that from the start feels discomfortingly intimate. Too intimate and too bewildering an undertaking, because like all other bodies mine has become so many things over time, has changed dramatically through forces both natural and social. I am also, it must be noted, a person whose body has been broken and maimed many times over—a fact that I cannot yet entirely account for.

Noise Thinks the Anthropocene: An Experiment in Noise Poetics - Aaron Zwintscher (punctum books, 2019)
In an increasingly technologized and connected world, it seems as if noise must be increasing. Noise, however, is a complicated term with a complicated history. Noise can be traced through structures of power, theories of knowledge, communication, and scientific practice, as well as through questions of art, sound, and music. Thus, rather than assume that it must be increasing, this work has focused on better understanding the various ways that noise is defined, what that noise can do, and how we can use noise as a strategically political tactic. Noise Thinks the Anthropocene is a textual experiment in noise poetics that uses the growing body of research into noise as source material. It is an experiment in that it results from indeterminate means, alternative grammar, and experimental thinking. The outcome was not predetermined. It uses noise to explain, elucidate, and evoke (akin to other poetic forms) within the textual milieu in a manner that seeks to be less determinate and more improvisational than conventional writing. Noise Thinks the Anthropocene argues that noise poetics is a necessary form for addressing political inequality, coexistence with the (nonhuman) other, the ecological crisis, and sustainability because it approaches these issues as a system of interconnected fragments and excesses and thus has the potential to reach or envision solutions in novel ways.

Non-Conceptual Negativity: Damaged Reflections on Turkey - Zafer Aracagök (punctum books, 2019)
Non-Conceptual Negativity: Damaged Reflections on Turkey critiques those who have accused Deleuze of an unbounded affirmation which, according to them, has played directly into the hands of capitalist modes of production. Yet no one has acknowledged that under the aegis of nano-fascism, late capitalism has grown into Neanderthal capitalism, invented and developed in laboratory countries like Turkey with the aid of an international Neanderthal league. Layer upon layer, Aracagök explains in fragmentary fashion that it is not only a matter of how Turkey has grown into a prime laboratory of nano-fascism with the aid of the US and the European Union, but also how the results obtained from this laboratory are put into practice in different countries under Neanderthal capitalism, enslaving each and every one of us into accepting even the position of suicide bomber. As none of us is exempted from nano-fascism today, perhaps it is timely to reconsider the ways in which Deleuzian thought is appropriated in the form of an unquestioned affirmation of everything and how its critique has ended up in an old-fashioned formulation of the in-dividual according to a party program. If this all goes to show that we are face to face with a route different from the accepted forms of affirmation — that is, if we are all affirmed and seem to be happily affirming life as it is as a result of the Neanderthal manipulation of the negative — then isn’t it timely to rethink the Deleuzian affirmation in its non-originary origin with regard to Adorno’s resistance against affirmation? That is, the double negation never ends up in affirmation, and if it does so, it might mean your negation is not strong enough.

Northeastern Asia and the Northern Rockies: Treasures from the Los Angeles County Museum of Art and the Daryl S. Paulson Collection - Stephen Little; T. Lawrence Larkin (punctum books, 2022)
The philosophical ties between Northeastern Asia and the Northern Rockies as represented in a selection of fine art—including Daoist nature deities and immortals, Confucian scholar brushes and inkstones, and Buddhist guardian kings and compassionate bodhisattvas—have never been explicated. This catalog lays the groundwork for a serious discussion of trans-Pacific acculturation: first by explaining the fundamentals of Daoism, Confucianism, and Buddhism in reference to rare works of art produced in China, Korea, and Japan between the Tang Dynasty and the Qing Dynasty, and second, by assessing the prevalence of these philosophies as indicated by photographs of temples, shrines, deities, and rituals recreated in Idaho, Montana, Wyoming, and Colorado between the Civil War and World War I. Drawing from the collections of the Los Angeles County Museum of Art and the Daryl S. Paulson Collection in Bozeman, Montana, Asian art curator Stephen Little offers three brief essays that distinguish the philosophies of Daoism, Confucianism, and Buddhism according to their founding values, each followed by several object case studies that illustrate, elaborate, and develop those ideals. Mining the photographs of the state historical societies of Boise, Helena, Cheyenne, and Denver, Euro-American art professor T. Lawrence Larkin offers a long essay that compares religious values and artistic forms on both sides of the Pacific illustrated by objects that highlight migrant and settler culture in the Inner West. Profusely illustrated with new color and rarely seen black-and-white images, and containing useful maps, chronologies, and an index, Northeastern Asia and the Northern Rockies is an invaluable reference for the general reader and an important resource for the regional scholar.

Notes on Trumpspace: Politics, Aesthetics, and the Fantasy of Home - David Markus (punctum books, 2023)
In the wake of the 2016 U.S. Presidential election, considerable ink was spilled on the architecture and interior design of the buildings owned and inhabited by Donald J. Trump. In an effort to understand the inner workings of America’s first real-estate-mogul-in-chief, commentators remarked on everything from the president’s fastidious taste in window dressings to the exaggerated floor counts boasted by many Trump-branded towers. Notes on Trumpspace takes this discursive trend as a point of departure. It examines not only key examples of “Trumpitecture” but also works of film, fiction, and contemporary art that center on or otherwise illuminate the psychogeography of “super luxury” real estate. Engaging closely with current political debates, the book takes a critical approach to mainstream liberal reactions to the Trump presidency. It argues that the fascination and horror Trump has provoked is owing in part to the way he lays bare the obsession with status, self-branding, and achievement-at-any-cost that has been part and parcel of the broader neoliberal ethos. Finally, it analyzes the January 6, 2021 storming of the US Capitol through the lens of spatio-political theorizations of settler colonial power and conceptions of home and homeland. A genre-defying work of political and aesthetic inquiry, Notes on Trumpspace offers a sustained investigation into the relationship between the built environment, late capitalist fantasy, and national identity. It asks what it means for current and future understandings of home and dwelling that this era’s most notorious peddler of high-end real estate succeeded in peddling his way into the White House in 2016.

Nothing As We Need It: A Chimera - Daniela Cascella (punctum books, 2022)
Nothing As We Need It: A Chimera imagines and writes a composite and impure form of criticism that embodies the writing of research as recursive, entangled, and many-voiced. Shaped by encounters with literature not translated in English, by the polyphonies, artifices, and concealments of a bilingual self, and by the sense of speechlessness and haunting when writing works that cannot be instantly quoted, this book’s subtitle derives from the mythological Chimera: a monstrous creature made of three different parts, impossible in theory but real in the imagination and in the reading of the myth. Similarly, the book is written in different styles, some of which may seem impossible, monstrous, and disturbing. It manifests critical writing as enmeshment and conversation with its subject matters; favours impurity rather than detachment; and embraces exaggeration, repetition, laughter, and self-parody as legitimate forms of knowledge. Yet a chimera also designates the object of a yearning deemed unattainable: this book exists in the space of such yearning, in the tension between words and what exceeds them and their overtones. The critic is exhausted by yearning, rather than the owner of exhaustive knowledge. A Menippean satire for critical writing, Nothing As We Need It sustains its argument for composite and impure writing in its form. It demands ways of reading equally varied and wildly imaginative. Listening to literature beyond the limits of textual analysis, it dismisses the visual implications of reflection, which assumes detachment and polished surfaces, in favor of an aural method of resonance, allowing enmeshment and interference. This book unsettles language, welcomes uninhibited exaggeration and wordplay, and manifests possibilities for working with citation beyond the boundaries of inverted commas.

Nothing in MoMA - Abraham Adams (punctum books, 2018)
Nothing in MoMA is a series of photographs captured in areas of Manhattan museums in which there are no artworks, written words, or people. Addressing the “grammar that organizes and secures our scene of looking,” in the words of art historian David Joselit’s introduction, the book imagines a composite empty museum or a narrative of marginal attention. Originally displayed in partial prototype as a children’s board book at Artists Space in 2015, Nothing in MoMA is here collected for the first time in the series’ entirety. Evoking the history of indeterminacy as much as that of institutional critique, the deadpan composition of Adams’s photographs likewise recalls François Jullien’s theory of bland aesthetics, in a playful reductio of socio-institutional space to a bare literality. Both a visual essay on museum phenomenology and a performance document, Nothing in MoMA describes a choreography of avoidance, in which a conceptual constraint becomes a means of seeing and navigating concrete space.

Nubian Proverbs (Fadijja/Mahas) - Maher Habbob (punctum books, 2022)
In the 1995/96 academic year, twenty-five Egyptian Nubian students of the Faculty of Social Work in Aswan were recruited by Dr. Muddathir Salim to complete a brief Nubian ethnological survey, largely restricted to the area of New Nubia, over a period of several months. They documented Egyptian Nubian culture and heritage, among them proverbs, tales, lullabies, marriage customs, and moulid and mourning songs, as well as models of Nubian clothes, jewelry, and houses. This research has culminated in Maher Habbob’s Nubian Proverbs, which presents the fruits of decades of collecting proverbs from his native Nubian region in Fadijja (Nobiin). The five hundred proverbs gathered in this volume give a vivid picture of the Nubian imagination and represent a priceless archive of cultural heritage threatened by ongoing assimilation and cultural genocide. The proverbs are presented in Nubian script, accompanied by a transliteration in Roman script, and a literal translation and paraphrase in English.

Obiter Dicta - Erick Verran (punctum books, 2021)
Stitched together over five years of journaling, Obiter Dicta is a lyrical compendium representing the transcription of twelve notebooks, since painstakingly reimagined for publication. This unschooled exercise in aesthetic thought, interlaced with quotations from hundreds of diverse authors, interrogates a wide array of subject matter through notes, commentary, observations, and musings. With lessons stolen from seemingly unrelatable disciplines, the restless candor of Erick Verran’s approach to philosophical and social inquiry will be familiar to readers of Dave Hickey’s Air Guitar and Mark Fisher’s K-Punk. Obiter Dicta is an experiment in intellectual dot-connecting that challenges much long-standing wisdom about everything from illuminated manuscripts to photography to the evolution of European music. A Zibaldone for the 21st century.

Object Oriented Environs - Jeffrey Jerome Cohen (punctum books, 2016)
Object Oriented Environs is the lively archive of a critical confluence between the environmental turn so vigorous within early modern studies, and thing theory (object oriented ontology, vibrant materialism, the new materialism and speculative realism). The book unfolds a conversation that attempts to move beyond anthropocentrism and examine nonhumans at every scale, their relations to each other, and the ethics of human enmeshment within an agentic material world. The diverse essays, reflections, images and ephemera collected here offer a laboratory for probing the mystery and potential autonomy of objects, in their alliances and in performance. The book is the trace of an event-space crafted over a day of conversation in two seminars at the Shakespeare Association of America meeting in 2014 in St. Louis and offers its nineteen essays as the end to the work-cycle of the collective we crafted that day. It is a noisy collation, full of bees, bushes, laundry, crutches, lists, poems, plague vectors, planks, chairs, rain, shoes, meat, body parts, books, and assorted humans (living and dead), and also a repertoire of dance steps, ways of configuring the relations between subject and object, actors or actants (human and otherwise). It is also a book that asks readers to ponder their environs, to consider the particularities of their world, of their reading experiences, and to consider what orders of meaning we might be able to derive from attending closely to all the very many things we come into being with.

Oblation: Essays, Parables, Paradoxes - M.H. Bowker (punctum books, 2024)
Elements of this book, Oblation: Essays, Parables, Paradoxes, defy reason. They do so for good reason. Much of what we do, much of what we think, is oblation: sacrifice, offering, to something or someone. The root of “oblation” is “to draw near” or “to dwell in.” It refers to what is brought unto the altar, literal or proverbial—the profoundest oblation being what binds us together, our very souls, our dearest loves, indistinguishable from ourselves, our Isaacs on our Mount Moriahs. The natures of our oblations characterize our relationships to objects great and small, e.g., Lords and loved ones, groups and masses of signifiers. Oblative transactions promise meaning, yet we are full of uncertainty. What is it that cries out for oblation? How do we hear its voice? Are we, in fact, called, or do we, on the contrary, offer every bit gratuit? Why, as Albert Camus famously remarked, do “the stage sets collapse” as we offer ourselves to life’s routine? In Oblation, M.H. Bowker considers these questions in a series of essays touching upon figures such as Franz Kafka, Edgar Allan Poe, Baron van Münchhausen, and Jacques Lacan, unraveling themes of loss, hatred, and the Munchausen syndrome by proxy. Interspersed with brief parables and paradoxes, Bowker’s essays push us to wonder who or what we are offering ourselves and others to—and how we get away with this.

Oceanic New York - Steve Mentz (punctum books, 2015)
This volume comprises a three-fold object, Book and Ocean and New York City. If this Book were Ocean, how would it feel between your fingers? Wet and slippery, just a bit warmer or colder than the air around it, since the Ocean is our planet’s greatest reservoir of heat, a sloshing insulator and incubator girdling our globe. If its pages were New York City, how would they abrade your imagination? Human and teeming, endlessly humming along with that same old tune. Imagine that these three things were one thing. All together: Book and Ocean and New York City. During the long historical pause between the day the last sailing ship docked at South Street and that day in October 2012 when Hurricane Sandy brought the waves back in fury, New York turned its back on the sea. This Book remembers that the City was founded on Ocean, peopled by its currents, grew rich on its traffic. The storm taught what we should never have forgotten: under New York’s asphalt lies not beach but Ocean. Oceanic New York salvages the City’s salt-water past and present. It takes inspiration from Elizabeth Albert’s gorgeous exhibition of historical artifacts and contemporary art, “Silent Beaches, Untold Stories: New York City’s Forgotten Waterfront,” which was on display at St. John’s University in Queens in Autumn 2013. Buoyed up by art, the Book plunges into the urban and oceanic. “Circumambulate the city of a dreamy Sabbath afternoon,” entices our friend Ishmael. “Nothing will content [us] but the extremest limit of the land.”

Pen in the Park: A Resistance Fairytale – Pen Parkta: Bir Direniş Masalı - Raşel Meseri (punctum books, 2014)
Pen in the Park is a unique revolutionary children’s book written by Raşel Meseri and illustrated by Sanne Karssenberg. Meseri narrates the Gezi Park protests in Istanbul through the figure of a penguin named Pen, whogoes on a trip from Antarctica to Gezi Park to save his fellow penguins, and gets involved in various adventures with his friends Chapulletta, the cat Trafo, and the dog Loukanikos. The Gezi movement of 2013–14 started with the threat of the destruction of the Gezi Park, a public space, which became quickly occupied by protestors from all generations and political backgrounds to build a movement that addressed not only the destruction of green areas and gentrification of public space, but also the democratic deficit of the country as such. At the height of the protests, dozens of protesters were killed and thousands injured. As the result of the protests, the park remained a public space and the struggle continues in different forms up to this day. During the protests, penguins were reclaimed as one of the symbols, as the main television channels preferred to show documentaries about the lives of penguins, instead of the uprising in Turkey. In Meseri’s story, Pen the brave penguin, Pen, is both a symbol and an active agent in the course of events, guiding us through the process of political emancipation, democratic experiment, friendship, and solidarity that characterizes the Gezi movement.

Perceptron - James E. Dobson; Rena J. Mosteirin (punctum books, 2025)
Perceptron is a work of experimental poetry and a critical biographical reading of Frank Rosenblatt (1928–1971) and his 1957 invention, the Perceptron. The Perceptron was the first widely publicized and used machine learning device and the origin of much contemporary neural network technology. Rosenblatt was a psychologist, a computer engineer, a musician, an amateur astronomer, a sailor, and a poet. The Perceptron was born from an interdisciplinary mix of ideas and was so far ahead of its time that it was widely misunderstood by other scientists and the public. This mechanical invention, imagined as an alternative to general purpose digital computers, and its algorithmic implementation as a simulation of the device was deeply rooted in mid-twentieth-century neuroscience and psychological theories of behavior. Introduced to the world by one newspaper under the headline “Shades of Frankenstein!” in 1958, following a public demonstration in Maryland sponsored by the US Navy, the Perceptron was a radical new approach to designing computer systems. What made it different was its design as a simplified model of animal vision systems. The Perceptron could perform pattern recognition and matching from a collection of simple visual objects. It was innovative and impressive, but it was also constantly oversold by its financial supporters, the press, and by its inventor. Perceptron traces, contextualizes, and celebrates the ideas that would become embedded in this early thinking machine and that animated the excitement and promise that would eventually turn to frustration and failure during Rosenblatt’s tragically short lifetime.

Philosophy for Militants - Michael Munro (punctum books, 2017)
My thinking is related to theology as blotting pad is related to ink. It is saturated with it. Were one to go by the blotter, however, nothing of what is written would remain. “No longer imminent, the End is immanent.” “Ends are ends,” Frank Kermode goes on to clarify, “only when they are not negative but frankly transfigure the events in which they were immanent.” From its imminence to its immanence, not “negative,” “no longer,” but transformative, how is “the End” in turn “transfigured”? In what may ending be said then to consist? To “the end times” of apocalypse and eschatology Giorgio Agamben, following Gianni Carchia, opposes messianism and “messianic time”—to the end of time, in a formula, the time of the end. To the writings of those for whom to philosophize is to learn how to die—from Plato to Montaigne and beyond—one may oppose, in like manner, the writings of Spinoza, who “thinks of death least of all things”—“for nature is Messianic by reason of its eternal and total passing away,” as Benjamin writes—and so in whose pages “wisdom,” transfigured, “is a meditation on life.”

Photography in the Middle: Dispatches on Media Ecologies and Aesthetics - Rob Coley; Dean Lockwood (punctum books, 2016)
It’s easy to forget there’s a war on when the front line is everywhere encrypted in plain sight. Gathered in this book’s several chapters are dispatches on the role of photography in a War Universe, a space and time in which photographers such as Hilla Becher, Don McCullin and Eadweard Muybridge exist only insofar as they are a mark of possession, in the sway of larger forces. These photographers are conceptual personae that collectively fabulate a different kind of photography, a paraphotography in which the camera produces negative abyssal flashes or ‘endarkenment.’ In his Vietnam War memoir, Dispatches, Michael Herr imagines a ‘dropped camera’ receiving ‘jumping and falling’ images, images which capture the weird indivisibility of medium and mediated in a time of war. The movies and the war, the photographs and the torn bodies, fused and exchanged. Reporting from the chaos at the middle of things, Herr invokes a kind of writing attuned to this experience. Photography in the Middle, eschewing a high theoretical mode, seeks to exploit the bag of tricks that is the dispatch. The dispatch makes no grand statement about the progress of the war. Cultivating the most perverse implications of its sources, it tries to express what the daily briefing never can. Ports of entry in the script we’re given, odd and hasty little glyphs, unhelpful rips in the cover story, dispatches are futile, dark intuitions, an expeditious inefficacy. They are bleak but necessary responses to an indifferent world in which any action whatever has little noticeable effect. As luck would have it, Photography in the Middle begins with some nasty accidents, and extracts from the wreckage a few lessons learned. Dusting itself off, it ships out and puts up with a bunch of battle scarred, big gun photojournalists in the Holiday Inn of a typical world city. Later, it immerses itself within the leaked files of an enigmatic police cabal which detail the surveillance of conceptual photographers Bernd and Hilla Becher, an operation that even extends to the duo’s dreams. Further back in time, in 1897, we are invited to an inflammatory, yet patchily documented public lecture given by the Titan, Muybridge. More than any other, it is William Burroughs, conceived here as a war photographer, who is our tutelary figure, hovering over all these pages in his attempt to map emergent vectors of mediation, ever more intimate forms of control and accelerants of planetary catastrophe. Burroughs believed that it was necessary to both keep pace with and formulate new vectors, vectors that might act as intersections with a nonhuman outside. Photography has an agency of its own, one that scrambles the patterns and refrains of mediation upon which human life is based, glitching the human and provoking relations with external coordinates. With Burroughs, and other inspirations such as J.G. Ballard, Georges Bataille, Tom McCarthy and Eugene Thacker, our notion of the dispatch does not offer positive knowledge of something that we can reconcile with existing rational explanations, but rather the revelation of a nightside, our redundancy in a photography that suspends all operations in a general blindness.

Pitch and Revelation: Reconfigurations of Reading, Poetry, and Philosophy through the Work of Jay Wright - Will Daddario; Matthew Goulish (punctum books, 2022)
Pitch and Revelation is the first book-length study of the poetry, prose, and dramatic literature of the African American poet Jay Wright (b. 1934). The authors premise their reading on joy as a foundational philosophical concept. In this, they follow Spinoza, who understood joy as an affect necessary for the construction of an intellectual love of God, leading into the infinite univocity of everything. Similarly, with Wright, joy leads to a visceral sense of what the authors call the great weave of the world. This weave is akin to the notion of entanglement made popular by physicists and contemporary scholars of Science Studies, such as Karen Barad, which speaks of the always ongoing, mutually constitutive connections of all matter and intellectual processes. By exhibiting and detailing the joy of reading Wright, Pitch and Revelation intends to help others chart their own paths into the intellectual, musical, and rhythmical territories of Wright’s world so as to more fully experience joy in the world-at-large. Although the exhibitions of meaning-making presented are instructive, they do not follow the “do as I do” or “do as I say” model of instructional texts. Instead, Goulish and Daddario invite the reader to “do along with us” as they make meaning from selections across Wright’s erudite, dense, rhythmically fascinating, endlessly lyrical, highly structured, and seemingly hermetic body of work.

Poetry from Beyond the Grave - Francisco Cândido "Chico" Xavier (punctum books, 2013)
Poetry from Beyond the Grave is the first English publication of a large selection of poems by the Brazilian medium and Spiritist leader Francisco Cândido “Chico” Xavier. These poems, originally collected in the volume Parnaso de Além-Túmulo (http://www.autoresespiritasclassicos.com/Chico%20Xavier/1/Chico%20Xavier%20(Esp%C3%ADritos%20Diversos)%20-%20Parnaso%20de%20Al%C3%A9m-T%C3%BAmulo.pdf), were dictated to Xavier by a variety of spirits of Brazilian poets from the afterlife, as journeying souls or as witnesses of the spiritual city Nosso Lar, “our house.” Poetry from Beyond the Grave is a veritable collection of haunted writing, in which poets present their posthumous work as if they were alive. The brilliant translation by Vitor Pequeno is supplemented by an extensive afterword by Jeremy Fernando, who traces what it means to speak through the other.

Poetry Vocare - Adam Staley Groves (punctum books, 2011)
Poetry Vocare is the first collection of poetry published by young American poet A. Staley Groves. A dense fabric of resemblances and reflections, this work engages with Wallace Stevens, Ossip Mandelstam, and Emily Dickinson. In addition to poems Groves gives a supplement of prose, a short essay titled “Affirmation of Instruction.” Poetry scholar Judith Balso wrote a foreword in French to the work.

Porno-Graphics and Porno-Tactics: Desire, Affect, and Representation in Pornography - Eirini Avramopoulou; Irene Peano (punctum books, 2016)
Porno-Graphics and Porno-Tactics asks whether, and how, it is possible to re-appropriate pornography and think through it critically and creatively for a project of liberation. In the different contributions which make up this deliberately heterogeneous collection of short, non-canonical essays, such a quest proceeds by re-articulating the aporias of desire, intimacy, touch and seduction. It also relates them to claims of visibility, visions of emancipation and its failures, as well as to the politics of violence that we get exposed to through circulating images and affects. This is an attempt to exceed the limits set by and for ourselves in relation to how we connect to our own bodies, to the bodies of our lovers and to the bodies of the theories we live with, sleep with and dream about – in short, to all that we get attached to. The editors and contributors of this collection do not claim the euphoric potentiality of pornography as necessarily subversive and emancipatory, but are nevertheless open to the possibilities of re-shaping it (in textual, contextual, intertextual, but also affective and embodied forms) through different graphic and tactical/tactile inscriptions. On the one hand, authors reflect on definitions and practices of pornography as a genre adopting specific codes and canons, whether it is concerned with sex acts and the industry of porn or with other predominant forms of representation and the structures of power underlying them. On the other hand, chapters relate to the more affective, libidinal, synaesthetic and inter/subjective dimensions of pornography, and on the capacity of different reappropriations to subvert its limits.

Posthuman Lear: Reading Shakespeare in the Anthropocene - Craig Dionne (punctum books, 2016)
Approaching King Lear from an eco-materialist perspective, Posthuman Lear examines how the shift in Shakespeare’s tragedy from court to stormy heath activates a different sense of language as tool-being — from that of participating in the flourish of aristocratic prodigality and circumstance, to that of survival and pondering one’s interdependence with a denuded world. Dionne frames the thematic arc of Shakespeare’s tragedy about the fall of a king as a tableaux of our post-sustainable condition. For Dionne, Lear’s progress on the heath works as a parable of flat ontology. At the center of Dionne’s analysis of rhetoric and prodigality in the tragedy is the argument that adages and proverbs, working as embodied forms of speech, offer insight into a nonhuman, fragmentary mode of consciousness. The Renaissance fascination with memory and proverbs provides an opportunity to reflect on the human as an instance of such enmeshed being where the habit of articulating memorized patterns of speech works on a somatic level. Dionne theorizes how mnemonic memory functions as a potentially empowering mode of consciousness inherited by our evolutionary history as a species, revealing how our minds work as imprinted machines to recall past prohibitions and useful affective scripts to aid in our interaction with the environment. The proverb is that linguistic inscription that defines the equivalent of human-animal imprinting, where the past is etched upon collective memory within ‘adagential” being that lives on through the generations as autonomic cues for survival. Dionne’s reimagining of this tragedy is important in the way it places Shakespeare’s central existential questions — the meaning of familial love, commitments to friends, our place in a secular world — in a new relation to the main question of surviving within fixed environmental limits. Along the way, Dionne reflects on the larger theoretical implications of recycling the old historicism of early modern culture to speak to an eco-materialism, and why the modernist textual aesthetics of the self-distancing text seems inadequate when considering the uncertainty and trauma that underscores life in a post-sustainable culture. Dionne’s final appeal is to “repurpose” our fatalism in the face of ecological disaster.

Post Memes: Seizing the Memes of Production - Alfie Bown; Dan Bristow (punctum books, 2019)
Art-form, send-up, farce, ironic disarticulation, pastiche, propaganda, trololololol, mode of critique, mode of production, means of politicisation, even of subjectivation — memes are the inner currency of the internet’s circulatory system. Independent of any one set value, memes are famously the mode of conveyance for the alt-right, the irony left, and the apoliticos alike, and they are impervious to many economic valuations: the attempts made in co-opting their discourse in advertising and big business have made little headway, and have usually been derailed by retaliative meming. Post-Memes: Seizing the Memes of Production takes advantage of the meme’s subversive adaptability and ripeness for a focused, in-depth study. Pulling together the interrogative forces of a raft of thinkers at the forefront of tech theory and media dissection, this collection of essays paves a way to articulating the semiotic fabric of the early 21st century’s most prevalent means of content posting, and aims at the very seizing of the memes of production for the imagining and creation of new political horizons. With contributions from Scott and McKenzie Wark, Patricia Reed, Jay Owens, Thomas Hobson and Kaajal Modi, Dominic Pettman, Bogna M. Konior, and Eric Wilson, among others, this essay volume offers the freshest approaches available in the field of memes studies and inaugurates a new kind of writing about the newest manifestations of the written online. The book aims to become the go-to resource for all students and scholars of memes, and will be of the utmost interest to anyone interested in the internet’s most viral phenomenon.

Pray for Brother Alexander - Constantin Noica (punctum books, 2018)
Constantin Noica’s (1909–1987) Pray for Brother Alexander is a meditation on responsibility, freedom, and forgiveness. On the surface, the book describes events and people from Noica’s life during his time in a political communist prison in Romania. However, the volume is not a historical account only, but rather an honest introspection into how a human being may keep sanity when everything around him makes no sense. Unlike his famous Romanian contemporaries, scholar Mircea Eliade, dramatist Eugène Ionescu, and philosopher Emil Cioran, who lived abroad, Constantin Noica did not leave communist Romania. Considered an “anti-revolutionary” thinker, Noica was placed under house arrest in Câmpulung-Muscel between 1949 and 1958. In 1958, he was sentenced to 25 years in prison. He was released after 6 years, and Pray for Brother Alexander covers his experiences during this time. In his writings, Noica rekindles universal themes of philosophy, but he deals with them in a profoundly original manner, based on the culture in which he lived and for which he also suffered persecution. The volume will be of great of interest to scholars and students in history of philosophy and continental philosophy, but also to people interested in the recent history of Eastern Europe and the political persecution that took place after WWII in those countries.

Œ Case Files, Vol. 01 - Simone Ferracina (punctum books, 2021)
Over the past ten years, the journal Organs Everywhere (https://organseverywhere.com/) (Œ) has promoted conversations that approach architectural design from the edges of the discipline—testing its boundaries, technologies, methods and (e)valuation systems, and keeping them unstable. It has valued transdisciplinary, speculative, and irreverent explorations over strict publishing formats and academic purity, promoting a profanatory and open-ended ethos. Each issue of Organs Everywhere has strung together disparate organs and limbs, activating precarious couplings and associations, and testing new metabolisms and assemblages. Œ Case Files continues this commitment to the making and unmaking of monsters, both by anthologising past contributions into fresh configurations and designs, and by combining them with entirely new articles and voices. Here, philosophers, designers, experimental architects, artists, science fiction writers, activists, and poets shift, expand, and re-imagine notions of space, time, inhabitation, technology, knowledge, use, value, and experience. A patchwork of essays, stories, design experiments, buildings, art installations, drawings, prose poems, photographs and speculative projects collide in the book, infecting simple disciplinary orthodoxies with doubt and potentials, uncertainty and hope—indecisive photons and softness; metatactility and haunted houses; neurodiversity and protocells; prosthetics, grease and darkness; post-human scenographies, software and GPS anklets; anthropocenic devices, paprika, and synthetic biology.

Of Great Importance - Nachoem M. Wijnberg (punctum books, 2018)
Of Great Importance is Nachoem Wijnberg’s 16th volume of poetry. One of the most prominent living Dutch writers, Wijnberg’s poetry is known for its deceptively plain language and his poems, according to the poet himself, can be read well by anyone who can read a newspaper. The poems in Of Great Importance engage with statecraft, economics, and world history, lyricizing taxes and debts, stocks and flows, citizenship and labor contracts, notaries and accountants, factories and strikes, freedoms and fundamental rights, banks and railroads, property rights and codes of honor, sieges and treaties, gods and generals, how to make money and how to win elections, when to declare war and when to found a new state. Wijnberg’s engagement with these and other related topics is based on his belief that economics, politics, and history — and all of the tangled relations therein, no matter how asymmetrical — concern how people live together, and his poetry is a creative form of historiography that attends to tracing the theater of an affective commonwealth, in which he builds upon the best work of those thinkers and poets who came before — including Karl Marx, John Maynard Keynes, Heinrich Heine, Czesław Miłosz, and especially C.P. Cavafy. Ultimately, Wijnberg understands that “Something important that changes the world only happens if there is a lever with a fulcrum you cannot know enough about,” and yet his poetry gorgeously illuminates this fulcrum. Van groot belang, a substantial part of which has been translated in Of Great Importance, was shortlisted for the Dutch VSB Poetry Prize. According to the jury report, the book For his entire body of work, Wijnberg has also received (http://www.poetryinternationalweb.net/pi/site/cou_article/item/28917/PC-Hooft-Prize-goes-to-Nachoem-Wijnberg) the most prestigious Dutch literary award, the P.C. Hooftprijs, in 2018.

Of Learned Ignorance: Idea of a Treatise in Philosophy - Michael Munro (punctum books, 2013)
What is a problem? What’s asked in that question, and how does one even begin to take its measure? How else could one begin, except as one does with any other problem—by way of its impulsion. Of Learned Ignorance: Idea of a Treatise in Philosophy is about philosophy because philosophy is about problems: philosophy, in a word, is where problems become a problem. After Anti-Oedipus, in the Kafka book and in A Thousand Plateaus, what Deleuze and Guattari counsel, strikingly, is sobriety. Sobriety is what they praise in Kafka. And it is sobriety that seems above all else to be necessary here. (Steven Shaviro has pointed out (http://www.shaviro.com/Blog/?p=478) the prominence of structure in Deleuze’s writing: “even when Deleuze’s prose, by himself or with Guattari, seems to be ranging anarchically all over the place, in fact it has a rigid and unvarying architecture, which is what keeps it from falling apart.”) Of Learned Ignorance is a dead letter because it names a problem. It’s a dead letter because it is, cautiously, a love letter. It’s a dead letter because it lovingly stages an experiment in whimsy, and perhaps above all, because it is problematic (in the Kantian sense): It is a (sober) attempt at exemplifying what it talks about — and what eludes it: A series of footnotes, with blank (transcriptive) pages above, effects something like the integration of a differential, the reciprocal determination where the sources enter into in relation to one another in order to produce a paper, essay, or (inexistent) (chap)book. Of Learned Ignorance, in facing down a problem, makes a wager; it courts failure; it puts it all on the line. All, yes, for love — a kind of love … (of wisdom?).

Of the Contract - Christopher Clifton (punctum books, 2017)
Of the Contract is a version of a text that is as old as any memory, or a form of legal instrument that constitutes the basis of the world in which its terms have been translated. The text remains as open to renewal as that world remains to future alteration, and the terms are both already past, and always yet to come. The notion of the debt that is presented by the contract corresponds to a conception of accountancy and finance that provide a new approach to the contemporary problem of the sense of that external to the terms of human access. A reinterpretation of the philosophical tradition that runs through Levinas and Heidegger to Kant, Of the Contract is also grounded in the medieval tradition that was centered on the notion of “contraction,” and its writing was inspired by forms of life such as those found in the development of monastic constitutions, and the novels of knight errantry. It is also an oblique contribution to the recent discussions on the nature of debt, and is deeply marked by an awareness of climate change, and the insufficiencies of capital to overcome this crisis. All of these concerns however were contracted in a more acute awareness of the process of expression, and the work is given first of all as literature. It is the nature of the terms that they are open to untold interpretations.

On an Ungrounded Earth: Towards a New Geophilosophy - Ben Woodard (punctum books, 2013)
For too long, the Earth has been used to ground thought instead of bending it; such grounding leaves the planet as nothing but a stage for phenomenology, deconstruction, or other forms of anthropocentric philosophy. In far too much continental philosophy, the Earth is a cold, dead place enlivened only by human thought—either as a thing to be exploited, or as an object of nostalgia. Geophilosophy seeks instead to question the ground of thinking itself, the relation of the inorganic to the capacities and limits of thought. This book constructs an eclectic variant of geophilosophy through engagements with digging machines, nuclear waste, cyclones and volcanoes, giant worms, secret vessels, decay, subterranean cities, hell, demon souls, black suns, and xenoarcheaology, via continental theory (Nietzsche, Schelling, Deleuze, et alii) and various cultural objects such as horror films, videogames, and weird Lovecraftian fictions, with special attention to Speculative Realism and the work of Reza Negarestani. In a time where the earth as a whole is threatened by ecological collapse, On an Ungrounded Earth generates a perversely realist account of the earth as a dynamic engine materially invading and upsetting our attempts to reduce it to merely the ground beneath our feet.

On Blinking - Jeremy Fernando; Sarah Brigid Hannis (punctum books, 2012)
On Blinking opens a dossier on seeing. It looks not only to the epistemological sense of what it means to see or the hermeneutical sense of what is the meaning of that which is seen but attends to various sites of knowledge – photography, literature, and philosophy. And in doing so, it questions the privileging of presence and sight in Western thought. Thus, this book, through the essays – “Emerging Sight, Emerging Blindness” (Brian Willems); “Augen, Blicke, Stätten” (Julia Hölzl); “At the Risk of Love” (Jeremy Fernando); and “Suspended in a Moving Night: Photography, or the Shiny Relation Self-World” (Jessica Aliaga Lavrijsen) – attempts to address the question what is seeing.

One Thing Follows Another: Experiments in Dance, Art, and Life through the Lens of Simone Forti and Yvonne Rainer - Sarah Rosenthal; Valerie Witte (punctum books, 2025)
In the 1950s, Yvonne Rainer, Simone Forti, and a handful of other young artists based in New York’s Greenwich Village set out to challenge the practices and principles of professionalized dance. Inspired by the groundbreaking work of choreographers Anna Halprin, Robert Dunn, and Merce Cunningham, as well as composer John Cage, they were determined to change what dance is and can be. In One Thing Follows Another, a boundary-crossing collection of ten experimental-poetic essays, poets Valerie Witte and Sarah Rosenthal explore the work of dancer-choreographers Rainer and Forti, both at various inflection points throughout their careers and in this particular moment. Through a combination of chance operations and intentional artistic choices that push the authors to unexpected places—including the zoo, the dance studio, the street corner—and via innovative forms and techniques, such as collage, erasure, and their own artistic inventions, they deconstruct the essay form to examine what they as poets, each with their own highly charged relationships to dance, can contribute to the conversation about these pivotal figures in postmodern performance art.

On Style: An Atelier - Eileen A. Joy; Anna Kłosowska (punctum books, 2013)
Scholarship in medieval studies of the past 20 or so years has offered some provocative experiments in, and elegant exempla of, style. Scholars such as Anne Clark Bartlett, Kathleen Biddick, Catherine Brown, Brantley Bryant, Michael Camille, Jeffrey Jerome Cohen, Carolyn Dinshaw, James Earl, L.O. Aranye Fradenburg, Roberta Frank, Amy Hollywood, Cary Howie, C. Stephen Jaeger, Eileen Joy, Anna Klosowska, Nicola Masciandaro, Peggy McCracken, Paul Strohm, David Wallace, and Paul Zumthor, among others, have blended the conventions of academic writing with those of fiction, drama, memoir, comedy, polemic, and lyricism, and/or have developed what some would describe as elegant, and arresting (and in some cases, deliciously difficult) prose styles. As these registers merge, they can produce what has been called a queer historiographical encounter (or in queer theorist Elizabeth Freeman’s terms, “an erotohistoriography”), a “poetics of intensification,” and even a “new aestheticism.” The work of these scholars has also opened up debates (some rancorous) that often install what the editors of this volume feel are false binaries between form and content, feeling and thinking, affect and rigor, poetry and history, attachment and critical distance, enjoyment and discipline, style and substance. As Anna Klosowska writes in her contribution to this volume, "The question of style, as it applies to medieval studies, is precisely the overcoming of that dichotomy between Nature and Man: a third element. And when the critique proceeds through the denunciation of the inimitability of someone’s style, as if it were the third sex, ungenerative, queer, sterile, sodomitic, lesbian, etc., the critic unconsciously puts his finger on exactly what style is; but that critic is mistaken about the style’s supposedly non-generative powers. In fact, style, neither fact nor theory but facilitating the transition between the two, is […] the generative principle itself." What can be said about the “style” of academic discourse at the present time, especially in relation to historical method, theory, and reading literary and historical texts? Is style merely supplemental to scholarly substance? As scholars, are we “subjects” of style? And what is the relationship between style and theory? Is style an object, a method, or something else? These were the questions that guided two conference sessions organized by the BABEL Working Group (http://www.babelworkinggroup.org) in 2010 (in Kalamazoo, Michigan and Austin, Texas), out of which this volume was developed. On Style: An Atelier gathers together medievalists and early modernists, as well as a poet and a novelist, in order to offer ruminations upon style in scholarship and theoretical writing (Roland Barthes, Carolyn Dinshaw, Lee Edelman, Bracha Ettinger, Charles Fourier, L.O. Aranye Fradenburg, Heidegger, Lacan, Ignatius of Loyola, and the Marquis de Sade, among others), as well as upon various trajectories of fashionable representation and self-representation in literature, sculpture, psychoanalysis, philosophy, religious history, rhetoric, and global politics.

On the Trail of the Morning Star: Psychosis as Self-Discovery - Dorothea Buck (punctum books, 2024)
In 1936, at age nineteen, Dorothea Buck followed the trail of a star along the mudflats of her North Sea home, Wangerooge Island in Germany. Hospitalized at a Christian institution called Bethel, she was sterilized under Nazi law upon a diagnosis of schizophrenia. Buck lost her lifelong dream of becoming a teacher—the sterilized could not get a college degree. Instead, she became an artist and activist. Buck, who lived to the age of 102, fought throughout her life for psychiatric reform. She created her own form of psychiatric treatment, which she called “trialogue,” in which psychosis experiencers, family, and clinicians join together to examine the experience of psychosis. Trialogue seminars still take place today. Buck also demanded recognition of the Nazi murders of the disabled and the mentally ill. Many of these victims were psychiatric patients gassed in chambers built into six of Germany’s asylums. In 2008, Buck told an audience commemorating these murders that there must be “no second-class victims” of Nazi rule. Psychiatry rooted in biology, Buck believed, would always reduce a condition like hers to something “genetically caused, meaningless, and incurable.” Like fellow German Paul Schreber’s Memoirs of My Nervous Illness, Buck’s On the Trail of the Morning Star calls for a radical rethinking of what it means to live with and in psychosis. This publication is the first time one of Buck’s major writings has appeared in English.

Ontohackers: Radical Movement Philosophy in the Age of Extinctions and Algorithms, Part III: Metahistories of Movement: Philosophies in Becoming - Jaym*/Jaime del Val (punctum books, 2025)
Ontohackers redefines what movement, worlds, and bodies are through the sense of proprioception reconceptualized as formless fluctuation field, a movement matrix that is itself also thought, and which underlies all life forms and fields, including the inorganic. Our worlds are made of endless such entangled fields n-folding in neverending variation or enferance. The current planetary crisis has emerged due to an accidental evolutionary alignment, narrowing, and impoverishment of that matrix’s indeterminacy, that appeared gradually and eventually with bipedalism, and which created an imbalance between the larger proprioceptive field and its brain, and made the atrophied body extend itself technically in geometric fields gradually covering the planet, along with its fears, with disastrous consequences that are unleashing an unprecedented type of mass extinction and species suicide. The reply to this crisis – which is urgently due if we are to reduce even slightly the collapse coming over the next decades – is in recovering a lost sensorimotor plasticity which is also cognitive, affective, and relational plasticity, through developing movement technes for cultivating Body Intelligence (BI), reversing and taking elsewhere the failed evolution culminating in AI, stepping down from humanist supremacist pedestals, undoing our dependency upon unsustainable killing machines of sedentary consumerism that impoverish experience, stopping the reproduction of a species that has become plague (by reversing heteronormative reproductive dogmas till we reach preagricultural population levels), and recovering the joys of moving with the world, in symbiotic mutation, towards unprecedented evolutionary variations: this is our cosmic responsibility for all life on Earth. The book’s structure expresses Enferance Theory with regard to how processes of becoming have a triple movement: an incipiency unfolding the field (Part I (https://punctumbooks.com/titles/ontohackers-radical-movement-philosophy-in-the-age-of-algorithms/)), a condensation-expansion where the field acquires full consistency (Part II (https://punctumbooks.com/titles/ontohackers-radical-movement-philosophy-in-the-age-of-extinctions-and-algorithms-part-ii-r-evolution-technologies/)), and a resonance or memory of the field relating to other fields (Part III). Part III provides a critical history of (movement) philosophies, exposing the rise of the mechanistic vision as dominant anomaly emerging from a variety of other older proposals which have continued to exist in the background, returning more strongly since the 19th century, while exposing the limitations of recent attempts to free movement from the metaphysical tradition, which the book associates to the rise of human supremacism and its associated mass extinction cycle. The book proposes that movement is the core hidden motif of philosophy and diagnoses philosophies following a metaphilosophical and metaformative methodology that considers the perceptual–kinetic frames and biases underlying them. It is both a sketch for future expansion and an appendix to the previous two volumes, which grounds Radical Movement Philosophy in a critical revision of the literature, exposing the differences, while undoing some errors, and rescuing philosophies like that of many Presocratics from the misreading stemming from Aristotle. Hereby a shift from philosophia to philokinesia is proposed, toward a thinking of the body in motion, reversing philosophy from a tool of human supremacism to an undoing of it and a regeneration of movement diversification – and with it life – in the Biosphere.

Ontohackers: Radical Movement Philosophy in the Age of Extinctions and Algorithms, Part II: R/evolution Technologies - Jaym*/Jaime del Val (punctum books, 2025)
Ontohackers redefines what movement, worlds, and bodies are through the sense of proprioception reconceptualized as formless fluctuation field, a movement matrix that is itself also thought, and which underlies all life forms and fields, including the inorganic. Our worlds are made of endless such entangled fields n-folding in neverending variation or enferance. The current planetary crisis has emerged due to an accidental evolutionary alignment, narrowing, and impoverishment of that matrix’s indeterminacy, that appeared gradually and eventually with bipedalism, and which created an imbalance between the larger proprioceptive field and its brain, and made the atrophied body extend itself technically in geometric fields gradually covering the planet, along with its fears, with disastrous consequences that are unleashing an unprecedented type of mass extinction and species suicide. The reply to this crisis—which is urgently due if we are to reduce even slightly the collapse coming up over the next decades—is in recovering a lost sensorimotor plasticity which is also cognitive, affective, and relational plasticity, through developing movement technes for cultivating Body Intelligence (BI), reversing and taking elsewhere the failed evolution culminating in AI, stepping down from humanist supremacist pedestals, undoing our dependency upon unsustainable killing machines of sedentary consumerism that impoverish experience, stopping the reproduction of a species that has become plague (by reversing heteronormative reproductive dogmas till we reach preagricultural population levels), and recovering the joys of moving with the world, in symbiotic mutation, towards unprecedented evolutionary variations: this is our cosmic responsibility for all life on Earth. The book’s structure expresses Enferance Theory with regard to how processes of becoming have a triple movement: an incipiency unfolding the field (Part I (https://punctumbooks.com/titles/ontohackers-radical-movement-philosophy-in-the-age-of-algorithms/)), a condensation-expansion where the field acquires full consistency (Part II), and a resonance or memory of the field relating to other fields (Part III (https://punctumbooks.com/titles/ontohackers-radical-movement-philosophy-in-the-age-of-extinctions-and-algorithms-part-iii-metahistories-of-movement-philosophies-in-becoming-an-appendix-or-extension/)). Part II, subtitled R/evolution Technologies, includes Books 4, 5, and 6 and is by far the longest volume, elaborating in depth the book’s proposals in a triple movement. It first exposes the technologies of variation in nature (Book 4), followed by the technologies of reduction in the Algoricene (Book 5), and finally the possibilities for overcoming the reductive fold (Book 6). Book 4 proposes a swarming chaosmology as theory of orgiastic evolution, culminating in the concept of metabiosis: life as indeterminate, symbiotic mutation. Book 5 diagnoses the regimes that have formatted movement and presents the theory of the Algoricene, or Age of Extinctions and Algorithms. It exposes a kinetic ontology, genealogy, and dynamics of power. An interlude discusses post-, trans-, and metahumanism, and a second part of the book unfolds a radical critique of the Planetary Holocaust. Book 6 unfolds metaformance aesthetics and metahuman politics, including the theory of metaformativity, the ontohacking pragmatics, and a choral Dionysian ontology, where the author also discusses at length hir own techniques and art projects, involving a radical challenge to human supremacism to face the extinction challenge now threatening all life on Earth, toward an Earth liberation and regeneration.

Ontohackers: Radical Movement Philosophy in the Age of Extinctions and Algorithms, Part I: Radical Movement Philosophy and the Body Intelligence R/evolution - Jaym*/Jaime del Val (punctum books, 2024)
Ontohackers redefines what movement, worlds, and bodies are through the sense of proprioception reconceptualized as formless fluctuation field, a movement matrix that is itself also thought, and which underlies all life forms and fields including the inorganic. Our worlds are made of endless such entangled fields n-folding in neverending variation or enferance. The current planetary crisis has emerged due to an accidental evolutionary alignment, narrowing, and impoverishment of that matrix’s indeterminacy, that appeared gradually and eventually with bipedalism, and which created an imbalance between the larger proprioceptive field and its brain, and made the atrophied body extend itself technically in geometric fields gradually covering the planet, along with its fears, with disastrous consequences that are unleashing an unprecedented type of mass extinction and species suicide. For del Val, the reply to this crisis – which is urgently due if we are to reduce even slightly the collapse coming up over the next decades – is in recovering a lost sensorimotor plasticity which is also cognitive, affective, and relational plasticity, through developing movement technes for cultivating Body Intelligence (BI), reversing and taking elsewhere the failed evolution culminating in AI, stepping away from humanist-supremacist pedestals, undoing our dependency upon unsustainable killing machines of sedentary consumerism that impoverish experience, stopping the reproduction of a species that has become a plague (by reversing heteronormative reproductive dogmas until we reach pre-agricultural population levels), and recovering the joys of moving with the world, in symbiotic mutation, towards unprecedented evolutionary variations: this is our cosmic responsibility for all life on Earth. The book’s structure expresses Enferance Theory with regard to how processes of becoming have a triple movement: an incipiency unfolding the field (Part I), a condensation-expansion where the field acquires full consistency (Part II (https://punctumbooks.com/titles/ontohackers-radical-movement-philosophy-in-the-age-of-extinctions-and-algorithms-part-ii-r-evolution-technologies/)), and a resonance or memory of the field relating to other fields (Part III (https://punctumbooks.com/titles/ontohackers-radical-movement-philosophy-in-the-age-of-extinctions-and-algorithms-part-iii-metahistories-of-movement-philosophies-in-becoming-an-appendix-or-extension/)). Part I includes Books 1 to 3 out of seven books total. The preface sets the context of the book: the extinction crisis. Book 1 provides an introduction to the entire field of the book and reflects on the book’s structure and process. Book 2 is a full treatise on proprioception, developing the theory of Body Intelligence and addressing core issues of cognition, perception, communication, and an ontological redefinition of the body as proprioceptive swarm. Book 3 develops all core concepts of Radical Movement Philosophy, unfolding in several sections, first introducing fluctation, field, and swarm theory, secondly the core concepts of clinaos (indeterminacy), metabody (consistency), and intraduction (variation), all coming together in the concept of enferance. Finally, another triad further unfolds the previous triad as rhythm (affect), orientation (desire), and contact (sex), closing with an orgiastic cosmo-ontology that opens the way to Part II.

Ontological Anarché: Beyond Materialism and Idealism - Duane Rousselle; Jason Adams (punctum books, 2014)
Radical theory has always been beset by the question of ontology, albeit to varying degrees and under differing conditions. In recent years, in particular, political metaphysics has returned with force: the rise of Deleuze-influenced “new materialisms,” along with post-/non-Deleuzian Speculative Realism (SR) and Object-Oriented Ontology (OOO), all bear testament to this. In this same period, anarchism has returned as a major influence on social movements and critical scholarship alike. What, then, are some of the potential resonances between these currents, particularly given that anarchism has so often been understood/misunderstood as a fundamentally idealist philosophy? This special issue of Anarchist Developments in Cultural Studies (Issue 2013.2) considers these questions in dialogue with the new materialisms, Speculative Realism, and Object-Oriented Ontology, in order to seek new points of departure. It is in this sense that ADCS also strives to play a critical role recent discussions in the wider political, cultural, and philosophical milieu.

Open Book in Ways of Water - Adam Wolfond (punctum books, 2023)
In Open Book in Ways of Water, poet and artist Adam Wolfond explores the synaesthetic quality of autistic perception, the way in which water in its different materializations shapes and channels language. Building on notions such as “wetness,” “streams,” and “currents,” Wolfond constructs a linguistic universe in which writing and perception merge, move, and “pace to gether”—echoing both the togetherness of the senses and the gathering rhythms of water. Open Book in Ways of Water is as much a book of poetry and a book about poetry, a self-reflection in an endlessly moving and transforming element. As the author himself explains: Language is a way to understand each other but it is also reductive in the ways that it is abstracted and non-sensuous, and open writing as movement tends to be ignored as autistics are forced into neurotypical ways of seeing, and the thinking around artistic practices feels of a pace that intensifies the use of forms forming, and similarities with open processes are languaging the way of water, making language about artful relations with the more than human. Water is a game of ways and patterns that wave and ripple and can pull us under, the talk is about surfacing but languaging is about feeling, moving the ways that it makes are having variances moving the thresholds in thinking feeling of a rally that comes from cutting the grammars out and that is the way of perception that is cut by grammar and people need art to dance this dance of relation. A man of autism answers the ways of the body much of the time and that means my body rallies the artful atmospheres that are dancing me and the real feeling can dance the atmospheres as my body presence and pace shifts other bodies to be free. Having a ticcing body is making the dance about disorder but really it is about a different and diverse way of languaging with many feelings and bathing and immersing and I don’t have any other way.

Opioids: Addiction, Narrative, Freedom - Maia Dolphin-Krute (punctum books, 2018)
An epidemic is a feeling set within time as much as it is a matter of statistics and epidemiology: it is the feeling of many of us in the same desperate place at the same desperate time. Opioid epidemic thus names a present moment — at once historic and historical — centered on the substance of opioids as much as it names the urgency of all of us who are currently in proximity to these substances. What is the relationship between these historic and historical moments, the present moment, the history of pharmacological capitalism, and a set of repeated neurological activities, as well as human loss and desire, that has fueled the exponential rise in the rates of opioid use and abuse between 2000-2018? Opioids: Addiction, Narrative, Freedom is an auto-ethnography written from deep within—biologically within—this opioid epidemic. Tracing opioids around and through the bodies, governmental, and medical structures they are moving and being moved through, Opioids is an examination of what it means to live within an environment saturated with a substance of deep economic, political, neuroscientific, and pharmacological implications. From exploring media coverage of the epidemic and emerging medical narratives of addiction to detailing the legal inscription of differences between “pain patients” and people addicted to drugs, Opioids consistently asks: what is it like to live within an epidemic? What forms of freedom become possible when continually modulated by our physical experiences of the material proximities of an epidemic? How do you live with something for a long time?

Ostranenie: On Shame and Knowing - M.H. Bowker (punctum books, 2012)
Ostranenie, the term for defamiliarization introduced by Russian writer and critic Victor Shklovsky, means, among other things, to see in strangeness. To see in strangeness is to participate in an illusion that is more real than real. It may be achieved by (re)presenting the surface as the substance, the play as the thing, or by examining (from exigere: to drive out) what is present before one’s eyes. Ultimately, ostranenie means confessing one’s complicity in making known what is known. M.H. Bowker’s Ostranenie: On Shame and Knowing is a meditation upon the moment of a mother’s death: a moment of defamiliarization in several senses. The body of the work consists of footnotes which elaborate, by exegesis, by parataxis, and sometimes by surprise, the intimate and often hidden relationships between parent and child, illusion and knowledge, shame and loss. These elaborations raise questions about the power of the familiar, the limitations of discursive thought, and the paradoxical nature of the interpersonal, political, and spiritual bargains we make for the sake of security and freedom. Ostranenie treats the personal relationship between the author and his mother in both direct and oblique ways. In a candidly unsettled examination of this relationship and its influence upon the reflections and concerns of the author, the reader is invited to experience a family, a disintegration, a psyche, and its defamiliarization, from the perspectives of both an adult and a child.

Other Grounds: Breaking Free of the Correlationist Circle - David Lindsay (punctum books, 2016)
Is it possible to get outside your assumptions and know the world for what it is? As the 20th century came to a close, the verdict seemed to be a resounding “no,” but in recent years a renaissance in speculative thought has sparked new lines of inquiry into de-centering the human. Other Grounds enters this conversation with a decidedly lively voice and an ambitious project to match. Not only can we believe in a reality uncolored by our imaginations, says Lindsay, we can also experience it. Closely argued yet expansive in its reach, Other Grounds is built on the premise that we are by our very nature de-centered – that more than one agent is at work in the human body, and that this plurality can serve as a gateway to the experience of otherness in general. Leading the reader with a steady hand through the literature on coincident entities, set theory and the kinesthetic work of F.M. Alexander, Lindsay makes the case for the possibility of objects interceding on us from their own grounds. The result is that rare specimen in the annals of critical thought: a book that is as reasoned as it is readable, as sage as it is sardonic, and unmistakably original throughout.

Out of Place: Artists, Pedagogy, and Purpose - Tim Doud; Zoë Charlton (punctum books, 2021)
Broad in scope, Out of Place: Artists, Pedagogy, and Purpose presents an overview of the different paths taken by artists and artist collectives as they navigate their way from formative experiences into pedagogy. Focusing on the realms inside and outside the academy (the places and persons involved in post-secondary education) and the multiple forms and functions of pedagogy (practices of learning and instruction), the contributors in this volume engage individual and collective artistic practices as they adapt to meet the factors and historical conditions of the people and communities they serve through solidarity, equity, and creativity. With this critically, historicist approach in mind, the contributions in Out of Place historicize, study, critique, revise, reframe, and question the academy, its operations, and exclusions. The extensive range of contributions, emphasizing community-oriented projects both inside and outside the United States, is grouped into three overarching categories: artists who work in academic institutions but whose social and pedagogical engagement extends beyond those walls; artists who engage in pedagogical initiatives or forms of institutional critique that were established outside of an art school or university setting; and artist–scholars who are doing transformative and inter/transdisciplinary work within their respective institutions. Collectives and projects represented in Out of Place comprise Art Practical, Axis Lab, BFAMFAPhD, Beta-Local, Black Lunch Table Project, The Black School, The Center for Undisciplined Research, Devening Projects, ds4si, Elsewhere, Ghana ThinkTank, Gudskul, The Icebox Project Space, Las Hermanas Iglesias, The Laundromat Project, Occupy Museums, Peebls, PlantBot Genetics, Queer Conversations on Culture and the Arts, Related Tactics, Side by Side, ‘sindikit, Sustainable Native Communities Collaborative, and Tiger Strikes Asteriod.

paq'batlh: The Klingon Epic - Floris Schönfeld; Kees Ligtelijn; Vincent W.J. van Gerven Oei; David Yonge-Mallo (punctum books, 2022)
paq’batlh: The Klingon Epic is the definitive edition of the grand Klingon epic of Kahless the Unforgettable (qeylIS lIjlaHbogh pagh). The story of Kahless is a tale of legendary proportions comparable to those of ancient heroes Hercules, Ulysses, and Gilgamesh. Betrayed by his brother and witness to his father’s brutal slaying, Kahless is pitted against his bitter enemy, the mighty tyrant Molor. To regain his honor he must travel into the Underworld, create the first bat’leth, and unite with his true love, Lady Lukara, to fight many epic battles. Through this awe-inspiring adventure Kahless redefines what it is to be truly Klingon. Reconstructed from several sources, this bilingual Klingon/English edition provides a keen insight into the nature of Klingon culture and mythology, and features the first publication of Ancient Klingon (no’ Hol) fragments. Meticulously translated by the world’s leading Klingon language expert, Marc Okrand, this classic epic is a must have for anyone interested in Klingon culture and language. The second edition includes a fully revised text and translation, as well as a new preface on no’ Hol by DeSDu’ jen puqloD.

paq'batlh: The Klingon Epic - Floris Schönfeld; Kees Ligtelijn; Vincent W.J. van Gerven Oei (punctum books, 2011)
paq’batlh: The Klingon Epic is the definitive edition of the grand Klingon epic of Kahless the Unforgettable (qeylIS lIjlaHbogh pagh). The story of Kahless is a tale of legendary proportions comparable to those of ancient heroes Hercules, Ulysses, and Gilgamesh. Betrayed by his brother and witness to his father’s brutal slaying, Kahless is pitted against his bitter enemy, the mighty tyrant Molor. To regain his honor he must travel into the Underworld, create the first bat’leth, and unite with his true love, Lady Lukara, to fight many epic battles. Through this awe-inspiring adventure Kahless redefines what it is to be truly Klingon. Reconstructed from several sources, this bilingual Klingon/English edition provides a keen insight into the nature of Klingon culture and mythology, and features the first publication of Ancient Klingon (no’ Hol) fragments. Meticulously translated by the world’s leading Klingon language expert, Marc Okrand, this classic epic is a must have for anyone interested in Klingon culture and language. The second edition includes a fully revised text and translation, as well as a new preface on no’ Hol by DeSDu’ jen puqloD.

Paris Bride: A Modernist Life - John Schad (punctum books, 2020)
In July 1905, in Paris, a young Anglo-French woman called Marie Wheeler became the bride of a Swiss émigré, Johannes Schad. Immediately after the wedding, Marie and Johannes moved to London. And there they lived for nineteen years. In 1924, however, something happened to change their lives, and Marie, in many respects, simply disappeared. Paris Bride is an exploration of the lost life of Marie Schad, of whom little is known beyond a few legal papers, a number of letters, some photographs, the diaries of a friend, and her obituary. With so little else known of Marie’s life, this book seeks to read her back into existence by drawing on a host of contemporaneous texts — largely modernist texts, by Virginia Woolf, Franz Kafka, the Paris Surrealists, Stéphane Mallarmé, Oscar Wilde, Katherine Mansfield, and Walter Benjamin. All of the selected authors are connected with Marie through some coincidence of time, place, or theme. In an attempt to do justice to Marie’s in-visibility, or to her un-life, Paris Bride takes as its guide Wilde’s declaration that “the true function of criticism is to see the object as in itself it really is not.” In other words, this book seeks to evade the positivist or realist assumptions of conventional literary criticism, and instead pursue a post-critical method with its sources and texts. Paris Bride is not confined to academic discourse but instead draws on a range of literary genres and devices that are more in sympathy with the non-realist character of modernism itself — devices such as fragmentation, flânerie, textual collage, stream of consciousness, imagism, perspectivism, dream-text, the absurd, etc. Ultimately, Paris Bride is a modernistic experiment in life-writing.

'Pataphilology: An Irreader - Sean Gurd; Vincent W.J. van Gerven Oei (punctum books, 2018)
1883. Jean-Pierre Brisset realizes that a close phonological analysis of spoken words will demonstrate that the French language, and therefore the human species, was evolved from frogs. 1896. Consulted as an expert in linguistics and comparative philology, Ferdinand de Saussure reports that the passages of Martian Language transcribed during the “sonambulistic glossolalias” of one (pseudonymously named) “Hélène Smith” (in fact Müller) may contain a few roots related to those found in Sanskrit and other Indo-Aryan languages. 1897. Using recognized techniques of historical reconstruction and close reading, Samuel Butler proposes that the composer of the Odyssey was not Homer but Nausikaa, a character in the epic. What do the bizzare etymologies of Jean-Pierre Brisset, made-up languages for literary fiction, The Dialectic of Enlightenment, Latin grammarians, Horace’s Epodes, and the Papyrus of Ani have in common? Absolutely nothing. Yet, taken together they provide an unusually coherent picture of a hitherto unacknowledged non-tradition of linguistic investigation. At these moments, particularly within the traditions of European writing which can loosely be termed “avant-garde,” philology goes rogue, hearkening to unearthly imperatives and barely comprehended intimations, and producing results well beyond those generated by more respectable – and supposedly more grounded – philological endeavors. ‘Pataphilology: An Irreader seeks to document and analyze such moments of philological speculation, invention, and détournement. In using the term ‘pataphilology, Gurd and van Gerven Oei are not proposing a facile analogy with ‘pataphysics, where ‘pataphilology would be philology’s wacky twin, always out for a lark, never doing anything real. This would presuppose an operation (even if parenthetical) on philology analogous to a shift from physics to ’pataphysics, something which Alfred Jarry, to whom this volume owes the latter neologism, appears to contradict in his initial definition: “Pataphysics […] is the science of that which is superinduced upon metaphysics, whether within or beyond the latter’s limitations, extending as far beyond metaphysics as the latter extends beyond physics.” Any way you cut it, ‘pataphysics is a physics that demands — or, better, that relies on — an utmost philological sensitivity to writing, unheard etymologies, unstable translations, incomplete formalizations, and haphazard decryptions. This volume seeks, then, to document how philological practices — no matter how non-standard, disreputable, or academically useless — have played a role in the production of avant-garde literature and knowledge, as well as forgotten, alternative, or fictitious scholarly projects. Ranging from the papyrus of Ani to the future languages of speculative fiction, from the fictional tablets of Armand Schwerner to the Attic Nights of Aulus Gellius, from Horace to Lacan, ’Pataphilology: An Irreader is a cabinet of philological curiosity — and a map of the ever-changing constellations that emerge when human language loses its chains.

Pedagogics of Liberation: A Latin American Philosophy of Education - Enrique Dussel (punctum books, 2019)
Enrique Dussel is considered one of the founding philosophers of liberation in the Latin American tradition, an influential arm of what is now called decoloniality. While he is astoundingly prolific, relatively few of his works can be found in English translation — and none of these focus specifically on education. Founding members of the Latin American Philosophy of Education Society David I. Backer and Cecilia Diego bring to us Dussel’s The Pedagogics of Liberation: A Latin American Philosophy of Education, the first English translation of Dussel’s thinking on education, and also the first translation of any part of his landmark multi-volume work Towards an Ethics of Latin American Liberation. Dussel’s ouevre is an impressive intellectual mosaic that uses Europeans to disrupt European thinking. This mosaic has at its center French philosopher Emmanuel Levinas, but also includes Ancient Greek philosophy, Thomist theology, modern Enlightenment philosophy, analytic philosophy of language, Marxism, psychoanalysis (Freud, Klein, evolutionary psychology, neuroscience), phenomenology (Sartre, Heidegger, Husserl, Hegel), critical theory (Frankfurt School, Habermas), and linguistics. Dussel joins these traditions to Latin American history, literature, and philosophy, specifically the work of Octavio Paz, Ivan Illich, and the philosophers of liberation whom Dussel studied with in Argentina before his exile to Mexico in the late 1970s. Drawing heavily from the ethics of Levinas, Dussel examines the dominating and liberating features of intimate, concrete, and observable interactions between different kinds of people who might sit down and have face-to-face encounters, specifically where there may be an inequality of knowledge and a responsibility to guide, teach, learn, care, or study: teacher–student, politician–citizen, doctor–patient, philosopher–nonphilosopher, and so on. Those occupying the superior position of these face-to-face encounters (teachers, politicians, doctors, philosophers) have a clear choice for Dussel when it comes to their pedagogics. They are either open to hearing the voice of the Other, disrupting their sense of what is and should be by a newness beyond what they know; or, following the dominant pedagogics, they can try to communicate and instruct their sense of what is and should be (which Dussel, in a Latin American context, associates with dominant cultures) to the (supposed) tabula rasas in their charge. Dussel calls that sense of what is and should be “lo Mismo.” [The French in Levinas is “le Même,” and Backer and Diego have translated Dussel’s “lo Mismo” as “the Same.”] This groundbreaking translation makes possible a face-to-face encounter between an Anglo Philosophy of Education and Latin American Pedagogics. “Pedagogics” should be considered as a type of philosophical inquiry alongside ethics, economics, and politics. Dussel’s pedagogics is a decolonizing pedagogics, one rooted in the philosophy of liberation he has spent his epic career articulating. With an Introduction by renowned philosopher Linda Martín Alcoff, this book adds an essential voice to our conversations about teaching, learning, and studying, as well as critical theory in general.

Pedagogies of Disaster - Adam Staley Groves; Nico Jenkins; Vincent W.J. van Gerven Oei (punctum books, 2013)
We live in an era where the university system is undergoing great changes owing to developments in financing policies and research priorities, as well as changes in the society in which this system is embedded. This change toward a more market-oriented university, which also has immediate effects in academic peripheries such as the Balkans, the Middle East, or South-East Asia, is of great influence for the pedagogical practice of “less profitable” academic areas such as the Humanities: philosophy, languages, sociology, anthropology, history. Because of the absence of a historically grounded establishment of the Humanities, academic peripheries, usually accompanied by a weak civil society infrastructure, seem to offer the most fertile ground for rethinking the Humanities, their pedagogical practice, and their politics, as well as the greatest threats, such as the ongoing capitalization of research, and profitability as the norm of educational achievement. The sprawling presence of for-profit universities and in academic peripheries such as Albania and Kosovo is indicative of this problematic, as are consistent underfunding of universities and the relentless budget cuts in American and English, and to a lesser extent European, universities. Motivations for this ongoing attack on the university are often driven by a political system or a politics with an aggressive stance to critical thought. At the same time, such an absence of historical grounding may inspire a rejuvenation and reinvigoration of research in the Humanities, such as may be seen in academic centers around Asia, as many young scholars are attracted to an educational environment which is not yet completely petrified in bureaucratic procedures. In this case, a different set of questions appear concerning the place of the scholar in societies with semi-democratic or even authoritarian rule. For civil society to flourish, an educational system that reflects and interrogates the values and concepts that underlie a healthy social fabric are of crucial importance. This volume comprises papers culled from continent. (http://www.continentcontinent.com/index.php/continent) journal’s Pedagogies of Disaster conference held in Tirana, Albania, hosted by The Department of Eagles (Departamenti i Shqiponjave) in June 2013, and organized to address the fate of relation and the future of pedagogical practice in the University, and especially as it concerns the humanities. The papers gathered here seek to address the infrastructural or interpersonal changes in the modes of production as it relates to current academia, examining the elements and spaces of the rifts opening up in the polis of the University—its students, professors, and administrators. The volume further addresses the pedagogical horizon at a critical limit, asking: for whom or for what are we teaching and from whom or from what are we learning?

Preternatural - Celina Jeffery (punctum books, 2011)
The preternatural, as explored by these artists, disturb the ontological boundaries of art, nature and metaphysics. They exist within the folds of classificatory thresholds: both beyond and between nature and supernature; human and animal; vegetable and mineral; living and dead. The confusion between animate and inanimate is a primary concern, a surreality which unites with the preternatural’s love for reveling in the mysterious: bizarre fragments, unreadable words, objects of absurd scale, and distortions of the relativity of time and space flourish throughout this exhibition. Preternatural is the catalogue for a multi-site art exhibition (9 December 2011 through 17 February 2012, in Ottawa, Canada) that draws from the idea that art itself is a form of preternatural pursuit, in which the artists participating explore the bewildering condition of being in between the mundane and the marvelous in nature. It questions a world that understands itself as accessible, reachable, and ‘knowable’ and counters it with a consideration of this heterogenous proposition. This exhibition retains the preternatural’s engagement with prodigies: the exceptional and wonderful in the context of the natural, while acknowledging its critical unravelling of nature as art and art as nature. As such, it accepts the bizarre and incongruous nature of its etymology, in which art, nature, and comprehension collide and asks: what may be the experience of the preternatural in contemporary art?

[provisional self-evidence] - Rachel Arrighi (punctum books, 2015)
As Jesus of Nazareth once said (or was, more precisely, read [transcribed (by sets of translators [NIV])]), “Why do you look at the speck of sawdust in your brother’s eye and pay no attention to the plank in your own eye?” [provisional self-evidence] pays all attention to the plank in academia’s/its own eye. Example: members of marginalized groups experience a sense of anxiety, such sense — academia advancing — being by no means merely ‘natural’ as an end of society (institutionalized racism/classism/sexism/etc.). Extension: to academia — members of which experiencing such sense relative to research, reading, writing; processes —, such sense is natural (imagine the teacher to the student: ‘it is only natural’). [provisional self-evidence] turns academia against itself, re-claiming naturality. // Nature’s handwriting is asemic

Queer Ancient Ways: A Decolonial Exploration - Zairong Xiang (punctum books, 2018)
Queer Ancient Ways advocates a profound unlearning of colonial/modern categories as a pathway to the discovery of new forms and theories of queerness in the most ancient of sources (thereby also unlearning queer theory as it has been understood in contemporary, primarily Anglo-American and western European contexts). In this radically unconventional work, Zairong Xiang investigates scholarly receptions of mythological figures in Babylonian and Nahua creation myths, exposing the ways they have consistently been gendered as feminine in a manner that is not supported, and in some cases actively discouraged, by the texts themselves. An exercise in decolonial learning-to-learn from non-Western and non-modern cosmologies, Xiang’s work uncovers a rich queer imaginary that has been all-but-lost to modern thought, in the process critically revealing the operations of modern/colonial systems of gender/sexuality and knowledge-formation that have functioned, from the Conquista de America in the sixteenth century to the present, to keep these systems in obscurity. At the heart of Xiang’s argument is an account of the way the unfounded feminization of figures such as the Babylonian (co)creatrix Tiamat, and the Nahua creator-figures Tlaltecuhtli and Coatlicue, is complicit with their monstrification. This complicity tells us less about the mythologies themselves than about the dualistic system of gender and sexuality within which they have been studied, underpinned by a consistent tendency in modern/colonial thought to insist on unbridgeable categorical differences. By contextualizing these deities in their respective mythological, linguistic, and cultural environments, through a unique combination of methodologies and critical traditions in English, Spanish, French, Chinese, and Nahuatl, Xiang departs from the over-reliance of much contemporary queer theory on European (post)modern thought. Much more than a queering of the non-Western and non-modern, Queer Ancient Ways thus constitutes a decolonial and transdisciplinary engagement with ancient cosmologies and ways of thought which are in the process themselves revealed as theoretical sources of and for the queer imagination.

Queer and Bookish: Eve Kosofsky Sedgwick as Book Artist - Jason Edwards (punctum books, 2022)
Queer and Bookish: Eve Kosofksy Sedgwick as Book Artist represents the first booklength study to explore the intersections of Sedgwick’s critical writing, poetry, and most importantly, book art, making the case that her art criticism, especially her meditations on domestic and nineteenth-century photography, and “artist’s book” projects are as formally complex and brilliant, conceptually significant and life-changing, as her literary criticism and theory. In addition, Edwards’s book represents a significant intervention into recent debates about reparative reading, surface reading, and the descriptive turn across the humanities, because of its sustained, positive accounts of Sedgwick’s books as visual, textural, and material objects. The book ranges widely across Sedgwick’s published output, from The Coherence of Gothic Conventions (1980) to the posthumously published The Weather in Proust (2011), and features her meditations on a wide variety of art-historical topoi, including Judith Scott’s queer/crip fiber art; the anality of Polykleitos’s Doryphorus; queer Modernist typography; Piranesi’s punitive space; Duncan Grant and Vanessa Bell’s queer holy family; Manet’s frontality and thalassic aesthetics; fat and thin aesthetics of various stripes; the queer photography of Anna Atkins, Clementina Hawarden, and Julia Margaret Cameron; Baron De Mayer, Eugene Atget, and P.H. Emerson; as well as David Hockney, Ken Brown, and her own father, a NASA lunar photographer. The book climaxes with two chapter-length explorations of Sedgwick’s own late-life book-art practice: her panda Valentine alphabet cards (c. 1996) and her Last Days of Pompeii/Cavafy artist book (c. 2007).

Queer Communal Kinship Now! - Robinou (punctum books, 2023)
Queer communal kinship is a long overdue replacement for the naturalized model of the modern western family; a post-capitalist regime of social reproduction, aiming for redistributive justice through the politics of pleasure; a timely proposal for the demise of possessive and accumulative ideology, and the upsurge of a counter-imaginary; a manifesto for the collectivization of reproductive labor; an ethical conceptual framework for a joyful cultural shift: Queer Communal Kinship Now! This manifesto pushes for a radical redefinition of love, intimacy, and care in support of a much needed redistributive justice movement. This project must be accompanied by an exit from heteronormativity as a regime of relational scarcity, as well as from the metaphysics of private property which is at the heart of our economies and by extension of our social ecologies—at odds with much of life on this planet. Queer Communal Kinship Now! examines the role of western normative family ideals in the mechanisms of the preservation and intensification of this status quo, as well as potential approaches to guide us out of this unsavory situation. Both handbook and personal narrative, Queer Communal Kinship Now! discusses the conceptual leaps required to emancipate ourselves from the conventional western family model, towards different regimes of bonding, care, and attention, to allow us to imagine a different type of social reality driven by queer and feminist ethical concerns. Directed to those interested in building queer families and wondering how not to repeat the mistakes of their parents, Queer Communal Kinship Now! offers radical ways of rethinking being together.

Queer Finitude - John Paul Ricco (punctum books, 2026)
What if intimacy wasn’t defined by identities, couples, or other congruencies, but by incongruity and the seemingly empty moments of anonymity and solitude? In this compelling final volume of his trilogy on “the intimacy of the Outside,” John Paul Ricco articulates the aesthetics and ethics of finitude, exploring how the ordinary limits of our bodies, thoughts, and surroundings shape our deepest connections. The book asks us to consider the kind of attention that two or more people give to each other in their non-fused intimacy, mutual anonymity, or shared solitude (including as readers). Queer Finitude redefines intimacy through the lens of the unnoticed and the overlooked—the slight opening of a mouth, a fleeting touch, the clandestine and the fugitive. Ricco’s narrative brings to life the figures of the outsider, the self-excluded, and the unloved, as it offers glimpses of a world where intimacy thrives along the contours and edges of anonymity and solitude. Drawing inspiration from iconic moments in contemporary art, film, photography, and literature, Ricco examines the lives of anonymous passersby and solitary strangers, elaborating a non-figural aesthetics and ethics. From Chiron in Barry Jenkins’s Moonlight to the unnamed Palestinian woman in Adania Shibli’s Minor Detail, and from an anonymous portrait by Shaan Syed to the reclusive silhouettes in Dean Sameshima’s photographs, Ricco illustrates the delicate balance between intimacy and solitude. Through philosophical close readings, meditations on the moment’s temporality, and a novel deployment of the concept of “the time that remains,” Ricco effectively challenges and transcends the dominant theoretical frameworks of optimism and pessimism that currently define queer theory. Queer Finitude is not just a scholarly study; it’s an enactment of estrangement from figuration, dedicated to the itinerant and the anonymous. It reveals how ethical forms of intimacy can flourish through non-coerced solitude and a shared sense of the inappropriable, offering a fresh perspective on the queerly exorbitant pleasures of finitude. Ultimately, Queer Finitude asks, What kind of intimate connections lie beyond the visible and legible, in the commonality of our finitude?

Queer Insists (for José Esteban Muñoz) - Michael O'Rourke (punctum books, 2014)
Queer Insists is a memorial essay, a work of mourning, written for the queer theorist and performance scholar José Esteban Muñoz (1967-2013) shortly after his untimely death in December 2013. In a series of fragments, not unlike Roland Barthes’s Mourning Diary, Michael O’Rourke shares memories of Muñoz, the stories and reflections of his friends in the wake of his passing, and readings of his work from Disidentifications to Cruising Utopia and beyond. O’Rourke argues that, for Muñoz, queer does not exist, per se, but rather insists, soliciting us from the future to-come. Muñoz reached towards teleopoietic worlds as he invented a queer theory we have yet to find, but are invited to glimpse. Among the Muñozian themes this chapbook discusses are hope, utopia, affect, punk rock, heresy, the undercommons, temporality, hauntology, forgetting, loss, ephemera, partage, sense, incommensurability, the event and democracy. In reading Muñoz as a Rogue Theorist, this book borrows many of the gifts we have received (and have yet to receive) from him, marking the force and luminescence of his thought, and insisting upon the rare and precious singularity of his work. Muñoz bequeaths to us a queer studies without condition which it is our duty to foster and to bear as we carry it and him into the unknowable futures of an indiscipline.

Ravish the Republic: The Archives of the Iron Garters Crime/Art Collective - Michael L. Berger (punctum books, 2015)
In the 2011 book Dark Matter: Art and Politics in the Age of Enterprise Culture (http://www.plutobooks.com/display.asp?K=9780745327525&sf1=author&st1=Gregory+Sholette&m=1&dc=1), the artist Gregory Sholette posits that we are living in an era of surplus creative energies concentrated in a teeming archive of artists, the poor, the “unskilled” and the “economically invisible.” It is a potentially disruptive archive that capitalism can’t always manage but can still hope to eventually exploit and assimilate. Within this archive seethes creative energy that can extend itself in unique and unsettling ways, across multiple categories and disciplines. Often, however such energy is captured by the winners and arbiters in our “risk society” and thereby sanitized and neutralized. So it becomes necessary for artists, theorists, writers and activists to be versatile in their tactics, cryptic and evasive in their manifestations and criminally implacable in their visions. The Iron Garters are an “art gang” that masquerades, disseminates and performs as your archetypal “criminals,” “outcasts” “mystics,” “losers” and “lunatics”: in short, a vital and necessary social surplus. Their antics have been traced back to Jean Genet’s novel The Thief’s Journal, the films of Kenneth Anger, as well as the Dada poems of Baroness Elsa and Hugo Ball. Yet still other Garters have been nourished on the Vienna Actionists, Genesis P-Orridge, Diamanda Galas, Gilles Deleuze, Samuel Delany, and the dulcet sounds of The Cramps. With a critical and aesthetic arsenal salvaged from underground “kulchurs” and academia’s collective libido, the Iron Garters are not afraid to demand excitement along with analysis, frenzy coupled to resistance, and fashion inseparable from infiltration. Founded in San Francisco on a full moon night after a “deathpunk” show, the original members grew adversely impacted by the economic invasions reducing a once great city to a tepid monoculture. Fueled by queer, antinomian, heretical and radical traditions, the Garters pilgrimaged into various trans-continental sanctuaries and beachheads, leaving behind them radiant paper trails of provocation and sedition. This volume is one such radiant paper trail.

Reading Postures: On Close Reading, Feminism, and Academic Life - Erica Delsandro; Jennifer Mitchell (punctum books, 2026)
Reading Postures: On Close Reading, Feminism, and Academic Life, Erica Delsandro and Jennifer Mitchell anatomize the many positions that readers embody, willfully perform, fall into unthinkingly, and are compelled to assume. Such postures shape the way we read, write, and even teach the texts we love—and those we love to hate. Informed by modernist studies, queer studies, and critical university studies, the individual entries in this abcdarium situate autotheory within academic life by examining the various ways we read as scholars, teachers, and women, critiquing structural inequities but also celebrating joy. Each essay, co-authored and alphabetically organized, examines a specific posture — such as “angry reading,” “girly reading,” “killjoy reading,” “zombie reading,” and so on — and bridges feminist theory with deeply attentive close readings of literary texts, lived experiences, popular culture, politics, and academia. Cultivating intimacy and humor, the critical framework of this book invites an examination of the ways we have been and continue to be socialized as readers, writers, thinkers, and teachers within the neoliberal university and how we might betray the traditions that have shaped us. A hybrid, collaborative work that brings together the genres of personal essay, cultural critique, and manifesto, Reading Postures is ultimately an investigation of the shifting positions and shifting grounds that face queer feminist readers in the twenty-first century.

Reality in the Name of God, or, Divine Insistence: An Essay on Creation, Infinity, and the Ontological Implications of Kabbalah - Noah Horwitz (punctum books, 2012)
What should philosophical theology look like after the critique of Onto-theology, after Phenomenology, and in the age of Speculative Realism? What does Kabbalah have to say to Philosophy? Since Kant and especially since Husserl, philosophy has only permitted itself to speak about how one relates to God in terms of the intentionality of consciousness and not of how God is in himself. This meant that one could only ever speak to God as an addressed and yearned-for holy Thou, but not to God as infinite creator of all. In this book-length essay, the author argues that reality itself is made up of the Holy Name of God. Drawing upon the set-theoretical ontology of Alain Badiou, the computational theory of Stephen Wolfram, the physics of Frank Tipler, the psychoanalytical theory of Jacques Lacan, and the genius of Georg Cantor, the author works to demonstrate that the universe is a computer processing the divine Name and that all existence is made of information (the bit). As a result of this ontic pan-computationalism, it is shown that the future resurrection of the dead can take place and how it may in fact occur. Along the way, the book also offers compelling critiques of several significant theories of reality, including the phenomenological theologies of Emmanuel Levinas and Jean-Luc Marion, Process Theology, and Object-Oriented Ontology. Reality in the Name of God explores how the concepts of Jewish mysticism can be articulated and deployed as philosophical theses within current metaphysical debates. It provides a new and dynamic Structural Realist ontology of information. Ultimately, the book aims to deal a death blow to the restriction of philosophy and theology in relation to elaborations of a how a believer relates to a God outside the mind and to return thought to a direct encounter with the divine nature of reality itself and its creator.

Recovering the Radical Promise of Superheroes: Un/Making Worlds - Ellen Kirkpatrick (punctum books, 2023)
Superhero meaning making is a site of struggle. Superheroes (are thought to) trouble borders and normative ways of seeing and being in the world. Superhero narratives (are thought to) represent, and thereby inspire, alternative visions of the real world. The superhero genre is (thought to be) a repository for radical or progressive ideas. In the superhero world and beyond, much is made of the genre’s utopian and dystopian landscapes, queer identity-play, and transforming bodies, but might it not be the case that the genre’s overblown normative framing, or representation, serves to muzzle, rather than express, its protagonists’ radical promise? Why, when set against otherwise unbounded, and often extreme, transformation—human to machine, human to animal, human to god—are certain categories seemingly untouchable? Why does this speculative genre routinely fail to fully speculate about other worlds and ways of being in those worlds? For all their nonconformity, superhero stories do not live up to the idea of a radical genre, in look, feel, or tone. The mainstream American superhero genre, and its surrounding discourses, tells and facilitates an astonishingly seamless tale of opposing ideologies. But how? Recovering the Radical Promise of Superheroes: Un/Making Worlds serves a speculative response, detailing not so much a hunt for genre meaning as a trip through a genre’s meaningscape. Looking anew at superhero meaning-making practices allows a distinct way of thinking about and describing the creative, formal, and ideological conditions of the genre and its protagonists, one removed from corralling binaries, one foregrounding the idea of a synergy—often unseen, uneasy, and even hostile—between official and unofficial agents of superhero meaning and one reframing familiar questions: What kinds of meaning do superhero texts engender? How is this meaning made? By whom and under what conditions? What processes and practices inform, regulate, and extend superhero meaning? And finally, superhero narratives present a new question: How might we reimagine its agents, surfaces, and spaces? Centering the experiences and practices of excluded and marginalized superhero fans, Recovering the Radical Promise of Superheroes reveals that genre meaning is not lodged in one place or another, neither in its official creators or fans, nor in “black and white” conservatism or in a “rainbow” of progressive possibilities. Nor is it even located somewhere in the in-between; it is instead better conceived of as an antagonistic, in-process nexus of meaning undergirded by systems of power.

Redacted: Writing in the Negative Space of the State - Lisa Min; Franck Billé; Charlene Makley (punctum books, 2024)
When it comes to the political, acts of redaction, erasure, and blacking out sit in awkward tension with the myth of transparent governance, borderless access, and frictionless communication. But should there be more than this brute juxtaposition of truth and secrecy? Redacted: Writing in the Negative Space of the State brings together essays, poems, artwork, and memes—a bricolage of media that conveys the experience of living in state-inflected worlds in flux. Critically and poetically engaging with redaction in politically charged contexts (from the United States and Denmark to Russia, China, and North Korea), the volume closely examines and turns loose this disquieting mark of state power, aiming to trouble the liberal imaginaries that configure the political as a left-right spectrum, as populism and nationalism versus global and transnational cosmopolitanism, as east versus west, authoritarianism versus democracy, good versus evil, or the state versus the people—age-old coordinates that no longer make sense. Because we know from the upheavals of the past decade that these relations are being reconfigured in novel, recursive, and unrecognizable ways, the consequences of which are perplexing and ever evolving. This book takes up redaction as a vital form in this new political reality. Contributors both critically engage with statist redaction practices and also explore its alluring and ambivalent forms, as experimental practices that open up new dialogic possibilities in navigating and conveying the stakes of political encounters.

Red Lives: Our Years in the U.S. Communist Party (1950–2000), Vol. 1: Coming of Age in the Communist and Labor Movements - Jay Schaffner; Paul Friedman; Cindy Hawes; Geoffrey Jacques; Timothy Johnson; Carol Pittman; Donna Ristorucci; Daniel Rosenberg; Jackie Saindon (punctum books, 2026)
Red Lives: Our Years in the US Communist Party (1950–2000) is the first collection of historical analyses and reminiscences by members of the Communist Party USA (CPUSA) and the Communist youth movement in the US from the 1950s through the 1990s. The nearly fifty first-person testimonies bring to life a missing chapter in the history of US radicalism and demonstrate the influence of the post–World War II generation of Communists on social justice movements. Most histories of US Communism end in 1956 when Red Lives just begins, when McCarthyism was on its final legs, the Civil Rights Movement was sweeping the American South and the whole country, the student movement was taking its first breaths, and a new generation of young people were seeking out socialists, communists, and the Communist Party in order to craft a radical, anti-establishment politics. At a time when the launching of Sputnik, the Cuban Revolution, other revolutions sweeping Africa, and the example of the Vietnamese people fighting for their freedom and independence were inspiring the world, one-third of the world was also socialist, led by the Soviet Union and China. The time was propitious for a new generation in the US to also be seeking out, and joining, the CPUSA. This first volume of Red Lives, Coming of Age in the Communist and Labor Movements, brings the stories of that generation to the forefront of American history at a time when narratives of resistance are more needed than ever before.

Red Lives: Our Years in the U.S. Communist Party (1950–2000), Vol. 2: The Long 1960s - Jay Schaffner; Paul Friedman; Cindy Hawes; Geoffrey Jacques; Timothy Johnson; Carol Pittman; Donna Ristorucci; Daniel Rosenberg; Jackie Saindon (punctum books, 2026)

re: evolution - Kim Rosenfield (punctum books, 2023)
Delving into the fissures of language as an opportunity to create something new, Rosenfield appropriates texts from various fields of knowledge (evolutionary theory, psychoanalysis, advice on the science of living, and feminist theory) to rewire ideas of authority, subjectivity, and expert opinion. The resulting re: evolution is part text-book, part poem, part song-of-science, part feminist guide-to-living. Presented alongside research and analysis from a literary critic (Sianne Ngai), a poet/academic (Diana Hamilton), and an evolutionary biologist (Jennifer Calkins), re: evolution prompts the question: what moves around what? This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

Reiner Schürmann and the Poetics of Politics - Christopher Long (punctum books, 2018)
Reiner Schürmann’s thinking is, as he himself would say, “riveted to a monstrous site.” It remains focused on and situated between natality and mortality, the ultimate traits that condition human life. This book traces the contours of Schürmann’s thinking in his magnum opus Broken Hegemonies in order to uncover the possibility of a politics that resists the hegemonic tendency to posit principles that set the world and our relationships with one another into violent order. The book follows in the footsteps of Oedipus who, in abject recognition of his finitude, stumbles upon the possibility of another politics with the help of his daughters at Colonus. The path toward this other, collaboratively created and thus poetic politics begins with an encounter with Aristotle, a thinker whom Schürmann most frequently read as the founder of hegemonic metaphysics, but whose thinking reveals itself as alive to beginnings in ways that open new possibility for human community. This return to beginnings leads, in turn, to Plotinus, who Schürmann reads as marking the destitution of the ancient hegemony of the Parmenidean principle of the One. By bringing Schürmann’s innovative and compelling reading of René Char’s poem, The Shark and the Gull, into dialogue with Plotinus we come to encounter the power of symbols to transform reality and open us to new constellations of possible community. In Plotinus, where we expected to encounter an end, we experience a new way of thinking natality in terms of what comes to language in Char as the nuptial. Having thus been awakened to the power of symbols, we are prepared to experience how in Kant being itself comes to expression as plurivocal in a way that reveals just how pathologically delusional it is to attempt to deploy univocal principles in a plurivocal world. This opens us to what Schürmann calls the “singularization to come,” a formulation that gestures to a mode of comportment at home in the ravaged site between natality and mortality. This then returns us to Oedipus at Colonus; but not to him alone. Rather, it points to the relationship that emerges for a time between Antigone, Ismene, and Oedipus, as they navigate a way between their exile from Thebes and Oedipus’s final resting place near Athens. Here, having been awakened to the power of a poetic politics, we attend to three symbolic moments of touching between Oedipus and his daughters through which we might discern something of the new possibilities a poetic politics opens for us if we settle into the ravaged site that conditions our existence, together.

Shift Work: Art and Life in the Third Millennium - Susan Ballard; Liz Linden (punctum books, 2026)
Shift Work is a book of experimental art writing and collaborative autotheory, presenting an ongoing conversation between two friends. Liz Linden is an artist who writes based in California, Su Ballard, an art historian and curator living in Aotearoa New Zealand. They met in 2016 while teaching together in Wollongong, Australia. Shift Work traces their ongoing critical practices, as they consider the intersections of art and writing—those moments when aesthetic experiences are transmitted in texts, and the moments when art makes words irrelevant. Shift Work also traces how their relationship to the art they love, or love to think about, evolves in tandem with their own shifting places in the world, and asks what does it mean to take art seriously in a time of social and environmental change. In this collection of time-stamped—but not necessarily chronological—essays, Ballard and Linden’s conversation drifts from the challenges of interpretation to a sculpture park in contemporary Aotearoa New Zealand to the shared spaces of the classroom to the uncertain edges of a framed photograph, to New York galleries flooding, cratered, inhabited, and otherwise, to consider some of the shifting realities and experiences of life at the cusp of the third millennium, where art and life flow both ways.

Signs of the Great Refusal: The Coming Struggle for a Postwork Society - Tedd Siegel (punctum books, 2023)
In recent years, developed countries have seen the rise of discussions concerning “the problem with work today.” Since this literature tends to reflect the frustrations of the professional–managerial class (as well as other workers in globalized services industries in the digital age), it is often at a significant distance from the concerns of the organized labor movement and the traditional Left. Much of this literature presents an unacceptable either/or: workers are encouraged either to “lean in,” and become better “human capital,” or else to develop forms of palliative care for these same neoliberal selves by means of personal projects of self-optimization, recovery, and wellness. In Signs of the Great Refusal, Tedd Siegel challenges the assumptions supporting these highly constrained possibilities, asking instead what it might take to deprivatize and repoliticize work itself under contemporary conditions, in order to make a broad-based politics of refusal potentially viable. Where postwork, antiwork, and degrowth discussions taking place today often describe and promote various “postwork imaginaries” in which the decommodification of labor is only implied, Signs of the Great Refusal is concerned specifically with the “postwork political imaginary.” Taking up a question formulated by Peter Fleming, Siegel asks, “Can the impossibility at the heart of contemporary capitalism be politically activated to oppose and escape work-as-we-know-it?”

Siting Futurity: The “Feel Good” Tactical Radicalism of Contemporary Culture in and around Vienna - Susan Ingram (punctum books, 2021)
Siting Futurity: The “Feel Good” Tactical Radicalism of Contemporary Culture in and around Vienna shows how cultural practitioners in and around Vienna draw on their historical knowledge of locality to create rousing productions designed to get audiences to inform themselves about useful aspects of history, to engage their presents, and to help make possible more socially equitable futures. Analyses of politically engaged works of contemporary theatre, film, and photography set in and around Vienna help to identify a historically oriented mechanism that enables artists to tap into Vienna’s extraordinary, and extraordinarily under-appreciated, tradition of protest culture that dates back to the action that brought about the Wiener Neustadt “Blood Court” in the 16th century, but really came into its own with the city’s most influential occupation of an abandoned slaughterhouse for 100 days in the late summer of 1976. It also shows how work with a connection to Vienna by international stars like David Bowie, Wes Anderson, and Christoph Schlingensief has absorbed the same principles. While the overwhelming scale of technological development and the ensuing problems and crises may not have been deliberately designed to induce resignation, passivity, and despair, those who benefit from the related hyperobjects of financialization and climate change must find it convenient that they do, as demoralization reduces resistance to their profit-making machinations. It is in this context that Red Vienna’s proud tradition of social engagement and long history of resistance and radicality deserves to be better known.

Skirmishes: With Friends, Enemies, and Neutrals - Graham Harman (punctum books, 2020)
One of the fifty most influential living philosophers, a “self-promoting charlatan” (Brian Leiter), and the orchestrator of an “online orgy of stupidity” (Ray Brassier). In Skirmishes: With Friends, Enemies, and Neutrals, Graham Harman responds with flair and wit to some of his best-known critics and fellow travelers. Pulling no punches, Harman gives a masterclass in philosophical argumentation by dissecting, analyzing, and countering their criticism, be it from the Husserlian, Heideggerian, or Derridean corner. At the same time, Skirmishes provides an excellent introduction to the hottest debates in Speculative Realism and Object-Oriented Ontology, a speculative style of philosophy long foreclosed by the biases of mainstream continental thought, but which has turned in recent years into one of the most encompassing philosophies of our time, with a major impact on the arts, humanities, and architecture. Part One considers four prominent books on speculative realism. In dialogue with Tom Sparrow’s The End of Phenomenology, Harman expresses agreement with Sparrow’s critique while taking issue with Lee Braver’s “transgressive realism” as not realist enough. Turning to Steven Shaviro’s The Universe of Things, Harman defends his own object-oriented model against Shaviro’s brand of process philosophy, while also engaging in side-debate with Levi R. Bryant’s distinction between virtual proper being and local manifestations. In the third chapter, on Peter Gratton’s Speculative Realism: Problems and Prospects, Harman opposes the author’s attempt to use Derridean notions of time and difference against Speculative Realism, in what amounts to his most extensive engagement with Derrida to date. Chapter Four gives us Harman’s response to Peter Wolfendale’s massive polemic in Object-Oriented Philosophy, which he shows is based on a failed criticism of Harman’s reading of Heidegger and a grumpy commitment to rationalist kitsch. Part Two responds to a series of briefer criticisms of object-oriented ontology. When Alberto Toscano accuses Harman and Bruno Latour of “neo-monadological” and anti-scientific thinking, Harman responds that the philosophical factors pushing Leibniz into monadology are still valid today. When Christopher Norris mocks Harman for seeing merit in the occasionalist school, he shows why Norris’s middle-of-the-road scientific realism misses the point. In response to Dan Zahavi’s contention that phenomenology has little to learn from speculative realism, Harman exposes the holes in Zahavi’s reasoning. In a final response, Harman gives a point-by-point answer to Stephen Mulhall’s critical foray in the London Review of Books. Amidst these lively debates, Harman sheds new light on what he regards as the central bias of philosophical modernism, which he terms the taxonomical standpoint. It is a book sure to provoke lively controversy among both friends and foes of object-oriented thought.

Snowline - Donato Mancini (punctum books, 2015)
“Mais où sont les neiges d’antan?” François Villon’s most famous line is a kind of translation, a variation of the old “ubi sunt” trope: Where are the things that used to be? But Villon specifically asks: Where are the snows? Even in the thick of a snowy winter, this snow is not the same as the remembered snows. The difference is affective, but it is also ecological: the world’s climate is dramatically changing. Winter itself is changing. Donato Mancini has collected over eighty translations of Villon’s line, from Thomas Urquhart’s 1653 translation of Rabelais’s quotation of the line, all the way up to translations by Florence Dujarric (2013) and Michael Barnholden (2014). From these he has arranged forty – a number that once stood for a countless number, like the forty thieves or the forty years of the biblical flood – into a booklength poem. Taking a cue from Caroline Bergvall’s “Via (http://www.poetryfoundation.org/poem/245738),” but deviating from it in significant ways, snowline traces how Villon’s line has changed and yet stubbornly stayed the same over six hundred years. It is a meditative and pointedly nostalgiac book: You will grow older as you read it, and the world around you will continue to melt into air.

Social and Intellectual Networking in the Early Middle Ages - Michael J. Kelly; K. Patrick Fazioli (punctum books, 2023)
Social and Intellectual Networking in the Early Middle Ages seeks to expand our understanding of early medieval connectivity by interrogating social and intellectual collaborations, competitions, and communications among persons, places, things, and ideas in the European and Mediterranean West during the second half of the first millennium CE. In so doing, its contributors explore the existence, performance, and sustainability of diverse political, scholarly, ecclesiastical, and material networks via manuscripts, artifacts, and theories framed by two broad interpretive categories. The first examines networks of scholars, writers, and the social and political histories related to their productions. The second imagines the transmission of “knowledge” as information, rhetoric, object, and epistemic grounding. In addition, the book rigorously investigates the theoretical possibilities and problems of researching early medieval networks, attempts to reconstruct historical networks, and critically analyzes the concept of “information.”

Solar Calendar, And Other Ways of Marking Time - Jeremy Bendik-Keymer (punctum books, 2017)
At the end of his life, Pierre Hadot was a professor at the Collège de France — a “professor’s professor” — and he helped Michel Foucault, most famously, conceptualize ethics. Hadot devoted his career to recovering the ancient conception of philosophy, according to which the discourses of universities are but a fragment of what philosophy is. His engagement with this theme helped Bendik-Keymer understand and develop a personal counter-culture to his academic work, a kind of original academics truer to the idea of the philosophical school Plato first developed in his Ἀκαδήµεια. But while Plato’s school developed a useful form of life, it had an ambivalent relation to democracy and to everyday people. Whereas Plato was in some ways one of the first egalitarians by merit (especially concerning women), he was also deeply classist in his categorization of intellectual potentials. He effectively thought some people were stupid by nature, having no philosophical worth. Hence the Ἀκαδήµεια existed outside the city, in practice exclusive and somewhat sequestered. To some extent, Plato’s vision of philosophy — at least as explained by Hadot — had the practical point of philosophy right, but this point still needed to be rendered thoroughly democratic in the polyphony and multiple intelligences of people. Doing so coheres with what Foucault was after in his application of Hadot. It is also what Bendik-Keymer is after — to extract what is good from original academics and make it democratic, as opposed to dumbing people down. Imagine the kind of philosophy book you might have wished for when you were growing up. Seeking a reader who would be patient and open-minded enough to live with her own questions and to walk around town with her thoughts, this book would not have a single thesis but would rather work through multiple problems and be an experience, born out of life-experience. It would not be summarizable. It would be larger than the reader and open onto different kinds of readings. This is the kind of philosophy book that was at home in the 19th century. Solar Calendar (a follow-up to Bendik-Keymer’s The Ecological Life: Discovering Citizenship and a Sense of Humanity (https://rowman.com/ISBN/9780742534476/The-Ecological-Life-Discovering-Citizenship-and-a-Sense-of-Humanity)) contains six oddities: a family portrait, a parody-essay, a time-capsule poem, an exploded essay, a poetic record of an act, and an aphorism journal for a year. Their inspirations are Epictetus’s notebooks, Tarkovski’s Mirror, and Apollinaire’s roving “Zone.” Also experiments in ecology — the study of home — the six sections originate in rifts that challenge us as growing people. They alternate between environmental problems and tensions within families, as if the fissures in love and in society wash back and forth between each other as we try to make a home in the world. Multiple times layer over each other like the sounds of a large, democratic city. The personal and the planetary intersect. The space before, and against, policy where politics arises as assertion opens up in glimpses, fragmenting the body and inertia of oppressive orders. Philosophy arises as a homely and idiosyncratic practice of multiple forms of intuition, reflection and intelligence for muddling through life. Painstaking exercises in being human are grounded in unconditional love and in truthfulness — in the desire to become.

Solarities: Elemental Encounters and Refractions - Cymene Howe; Jeff Diamanti; Amelia Moore (punctum books, 2023)
Solarities: Elemental Encounters and Refractions is a transdiciplinary essay collection that explores the physical, conceptual, and political possibilities materialized by “solarity”— a form of relation to the sun and its elemental force upon planetary life. The authors propose that a different set of questions becomes possible when the material specificities of solar become the compass for thought, prompting us to uncover our relationship to the sun. How does solarity materialize in the bodies and lives of humans and non-humans now and in the future? What can we learn if we no longer take the sun for granted? How do we continue to persist on a planet that is so intimately bound up in a state of love, fear, and dependence on this primary source of all living energy? Each of the essays in Solarities take solar radiation as an interpretive lens that takes multiple forms, often transforming as it does so. Solarities draws inspiration from Black ecologies, Indigenous philosophy, feminist science & technology studies, and more-than-human discussions in the human sciences, recognizing the phenomenological and ontological openings they make available. The authors understand solarity as an energy source (channeled through photovoltaic cells, for example), but the essays gathered here focus on the lives that solarity creates or impedes. The experimental task is to find how solarities work their way into materials and processes across our work, seeking out the particular influences of solarity in making being(s). These relations are core to thinking the elemental conditions of solarity, since it is through particular forms of focalizing the sun that life is sustained, or made to wither, across the planet. In these ways, the elemental condition of solarity is at once hyper-particular and also shared across organic and inorganic bodies, conditioned by physical form and material composition. Throughout the collection, the authors explore how solarity appears or recedes from view when we concentrate our attentions on it, surfacing the existential omnipresence of the sun to open new thought possibilities, inspire new actions, and refract new dimensions of socionatural encounter.

Something More Splendid Than Two - josé rivers alfaro (punctum books, 2022)
Blending literary analysis and memoir, Something More Splendid Than Two is at once an excavation of intergenerational wounds, a dance number, a poem, and a fraught love letter from son to father that disrupts the dominant narratives surrounding the life and myth of Joaquín Murrieta. In the Mexican American imaginary, the legend of Joaquín Murrieta has been recast to explain the wounding of Mexican American men after the 1848 border formation. In these versions, Joaquín is a vigilante hero and the patriarchal father of the Chicanx movement. Revisiting the most circulated version of the Joaquín myth, The Life and Adventures of Joaquín Murieta written by Cherokee writer John Rollin Ridge, the first published Native American author in the US, Something More Splendid Than Two offers an alternative to these versions. Stitching together multiple tangled histories of Indigenous and Mexican woundings living in the margins of Ridge’s 19th-century novel, alfaro opens a queer timeline where Chicanx and Indigenous solidarities can be imagined. By attuning to the choreographies of power and patriarchy that produced readers and writers like Ridge and the author of this book, josé rivers alfaro imagines that in that endless encounter between reader and writer, both time travel and collective healing are possible.

Some Ways of Making Nothing: Apophatic Apparatuses in Contemporary Art - Curt Cloninger (punctum books, 2021)
What if all works of art were better understood as functioning apparatuses, entangling their human audiences in experiences of becoming? What if certain works of art were even able to throw the brakes on becoming altogether, making nothings rather than somethings? What would be the ethical value of making nothing, of stalling becoming; and how might such nothings even be made? Some Ways of Making Nothing: Apophatic Apparatuses in Contemporary Art borrows its understanding of apparatuses from quantum mechanics and the process philosophy of Alfred North Whitehead, and its understanding of nothing from apophatic (negative) theology. It then proposes a new way of understanding art, applying this understanding to artworks by Arakawa and Gins, Robert Fludd, David Crawford, Joshua Citarella, William Pope.L, and Haim Steinbach. Philosophy, physics, theology, and media theory are traversed and involved in order to understand art differently so that it might be made to matter more.

Sonic Detection: Necessary Notes for Art and Performance - Rebecca Collins; Johanna Linsley (punctum books, 2026)
Sonic Detection is part sonic noir, part performance document, and part critical investigation of listening at the margins for readers interested in prospecting the boundaries of performance studies, sound studies, and interdisciplinary writing. The book opens with a group of sonic detectives (exact number unknown) who investigate the mystery of an as-yet-unidentified event that leaves traces only in the acoustic atmosphere. This hybrid fiction propels the reader up and down the UK coast and offers overheard fragments from a faded seaside resort, a container shipping port, a former coal-mining town, and the Scottish headquarters for North Sea oil. A heterogeneous collection of texts follows, from creative-critical essays, performance scores, engagement with the archives of earlier sonic detectives (including poet/performance artist Fiona Templeton and the sound art collective Bow Gamelan Ensemble), to a series of dispatches from expert witnesses with their ears to the ground. Sonic Detection is not so much a monograph as a polygraph, tongue-in-cheek associations with questionable forensic technologies firmly in place. The book emerges from a decade-long collaboration between artists Rebecca Collins and Johanna Linsley, who used eavesdropping as an expanded creative methodology. The project began as a series of hyper-local, community-based performance works in coastal locations in the UK (from Bournemouth to Aberdeen) and grew into an international, multi-disciplinary life work devoted to an ongoing, organized curiosity. Sonic detectives hold open a collective sonorous space. They are the embodiment of the phenomenophile, lingering longer in listening.

Speaking for the Social: A Catalog of Methods - Hannah Knox; Gemma John (punctum books, 2022)
What does it mean to “speak for the social” in projects of technical and infrastructural change? This is the problem that the contributors to Speaking for the Social: A Catalogue of Methods set out to explore through a series of creative interventions that reimagine the role for qualitative social science in understanding and shaping design and engineering projects. The book departs from familiar methods like interviews, surveys, and participant observations, to propose walks, exhibitions, performances, dialogues, online museums, meetings, and staged performances as an array of alternative ways of thinking about and eliciting the social implications of infrastructure projects. Prompted both by a turn to infrastructure and material relations in social research and the concern with social impact and social value in technical projects, this book seeks to outline new ways for social scientists to engage with, critique, and participate in infrastructure design. The chapters build on theoretical attention to the social life of objects like roads, buildings, cities, and environments to devise practical methods that can help make social issues newly visible in infrastructure projects. Individually the entries offer a range of practical methods for “speaking for the social” in technical infrastructure projects. Taken together the book lays the ground for new kinds of collaborative, applied social research embedded in the latest discussions in social theory to explore how social value, impact, and responsibility might be rethought and achieved in the process of designing and engineering social change.

Speaking with the Dead: An Ethnography of Extrahuman Experience - Matt Tomlinson (punctum books, 2024)
If you tried speaking with a dead person and they gave you a clear response, how would you react? Mediums develop their minds and bodies to communicate messages from the deceased to their living loved ones, and in Speaking with the Dead, anthropologist Matt Tomlinson describes his experiences training as a medium with a Spiritualist congregation in Canberra, Australia. The book is written in a first-person narrative style that brings “extrahuman” relationships to life, showing what it is like to learn and practice mediumship: the strategic suspension of skepticism; the wobbly first attempts; the embarrassing failures; and the moments, both unsettling and enthralling, when someone tells you that yes indeed, you’ve just described her grandfather who died in 1978. Speaking with the Dead brims with stories of talented mediums and Tomlinson is not interested in proving or disproving mediumship, preferring instead to illustrate how mediums bring their practices to life. In contrast to the popular image of mediums as shameless frauds, Tomlinson describes earnest and committed seekers from a wide range of backgrounds who often struggle to understand their own experiences. Their profits are therapeutic rather than financial. And they worry about endings as much as anyone else: the passing of physical lives, the closure of beloved churches. Speaking with the Dead is ultimately a book about the lively side of death, grounded in Spiritualists’ conviction that life is eternal and your social network extends to the astral plane. It is a close examination of how mediumship works culturally, which is to say, how mediums and audiences work together to create senses of transcendent connection.

Speculations - Paul J. Ennis (punctum books, 2020)
From the Editorial Introduction: "Since I am convinced that nobody reads editorials I will keep my remarks brief. Putting together the inaugural issue of Speculations has been an unusual experience. It has depended on the collusion of fellow speculative types, the help of many anonymous reviewers, the endless patience of designer Thomas Gokey, and more hours than someone in the final year of their PhD should ever spend on a project. Looking over the final product I think it has all been worth it. This is the first journal dedicated to speculative realism and despite the obscurity of that term I think we all understand it as a handy label under which weird realists, continental metaphysicians, object oriented ontologists, transcendental realists, vitalists, and Lovecraftians can unite. This is also, perhaps, the first time a journal can boast that each contributor is also a blogger. This is the reason why Speculations could only ever be an online, open-access journal. …"

Speculations 3 - Michael Austin; Fabio Gironi; Robert Jackson; Paul J. Ennis; Thomas Gokey (punctum books, 2012)
In this third volume of Speculations, a serial imprint created to explore post-continental philosophy and speculative realism, a wide range of topics are covered, from the philosophy of religion to psychoanalysis to the philosophy of science to gender studies, and in a wide variety of formats (articles, interviews, position pieces, translations, and review essays).

Speculations II - Michael Austin; Paul J. Ennis; Thomas Gokey (punctum books, 2020)
From the Editorial Introduction: "If the first volume of Speculations was enough of an explicit wager, a willing blind leap in the terra incognita of the publishing world, then this volume forces us to stop and evaluate the reasons for the journal’s protracted existence. This is all the more important when we consider how the range of meanings of the term ‘speculative realism’ seems to be growing—with increasing numbers of thinkers situating themselves in its trail, or holding a somewhat cautious interest in it—while its e ective reference seems nowhere to be found. …"

Speculations IV: Speculative Realism - Michael Austin; Fabio Gironi; Robert Jackson; Paul J. Ennis; Thomas Gokey (punctum books, 2013)
With this special volume of Speculations, the editors wanted to challenge the contested term “speculative realism,” offering scholars who have some involvement with it a space to voice their opinions of the network of ideas commonly associated with the name. Whilst undoubtedly born under speculative realist auspices, Speculations has never tried to be the gospel of a dogmatic speculative realist church, but rather instead to cultivate the best theoretical lines sprouting from the resurgence, in the last few years, of those speculative and realist concerns attempting to break free from some of the most stringent constraints of critique. Sociologist Randall Collins observed that, unlike other fields of intellectual inquiry, “[p]hilosophy has the peculiarity of periodically shifting its own grounds, but always in the direction of claiming or at least seeking the standpoint of greatest generality and importance.” If this is the case, to deny that a shift of grounds has indeed become manifest in these early decades of the twenty-first century would be, at best, a sign of a severe lack of philosophical sensitivity. On the other hand, whether or not this shift has been towards greater importance (and in respect to what?) is not only a legitimate but a necessary question to ask. Whatever the intrinsic value in the name, the contributors to this volume have all engaged, more or less directly, with a critical analysis of the vices and virtues of “speculative realism”: from the extent to which its adversarial stance towards previous philosophical stances is justified to whether it succeeds (or fails) to address satisfactorily the concerns that ostensibly motivate it, through to an assessment of the methods of dissemination of its core ideas. The contributions are divided in two sections, titled “Reflections” and “Proposals,” describing, with some inevitable overlap, two kinds of approach to the question of speculative realism: one geared towards its retrospective and its critical appraisal, and the other concerned with the positive proposition of alternative or parallel approaches to it. It is believed that the final result, in its heterogeneity, will be of better service to the philosophical community than a dubiously univocal descriptive recapitulation of “speculative realist tenets.”

Speculations V: Aesthetics in the 21st Century - Ridvan Askin; Paul J. Ennis; Andreas Hägler; Philipp Schweighauser (punctum books, 2014)
Ever since the turn of the century aesthetics has steadily gained momentum as a central field of study across the disciplines. No longer sidelined, aesthetics has grown in confidence. While this recent development brings with it a return to the work of the canonical authors (most notably Baumgarten and Kant), some contemporary scholars reject the traditional focus on epistemology and theorize aesthetics in its ontological connotations. It is according to this shift that speculative realists have proclaimed aesthetics as “first philosophy” and as speculative in nature. With speculative realism aesthetics no longer necessarily implies human agents. This is in alignment with the general speculative realist framework for thinking all kinds of processes, entities, and objects as free from our all-pervasive anthropocentrism, which states, always, that everything is “for us.” This special volume of Speculations explores the ramifications of what could be termed the new speculative aesthetics. In doing so, it stages a three-fold encounter: between aesthetics and speculation, between speculative realism and its (possible) precursors, and between speculative realism and art and literature.

Speculations VI - Fabio Gironi; Michael Austin; Robert Jackson (punctum books, 2015)
In this sixth issue of Speculations, a serial imprint created to explore post-continental philosophy and speculative realism, a wide range of contemporary philosophical issues pertaining to the contemporary philosophical scene is touched upon, from the continental realism of Tristan Garcia, Graham Harman and Quentin Meillassoux to the "new realism" of Maurizio Ferraris, from Lacanian and Laurellian speculations to the synthetic philosophy of Fernando Zalamea’s mathematics.

Speculative Medievalisms: Discography - Eileen A. Joy; Anna Kłosowska; Nicola Masciandaro; Michael O'Rourke; The Petropunk Collective (punctum books, 2013)
Proceedings from the two Speculative Medievalisms symposia, held at King’s College London (Jan. 2011) and The Graduate Center, City University of New York (Sep. 2011), and organized by The Petropunk Collective (Eileen Joy, Anna Klosowska, Nicola Masciandaro, and Michael O’Rourke). These interdisciplinary events were dedicated to dialogue and cross-contamination between traditional concepts of speculatio, present-minded premodern studies, and contemporary speculative realist and object-oriented philosophies. In its medieval formulation, speculatio signifies the essentially reflective and imaginative operations of the intellect. Here the world, books, and mind itself are all conceived as specula (mirrors) through which the hermeneutic gaze can gain access to what lies beyond it. “To know is to bend over a mirror where the world is reflected, to descry images reflected from sphere to sphere: the medieval man was always before a mirror, both when he looked around himself and when he surrendered to his own imagination” (Giorgio Agamben, Stanzas). Correlatively, speculative realism, as the term suggests, is characterized by the self-contradictory intensity of a desire for thought that can think beyond itself — a desire that proceeds, like all philosophy, in a twisted and productive relation to the phantasm of the word. Aiming to rise above and tunnel below the thought-being or self-world correlation, speculative realism “depart[s] from the text-centered hermeneutic models of the past and engage[s] in daring speculations about the nature of reality itself” (The Speculative Turn). Speculative Medievalisms, like some weird friar-alchemist in an inexistent romance, plays the erotic go-between for these text-centered and text-eccentric intellectual domains by trying to transmute the space between past and present modes of speculation from shared blindness to love at first sight. Possibly succeeding, the volume brings together the work of a motley crew of philosophers and premodernists into prismatic relation.

Speechsong: The Gould/Schoenberg Dialogues - Richard Cavell (punctum books, 2020)
Speechsong is a work of imaginative musicology that addresses the engimas of Schoenberg and Gould, of singing and speaking, of Moses und Aron, of technology and being. Its point of departure is Gould’s last public performance, given at the Wilshire Ebell Theatre in Los Angeles, where a number of Schoenberg’s works were performed during his California exile. It is here, after that last performance, that Gould encounters a spectral Schoenberg in a staged conversation that explores Schoenberg’s travails in rethinking the fundamentals of Western music. This first part of Speechsong recalls Schoenberg’s operatic masterpiece, Moses und Aron, in which the divinely inspired Moses seeks the help of his brother to relate his vision: Moses speaks and Aron sings. Written as a twelve-tone composition, the opera produces an involution of harmonics that was Schoenberg’s response to Richard Wagner’s diatribes about synagogue noise. For Gould, Schoenberg’s is a formalist revolution; Schoenberg’s life, however, suggests that it was a search for personal and political freedom. The second half of Speechsong is a critical essay in twelve “moments” that re-articulates the staged conversation as an inquiry into the intersections of music and mediation. Gould’s turn to the recording studio emerges as a post-humanist inquiry into recorded music as a repudiation of the virtuoso tradition and a liberation from unitary notions of selfhood. Schoenberg’s exodus from musical tradition likewise takes his twelve-tone invention beyond musical performance, where it emerges, along with Gould’s soundscapes, as a prototype of acoustic installations by artists such as Stephen Prina and Cory Arcangel. In these works, music abandons the concert hall and the exigencies of harmony for an acoustic space that embraces at once the recordings of Gould and the performances of Schoenberg that have found their home on the internet.

Static Palace - Leora Fridman (punctum books, 2022)
In the face of unimaginably violent systems, our most vulnerable bodies—sick, disabled, unable to rise from bed—offer the resistance of imperative vulnerability. What can we learn from the body that cannot help but fail? How can porosity perform treachery within entrenched opressions? What kind of reading and relationship to text can enrich relationship instead of inscribing boundaries between us? What does it mean to accept the unacceptable, and what kind of power becomes available when we submit to forces larger than ourselves? How might we take refuge in discomfort, and in the process refuse the stale comforts offered by hyper-capitalist economics and white supremacy? Static Palace, a collection of linked essays, weaves the writer’s experiences of chronic illness and activism under Trump rule to explore the possibility that arises from circumstances we often perceive as ruin: hopeless political systems, disabled bodies, narratives that stutter and do not complete themselves, the devastation of climate change. Spurred by the writer’s diagnosis with endometriosis and accompanying chronic conditions, which occurred immediately following the 2016 US Presidential Election, Static Palace is especially relevant in the context of rising fascism, pandemics, and the decay of social services and support networks. A direct engagement with the patchwork, fragmented brain of digital life and sick brain, Static Palace is part lyric essay and part cultural criticism: it pulls from current events, including Black-led resistance movements and disability justice activism, and cites contemporary thinkers on gender, feminism, care, critical race, and disability studies towards an artful treatment of crisis and community. Its concerns move toward connection and inter-being. By threading a wide variety of theories and politics through the personal, Fridman seeks a fertile integrity through—and with—subjectivity. We witness a mind making, culling, and attempting to stave off isolation through intertextual and interpersonal conversation. This work complicates the meaning of belonging, family and tribe, challenges our impulses toward narrative resolution, and offers a nuanced understanding of interdependent being and thought.

Staying Alive: A Survival Manual for the Liberal Arts - L.O. Aranye Fradenburg (punctum books, 2013)
Staying Alive: A Survival Manual for the Liberal Arts fiercely defends the liberal arts in and from an age of neoliberal capital and techno-corporatization run amok, arguing that the public university’s purpose is not vocational training, but rather the cultivation of what Fradenburg calls “artfulness,” including the art of making knowledge. In addition to sustained critical and creative thinking, the humanities develop the mind’s capacities for real-time improvisational communication and interpretation, without which we can neither thrive nor survive. Humanist pedagogy and research use play, experimentation and intersubjective exchange to foster forms of artfulness critical to the future of our species. From perception to reality-testing to concept-formation and logic, the arts and humanities teach us to see, hear and respond more keenly, and to imagine, or “model,” new futures and possibilities. Innovation of all kinds, technological or artistic, depends on the enhancement of the skills proper to staying alive. Bringing together psychoanalysis, neuroscience, animal behavioral research, biology & evolutionary theory, and premodern literarature (from Virgil to Chaucer to Shakespeare), Fradenburg offers a bracing polemic against the technocrats of higher education and a vibrant new vision for the humanities as both living art and new life science. Contrary to recent polemics that simply urge the humanities to become more scientistic or technology-focused, to demonstrate their utility or even trophy their uselessness, Staying Alive does something remarkably different: it argues for the humanism of a new scientific paradigm based on complexity theory and holistic and ecological approaches to knowledge-making. It urges us to take the further step of realizing not only that we can promote and enhance neuroplastic connectivity and social-emotional cognition, but also that the humanities have always already been doing so. “Nature always exceeds itself in its expressivity” — which is to say that living is itself an art, and artfulness is necessary for living: for adaptation and innovation, for forging rich and varied relationships with other minds, bodies and things, and thus, for thriving — whether in the boardroom or the art gallery, the biology lab or the recording studio, the alley or the playground, the book or the dream.

Steal This Classroom: Teaching and Learning Unbound - Jody Cohen; Anne Dalke (punctum books, 2019)
Jody Cohen and Anne Dalke construe “classrooms” as testing grounds, paradoxically boxed-in spaces that cannot keep their promise to enclose, categorize, or name. Exploring what is usually left out can create conditions ripe for breaking through, where real and abstract reverse and melt, the distinction between them disappearing. These are ecotones, transitional spaces that are testing grounds, places of danger and opportunity. In college classrooms, an urban high school, a public library, a playground, and a women’s prison, Anne and Jody share scenes where teaching and learning take them by surprise; these are moments of uncertainty, sometimes constructed as failure. Digging into and exploding such moments reveals that they might be results of institutional pressures, socioeconomic and other diversities not acknowledged but operating and entangling individuals and ideas. Classrooms are sometimes “stolen” by the complex systems surrounding and permeating the activities that take place there; Jody and Anne explore ways to steal them back. Examining what is hidden but present in such moments can turn them into breakthroughs, powerful learning for educators and students—revealing how failure itself might not be what it seems. Moving back and forth between micro and macro in a continual interplay across individuals, groups, and institutions, and organizing their experiences and philosophies of teaching under the rubrics of Playing, Haunting, Silencing, Unbecoming, Leaking, Befriending, Slipping, and Reassembling, Anne and Jody try out alternative tales, exploring a pedagogical orientation that is ecological in the largest sense, engaging teachers and students in re-thinking learning and teaching in classrooms, and in their larger lives, as complex, enmeshed, volatile eco-systems. Jody and Anne weave through their own voices those of students and colleagues, demonstrating the complex playfulness of collaborative and transdisciplinary forms of teaching and learning. Not solving the contradictions, but abstracting from the immediate, they offer a dialogue, telling hard stories and funny ones, involving others’ stories in response, demonstrating the complex playfulness of collaborative and transdisciplinary work. They make concrete suggestions about how academic and other structures might open up; they also remain porous and interactive, inviting reader-participants to join in transfiguring what spaces of teaching and learning are and can be-and-do.

Still Life: Notes on Barbara Loden's "Wanda" (1970) - Anna Backman Rogers (punctum books, 2021)
There is indeed a “miracle” in the 1970 film Wanda. This film has survived, despite decades of neglect, to emerge into the fuliginous light of an era that may just be ready to strain at grasping its harsh and brutal truths—truths that reveal the imbrication of the psychic in the social and the experiential in political structures. Barbara Loden’s film dares to suggest that the social and ethical functions of art should not necessarily be redemptive—that salvation is a cheap and spurious form of consolation that few can afford in this world. This film, made by a woman who knew all too well what it means to be defined through and by her material circumstances (and her relationships to men), and that is so relentlessly ferocious in its refusal to assuage and comfort the viewer, has always been a form of future feminism. Wanda does not brook the comforts of positivity, of aspiration, or even the luxury of selfhood. Loden’s film, Still Life contends, is so radical in its feminist-anti-capitalist politics of refusal that we are still struggling to keep up with it. It delineates precisely how the personal is political and why this matters now more than ever. Wanda, a film about a woman who refuses to be saved or to save herself, who lacks the means and energy to alter anything in her life, who lives in a permanent state of blockage, impasse and failure is, as this book suggests, the film of our contemporary moment.

Still Thriving: On the Importance of Aranye Fradenburg - Eileen A. Joy (punctum books, 2015)
The work of L.O. Aranye Fradenburg, especially her psychoanalytic criticism of Chaucer, and her formulations of discontinuist historical approaches to the Middle Ages, has been extremely influential within medieval studies for the past 20 or so years. More recently she has been focusing on more broad defenses of the humanities, especially with regard to the valuable role of literary studies relative to the arts of everyday living, eudaimonia [flourishing], ethical community, and well-being, and also on psychoanalysis itself as a “liberal art.” Relationality, intersubjectivity, aliveness, resilience, care of the self and also of others, adaptive flexibility, playfulness, shared attention, companionship, healing, and thriving seem, increasingly, to be the key watchwords and concerns of Fradenburg’s work, and at the same time, the so-called “literary” mode is still central to these concerns, such that, as Fradenburg has written, “Interpretation and relationality depend on one another because all relationships are unending processes of interpretation and expression, listening and signifying. In turn, sentience assists relationality: we can’t thrive and probably can’t survive without minds open to possibility, capable of sensing and interpreting the tiniest shifts in, e.g., pitch and tone.” This small volume features short essays and personal reflections on the importance of Fradenburg’s career, as teacher and scholar, and also on the valuable role(s) that her work, and medieval studies more generally, has played and might still play in the defense of the humanities as essential to living and thriving.

Styling Sagaciousness: Oh Great No! - Joseph Nechvatal (punctum books, 2022)
During the Paris pandemic confinement period of 2020, with the dread of viral death in the air, artist Joseph Nechvatal finished his second book of poetry, titled Styling Sagaciousness: Oh Great No! The mythopoeic mélange of Styling Sagaciousness is intended as a complicated forensic fairy-tale, suitable for Nô theater, which keeps slipping in and out of idiosyncratic narration, a ghostly appearance-disappearance act that turns on the nub of our narcissism concerning our death—that strange, incurable, and deeply irrational affliction we all share. Putting identity aside, Nechvatal’s poetry tests the limits of form and stretches the bounds of meaning by recasting our experiences of encountering our self as the sumptuous physicality of total negation. As such, Styling Sagaciousness delivers an airy irrational punch of needed nonsensical negation by tying together insouciant informality with a visceral camp irony: at turns hip and flamboyant and morally outrageous. This seven-part death farce epic poem follows up Nechvatal’s sex farce epic poem Destroyer of Naivetés (https://punctumbooks.com/titles/destroyer-of-naivetes/). Nechvatal intends these two books (with complementary cover images of his painting penelOpe in agOny) to be the sum total of his mature poetic output; addressing first Eros, and then, with Styling Sagaciousness, Thanatos.

Suite on "Spiritus Silvestre": For Symphony - Denzil Ford (punctum books, 2012)
Carbon dioxide. This small book aims to open a door. It is an experiment in thinking about an object made extremely familiar to many people across the world in recent years through science, the news, governments, and public discourses. One of the first names given to carbon dioxide was spiritus silvestre or wild spirit, a moniker that has fallen out of favor. This experiment is a chance to hold what we think we know about this object in our hand and ponder our own knowledge for a while by looking at it in one particular historical context long after more modern names became familiar. Music. The reader is asked to create a space of visualization where the potential for new understandings arise when seemingly unrelated things and practices are taken seriously next to one another and where previous conceptions of wildness may have continued to emit sound even after formal names changed. In the 20th century, Charles Keeling was one of the major scientists interested in the wild spirit — he was also a musician. Illumination. Denzil Ford highlights relationships between the musician and the scientist and further considers conceptualizing an object of scientific inquiry through the framework of a piece of music. Her narrative approach does not spell out every point but uses text and image together; this is a work of experimental thought written in experimental form. She joins other scholars looking at the multiple meanings of carbon dioxide across time and space, and her historical and philosophical approach allows the reader a moment to remember some of the social layers of scientific research that have led to our understanding of climate change, one of the greatest environmental problems of the 21st century.

Suture: Trauma and Trans Becoming - KJ Cerankowski (punctum books, 2021)
The landscape of trauma is scattered with ghosts. Wolves hunkering in the shadows. Memory’s spectral persistence and evasion. Leaky bodies and selves gathered up in the storm of pain. Genders imposed and genders made. History’s cruel excisions, scars, the spillage of wounds. A landscape in which we are nevertheless called to build home. Here, “storytelling is a kind of suturing.” Combining memoir, lyrical essay, and cultural criticism, KJ Cerankowski’s Suture: Trauma and Trans Becoming stitches together an embodied history of trauma and its ongoing impacts on the lived realities of trans, queer, and other marginalized subjects. Suture is a conjuration, a patchwork knitting of ghost stories attending to the wound as its own archive. It is a journey through many “transitions”: of gender; through illness and chronic pain; from childhood to adulthood and back again; of psyche and form in the wake of abuse and through the work of healing; and of the self, becoming in and through the ongoingness of settler colonial violence and its attendant subjugations of diverse forms of life. Refusing a traditional binary-based gender transition narrative, as well as dominant psychoanalytic narratives of trauma that center an individual process of symptom, diagnosis, and cure, Suture explores the refractive nature of trauma’s dispersed roots and lingering effects. If the wounds of trauma are disquiet apparitions—repetitions within the cut—these stories tend the seams through which the simultaneous loneliness of mourning and togetherness of queer intersubjective relations converge. Across these essays, healing, and indeed living, is a state of perpetual becoming, surviving, and loving, in the nonlinearities of trauma time, body-time, and queer time.

Sweet Spots: Writing the Connective Tissue of Relation - Mattie-Martha Sempert (punctum books, 2021)
Sweet Spots thinks transversally across language and body, and between text and tissue. This assemblage of essays collectively proposes that words—that is, language that lands as written text—are more-than-human material. And, these materials, composed of forces and flows and tendencies, are capable of generating text-flesh that grows into a thinking in the making. The practice of acupuncture—and its relational thinking—often makes its presence felt to twirl the text-tissue of the bodying essays. Ficto-critical thinking is threaded throughout to activate concepts from process philosophy and use the work of other thinkers (William James, Félix Guattari and Gilles Deleuze, Baruch Spinoza, and Virginia Woolf, to name a few) to forge imaginative connections. Entangled in the text-tissue are an assortment of entities, such as bickering body parts, quivering jellyfish, heart pacemaker cells, a narwhal tooth, Taoist parables, always with ubiquitous, stretchy connective tissue—from gooey interstitial fluid to thick planes of fascia—ever present to ensure that the essaying bodies become, what Alfred North Whitehead calls the one-which-includes-the-many-includes-the-one. The essaying bodies orient towards the sweetest sweet spot which is found, not in the center, but slightly askew, felt in the reverbing more-than that carries their potential. Crucially, this produces a shift in perspective away from self-enclosed bodies and experts toward a care for the connective tissue of relation.

Take Her, She's Yours - Eva-Lynn Jagoe (punctum books, 2020)
We say, you belong to me, or I belong to you. But is it possible to be possessed by others? And can we ever possess ourselves? In this raw and intimate account, Eva-Lynn Jagoe merges memoir with critical theory as she recounts the unraveling of everything she thought she knew about selfhood, relationships, and desire. Through the story of an upbringing in a patriarchal Spanish and American household, a dissociative and painful relationship towards men and power, and a chaotic marriage and divorce, she interrogates the destructive fantasy of possessive individualism that permeates our psyches and our cultural expectations. Woven through this narrative is an account of the unique relationship that Jagoe has with her psychoanalyst, in which she works through her tendency to give herself away to others, and learns to navigate the many contradictory selves that we all hold within us. This journey leads her to an enriched understanding of self-possession. Jagoe’s account of an examined life is inseparable from her commitment to the psychoanalytic, feminist, and queer theories that sustain and nourish her in her search for an expanded definition of self. Jagoe’s unique blend of musings and reflections on literature, fairy tale, and culture; her willingness to delve into abjection and contradictory desires; and her honest portrayal of the realities of psychoanalysis allow for a timely exploration of gender, sex, and power. Take Her, She’s Yours belongs in the company of Eve Kosofsky Sedgwick’s A Dialogue on Love and the memoirs of Maggie Nelson, Rachel Cusk, and Lidia Yuknavitch. It engrossingly conveys the lived urgency of critical thinking and the pleasures and perils of embodied selfhood. Take Her, She’s Yours is a story about loss and letting go, but also about the intimacy that emerges through an expanded definition of selfhood.

Tall, Slim & Erect: Portraits of the Presidents - Alex Forman (punctum books, 2023)
After stumbling upon a wooden box containing a complete set of miniature wax mold figurines of US presidents at a flea market, artist Alex Forman began photographing each little man, minus their pedestals. Presented for the first time in book format, Forman’s elegant black and white portraits are accompanied by brief biographies composed entirely of appropriated texts cleverly cut and reassembled by the author. What emerges in Tall, Slim & Erect: Portraits of the Presidents is not the tired tale of legendary men and their mythical quest for democracy, but rather, a gossip’s dream: Jefferson could not ride a horse for months due to boils on his backside; Hayes felt a crazed and tender devotion to his sister Fanny; Wilson remained a virgin until twenty-eight. While playfully shedding light on these powerful men, their quirks, bodily functions, and stained sheets, Tall, Slim & Erect ultimately asks the reader to question how history is written and built on hearsay, conjecture, rumor, and repetition. This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

Tar for Mortar: "The Library of Babel" and the Dream of Totality - Jonathan Basile (punctum books, 2018)
Tar for Mortar offers an in-depth exploration of one of literature’s greatest tricksters, Jorge Luis Borges. His short story “The Library of Babel” is a signature examplar of this playfulness, though not merely for the inverted world it imagines, where a library thought to contain all possible permutations of all letters and words and books is plumbed by pious librarians looking for divinely pre-fabricated truths. One must grapple as well with the irony of Borges’s narration, which undermines at every turn its narrator’s claims of the library’s universality, including the very possibility of exhausting meaning through combinatory processing. Borges directed readers to his non-fiction to discover the true author of the idea of the universal library. But his supposedly historical essays are notoriously riddled with false references and self-contradictions. Whether in truth or in fiction, Borges never reaches a stable conclusion about the atomic premises of the universal library — is it possible to find a character set capable of expressing all possible meaning, or do these letters, like his stories and essays, divide from themselves in a restless incompletion? While many readers of Borges see him as presaging our digital technologies, they often give too much credit to our inventions in doing so. Those who elide the necessary incompletion of the Library of Babel compare it to the Internet on the assumption that both are total archives of all possible thought and expression. Though Borges’s imaginings lend themselves to digital creativity (libraryofbabel.info (http://www.libraryofbabel.info/) is certainly evidence of this), they do so by showing the necessary incompleteness of every totalizing project, no matter how technologically refined. Ultimately, Basile nudges readers toward the idea that a fictional/imaginary exposition can hold a certain power over technology.

Taunting the Useful - Loumille Métros (punctum books, 2024)
In an epoch driven by hyper-consumption and marvelously destructive futility, and in the context of a hegemonic utilitarianism where one goes to university to work rather than to “develop a meaningful philosophy of life,” the concept of the useful is perhaps one most in need of interrogation. Taunting the Useful seeks to unsettle notions of usefulness and uselessness, not merely by deconstructing these terms, but by sidetracking them. It doesn’t reverse things by saying that what is useless is useful. Rather, taunting is teasing, heckling, tickling, scratching the useful. By elaborating a notion of the “virtual useless,” Taunting the Useful seeks to tease the dimensions of wonder, use, and play, through modalities, contingencies, and potentialities of the useless-useful. An experimental book, it (un)does what it tells, and is as much an object taunting and taunted as it is a description of taunting the useful. Includes bonus chapters!

Teaching Myself To See - Tito Mukhopadhyay (punctum books, 2021)
Teaching Myself to See deals with Tito’s struggles to participate in a world full of visual details. As a person with autism, Tito is visually selective, processing the myriad of details seeping in through the eye rather than the whole. Tracing Tito’s experiences to learn to see in his own, “hyper-visual” way, through art, through magazines, through everyday life, Teaching Myself to See is a work of auto-anthropology, capturing in words, sentences, paragraphs, poems, a way of seeing that might seem so bewildering that doctors and psychologists told his mother he wouldn’t be able to think. This book proves otherwise. By teaching us to look through his eyes, Tito shows us the miracle and immense complexity of sight, of neuro-atypicals and neuro-typicals alike.

Television Scales - Nick Salvato (punctum books, 2019)
How to reckon with the staggering volume of television materials, past and present? And how to comprehend all the potential, complex scales at which to grapple with television, from its tiniest units of audiovisual content to its most massive industrial coordinates and beyond? In Television Scales, Nick Salvato demonstrates how the problem of scale in the field of television may be turned into a resource and a method for a television studies that would pay better attention to messy medial complexities, peripatetic critical practices, and vulgar psychogeographies. Modeling his investigative practice on the meta-critical writing of social anthropologist Marilyn Strathern in Partial Connections and elsewhere, Salvato composes surprising, partial constellations of television’s elements. In the process, his consideration ranges from classic television sitcoms like I Love Lucy to contemporary reality series such as The Biggest Loser, Iron Chef, and House Hunters International. He simultaneously pores over a number of key television phenomena, including technological mystification, performers’ charismatic displays, binge viewing, and devoted fandom. An experiment in style and form, Television Scales maps, weighs, and rules television, while also undoing these very strategies for evaluating the medium.

Testing Knowledge: Toward an Ecology of Diagnosis, Preceded by the Dingdingdong Manifesto - Katrin Solhdju; Alice Rivières (punctum books, 2021)
This volume presents the collective adventure of Dingdingdong (https://dingdingdong.org/), the Institute for the Co-production of Knowledge about Huntington’s Disease, founded in 2012 between Paris and Brussels. Katrin Solhdju’s Testing Knowledge: Toward an Ecology of Diagnosis pursues the question of taming the violence of the new species of medical foreknowledge represented by genetic testing. Adopting historical and epistemological perspectives on diagnostic situations, including observations from anthropological field research, speculative storytelling, and ancient oracles, Testing Knowledge proposes a new ecology of predictive diagnostic gestures, which potentially concern us all. Testing Knowledge is preceded by the Dingdingdong collective’s Manifesto (2013), which tells the story of the young Alice Rivières, who in 2006 took the presymptomatic, genetic test, foretelling her that she will eventually develop Huntington’s. Her first-person account of the revelation of her test results, which she experienced as an act of poisoning or cursing, pulls the reader into the manifold ethical, psychological, and existential issues inherent to medical predictions. Testing Knowledge is also preceded by a foreword from Alice Wexler, author of Mapping Fate: A Memoir of Family, Risk, and Genetic Research, and is followed by an afterword by philosopher Isabelle Stengers.

The Afterlife of Genre: Remnants of the Trauerspiel in Buffy the Vampire Slayer - Anthony Curtis Adler (punctum books, 2014)
Could there have been television without California? California without television? The one shows the other: the ostentatiously novel singularity of the place and the seemingly self-effacing transparency of the medium. Yet if television and California both promise again and again to offer us something new, young, immaculate in its transience — a pure surface that will never get caught in the ditch of time — they are also both haunted through and through: by the itinerant contents of the past that they cannot banish, by memories of the infantile-perverse utopian fantasies that taunt us in constant replay (“If you’re going to San Francisco…,” “two girls for every guy”), by the contradiction played out in the very gesture of dismissing history and leaving the dead to bury the dead. California and television, as it were, conspire in a vampirologic: the forever-young is what has been there the longest, what really “takes us back.” And so we also will take ourselves back: to Buffy the Vampire Slayer, already almost charmingly quaint, and Walter Benjamin’s magnum opus The Origin of the German Mourning-Play. What can come of this improbable conjunction? It will not seem too strange that Benjamin, posthumous wanderer across the textures of Americana, should again take up lodging at the Hotel California. But more is at stake than just another hapless visitation from the on high of high theory: reading Buffy as the remediated afterlife of the dead-on-arrival genre of the baroque German mourning play, Adler’s book records the first broken, awkward steps toward a project that, with the recent rise of “quality television,” seems more urgent than ever before: a political-theological characteristic of the television series.

The Angels Won't Help You - M.H. Bowker (punctum books, 2022)
The Angels Won’t Help You is a book about the uniqueness and primacy of help, particularly in relation to care, love, and caritas. It relies heavily on psychoanalytic and philosophical accounts of help and care and finds that help requires the establishment of a real relationship between persons, where help is given and received in a transitional space that is collapsed by care, unity, or love, which are mental constellations that, while profound, remain within the individuals involved. It contains reflections, memoir, and prose poetry, with an emphasis on psycho-philosophical examinations of help. In trying to understand help, especially in the ways that it is not a synonym for care, Bowker turns to diverse sources and topics, including treatments of children in a helpless world, as featured in the literature of Kathy Acker and Jerzy Kosiński, a first-person account of help in psychiatric hospitals, an analysis of the phenomenon of Japanese hikikomori (“shutting oneself in”), anxiety and helplessness, an exploration of the nature of help and helplessness in Wilfred Bion’s “Attacks on Linking,” a rethinking of trauma in light of the circuital structure of the self, and more. Put differently, The Angels Won’t Help You is a cruel helpless hopeless book raised in Texas roped ridden waddled clowned it developed catastrophic methods of coping. Angels’ mama split her tongue and hissed her words like silent / soldier / crisis in the torment of her sunken trailer in the summer where Angels practiced lighting cigarettes with her eyes fetching fireflies making tinctures of dead tissue becoming extraordinarily promiscuous. Angels’ nature was to hide in dark places to ride with abandon to sink in the spurs to gnash silver teeth to kick up tipped boots ruining every square dance. Angels, you make me need like a choke rope dream of being sick from head to foot. You are the petaled froth on every steep lapel. You are original and dilapidated depilatory and inflationary ovulary and delusional. O Angels, the scholars will say I failed to know you address you presage you protect you protest you, but we know the truth.

The Anguished and the Enchanted: "The Little Prince," Revisited - M.H. Bowker (punctum books, 2021)
In The Anguished and the Enchanted, M.H. Bowker offers a lengthy critical essay and richly annotated English translation of a lost Finnish translation of Antoine de Saint-Exupéry’s The Little Prince. Featuring a substantial Translator’s Preface, M.H. Bowker develops a psychoanalytic lens through which to regard Saint-Exupéry’s classic work, offering a more nuanced and less “fable-esque” text than any translation and interpretation to date. On Bowker’s reading, dark and primitive unconscious forces — including neglect and abuse at home, the hatred of maturation and development, the projection of feelings of worthlessness onto others, the creation of an absurd and futile world, and more — infest the story, not unlike the Baobab trees dreaded by the little prince. Those already familiar with The Little Prince will find in The Anguished and the Enchanted a new way of regarding what has perhaps become a favorite or even a beloved book. Those unfamiliar with the original work will discover a sometimes tragic, sometimes sympathetic, sometimes harrowing account of the lengths to which persons will go in their struggle to find — or to escape from — meaningful places for themselves in the world of adults.

The Anthology of Babel - Ed Simon (punctum books, 2020)
Why should there only be literary scholarship about authors who actually lived, and texts which exist? Where are the articles on Enoch Campion, Linus Withold, Redondo Panza, Darshan Singh, or Heidi B. Morton? That none of these are real authors should be no impediment to interpreting their invented writings. In the first collection of its kind, The Anthology of Babel publishes essays by scholars on authors, books, and movements that are completely invented. Blurring the lines between scholarship and creative writing, The Anthology of Babel inaugurates a completely new literary genre perfectly attuned to the era we live in, a project evocative of Jorge Luis Borges, Umberto Eco, and Italo Calvino.

The Ants - Sawako Nakayasu (punctum books, 2025)
The Ants is a study not of, but through, ants. In a dashing sequence of prose pieces, Sawako Nakayasu takes the human to the level of the ant, and the ant to the level of the human. Prima facie, The Ants is a catalogue of insect observations and observations of insects. But the exposé of insect life humbles and disrupts the myopia that is human life, where experience is seen in its most raw and animal form and human “nouveau-ambitious” and “free-thinking” lifestyles become estranged, uncovered, and humbled. Found in dumpling soups and remembered in childhood vignettes, these ants trail through what Nakayasu describes as the “industry of survival,” exploring interfaces of love, ambition, and strategy. The danger is not in sentiment, but rather, in a gash, a wall, an argument, an intention. Is it more lonely to be crushed into the core of a non-mechanical pencil, to be isolated in the safety of home, or to “find” “it” “all” at the very very last moment? The Ants is the distance, the break, and the tenuous wilderness between exoskeleton and endoskeleton, and Nakayasu puts her finger on it, and it, and it. This title is a new and expanded edition released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project, inclduing seventeen additonal bilingual English–Japanese poems from the chapbook Insect Country E: Bilingual Insects.

The Apartment of Tragic Appliances: Poems - Michael D. Snediker (punctum books, 2013)
The Apartment of Tragic Appliances Listed as a Finalist for a 2013 Literary Lambda Award (Gay Poetry)! (http://www.lambdaliterary.org/features/news/03/06/26th-annual-lambda-literary-award-finalists-announced/) The Apartment of Tragic Appliances is a literal place in which a hapless, portable dishwasher “heats residue only to reimagine cleanliness as an art project,” a recalcitrant microwave neglects to heat, and a refrigerator dies an inconvenient, bulky death. It is also that psychic space in which we consider our loneliness, our wandering hearts, our unpacked boxes, our vulgar desires. In Queer Optimism: Lyric Personhood and Other Felicitous Persuasions (Minnesota, 2007), Michael Snediker worked “in the interests of felicity” to undermine the ways in which queer theory customarily privileges shame and melancholy. Here, in his first full-length collection of poetry, he undertakes a similar upending of expectation, acknowledging “gay sadness” but refusing to fall fully under its sway. The demi-tragedies of daily life are recounted by a voice that is variously wistful, giddy, bawdy, silly, and tart. Along the way, Michael Snediker sets off an impressive pyrotechnic display of literary allusion, drawing on the superstars of the Western canon (think: Virgil, Racine, Proust, James, Wharton, Tennessee Williams) and of popular culture (Lucille Ball, John Travolta, Alex Trebek). Buyer beware: In these pages you will not find advice on how to feng shui your duplex or tame a Cuisinart run amok. Instead, you will find something far rarer: a book of poetic sustenance. As Daniel Tiffany observes, “We have been missing poems like these for a long time.”

The Art of Compilation: Manuscripts and Networks in the Early Medieval Latin West - Anna Dorofeeva; Michael J. Kelly (punctum books, 2025)
The Art of Compilation: Manuscripts and Networks in the Early Medieval Latin West interrogates the medieval manuscript book as a dynamic, constantly changing object entangled in intellectual and cultural networks, constructed and deconstructed by different people, and transmuting in form and meaning over time. Medieval manuscripts are not static, permanently bound, and delimited, but rather serve as evidence for the layered relationships between texts and their material supports, and when we realize that, we gain a clearer view of medieval manuscript culture as driven by the agency and intellectual exchange of the people behind it. This volume of essays investigates early medieval Western European manuscript culture as a field of entangled objects, focusing on the connections between knowledge selection, material representation, and scribal agency. The complex road of compiling selected texts into manuscripts (compilatio) in the early Middle Ages is still not well understood, yet it is the key to the historical context surrounding medieval manuscript culture. The practice of knowledge selection consisted of three key stages: the intellectual selection of the textual content of manuscript collections; the pragmatic action of arranging the textual content in a draft form by authors or editors; and the material representation and aesthetic exposition of texts in manuscripts. These stages were part of a linear development, but also exercised reciprocal influence upon one another. By tracing this process in surviving manuscript collections, we can better understand in what practical ways knowledge was encoded and how these often innovative and experimental practices contributed to the emergence and consolidation of intellectual and scribal traditions. This has important implications for how we understand education, reform, and the exercise of power in the early Middle Ages.

The Ballad of the Lone Medievalist - Kisha G. Tracy; John P. Sexton (punctum books, 2018)
Working medievalists are often the only scholar of the Middle Ages in a department, a university, or a hundred-mile radius. While working to build a body of focused scholarly work, the lone medievalist is expected to be a generalist in the classroom and a contributing member of a campus community that rarely offers disciplinary community in return. As a result, overtasked and single medievalists often find it challenging to advocate for their work and field. As other responsibilities and expectations crowd in, we come to feel disconnected from the projects and subjects that sustain our intellectual passion. An insidious isolation even from one another creeps in, and soon, even attending a conference of fellow medievalists can become a lonely experience. Surrounded by scholars with greater institutional support, lower teaching loads, or more robust research agendas, we may feel alienated from our work — the work to which we’ve dedicated our careers. The Lone Medievalist (the collaborative community (https://lonemedievalist.hcommons.org/) and the book) is intended as an antidote to the problem of professional isolation. It is offered in the spirit of common weal that marks the ideals (if not always the realities) of so many of the communities we study — agricultural, professional, national, notional, and of course, monastic. The Ballad of the Lone Medievalist isn’t only about scholarship, or teaching, or institutional life, or the pursuit of new learning — it’s about all of them. The essays in this volume address all aspects of the professional and intellectual life of medievalists. Though many of us acknowledge and address the challenges in being Lone Medievalists, these essays are not intended as voces clamantium; they are offered to provide strategies, camaraderie, and an occasional bit of inspiration. They are a call to action, a sharing of hard-won wisdom, and a helping hand — and, above all, a reminder that we are not alone.

The Before and the After: Critical Asynchrony Now - Sean Gurd; Mario Telò (punctum books, 2025)
Between 2020 and 2021, in the depths of the Covid-19 pandemic, the thirteen authors included in The Before and the After: Critical Asynchrony Now turned to reflections on the late work of Jacques Derrida in an attempt to think through the temporal disjunctions imposed by the global emergency. They found themselves thinking through ideas and philosophical tropes that had been in vogue more than twenty years earlier—as though a deep theoretical nostalgia could somehow rescue them from the moment that beset them. As a belated turn to Derrida’s late work, The Before and the After provides a series of visions of what we might become, in our engagements with the past—both the contemporary and ancient past—in our occupation of every fractured “now.” This book is a document of a moment now largely (hopefully) behind us and an attempt to imagine what remains to come.

The Bodies That Remain - Emmy Beber (punctum books, 2018)
The Bodies That Remain is a collection of bodies and absences. Through biography, experimental essay, interview, fictional manifestation, and poetic extraction, The Bodies That Remain is a collection of texts and images on the bodies of artists and writers who battled with the frustration of their own physicality and whose work reckoned with these limitations and continued beyond them. The essays in The Bodies That Remain look back at how the identities of these bodies were shaped by the spaces around them, through the retelling of memory, through stories told by others, of how their work, processed by their body, made it possible for others to experience sensations – mourning, desire, or a nostalgia that could not belong to another, to another’s body – and in capturing this ability, their work confirms the body’s urgency. Amongst others, The Bodies That Remain tells the story of Emily Dickinson’s decay, the missing grave of Valeska Gert, the voice and sound of the body of Judee Sill, and the derailed body (and work) of Jane Bowles. It questions the absent body but broken organs of JT Leroy as they find themselves scattered across texts, and also interrogates the loss of distinction of illness for Jules de Goncourt as syphilis riddled his nervous system. It retrieves the illusory body of Kathy Acker through dream and through horror, sees the morphing body of Michael Jackson in becoming all of the bodies he was asked to be, and looks toward Sylvia Plath and the language of her own body. Where ‘body’ as a verb makes material something abstract, The Bodies That Remain, as a collection, became bodily.

The Book / Or / The Woods - Jeff T. Johnson (punctum books, 2021)
Here is The Book / Or / The Woods, an epic song cycle that devours itself on repeat, taking cover in its own flames. We think epic in the sense of bpNichol writing Martyrology, Jabès with his books of books, Rosmarie Waldrop’s Curves to the Apple, Keith Waldrop’s Transcendental Studies, Harryette Mullen’s Recyclopedia, Craig Santos Perez’s from unincorporated territory, Nathaniel Mackey’s long song(s), & others. We think epic with these ongoing & collected meta-serial works rather than the traditional notion of the epic as heroic nation building story, though we borrow epic tropes from Dante’s supernal underworld forest (& infernal forested underworld), sing with Sappho’s lyre, are haunted by the spirit of Homer’s katabasis, & are formed by the Popol Vuh’s wordly cosmos, which influenced us before we read it.

The Case of California - Laurence A. Rickels (punctum books, 2026)
Focusing on the changing image of the West Coast through such varied social and cultural artifacts as bodybuilding, group therapy, suicide cults, Marilyn Monroe, milk-carton images of missing children, orgies, Mickey Mouse, zombies, teenage slang, shock therapy, and surf music, The Case of California offers a dizzying psycho-history of the twentieth century as crystallized in the symbolic configuration and “case” of California, which case is articulated in relation to German modernism, National Socialism, and Freudian psychoanalysis. As Laurence Rickels writes, “on the personalizable level or label, California is a death cult; on the social, outward, happy-face level, it distributes pleasure via sadomasochism, the adolescent group, or friendship.” Ultimately, The Case of California excavates the places “California” occupies as concept or placeholder within Freudian psychoanalysis and such systems as the Frankfurt School, East Coast psychoanalysis, and deconstruction. To excavate the full range of “California,” one must apply pressure to a series of adjacent (and often equally marginal or missing) concepts, including group and adolescent psychology, female sexuality, the haunting of music and of mass media at large, the charge of child abuse, and a certain convergence of religious and hysterical conversion. This publication was originally published by University of Minnesota Press in 1991, and is now being released as a new print and open-access edition as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) initiative.

The Christian Economy of the Early Medieval West: Towards a Temple Society - Ian Wood (punctum books, 2022)
The establishment of Christianity in the late- and post-Roman world caused an economic as well as a religious revolution, but while a great deal of attention has been paid to the religious developments of the period, the impact of the establishment of the Church on the economy has attracted remarkably little attention. The Christian Economy of the Early Medieval West: Towards a Temple Society examines the chronology of the Church’s acquisition of wealth, and particularly of landed property, as well as the distribution of its income, in the period between the conversion of Constantine and the eighth century. In this book, the society that emerged as a result of the Church’s acquisition of land is interpreted by Wood in the light of the anthropological model of the “Temple Society,” a concept developed from Karl Marx’s so-called “Asiatic Mode of Production.” The emergence of a socio-economic system dominated by the Church is presented as a crucial development in the history of western Europe.

The Communism of Thought - Michael Munro (punctum books, 2014)
The Communism of Thought takes as its point of departure a passage in a letter from Dionys Mascolo to Gilles Deleuze: “I have called this communism of thought in the past. And I placed it under the auspices of Hölderlin, who may have only fled thought because he was unable to live it: ‘The life of the spirit between friends, the thoughts that form in the exchange of words, by writing or in person, are necessary to those who seek. Without that, we are by our own hands outside thought.’” What, in light of that imperative, is a correspondence? What is given to be understood by the word, let alone the phenomenon? What constitutes a correspondence? What occasions it? On what terms and according to what conditions may one enter into that exchange “necessary,” in Hölderlin’s words, “to those who seek”? Pursuant to what vicissitudes may it be conducted? And what end(s) might a correspondence come to have beyond the ostensible end that, to all appearances, it (inevitably) will be said to have had? And what is the proximity, here, between correspondence and commentary? To what extent might commentary approximate a kind of correspondence? (And with whom? The author of the source text? The source text itself? A future reader of that text? Or then again a third, or fourth, or nth party? And by way of what channels?) The two texts — the two commentaries — that form the heart of The Communism of Thought are both short, late texts of Gilles Deleuze’s, and they’re both reprinted in Two Regimes of Madness: Texts and Interviews, 1975-1995. The first text is Deleuze’s last published article, widely considered to be something of a testament, “Immanence: A Life ….” The commentary is staged in the manner of a dictionary definition of the word immanence. The various subentries under the first (and only) sense of the word for Deleuze — “a life …” — develop in tandem with the article to progressively elaborate the centrality of the problematics of definition to Deleuze’s conception of immanence. The second text is that of a brief, beautiful correspondence: The five letters that comprise the correspondence between Gilles Deleuze and Dionys Mascolo were written between 23 April and 6 October 1988, and were first published a decade later, in 1998, a year after Mascolo’s death and nearly three years after Deleuze’s. The commentary, a kind of marginalia to that correspondence, comes gradually and progressively into focus around a single question: To what affinity might a correspondence attest? “What strikes me especially,” an interviewer once noted to Deleuze, “is the friendship you have for the authors you write about.” “If you don’t admire something,” Deleuze replied, “if you don’t love it, you have no reason to write a word about it.”

The Critique of Digital Capitalism: An Analysis of the Political Economy of Digital Culture and Technology - Michael Betancourt (punctum books, 2016)
Anything that can be automated, will be. The “magic” that digital technology has brought us — self-driving cars, Bitcoin, high frequency trading, internet of things, social networking, mass surveillance, the 2009 housing bubble — has not been considered ideologically. The Critique of Digital Capitalism identifies how digital technology has captured contemporary society in a reification of capitalist priorities. The theory proposed in this book is the description of how digital capitalism as an ideologically “invisible” framework is realized in technology. Written as a series of articles between 2003 and 2015, it provides a broad critical scope for understanding the inherent demands of capitalist protocols for expansion without constraint (regardless of social, legal or ethical limits) that are increasingly being realized as autonomous systems no longer dependent on human labor or oversight and implemented without social discussion of their impacts. The digital illusion of infinite resources, infinite production, and no costs appears as an “end to scarcity,” whereby digital production supposedly eliminates costs and makes everything equally available to everyone. This fantasy of production without consumption hides the physical costs and real-world impacts of these technologies. The critique introduced in this book develops from basic questions about how digital technologies directly change the structure of society: why is “Digital Rights Management” not only the dominant “solution” for distributing digital information, but also the only option being considered? During the burst of the “Housing Bubble” in 2009, why were the immaterial commodities being traded of primary concern, but the actual physical assets and the impacts on the people living in them generally ignored? How do surveillance (pervasive monitoring) and agnotology coincide as mutually reinforcing technologies of control and restraint? If technology makes the assumptions of its society manifest as instrumentality — then what ideology is being realized as the digital computer? This final question animates the critical framework this analysis proposes. Digital capitalism is a dramatically new configuration of the historical dynamics of production, labor and consumption that results in a new variant of historical capitalism. This contemporary, globalized network of production and distribution depends on digital capitalism’s refusal of established social restraints: existing laws are an impediment to the transcendent aspects of digital technology. Its utopian claims mask its authoritarian result: the superficial “objectivity” of computer systems are supposed to replace established protections with machinic function — the uniform imposition of whatever ideology informs the design. However, machines are never impartial: they reify the ideologies they are built to enact. The critical analysis of capitalist ideologies as they become digital is essential to challenging this process. Contesting their domination depends on theoretical analysis. This critique challenges received ideas about the relationship between labor, commodity production, and value, in the process demonstrating how the historical Marxist analysis depends on assumptions that are no longer valid. This book therefore provides a unique, critical toolset for the analysis of digital capitalist hegemonics.

The Dark Posthuman: Dehumanization, Technology, and the Atlantic World - Stephanie Polsky (punctum books, 2022)
The Dark Posthuman: Dehumanization, Technology, and the Atlantic World explores how liberal humanism first enlivened, racialized, and gendered global cartographies, and how memory, ancestry, expression, and other aspects of social identity founded in its theories and practices made for the advent of the category of the posthuman through the dimensions of cultural, geographic, political, social, and scientific classification. The posthuman is very much the product of world-building narratives that have their beginnings in the commercial franchise and are fundamentally rooted in science, governance, and economics around the hegemonic appropriation of environments and commodification of bodies that initially fueled white settler life worlds and continue to be operational in the way we conceive of these worlds as continuous ontological formations. The want has always been for ownership of any of these dimensions of being without regard to condition, to not remain stranded as the subsidiary of another’s being, to another’s claim to humanity, and finally, to escape the suffocating confines of an instrumental ontology that suggests a subcategory of humanity without rights onto itself. The Dark Posthuman distinguishes the posthuman’s place within both the liberal and neoliberal imaginary and reveals how its appearance first entrenched itself through the avarice of English settler colonialism, and subsequently, through the paranoia of American slavery. This same figure of the posthuman played a crucial role in the functional adaptation of Cold War behavioural cybernetics, and thereafter, in the fetishization of technology within the era of global financialization. The shadowing of this arrangement during and beyond the long duration of humanity’s domination of this world becomes the structural web work of this book.

The Death of Conrad Unger: Some Conjectures Regarding Parasitosis and Associated Suicide Behavior - Gary L. Shipley (punctum books, 2012)
The death by suicide of Gary J. Shipley’s close friend, Conrad Unger (writer, theorist and amateur entomologist), has prompted him to confront not only the cold machinery of self-erasure, but also its connections to the literary life and notions surrounding psychological bewitchment, to revaluate in both fictional and entomological terms just what it is that drives writers like Unger to take their own lives as a matter of course, as if that end had been there all along, knowing, waiting. Like Gérard de Nerval, David Foster Wallace, Ann Quin and Virginia Woolf before him, Unger was not merely a writer who chose to end his life, but a writer whose work appeared forged from the knowledge of that event’s temporary postponement. And while to the uninitiated these literary suicides would most likely appear completely unrelated to the suicide behaviors of insects parasitized by entomopathogenic fungi or nematomorpha, within the pages of this short study we are frequently presented with details that allow us to see the parallels between their terminal choreographies. He investigates what he believes are the essentially binary and contradictory motivations of his suicide case studies: where their self-dispatch becomes an instance of necro-autonomy (death as solution to an external thraldom, or the zombification of everyday life as something requiring the most extreme form of emancipation), while in addition being an instance of necro-equipoise (death as solution to an internal thraldom, or the anguish of no longer being able to slip back comfortably inside that very everydayness). The deadening claustrophobia of human life and achieving a stance outside of it: both barbs on the lines that can only ever detail the sickness, never cure it. Through extracts and synopses of Unger’s books, marginalia and underscorings selected from his extensive library, and a brief itinerary of his movements in that last month of exile, a picture of the writer’s suicidal obsession begins to form, and it forms at the expense of the man, the idea eating through his brain like a fungal parasite, disinterring the waking corpse to flesh its words.

The Diary of Anna Comnena, or The Very Political Adventures of a Transgender Byzantine Princess in African Elevators - Tis Kaoru Zamler-Carhart (punctum books, 2024)
In The Diary of Anna Comnena, or The Very Political Adventures of a Transgender Byzantine Princess in African Elevators, Zamler-Carhart impersonates the 12th-century Byzantine princess and historian Anna Comnena as she comes out as trans and tries to write her father’s imperial biography, The Alexiad, while in exile in contemporary West Africa. Outside the Empire, categories become fluid and elevators stop on strange floors. Prose slips into graphic poetry, medieval Christianity into mystical Sahelian Islam, Byzantine chronicles into erotic gore anime. Anna’s first-person diary careens down a series of sinister African elevators and intersectional magic spaces. She is an outcast of the Empire but also a product of it, exploring the dynamics of contemporary African textile production, vernacular theater, animal husbandry, jihad, urban design, television, and coin metallurgy from the perspective of a 12th-century trans Byzantine engineer. The Diary of Anna Comnena initially adopts the same Empire-centric perspective as the historical Alexiad, but the dystopian confrontation with African reality forces Anna to reflect on what it means for her to be specifically in Africa, and not just in a generic outside space. Together with the author’s previous work (https://punctumbooks.com/titles/the-goths-other-stories-2nd-edn/), The Diary of Anna Comnena forms a gelatinous ongoing treatise where seriousness is an emerging property, and the distinction between speculative fiction, design theory, and political philosophy is probably just matter of scale.

The Digital Dionysus: Nietzsche and the Network-Centric Condition - Dan Mellamphy; Nandita Biswas Mellamphy (punctum books, 2016)
Can Nietzsche be considered a thinker of media and mediation, as the German media theorist Friedrich Kittler declared in his influential book Gramophone, Film, Typewriter (http://www.electronicbookreview.com/thread/criticalecologies/future-anterior)? Nietzsche was a truly transdisciplinary thinker, one who never fit into his own nineteenth-century surroundings and who recognized himself as a “herald and precursor” of the future, of our globally-reticulated digital present. Perhaps not since Kittler has there been a study — let alone an anthology — that re-assesses and re-evaluates Nietzsche’s thought in light of the technically mediated and machinic conditions of the human in the age of digital networks. Drawing on the first four years of conference-proceedings from the annual Nietzsche Workshop @ Western (NWW, Western University), which culminated in the “New York NWW.IV”: Cyber-Nietzsche: Tunnels, Tightropes, Net-&-Meshworks (held at the Center for Transformative Media, Parsons The New School for Design), The Digital Dionysus explores Nietzschean themes in light of the problems and questions of digitization, information and technical mediation, offering its readers the opportunity to consider Nietzsche’s contemporary relevance in light of emerging theories in new media studies, political studies, critical aesthetics, the digital humanities and contemporary post-continental philosophy. Co-edited by Dan Mellamphy and Nandita Biswas Mellamphy (Western University, UWO) for the CTM Documents Initiative imprint (Center for Transformative Media, Parsons School of Design, The New School), the volume features essays and works by leading and emerging philosophers, artists, [h]activists, and political media theorists.

The Digital Humanist: A Critical Inquiry - Domenico Fiormonte; Teresa Numerico; Francesca Tomasi (punctum books, 2015)
This book, translated for the first time from Italian into English, offers a critical introduction to the core technologies underlying the Internet from a humanistic perspective. It provides a cultural critique of computing technologies, by exploring the history of computing and examining issues related to writing, representing, archiving and searching. The book raises awareness of, and calls for, the digital humanities to address the challenges posed by the linguistic and cultural divides in computing, the clash between communication and control, and the biases inherent in networked technologies. A common problem with publications in the Digital Humanities is the dominance of the Anglo-American perspective. While seeking to take a broader view, the book attempts to show how cultural bias can become an obstacle to innovation both in the methodology and practice of the Digital Humanities. Its central point is that no technological instrument is culturally unbiased, and that all too often the geography that underlies technology coincides with the social and economic interests of its producers. The alternative proposed in the book is one of a world in which variation, contamination and decentralization are essential instruments for the production and transmission of digital knowledge. It is thus necessary not only to have spaces where DH scholars can interact (such as international conferences, THATCamps, forums and mailing lists), but also a genuine sharing of technological know-how and experience.

The Dream-Slaves - Darieck Scott (punctum books, 2024)
To fight the gods—you must first become a slave. Our universe is dead. All that’s left are memories. But the powers indigenous to the new world are fighting back. Alexander, a handsome immigrant fleeing trouble in his poor native land, doesn’t even have a claim to his own name in the magic-rich city of Norio, where they call him Aleixo. But his name may be the least of what the sorcerers of Norio take from him, when a seemingly random invitation to cater-waiter at a party of the wealthy and famous sweeps Aleixo up into a maelstrom of imperial politics and a millennia-long war between humans and gods. The empire of Norio rules the world because of its monopoly on magical high-tech devices called dream-slaves—and now the head of imperial intelligence has proof that Aleixo isn’t human at all, but a dream-slave assassin, smuggled into Norio by the empire’s enemies. Rescued by a cabal of sorcerers from a foiled attempt to kill him by a renegade sorcerer, Salvador, and his mysterious other-human ally Ydris, Aleixo finds his identity and humanity stripped from him in harrowing psychedelic adventures that transform his memories and bind him to a history of conflict, activating fabulous abilities he never dreamed he had. The world Aleixo lives in isn’t what he’s always believed it was: the forces that rule his destiny are not just economic class, race, gender, sexuality, body, nationality—they are much more sinister, and much more powerful. The greatest powers have secretly colonized his planet, and made its history strangely similar to our own. Aleixo discovers he may be the last line of defense against the dystopian present and future of Earth. He leads the struggle for emancipation as he grapples with who and what he is: is he human, or just a dream?

The End of Man - Jean-Paul Martinon (punctum books, 2013)
Masculinity? The End of Man attempts to answer this one-word question by revisiting key philosophical concepts in the construction of masculinity, not in order to re-write or debunk them again, but in order to provide a radically new departure to what masculinity means today. This new departure focuses on an understanding of sexuality and gender that is neither structured in oppositional terms (masculine-feminine, male-female, man-woman) nor in performative terms (for which the opposition remains always secretly in play), but in a perpendicular relation akin to that which brings space and time together. In doing so, this book doesn’t aim to establish yet another theory within the field of masculism or men’s studies, but to put forward a personal account of how a revised understanding of the relationship between space, time, and gender can thoroughly alter concepts of masculinity.

The Event of Art - Marc Lafia (punctum books, 2020)
The Event of Art is available as an open-access ebook only (no print edition). The Event of Art presents, in fifty-two modular chapters and over eight hundred pages and images, the works of artist Marc Lafia. The book interweaves essays, notes, photographic archives, and a host of exhibitions wherein Lafia traverses his wide body of work and examines how his early strategies of cultural reading of photography and film, of interface, network culture, and social media, transform into an investigation of materiality itself. If his interest was once the way media becomes the message, his interest later becomes the realm of the sensible and the sensate in themselves. Here he presents art as the medium itself, giving us wide permission to explore and examine our deepest feelings and senses, our world and its becoming. The book is introduced by two essays. The first is by curator and art dealer Mathieu Borysevicz, where he recounts meeting Lafia at his first artist residency, and the many projects they would go on to do together. He introduces Lafia’s interest in recording as it becomes digital and computational where “recording is not only memory, and a data structure, but a permutational instrument and ever-changing horizon of iterations.” The other introductory essay is by critic Daniel Coffeen, who writes, “while Lafia may not have a traditional medium – there is no such thing anymore – he does in fact have one consistent medium: imaging making itself, its apparati of creation, consumption, and circulation. In fact Lafia’s medium is the discourse of art – what it is, how it comes to be, how we experience it.” The Event of Art presents the work of art as a complex material and societal event. The event is multiple, a continual becoming of perception, being, materiality, participation, a coming to the senses and the making, shaping and opening to them, not only of one’s self, but the world becoming.

The Fight for Black Liberation: Breaking the Political Strings in the Trump Era - William T. Hoston (punctum books, 2025)
The first presidency of Donald J. Trump further unveiled the calamity of white America’s determination to maintain societal order during a period of landmark racial upheaval. From the restrictive voting measures led by Republicans and conservatives following the 2020 election, to the death of George P. Floyd Jr. and the subsequent Black Lives Matter protests in the summer of 2020, to the January 6, 2021 insurrection, each racial marker continues to show the endurance and even strengthening of white America’s racist traditions alongside its avowed and always unfulfilled commitments to equality for all. The Fight for Black Liberation: Breaking the Political Strings in the Trump Era presents a political critique of the state of Black America in the Trump era, especially when so many Democratic presidents (including Clinton, Obama and Biden) have done so little for Black Americans even while relying on their votes. The book argues that amid continued structural, institutional, and systemic barriers, Black people in America must establish political independence and demand a Black political agenda to chart a path toward a Black Liberation movement. What has hindered the process of reaching a Black Liberation movement has been the assimilationist loyalty of Black Americans to the false constructs of partisanship and ideology, and this book encourages Black eligible voters, of whatever party or other affiliation, to abstain from the two-party system and become an independent voting bloc only willing to give the Black vote to a chosen party in a free partisan market that best represents Black interests. Otherwise, the Black electorate remain frozen in a two-party system that has been built to serve white interests only, even when claiming otherwise, and no amount of assimilation will make a difference.

The Fire Trees - Melissa Matthewson (punctum books, 2026)
The Fire Trees studies the sense experience of the body and mind as it relates to wildness and nature—how do we embrace sensualism, pleasure, and joy as a daily practice in the company of our transience? And when we do, what new awareness might we embrace? How do the places we inhabit or occupy influence our intimacy, relationality, and sexuality? Central to these essays is this exploration of the relationship between the corporeal and the ethereal. As the essays radiate from those core questions, they also investigate queerness as it relates to bisexuality and liberation, negotiating of structure through experimentation with aesthetics, philosophy, criticism, and lyric prose. Subjects range from kinship with and queer ecology of the Siskiyou Mountains, the influence of nature on sexualities, wilderness and beauty, contemporary sex clubs and pleasure houses, historical Roman brothels and graffiti art, bisexuality and the performance of sexuality in nature, an auto-fictional/theoretical story on existential love in opposition to capitalism in the form of a dramatic play, masks and self-portraits as influenced by surrealist photographer Claude Cahun, intimacy as explored through sex and eroticism, and the exploration of psychedelics and sex. bell hooks said of queerness “…queer as not about who you’re having sex with, that can be a dimension of it, but queer as being about the self that is at odds with everything around it and has to invent and create and find a place to speak and to thrive and to live.” With the idea that queerness is about “finding a place to thrive and to live,” and navigating the interplay between self and environment, The Fire Trees explores a kind of relationship with the earth that embodies queer intimacy, complexity, and expansiveness.

The Funambulist Pamphlets - Léopold Lambert (punctum books, 2013)

The Funambulist Pamphlets 10: Literature - Léopold Lambert (punctum books, 2014)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist (http://thefunambulist.net/), collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema. See all published pamphlets HERE (https://punctumbooks.com/?s=funambulist+pamphlets). Volume 10 is devoted to the topic of Literature, with entries by Lambert and other authors. The idea that architecture can be created through narrative is popular in some academic circles. It seems a fruitful approach to the discipline as it unfolds an important imaginative field. It also envisions a resistance to forms of architectural teleology, since fiction is usually based on the disfunction of the environment in which it is set. For this reason, we could go as far as to affirm that fiction operates in contradiction to the traditional design method. The word “literature,” however, is not often pronounced by the people who seem to promote this creative method. The following texts intend to think of literature as a powerful field of ideas that translates to other creative disciplines. This translation should never be literal, and for this reason, some fictions that evoke architecture — Franz Kafka’s and Jorge Luis Borges’s labyrinths, for example — might be paradoxically more difficult to properly translate than less immediately spatial novels. The following texts do not propose any translation of their own but rather offer a humble toolbox in order to do so. This volume also constitutes an opportunity to archive the four texts written for the first event of Archipelagos (Brooklyn, November 2011), an non-institutionalized gathering of people conversing around a given topic. The first event was dedicated to literature and four architects were invited to talk about four authors they chose (Kerouac, Artaud, Dostoevsky and Pessoa) in the first half of the event, while the second half consisted of an open conversation generated by the presentations.

The Funambulist Pamphlets 11: Cinema - Léopold Lambert (punctum books, 2015)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist (http://thefunambulist.net/), collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema. See all published pamphlets HERE (https://punctumbooks.com/?s=funambulist+pamphlets). Volume 11 is devoted to the topic of Cinema: Spike Lee, Béla Tarr, Michelangelo Antonioni and the many other filmmakers named in this volume do not seem to have much in common at first sight; nevertheless, considered through the interpretation of a Spinozist materialist philosophy, their films might have something to say to one another. Take the mud of Red Desert (Antonioni), the volcanic slopes of The Bad Sleep Well (Kurosawa) and the soil of Pina Bausch’s Rite of Spring magnified in Pina (Wenders), for example. What these material manifestations have in common is that they are all in relation with bodies, themselves assemblages of moving matter. Similarly, consider Spike Lee’s dolly shot, Orson Welles’s labyrinth, Béla Tarr’s entropy, and Peter Watkins’s democratic improvisations: they all manifest the power of immanence and its inexorability. These films involve no deus ex machina; everything in them comes ‘from the ground’ in a continuous refusal of a celestial or other form of transcendence. Developing this kind of reading of these films allows us to avoid a traditional chronological reading of history of cinema in favor of another, one more dedicated to the philosophical vision of the world that cinema triggers.

The Funambulist Pamphlets 1: Spinoza - Léopold Lambert (punctum books, 2013)
The blog The Funambulist: Architectural Narratives (http://thefunambulist.net/), a daily architectural platform written and edited by Léopold Lambert (http://www.leopoldlambert.com/), finds its name in the consideration for architecture’s representative medium, the line, and its philosophical and political power when it materializes and subjectivizes bodies. If the white page represents a given milieu — a desert for example — and one comes to trace a line on it, (s)he will virtually split this same milieu into two distinct impermeable parts through its embodiment, the wall. The Funambulist, also known as a tightrope walker, is the character who, somehow, subverts this power by walking on the line. The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist, collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema.

The Funambulist Pamphlets 2: Foucault - Léopold Lambert (punctum books, 2013)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist (http://thefunambulist.net/), collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema.

The Funambulist Pamphlets 3: Deleuze - Léopold Lambert (punctum books, 2013)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist (http://thefunambulist.net/), collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema.

The Funambulist Pamphlets 4: Legal Theory - Léopold Lambert (punctum books, 2013)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist (http://thefunambulist.net/), collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema.

The Funambulist Pamphlets 5: Occupy Wall Street - Léopold Lambert (punctum books, 2013)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist (http://thefunambulist.net/), collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema.

The Funambulist Pamphlets 6: Palestine - Léopold Lambert (punctum books, 2013)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist (http://thefunambulist.net/), collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema.

The Funambulist Pamphlets 7: Cruel Designs - Léopold Lambert (punctum books, 2013)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist (http://thefunambulist.net/), collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema.

The Funambulist Pamphlets 8: Arakawa + Madeline Gins - Léopold Lambert (punctum books, 2014)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist (http://thefunambulist.net/), collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema. See all published pamphlets HERE (https://punctumbooks.com/?s=funambulist+pamphlets). Volume 8 is dedicated to The Reversible Destiny Foundation created by Arakawa and Madeline Gins. The Foundation is much more than an architectural practice. It articulates art, philosophy, poetry, architecture and, to some extent, science in a dialogue that benefits each of these disciplines and ultimately serves one of the most radical ideas that apply to architecture: the action of non-dying. Guest authors include Shingo Tsuji, Stanley Shostak, Russell Hughes, and Jean-François Lyotard.

The Funambulist Pamphlets 9: Science Fiction - Léopold Lambert (punctum books, 2014)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist (http://thefunambulist.net/), collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema.

The Funambulist Papers - Léopold Lambert (punctum books, 2013)

The Funambulist Papers, Volume 1 - Léopold Lambert (punctum books, 2013)
This book is a collection of thirty-five texts from the first series of guest writers’ essays, written specifically for The Funambulist (http://thefunambulist.net/) weblog from June 2011 to November 2012. The idea of complementing Lambert’s own texts on his blog with those written by others originated from the idea that having friends communicate with each other about their work could help develop mutual interests and provide a platform to address an audience. Thirty-nine authors of twenty-three nationalities were given the opportunity to write essays about a part of their work that might fit with the blog’s editorial line. Overall, two ‘families’ of texts emerged, collected in two distinct parts in this volume. The first part, The Power of the Line, explores the legal, geographical and historical politics of various places of the world. The second part, Architectural Narratives, approaches architecture in a mix of things that were once called philosophy, literature and art. This dichotomy represents the blog’s editorial line and can be reconciled by the obsession of approaching architecture without care for the limits of a given discipline. This method, rather than adopting the contemporary architect’s syndrome that consists in talking about everything but being an expert in nothing, attempts to consider architecture as something embedded within (geo)political, cultural, social, historical, biological, and dromological mechanisms that widely exceed what is traditionally understood as the limits of its expertise.

The Funambulist Papers, Volume 2 - Léopold Lambert (punctum books, 2015)
This book is the second volume of texts curated specifically for The Funambulist (http://thefunambulist.net/) since 2011. The editorial line of this second series of twenty-six essays is dedicated to philosophical and political questions about bodies. This choice is informed by Léopold Lambert’s own interest in the (often violent) relation between the designed environment and bodies. Corporeal politics do not exist in a void of objects, buildings and cities; on the contrary, they operate through the continuous material encounters between living and non-living bodies. Several texts proposed in this volume examine various forms of corporeal violence (racism, gender-based violence, etc.). This examination, however, can only exist in the integration of the designed environment’s conditioning of this violence. As Mimi Thi Nguyen argues in the conclusion of this book’s first chapter, “the process of attending to the body — unhooded, unveiled, unclothed — cannot be the solution to racism, because that body is always already an abstraction, an effect of law and its violence.” Although the readers won’t find indications about the disciplinary background of the contributors — the “witty” self-descriptions at the end of the book being preferred to academic resumés — the content of the texts will certainly attest to the broad imaginaries at work throughout this volume. Dialogues between dancers and geographers, between artists and biohackers, between architects and philosophers, and so forth, provide the richness of this volume through difference rather than similarity. The Funambulist Papers are published by the CTM Documents Initiative imprint, Center for Transformative Media (http://ctm.parsons.edu/), Parsons School of Design, The New School. CTM is a transdisciplinary media research initiative bridging design and the social sciences, and dedicated to the exploration of the transformative potential of emerging technologies upon the foundational practices of everyday life across a range of settings.

The Gentrified City of God: Queer & Medieval New York, from 9/11 to COVID-19 - A.W. Strouse (punctum books, 2026)
The United States is a spiritual wasteland—a two-party dictatorship that worships money and that eats human beings alive, where racial and gender oppression attack the body, and where partisan polarization stifles the mind. In this dreary context, A.W. Strouse pursues a life of sin and salvation. As a queer scholar of the Middle Ages and a promiscuous gay Catholic in New York City, Strouse takes Saint Augustine as a guide for turning the personal confession into a critical meditation on gentrified urban space. The Gentrified City of God narrates Strouse’s own spiritual quest in order to develop a queer-medievalist lens for understanding how white Christian nationalism is turning urban space into a puritanical discipline of moralistic detachment. Mixing first-person confession with cultural criticism, Strouse tours through gentrified spaces—gay bathhouses, Brooklyn ghettos, demolished Churches, and corporate universities—exploring how sex and spiritually intersect, in art and architecture, poetry and public policy. By closely examining the city from a first-person, queer-medieval vantage—communing with St. Patrick’s Cathedral, the HIV/AIDS Memorial, and St. Vincent’s Hospital, along with rap lyrics, Donald Trump, and paintings by Kehinde Wiley, and even folding in Strouse’s own bad romances and precarious academic labor conditions—The Gentrified City of God seeks to uncover a secret redemption that may yet lie within the brokenness of U.S. society, and to probe the mysteries of good and evil that reside within the heart of New York City.

The Getty Fiend - Ken White (punctum books, 2024)
The Getty Fiend, a contemporary medieval melodrama set in Los Angeles’s Getty Museum, takes the reader on a tour filled with rock stars and warrior-kings, werewolves and archivists, sartorial Huns and libertine saints, all seen through the keenly dramatic flair of a collector’s eye. A cinematic and labyrinthine take on pulp horror, Ken White’s screenplay-in-verse is a monster mash-up of forms and languages, facades and carnal catastrophes, archaic languages and misplaced rhetorics — a campy, fantastical gender-bending transformation into the inadvertently divine. This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

The Goths & Other Stories - Sasha Kaoru Zamler-Carhart (punctum books, 2020)
In the winter of 476 AD, the Ostrogoths, hungry and exhausted from wandering for months along the barren confines of the Byzantine Empire, write to Emperor Zeno in Constantinople requesting permission to enter the walled city of Epidaurum and just kinda crash and charge their phones. Closer to home, Orpheus walks Eurydice through a suburban refrigerator, Abidjan has 12,756 streets with no way to go from one to another, and the poetics of car accidents, capitalist consumption, and anarchist terrorism unfold at a Southern California car dealership. Readers of all centuries will feel at home in this book, as an apocalypse of tax law and classical mythology quietly descends upon their living room and reveals a medieval theology of design, theater, and light. The Goths & Other Stories is a collection of short works at the intersection of prose fiction, experimental poetry, philosophy, and design theory. The book’s six stories are set in different times and places—sometimes within the same narrative—but have in common a slippery approach to the boundaries between fiction and theory, between ontological planes, between the comical and the moral. Together they also form a treatise on the nature of writing as a branch of design—one whose medium is easier to reveal than to define.

The Goths & Other Stories - Tis Kaoru Zamler-Carhart (punctum books, 2023)
In the winter of 476 AD, the Ostrogoths, hungry and exhausted from wandering for months along the barren confines of the Byzantine Empire, write to Emperor Zeno in Constantinople requesting permission to enter the walled city of Epidaurum and just kinda crash and charge their phones. Closer to home, Orpheus walks Eurydice through a suburban refrigerator, Abidjan has 12,756 streets with no way to go from one to another, and the poetics of car accidents, capitalist consumption, and anarchist terrorism unfold at a Southern California car dealership. Readers of all centuries will feel at home in this book, as an apocalypse of tax law and classical mythology quietly descends upon their living room and reveals a medieval theology of design, theater, and light. The Goths & Other Stories is a collection of short works at the intersection of prose fiction, experimental poetry, philosophy, and design theory. The book’s six stories are set in different times and places—sometimes within the same narrative—but have in common a slippery approach to the boundaries between fiction and theory, between ontological planes, between the comical and the moral. Together they also form a treatise on the nature of writing as a branch of design—one whose medium is easier to reveal than to define.

The Great Awakening: New Modes of Life amidst Capitalist Ruins - Anna Grear; David (0002-3913-3930) Bollier (punctum books, 2020)
As we enter a time of climate catastrophe, worsening inequality, and collapsing market/state systems, can human societies transcend the old, dysfunctional paradigms and build the world anew? There are many signs of hope. In The Great Awakening, twelve cutting-edge activists, scholars, and change-makers probe the deep roots of our current predicament while reflecting on the social DNA for a post-capitalist future. We learn about seed-sharing in agriculture, blockchain technologies for networked collaboration, cosmolocal peer production of houses and vehicles, creative hacks on law, and new ways of thinking and enacting a rich, collaborative future. This surge of creativity is propelled by the social practices of commoning new modes of life for creating and sharing wealth in fair-minded, ecologically respectful ways. It is clear that the multiple, entangled crises produced by neoliberal capitalism cannot be resolved by existing political and legal institutions, which are imploding under the weight of their own contradictions. Present and future needs can be met by systems that go beyond the market and state. With experiments and struggle, a growing pluriverse of commoners from Europe and the US to the Global South and cyberspace are demonstrating some fundamentally new ways of thinking, being and acting. This ontological shift of perspective is making new worlds possible.

The Guerrilla Is Like a Poet: Ang Gerilya Ay Tulad ng Makata - Jose Maria Sison (punctum books, 2013)
This book is titled after the world-renowned poem of Jose Maria Sison, “The Guerrilla Is Like a Poet,” which celebrates with natural imagery and in a lyrical way the Filipino people’s revolutionary struggle for national liberation and democracy against foreign and feudal oppression and exploitation. The book contains poems from Sison’s Prison and Beyond, which won the Southeast Asia WRITE Award, as well as new poems that further develop the theme of struggle for national and social liberation as well as exile. It also carries articles of creative writers on the significance and relevance of his poetry. Sison is a Filipino revolutionary with extensive guerrilla experience and has been a recognized poet since his student days at the University of the Philippines. The publication of this book has been sparked by the effort of the Academy for Cultural Activism of the New World Summit to present the people’s culture in the national democratic struggle in the Philippines.

The Hegemony of Psychopathy - Lajos Brons (punctum books, 2017)
Any social and political arrangement depends on acceptance. If a substantial part of a people does not accept the authority of its rulers, then those can only remain in power by means of force, and even that use of force needs to be accepted to be effective. Gramsci called this acceptance of the socio-political status quo “hegemony.” Every stable state relies primarily on hegemony as a source of control. Hegemony works through the dissemination of values and beliefs that create acceptance and that serve the interests of the state and/or the ruling elite (the “hegemones”). Hegemony is most efficient if it remains invisible. A key hegemonic belief is the idea that there is no alternative to the current socio-political status quo or that the way things are is “natural.” The current hegemony – that is, the set of values and beliefs that bolster the current socio-political status quo – is a hegemony of psychopathy: it promotes “cultural psychopathy” and destroys empathy and compassion, thus threatening everything that makes us human. The hegemony of psychopathy is responsible for massive human suffering. It must be fought and replaced with a counter-hegemonic set of values and beliefs that promote compassion and care. Fighting hegemony requires fighting the “pillars” that support it. Most important among these are the mass media and culture industry, and mainstream economics. The former is responsible for a continuous stream of hegemonic propaganda; the latter – among others – for providing a pseudo-scientific justification for the false belief that there is no alternative. The Hegemony of Psychopathy concludes with some considerations on tactics and strategy in the struggle against the hegemony of psychopathy, but does not – and cannot – offer any concrete advice.

The Humid Condition: (More) Overheated Observations - Dominic Pettman (punctum books, 2020)
A Zibaldone for the Twitter age. An Anatomy of Mischievous Melancholy. A Commonplace book of uncommon opinions An avalanche of apposite apercus. An inventory of inappropriate malaproprisms. The Humid Condition continues on the clicking heels of Dominic Pettman’s Humid, All Too Humid (https://punctumbooks.com/titles/humid-all-too-humid/) (2016), providing a companion volume of pithy and witty observations for our overheated age. Covering topics from pop culture to academia to romance to politics to human mortality to everything in between, this collection of pointed musings aims to amuse, edify, instruct, provoke, tease, caution, and inspire. As with the first installment, the spirit of this book represents a fusion of Montaigne and Wilde; a mashup of Adorno and Yogi Berra; a parallel channeling of Marx and Marx (both Karl and Groucho). No doubt, Hannah Arendt would be appalled at the irreverence on display within these pages. Then again, “Heidegger has left the bildung.” And as the author himself notes: “I have nothing new to say. And I’m saying it!”

The Imagery of Interior Spaces - Dominique Bauer; Michael J. Kelly (punctum books, 2019)
On the unstable boundaries between “interior” and “exterior,” “private” and “public,” and always in some way relating to a “beyond,” the imagery of interior space in literature reveals itself as an often disruptive code of subjectivity and of modernity. The wide variety of interior spaces elicited in literature — from the odd room over the womb, secluded parks, and train compartments, to the city as a world under a cloth — reveal a common defining feature: these interiors can all be analyzed as codes of a paradoxical, both assertive and fragile, subjectivity in its own unique time and history. They function as subtexts that define subjectivity, time, and history as profoundly ambiguous realities, on interchangeable existential, socio-political, and epistemological levels. This volume addresses the imagery of interior spaces in a number of iconic and also lesser known yet significant authors of European, North American, and Latin American literature of the nineteenth, twentieth, and twenty-first centuries: Djuna Barnes, Edmond de Goncourt, William Faulkner, Gabriel García Márquez, Benito Pérez Galdós, Elsa Morante, Robert Musil, Jules Romains, Peter Waterhouse, and Émile Zola.

The Jews - Nachoem M. Wijnberg (punctum books, 2016)
The Jews is an anti-historical thriller in the form of a Talmudic tragicomedy, taking place sometime during the Second World War. Stalin and his Minister of Security Beria are worried about the political developments in Germany, where Martin Heidegger has replaced Adolf Hitler as Chancellor of the Third Reich. Suspecting that the Frankfurt School, headed by Vice-Chancellor Walter Benjamin, has masterminded this takeover, he dispatches two Jewish actors, Salomon Maimon and Natalia Goncharova, to investigate the situation in the hope of uncovering the extent of the Jewish conspiracy. Upon arrival in Berlin, Maimon and Goncharova are received by Benjamin, who introduces them to Heidegger. The latter has stopped speaking to anyone except his mother since his rise to power, and Benjamin holds long speeches on the history of theater, the law, God, the royal gods and the old goddesses. Eventually, prodded by his mother, Heidegger marries Goncharova, surrounded by a merry audience. The novel ends on a plain somewhere between Moscow and Berlin, where the final battle for Jerusalem is being waged. In front of the entrance of a camp, Maimon and Benjamin are joined by a group of old Jews arriving by train, bringing the news of Stalin’s death by circumcision. They reenact scenes from the Old Testament while Jerusalem is burning. Did the world to come finally arrive?

The Map and the Territory - Michael Munro (punctum books, 2021)
“I didn’t even know that was a question I could ask.” That remark from a student in an introductory philosophy course points to the primary body of knowledge philosophy produces: a detailed record of what we do not know. When we come to view a philosophical question as well-formed and worthwhile, it is a way of providing as specific a description as we can of something we do not know. The creation or discovery of such questions is like noting a landmark in a territory we’re exploring. When we identify reasonable, if conflicting, answers to this question, we are noting routes to and away from that landmark. And since proposed answers to philosophical questions often contain implied answers to other philosophical questions, those routes connect different landmarks. The result is a kind of map: a map of the unknown. Yet when it comes to the unknown, and all the more so to its cartography, might it not make sense to take our orientation from Borges: What’s in question here, with respect to philosophical questions, is an incipient, unlocalizable threshold—a terrain neither subjective, nor entirely objective, one neither of representation, nor finally of simple immediacy—there where the map perceptibly fails to diverge from the territory. Amid Inclemencies of weather and fringed, as per Borges, with ruin and singular figures—with Animals and Beggars—what’s enclosed is an attempt to chart the contours of this curious immanence.

The Mediterranean Question - Iain Chambers; Marta Cariello (punctum books, 2025)
Whose Mediterranean are we talking about? What languages are most appropriate to its reception and understanding? With two-thirds of the Mediterranean constituted by the histories and cultures of its African and Asian shorelines and hinterlands, and its principal spoken language being Arabic – in all its variants and dialects – then the Mediterranean clearly exceeds the Western frame of explanation. Without pretending to speak for or in the name of these ignored and repressed dimensions, The Mediterranean Question explores the resulting gaps of a Mediterranean reduced to a European and Western mirror by listening and attending to some of those other histories, cultures, and lives. How to puncture prevalent European understandings of the Mediterranean? The colonizing impulse inscribed in Western historiography cannot be undone simply by adding previously repressed and unacknowledged histories. Instead, a re-examination of the premises and procedures that produced such exclusions leads to a valuable change in coordinates. An order of knowledge that creates subaltern objects of study to reconfirm European centrality and subjectivity is interrogated. Insisting on a politics of registration and listening, further critical incentives drawn from the trans-local dissemination of literature, music, cinema, and the visual arts can be deployed to query existing representations. In this more ragged and open series of maps, there lies no complete picture but rather a challenge to the violence of existing explanations. Insisting that present-day knowledge is sustained in asymmetrical relations of power, The Mediterranean Question promotes a reconfiguration of historical archives and cultural ties, casting a critical light on the deeper histories that have made the Mediterranean, Europe, and Western modernity. Proposing a series of intersecting analyses that underline the colonial constitution of the present and its mobile and creolized formation, Chambers and Cariello seek to establish new coordinates for thinking and practicing the possibilities of another Mediterranean.

The Miracle of Saint Mina – Gis Miinan Nokkor - El-Shafie El-Guzuuli; Vincent W.J. van Gerven Oei (punctum books, 2012)
The Miracle of Saint Mina is one of the core texts in the small corpus of texts written in Old Nubian, a Nilo-Saharan language spoken between the third and fourth cataract of the Nile river until about the fifteenth century, and written in an adaptation of the Coptic script. It is one of the oldest written indigenous African languages. The Miracle of Saint Mina, most probably written around 1000 A.D., is a classical miracle story featuring one of the most well-known Egyptian saints. This publication features a translation of the text into one of the remaining modern Nubian languages, Dongolawi-Andaandi, by El-Shafie El-Guzuuli, thus establishing for the first time a link between the Old Nubian literary heritage and the contemporary colloquial language. The Old Nubian is also accompanied by a revised translation to English and a grammatical analysis.

The Negated Institution: Report from a Psychiatric Hospital - Franco Basaglia (punctum books, 2025)
The Negated Institution: Report from a Psychiatric Hospital was first published in 1968 in Italian and caused an immediate sensation. It was an instant bestseller and was translated into numerous languages, but never into English. Edited by the Venetian psychiatrist Franco Basaglia, the book is a collection of writings, interviews, and debates which tell the story of the transformation of the Psychiatric Hospital in Gorizia, on the northeast border of Italy, into an open and “negated” institution. This story of an historically unique process of de-institutionalization—with the elimination of walls and barriers, the humanization of the hospital, the introduction of debates and meetings, the unlocking of wards, and the questioning of the very basis of all psychiatric hospitals—struck a nerve with the student and worker movements of 1968. It also gave a voice to the patients themselves, telling their stories of violence but also of liberation. The Negated Institution was highly sensitive to the contradictions of this project of opening up and negation, and called for the abolition of the entire system of psychiatric asylums, as well as new ways of understanding and contextualising mental illness and mental health. It led to debates in many countries within and outside of psychiatry and played a part in the 1978 “Basaglia law,” which eventually closed down the entire psychiatric hospital system in Italy—the first example of such total closure in the world, which endures to our contemporary moment. This is the first translation into English of this seminal text. The translator, John Foot, is an expert in the life and work of Franco Basaglia and has added notes and a critical introduction.

The Non-Library - Trevor Owen Jones (punctum books, 2014)
The Non-Library is a non-standard expression for life that is lived without mediation from words, images, or even ideas. While a thing called “the Library” continues to terrorize humanity even as it enters its last stages as a consequence of cataclysmic climate change and late capitalism, the Non-Library is a strictly performative, ahistorical immanence that suspends the Library’s insistent calls to categorization, representation, and reification. Of course, to describe or circumscribe such ineffability has its limits, but it also has its thresholds to cross: with commentary on Derrida’s Archive Fever, a deconstruction of Fichte, a para-biographical meditation on librarianship, and a vamping on the possible “Non-Virgil,” The Non-Library gently proposes a negative capability in liminal spaces in order to best escape and resist the Library’s stranglehold on human knowledge and its requisite social imaginations.

The Ohiomachine - Mike Templeton (punctum books, 2026)
Ohio is the geographical no-place that you fly over to get from one coast to the other. Wedged into a vast geographical space known simply as “the American Midwest,” Ohio is a flat, dull, boring space in which someone—no one knows who—grows corn. It is just a dull place where nothing interesting happens. Yet, Ohio is stranger than one might imagine and more significant than one might like to admit. It is a land of cannibals and the children of the corn, ancient kingdoms brought down by incest and murder. Ohio is the substrate on which global Empire functions, and it brings the world the magic of the alchemist from the cornfield to the gas tank. The Ohiomachine is an exploration of the ways that Ohio has become the empty vessel of global capital while the people of the state have become near throwaways to the spectacular world of the image, twenty-first-century despair, and a quiet but deranged sense of being the most ordinary of all the ordinary people on Earth, and also the most virtuous by being the most ordinary. From the corn fields that fuel petrochemical industrial power, to the cowering civil warriors lost amid the forgotten small towns, and into the cities where the simulations of life manufactured by the culture industry have separated and atomized people according to their credit scores and criminal background checks, Ohio is the vacuous substrate of global capital and its digital imaginary.

The Old Nubian Language - Eugenia Smagina (punctum books, 2017)
Eugenia Smagina (Евгeния Б. Смaгина) first published her grammar of the Old Nubian language in 1986 in Russian. For more than thirty years the work has remained untranslated, even though the late Gerald M. Browne affirmed that “this lucid, well-argued presentation should be available to all Nubiologists and ought therefore be translated into a western language.” Slavicist José Andrés Alonso de la Fuente has prepared a first English translation of this concise but indispensable work, which forms a necessary counterpart to Browne’s classic Old Nubian Grammar. The grammar is divided into sections on script, lexicon, morphology, and syntax, and is followed by the analysis of a sample text, known as The Miracle of St. Mēnas. Smagina’s The Old Nubian Language provides an excellent first introduction into the grammar of this medieval Nilo-Saharan language.

The Old Nubian Texts from Attiri - Vincent W.J. van Gerven Oei; Vincent Pierre-Michel Laisney; Giovanni Ruffini; Alexandros Tsakos; Kerstin Weber-Thum; Petra Weschenfelder (punctum books, 2016)
The Old Nubian Texts from Attiri is the first publication in the Dotawo: Monographs series. It presents heretofore unpublished material: an edition of a series of manuscripts discovered during the Aswan High Dam campaign (https://link.springer.com/article/10.1007/s10437-007-9018-5) at the site of Attiri, a rocky island in the Batn el-Hajjar region in Sudan, and does so in an innovative way, through an intensive collaboration of the editors under the name of the Attiri Collaborative. By bringing together their diverse backgrounds in linguistics, archeology, Bible studies, history, anthropology, and philology, the editors hope to have provided an example of a new model of collective manuscript editing and the results such collaboration can attain. The collection consists of 15 manuscript fragments that were all written in Old Nubian. Among these manuscripts special mention should be made of two parchment leaves from a codex dedicated to works on the Archangel Michael, a lectionary containing fragments from the Gospel of Matthew and the Second Letter to the Corinthians, as well as a rare letter written on a leather sheet.

Theory Is Like a Surging Sea - Michael Munro (punctum books, 2015)
In a 1917 letter to Gershom Scholem, Walter Benjamin writes, “Theory is like a surging sea.” This small book takes more than its title from that line—it takes that line as a point of departure in Erich Auerbach’s sense, an Ansatzpunkt, as a compositional principle so that what follows can be read in its entirety as a gloss on the remainder of Benjamin’s sentence: “Theory is like a surging sea, but the only thing that matters to the wave […] is to surrender itself to its motion in such a way that it crests and breaks.” That motion, in the pages to follow, takes up in its sweep two threads: it folds an episodic meditation on the negative and the problematic into a series of singular interrogations exemplary of the positive being of the problematic, the objective being of problems and questions, in a movement of implication and explication between poetry and philosophy in the tradition of what’s come to be known as theory. Theory is like a surging sea because it’s as part of a revolutionary tradition that it crests and breaks.

The Pandemic Visual Regime: Visuality and Performativity in the Covid-19 Crisis - Julia Ramírez-Blanco; Francesco Spampinato (punctum books, 2023)
The Covid-19 pandemic has been expressed in various ways through visuality and performance, and some of its more nuanced cultural implications have taken place in a realm that goes beyond words. Through the exploration of the visual culture produced during and in response to the Covid-19 pandemic, The Pandemic Visual Regime: Visuality and Performativity in the Covid-19 Crisis highlights the key role played by images in shaping our understanding of the epochal transformations our society is undergoing. This book argues that visuality and its relationships with the performative have played such a significant role in the Covid-19 pandemic that we can even speak of the emergence of a “pandemic visual regime,” a new way of seeing and representing the world under this global emergency. Through an interdisciplinary framework, The Pandemic Visual Regime aims to answer an array of questions: In which ways have the effects of the pandemic been racialized, thereby reinforcing white supremacy? How are our responses to Covid-19 shaped by the Hollywood “outbreak narrative” of films such as Contagion? How has design responded to our new pandemic needs? How have infographics affected our perception? In which new ways have we come to inhabit private, public, and virtual spaces? Regarding the latter, what changes have there been in the forms of digital surveillance? On the other side of the spectrum, what forms has mutual aid taken and what have been our forms of relating with nature, both during lockdown and after lockdown was over? All these questions open the field to rethinking the visuality of our post-pandemic zeitgeist.

The Parasocialists: React Streamers, Video Essayists, Debate Bros, Podcasters, and the Cultural Politics of the Online Left - Liam Mitchell (punctum books, 2027)
Good, accessible political commentary has always been hard to come by, but the situation today seems worse than ever. Mainstream media is pure propaganda, alternative media remains resolutely alternative, and the once-wide expanse of social media has been narrowed to a handful of platforms governed by attention-maximizing algorithms that reward no one more than the grifting reactionaries of the new right. But these same platforms have been incubating a powerful undercurrent of dissent. YouTubers, Twitch streamers, debate bros, politigram radicals, dirtbag podcasters, Twitter shitposters, and Discord goblins are pumping out leftist content that is quietly reshaping political discourse on the internet and beyond. Largely if not entirely unbound by politeness, decorum, tradition, institutions, professionalism, and profit motive, the amateur content creators of the online left are speaking truth to power while attracting audiences as diverse as they are themselves. In The Parasocialists: React Streamers, Video Essayists, Debate Bros, Podcasters, and the Cultural Politics of the Online Left, Liam Mitchell takes an ethnographic and theoretical approach to the mediated populism of the online left. Spotlighting four of its better-known figures – Hasan Piker, ContraPoints, Vaush, and Chapo Trap House – but branching out to lesser-known ones, he reads the online left as a multivalent cultural phenomenon unified in response to its great enemy, fascism. It is, in this response, an index of the various violences wrought by the right, a comprehensible, collectively constructed map of the modern world.

The Passenger: Medieval Texts and Transits - James L. Smith (punctum books, 2017)
What strange transactions take place in the mobile spaces between loci? How does the flow of forces between fixed points enliven texts, suggest new connections, and map out the dizzying motion of myriad interactions? The essays in this volume were first presented at the 2014 New Chaucer Society Congress in Reykjavik, Iceland where a meeting of minds in a shared intermediate space initiated dialogue from diverse perspectives and wended its way through the invisible spaces between concrete categories, objects, and entities. The resulting volume asks a core question: what can we learn by tarrying at the nexus points and hubs through which things move in and out of texts, attempting to trace not the things themselves or their supposedly stable significations, but rather their forms of emergence and retreat, of disorder and disequilibrium? The answer is complex and intermediate, for we ourselves are emerging and retreating within our own systems of transit and experiencing our own disequilibrium. Scholarship, like transit, is never complete and yet never congeals into inertia. Through the manifold explorations of the dynamic transit, transports, scapes, and flows found within literary—and Chaucerian—thought-worlds, new vistas of motion and motivation emerge. Following John Urry’s mobile sociology, the volume advances the notion that we can no longer view either social worlds or textual worlds as uniform surfaces upon which one can trace or write a history of the horizontal movements of humans and human mentalities; rather, everything is in constant motion: objects, images, information/ideas, and mobility is thus also vertical, involving human and non-human actants. Ranging from the “black box” of human corporeality to the peregrinations of traveling hearts to literary physics, animal vehicles, didactic eagles, liquid landscapes, and beyond, the essays in this volume consider how medieval texts and objects rewarp time and space by the means of sophisticated transit and transport structures, where medieval cultural objects themselves emerge as transit systems in which we can glimpse the mobility of objects, figures, mentalities, tropes, and other “matter” in vibrant intermediate networks. Motive entities within literature twist and turn, interact and collide, and destabilise predictable trajectories with unpredictable vigor.

The Pedagogics of Unlearning - Éamonn Dunne; Aidan Seery (punctum books, 2016)
What does it mean to unlearn? Once we have learned something, is it ever possible to unlearn that something? If something is said to have been unlearned, does that mean that it is simply forgotten or does some residual force of learning, some perverse force, also resonate in ways that might help us to rethink traditional approaches to teaching and learning? Might we say that education today is haunted by the spectre of unlearning? This book invites readers to reflect on the possibilities of knowing, reflecting, understanding, teaching and learning in ways that allow us to imagine the other side of education, the side which understands non-knowledge, ignorance, stupidity and wonder as potentially the most important learning experiences we can ever have. In a series of provocative essays by some of the world’s most renowned theorists in philosophy, psychoanalysis, cultural studies, politics and education, The Pedagogics of Unlearning challenges us to think again about what we mean when we talk about learning — about what it really means to learn — and whether the kinds of learning we imagine in our classrooms and daily lives are actually synonymous with the sort of learning we envision when we think and talk about the purpose and passage of education. If you think you know what education and learning are doing, what teaching strategies do, and what learning outcomes are, then this book asks you to think again, to unlearn what you have learned, to learn to unlearn.

The Penetrated Male - Jonathan Kemp (punctum books, 2013)
Through nuanced readings of a handful of modernist texts (Baudelaire, Huysmans, Wilde, Genet, Joyce, and Schreber’s Memoirs), this book explores and interrogates the figure of the penetrated male body, developing the concept of the behind as a site of both fascination and fear. Deconstructing the penetrated male body and the genderisation of its representation, The Penetrated Male offers new understandings of passivity, suggesting that the modern masculine subject is predicated on a penetrability it must always disavow. Arguing that representation is the embodiment of erotic thought, it is an important contribution to queer theory and our understandings of gendered bodies.

The Perfect Mango - Erin Manning (punctum books, 2019)
In 1994, at the age of twenty-five, when the “terrible brokenness that comes with sexual assault” was folded deep within her body and thoughts of suicide were always close by, Erin Manning wrote The Perfect Mango at an almost feverish pitch: nineteen chapters in nineteen days, a sort of self-rescue operation, where writing became a form of making (and feeling) life otherwise. Throughout those nineteen days, and although not able to fully articulate it to herself at the time, Manning wrote her way into a “composition that asks how else life might be lived.” And in the rhythms of that composition, which was also a living, Manning was, and is, able to refuse the category and norm and stillness of “victim” (while still understanding the inheritances of violence) in order to follow instead the more-than-I as well as the joy of the “more-than of experience in the making.” Twenty-five years later, Manning allows these earlier writings to find their way back into the world, which is also a way of giving “voice to those moments of messy survival” while also asking us, who share in (and help to bear) those moments as readers, to consider “other ways of listening to the urgency that is living.” To (re)publish the book now is to give it a place in the world in a way that honors its force as something that is always beyond anyone’s claim to it, even Manning’s. In this sense, The Perfect Mango invites us, with Manning, to be in excess of ourselves, and also to consider, in Manning’s words, “how to create conditions for living beyond humanism’s fierce belief that we, the privileged, the neurotypicals, the as-yet-unscathed, the able-bodied, hold the key to all perspectives in the theatre of living.” Ultimately, The Perfect Mango and Manning’s reflections on its composition ask us to consider living “in the fierce celebration of a world invented by those modes of life which tear at the colonial, white, neurotypical fabric of life as we know it.”

The Petroleum Manga: A Project by Marina Zurkow - Valerie Vogrin; Marina Zurkow (punctum books, 2014)
The Petroleum Manga, first conceived of and rendered as 10-foot banners printed on Tyvek for gallery installation (http://www.o-matic.com/play/necrocracy/petromanga.html) is now reproduced in book form. Originally, manga was used in Japanese to refer to whimsical drawings or picture books. Long before manga was a multi-billion-dollar-a-year comic book industry, there was Hokusai’s thirteen-volume manga, depicting everything from trees to demons, from squirrels to shingles. This was the work that inspired the form for Marina Zurkow’s own crazy amalgam depicting a taxonomy of products derived from petroleum. Remaining true to this inspiration, this book compiles a curious array of imaginative-philosophical texts by a variety of poets, fiction writers, and theorists illuminating, illustrating, fabulating, and riffing upon a wide range of petrochemical-based objects and ideas. This “collection” maps new webs of relations between us and these seemingly ubiquitous yet often unremarked objects, along the lines of a fanciful petro-poetics. Fanciful, yet dead serious. As Duncan Murrell writes, “our plastics will live forever, no longer able to decompose, while we become molecules again. When we are long gone, there will still be plastic clown masks circling in the Pacific Ocean. This, and not our great works of art and literature, will be the persistent legacy of life on earth, these objects crafted out of life’s own ancient flesh.”

The Phonemes - Frances Richard (punctum books, 2026)
In The Phonemes, Frances Richard investigates perceptually distinct units of experience, such as sounds, energy surges, and scraps of national and natural history, to create episodes of disruption and dissolution. Organized into sequences that move from seismic notation and wave-form typography to lyric encounters with meteors, snakes, glaciers, and the domestic sublime, the poems break language into its smallest expressive particles and reassemble them at the threshold where sense tips into noise. Richard’s formal vocabulary is at once scientific and devotional: geological terms collide with fragments of political speech, advertising copy, lullaby, and prayer, while visual scores of nested parentheses, dashes, and radical signs interrupt the page like oscillograph readings of an unstable signal. What emerges is a poetics of phonemic attention, an insistence that a syllable, weather event, or fault line all can carry a full emotional charge and that the task of the poem is to hold open the instant in which raw perception has not yet hardened into meaning. This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

The Poet as Experiencer: Wallace Stevens and Nonhuman Intelligence - Adam Staley Groves (punctum books, 2025)
In The Poet as Experiencer: Wallace Stevens and Nonhuman Intelligence, Adam Staley Groves approaches Stevens, not merely as poet–thinker but rather as experiencer and theorist of what is today called “the phenomenon” (UFOs). Challenging both Stevens scholarship and our broader understanding of poetic consciousness, the book presents a radical appraisal of Stevens’s oeuvre as an extended, coded testimony of contact with nonhuman intelligence. Drawing from journals, uncollected poems, and landmark works such as Harmonium and The Necessary Angel, Groves argues that Stevens’s poetic evolution mirrors the psychological and spiritual trajectory of an experiencer grappling with anomalous phenomena long before cognitive frameworks for such were culturally available. From moths and owls to missing time and the ethics of the imagination, Groves reads Stevens’s work as a sustained effort to reckon with anomalous phenomena whose language has not yet come. Through careful textual analysis and historical correlation, Groves positions the poet within a lineage that includes Coleridge, Baudelaire, Kierkegaard, and Nietzsche, who are recast not only as theorists of the imagination but as precursors to a modern metaphysical crisis now resurfacing through the contemporary discourse on UFOs and UAPs (Unidentified Anomalous Phenomena). Integrating rigorous literary scholarship with insights from ufology, psychology, and metaphysical philosophy, Groves investigates Stevens’s use of abstraction, the ethics of poetic imagination, and the emergence of the “true subject” as a form of ontological rupture. In doing so, the book bridges the hermetic with the historical, and the poetic with the paranormal.

The Presence of Absence: Meditations on the Unsayable in Writing - Katina L. Rogers (punctum books, 2024)
The Presence of Absence: Meditations on the Unsayable in Writing is about writers navigating the unspeakable through image, sound, and structure. Each chapter focuses on a specific text, exploring the ways that four writers look to visual and auditory materials and metaphors as passageways to understanding and expressing the ineffable qualities of relationships, identity, and grief. Through gorgeously slow and close readings, Rogers explores absence and excess, fragmentation and translation, and—above all—the push and pull between presence and absence, with absence carrying as much significance as presence (and sometimes more). The Presence of Absence crosses languages and disciplines, working in French and English across poetry, photography, history, and literary theory. Through investigations of Nox by Anne Carson, Quelque chose noir by Jacques Roubaud, Wayward Lives, Beautiful Experiments by Saidiya Hartman, and Le livre des questions by Edmond Jabès, Rogers explores various truths—about loss but also about knowledge, beauty, even higher education—that are difficult to articulate and yet resonate deeply with lived experience.

The Republic of Cthulhu: Lovecraft, the Weird Tale, and Conspiracy Theory - Eric Wilson (punctum books, 2016)
If parapolitics, a branch of radical criminology that studies the interactions between public entities and clandestine agencies, is to develop as an academic discipline, then it must develop a coherent theory of aesthetics in order to successfully perform its primary function: to render perceptible extra-judicial phenomena that have hitherto resisted formal classification. Wilson offers the work of H.P. Lovecraft (1890–1937) as an example of the relevance of subversive literature—in this case, cosmic horror and the weird tale—to the parapolitical criminologist. Cosmic horror is a form of writing that relies heavily upon the epistemological assumption of a radical and irreconcilable disjunction between appearance and reality, perception and truth. In many ways, the well-constructed weird tale strongly resembles the hard-boiled detective story or the noir thriller in that the resolution of the narrative hinges upon a dramatically shattering confrontation with an unspeakable reality. Apart from its obvious utilization of conspiracy theory, the primary attraction of the Lovecraftian text lies with its remarkably sophisticated utilization of two central tropes of classical aesthetic theory—the sublime and the grotesque. Not only does Lovecraft’s oeuvre represent a remarkable use of both of these motifs, but the raw literary power of the Lovecraftian weird tale serves as an outstanding exemplar for the parapolitical scholar to emulate in formulating an alternative mode of discourse, or poetics.

There's No Such Thing as "The Economy": Essays on Capitalist Value - Samuel A. Chambers (punctum books, 2018)
Read an Excerpt from There’s No Such Thing as “The Economy” Here! (https://www.dropbox.com/s/vaa3iymh7cqimj6/Chambers_Theres_No_Such_Thing_as_the_Economy_Excerpt.pdf) Every Economics textbook today teaches that questions of values and morality lie outside of, are in fact excluded from, the field of Economics and its proper domain of study, “the economy.” Yet the dominant cultural and media narrative in response to major economic crisis is almost always one of moral outrage. How do we reconcile this tension or explain this paradox by which Economics seems to have both everything and nothing to do with values? The discipline of modern economics hypostatizes and continually reifies a domain it calls “the economy”; only this epistemic practice makes it possible to falsely separate the question of value from the broader inquiry into the economic. And only if we have first eliminated value from the domain of economics can we then transform stories of financial crisis or massive corporate corruption into simple tales of ethics. But if economic forces establish, transform, and maintain relations of value then it proves impossible to separate economics from questions of value, because value relations only come to be in the world by way of economic logics. This means that the “positive economics” spoken of so fondly in the textbooks is nothing more than a contradiction in terms, and as this book demonstrates, there’s no such thing as “the economy.” To grasp the basic logic of capital is to bring into view the unbreakable link between economics and value.

The Retro-Futurism of Cuteness - Jen Boyle; Wan-Chuan Kao (punctum books, 2017)
Is it possible to conceive of a Hello Kitty Middle Ages or a Tickle Me Elmo Renaissance? The Oxford English Dictionary dates the first reference to “cute” in the sense of “attractive, pretty, charming” to 1834. More recently, Sianne Ngai has offered a critical overview of the cuteness of the twentieth-century avant-garde within the context of consumer culture. But if cuteness can get under the skin, what kinds of surfaces does it best infiltrate, particularly in the framework of historical forms, events, and objects that traditionally have been read as emergences around “big” aesthetics of formal symmetries, high affects, and resemblances? The Retrofuturism of Cuteness seeks to undo the temporal strictures surrounding aesthetic and affective categories, to displace a strict focus on commodification and cuteness, and to interrogate how cuteness as a minor aesthetics can refocus our perceptions and readings of both premodern and modern media, literature, and culture. Taking seriously the retro and the futuristic temporalities of cuteness, this volume puts in conversation projects that have unearthed remnants of a “cult of cute”—positioned historically and critically in between transitions into secularization, capitalist frameworks of commodification, and the enchantment of objects—and those that have investigated the uncanny haunting of earlier aesthetics in future-oriented modes of cuteness. The Latin acutus, the etymological root of cute, embraces the sharpened, the pointed, the nimble, the discriminating, and the piercing. But as Michael O’Rourke notes, cuteness evokes a proximity that is at once potentially invasive and contaminating and yet softening and transfiguring. Deploying cuteness as a mode of inquiry across time, this volume opens up unexpected lines of inquiry and unusual critical and creative aporias, from Christian asceticism, medieval cycle drama, and Shakespeare to manga, Bollywood, and Second Life. The projects collected here point to a spectrum of aesthetic-affective assemblages related to racial, ethnic, gender, sexual, and class dimensions that exceed or trouble our contemporary perceptions of such registers within object-subject and subject-object entanglements.

The Romanian Sentiment of Being - Constantin Noica (punctum books, 2022)
The critical links and dependencies between language and thought formed a major new exploration of twentieth-century philosophy. Languages nuance our ideas and perceptions. From various angles and in different ways, Heidegger, Derrida, and Wittgenstein forged new ways of understanding the relationship between our views of the external world and our culturally and linguistically pre-determined modes of expression. Another important thinker in this field of exploration is the Romanian philosopher Constantin Noica (1909–1987), who has so far remained generally unknown in the West because of the Iron Curtain. The Romanian Sentiment of Being (Sentimentul românesc al ființei), first published in Romanian in 1978, is a philosophical work at the intersection of metaphysics and philosophy of language. The title of this book may be deceptive. “Romanian” does not mean ethnically circumscribed; it does not limit ontology to nationality but rather reflects on how language can carry ontological thought. The Romanian Sentiment of Being invites the readers to meditate on the fundamental theme of being and how it is expressed in a culture in time. This being in time marks the tension between moment and eternity, captured in the fairy tale by Petre Ispirescu, “Ageless Youth and Deathless Life” (“Tinerețe fără batrânețe și viață fără de moarte”), which Noica interprets in detail (a translation of the story is included in the appendix). Noica also analyzes one of the most famous poems in Romanian, Mihai Eminescu’s “The Evening Star” (“Luceafărul”), and readers will find its translation in the appendix.

The Ruins of Solitude: Maternity at the Limits of Academic Discourse - Lette Bragg (punctum books, 2024)
What happens when love unravels one’s knowledge structures? In The Ruins of Solitude, after the birth of a child, Bragg embraces the event of love and examines the resulting disintegration of her supposed authorial subjectivity. Against the pressure to produce and organize knowledge—the pressure of writing a dissertation, for example—Bragg contemplates the poetic modes of thinking and ethics that emerge from her experience of reading continental philosophy while caring for her infant child. Dwelling on what she would have once excluded from her intellectual work—her maternity, the mole on her chest, her palm against another body, her exhaustion at the work of deconstruction—Bragg details a shift in her orientation and method that leads to creative theoretical thought, allowing her to illuminate and interrogate what she names “solitude,” a condition of academic discourse that limits our critical-liberatory projects of transformation. Ultimately, The Ruins of Solitude lets go of authority and mastery, and engages in a poetic and fractured writing style that lets in the relationality of thought. Bragg offers a philosophy of bodies beyond solitude and an intimacy of love and writing that fractures solitude, bringing forward the possibility of selfhood and authorship uncontained by the isolationist, tangible time of the present. Bragg’s book also unravels familiar narratives of childcare, considering the parallels between poststructuralist theory and the embodied materiality of relation.

The Singing Detainee and the Librarian with One Book: Essays on Exile - Michael Beltran (punctum books, 2025)
In late 2019, journalist Michael Beltran found himself in the city of Utrecht, the Netherlands, deep in conversation with Filipino revolutionary leaders Jose Maria Sison and Julie de Lima. What was planned to be a feature article ended up as a collection of observations on what it means to live in exile. Sison and de Lima are maligned by governments and revered by activists worldwide, all while spending most of their time tucked away in a small Dutch neighborhood. What Beltran realized was that it was impossible to speak of their exile without understanding the history and community surrounding it. The Singing Detainee and the Librarian with One Book shares lesser known tales about two of the most well-known revolutionary exiles and their comrades. It speaks of a community and history behind the ordeal, weaving it into the Filipino diaspora. Sison passed away in December 2022, making this book a record of one of the last and arguably lengthiest interviews he ever gave. The essays track the couple’s prolonged stay as refugees, how the Philippine liberation movement found a home in Europe, and how migrants and activists alike gravitated toward each other while adrift from their homeland. “Exile,” Beltran says, “is imprisonment by displacement […] when people are condemned to leave their lands dressed in invisible chains.”

The Social Properties of Concrete - Eli Elinoff; Kali Rubaii (punctum books, 2025)
Concrete is a ubiquitous part of our world. It composes our dwellings and shapes our infrastructures. It unites and divides urban space and is used to wage both war and peace. Concrete is simultaneously an indicator of freedom and development and is an essential part of the carceral apparatus. The Social Properties of Concrete begins from the premise that concrete is as richly social as it is densely material. Just as concrete’s materiality permeates our everyday life, our political projects, social practices, religious concepts, environmental transformations, and ethical questions suffuse concrete structures. Like concrete itself, The Social Properties of Concrete is an aggregate: it draws together essays by social scientists, historians, architects, artists, and urban planners who each blend social theory, material science, and empirical analysis to explore the ways in which social life is embedded within concrete and to inquire about how concrete shapes social life. Across forty globally situated chapters, these essays open new conversations around our relationships with anthropogenic stone and serve as a teachable introduction to the social and political lives of materials. By taking this approach, this volume develops a conceptual language and methodological approach that should inform new understandings of material politics and our built environment. The social properties of concrete are neither metaphors nor are they simple reflections of the social. Instead, they are modes of materially enacting social, economic, and political life itself.

The South Station Hoard: Imagining, Creating and Empowering Violent Remains - Carlee A. Bradbury (punctum books, 2014)
This collaborative arts research project compares the landmark discovery of the Staffordshire Hoard (http://www.staffordshirehoard.org.uk/), the largest hoard of Anglo-Saxon gold and silver metalwork discovered in 2009, with an imagined hoard from present day pre-adolescent girls. The collaborators constructed a subterranean installation, generated speculative historical documents, collected and embellished social networking “artifacts,” and photographed the entire process. In addition to dealing with the notion of a medieval hoard as a signifier of a medieval warrior as both hero and anti-hero, this artbook, or work of futurist archaeology, addresses contemporary issues relating to gender, youth culture, bullying, adolescent development, iconicity, status symbols, and additional contemporary tween issues. The fabricated hoard presented here is comprised of the trappings of current “tween” girl culture — for example, cell phones decorated with hot pink crystals, necklaces with twinkling pendants, personalized/defaced dolls, and religious objects. As our future archeologists study these and other objects, the greater context of bullying emerges: the hoard objects were stolen from one group of tween girls by another. This project suggests a reconceptualization of treasure, the acts of hoarding and archiving, and the visual cultures of both tween girls and medieval warriors. Bloodshed and intense physicality marked the medieval warrior’s existence. Weaponry was not just a medieval necessity but also a status symbol. Young girls impose just as much meaning to their specific visual culture, and though they do not (always) rely on physical violence, the act of bullying can be just as devastating. The question of how we deal with violence associated with historical, and gendered, objects is central to this project, which also confronts the form of the traditional collection of scholarly essays with the intense visuality of an artist book. The photographs and graphic design of this volume are just as important as the content of the essays themselves. This volume depends on the fruitful collisions between the “scholarly” and “creative” processes. Even the tone of the writing showcased here intentionally travels from fictional accounts to academic scholarship to personal accounts of bullying. The South Station Hoard depends on such disciplinary fusion, intentionally mixing it up with medieval studies, art history, gender studies, art education, and photography, while also being aimed at various groups of students as well as experts in various fields. Because of the seemingly ubiquitous presence of bullies in all arenas of young adult life, and beyond, it is hoped that this volume will be useful for educators, counselors, and mentors of both young girls and boys.

The Spectacle of the False Flag: Parapolitics from JFK to Watergate - Eric Wilson (punctum books, 2014)
Eric Wilson’s work poses crucial challenges to social theory, unsettling our understanding of the nature of the liberal democratic state. In The Spectacle of the False Flag, he urges the reader to examine the, often unconsidered, deep state practices that confound conventional notions of the state as monolithic or uniform. This compelling volume traces deep state conflicts and convergences through central cases in the development of American political economic power — JFK/Dallas, LBJ/Gulf of Tonkin, and Nixon/Watergate. Rigorously documented and unflinchingly analyzed, The Spectacle of the False Flag provides a stunning example of a new criminological practice—one that takes the state seriously, making the inner workings of the state rather than its effects the primary object of study. Drawing upon a wealth of historical records and developing the theoretical insights of Guy Debord’s writings on spectacular society, Wilson offers a glimpse into a necessary criminology to come.

The Specter of AIDS - Néstor Perlongher (punctum books, 2026)
The Specter of AIDS is a transdisciplinary text originally written in 1980s Brasil in a time of pandemic emergency. It situates how HIV/AIDS reconfigured intimacy, sexuality, and power while also providing a minoritarian theory of desire lived by dissident sexualities in 1980s Latin America. Perlongher’s paper exposes a new barometer of life undergirded by medico-scientific reason, religious ideology, and morality — in other words, a re-actualization and intensification of normative reason. In nuanced prose combined with wit, rigorous scholarship, political alertness, and poetics, Perlongher delineates how HIV/AIDS serves as a blueprint for how viral threats shed light on the inequitable unevenness of this world. Written in Portuguese in 1987 and then published in Spanish in 1988, this translation offers an un/timely reading for the 21st century as it shows how new contaminants threaten national public health’s paradigms of gendered and racialized structures: their borders, bodies, and good comportment.

The Tales - Jessica Bozek (punctum books, 2023)
Stitching together a post-apocalyptic history from the scraps of fairy tales, war memorials, hunting songs, and disparate scholarship, Jessica Bozek’s The Tales traces the violence that humans inflict upon one another. As the central narrative of the Lone Survivor becomes revealed through the mouths of various perspectives, Bozek investigates the language that victims and perpetrators alike use to make sense of (and attempt to forget) the aftermath of violence. From ordinary objects—family photographs, sweaters that unravel, old batteries, and lightbulbs—to the remnants of destroyed art and architecture, an annihilated nation is brought into reality, and the Lone Survivor’s story is simultaneously documented and invalidated, becoming “a memorial that will disintegrate over time, gray and fray as most of the dead did not have a chance to.” This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

The Troll Inside You: Paranormal Activity in the Medieval North - Ármann Jakobsson (punctum books, 2017)
What do medieval Icelanders mean when they say “troll”? What did they see when they saw a troll? What did the troll signify to them? And why did they see them? The principal subject of this book is the Norse idea of the troll, which the author uses to engage with the larger topic of paranormal experiences in the medieval North. The texts under study are from 13th-, 14th-, and 15th-century Iceland. The focus of the book is on the ways in which paranormal experiences are related and defined in these texts and how those definitions have framed and continue to frame scholarly interpretations of the paranormal. The book is partitioned into numerous brief chapters, each with its own theme. In each case the author is not the least concerned with how the paranormal functions within medieval society and in the minds of the individuals who encounter and experience it and go on to narrate these experiences through intermediaries. The author connects the paranormal encounter closely with fears and these fears are intertwined with various aspects of the human experience, including gender, family ties, and death. The Troll Inside You hovers over the boundaries of scholarship and literature. Its aim is to prick and provoke but above all to challenge its audience to reconsider some of their preconceived ideas about the medieval past.

Making the Geologic Now: Responses to Material Conditions of Contemporary Life - Elisabeth Ellsworth; Jamie Kruse (punctum books, 2012)
Making the Geologic Now announces shifts in cultural sensibilities and practices. It offers early sightings of an increasingly widespread turn toward the geologic as source of explanation, motivation, and inspiration for creative responses to conditions of the present moment. In the spirit of a broadside, this edited collection circulates images and short essays from over 40 artists, designers, architects, scholars, and journalists who are actively exploring and creatively responding to the geologic depth of “now.” Contributors’ ideas and works are drawn from architecture, design, contemporary philosophy and art. They are offered as test sites for what might become thinkable or possible if humans were to collectively take up the geologic as our instructive co-designer—as a partner in designing thoughts, objects, systems, and experiences. Recent natural and human-made events triggered by or triggering the geologic have made volatile earth forces sense-able and relevant with new levels of intensity. As a condition of contemporary life in 2012, the geologic “now” is lived as a cascade of events. Humans and what we build participate in their unfolding. Today, and unlike the environmental movements of the 1970s, the geologic counts as “the environment” and invites us to extend our active awareness of inhabitation out to the cosmos and down to the Earth’s iron core. *Image from Trace — cameraless records of radioactive contamination: Shimpei Takeda (http://www.shimpeitakeda.com/biography/), 2012 (photo by Keisuke Hiei) A new cultural sensibility is emerging. As we struggle to understand and meet new material realities of earth and life on earth, it becomes increasingly obvious that the geologic is not just about rocks. We now cohabit with the geologic in unprecedented ways, in teeming assemblages of exchange and interaction among geologic materials and forces and the bio, cosmo, socio, political, legal, economic, strategic, and imaginary. As a reading and viewing experience, Making the Geologic Now is designed to move through culture, sounding an alert from the unfolding edge of the “geologic turn” that is now propagating through contemporary ideas and practices.

Malleus Daemonum: The Hammer of Demons - Alessandro Albertino (punctum books, 2026)
The Malleus Daemonum provides an exciting introduction into the religious world of early modern Italy. It consists of a series of personal exorcisms which the Italian Observant Franciscan Alessandro Albertino composed and which he claims have proven themselves by experience. It bears witness to the end of a period in which priests could freely compose their own exorcisms as a regular part of their pastoral functions. Albertino’s exorcisms faithfully follow the Passion narrative in the four Gospels designed both to parallel and to empower the Vulgate text. His strategy is to employ the words and instruments used against Christ by his detractors against the demons occupying the possessed individual in order to expel them. Those words and weapons which were once used to torment, harass, and crucify Christ thus become spiritual weapons which the exorcist may use to treat their patient. Albertino introduces each exorcism with an epigram based on Classical mythology followed by litanies, invocations, and prayers, and he also includes a general exorcism to expel demons from specific parts of the body, along with general blessings and prayers to drive out all sorcery and diabolical intervention from particular articles of clothing. This edition comprises a comprehensive historical and theological introduction, a Latin edition, and the first-ever English translation of The Hammer of Demons. The translation, research, and commentary unveil a long-buried gem of the seventeenth century, offering readers an alluring narrative about the evolving face of the ancient convention of exorcism. More than just a book, this introduction, edition, and translation are an essential contribution to the understanding of the intersection of exorcism, history, and religion in early modern Italy.

Mandela in Havana, Maria in the Favela: Black Hosts - Akin Adeṣọkan (punctum books, 2028)
Why is Pan-Africanism, an intellectual idea which carried much political weight in the twentieth century, no longer of consequential interest to most Africans and Blacks in the world? Why is it that the ideas and individuals that tend to be popular about the African world do not often grapple with the complexity of said world? Even with the brilliance of Bessie Head’s revelations in Lesotho in the shadow of apartheid to the willfully imaginative poetic acts of Martinican Aimé Césaire, the astonishing military genius of revolutionary leader Amilcar Cabral of Guinea Bissau and the self-flagellating howling sounds of Fẹla Anikulapo-Kuti’s music on the streets of Nigeria and beyond, why do rich experiences of global Blackness still struggle for active engagement in the plain light of routine reckoning? The essays in Mandela in Havana, Maria in the Favela: Black Hosts are an attempt to reflect on these questions, and many others like them. Anchored in two catalytic moments in the period following the Second World War—the Pan-African Congress in Manchester in 1945 and the founding in 1947 of the journal Présence Africaine—as well as the impact on contemporary Black selfhoods of the events they set in motion, the essays frame the subsequent events as opportunities for Black people, intellectuals especially, to become hosts to the world, in a manner that was impossible for them to do in the previous decades. The chapters look closely at trends that animated that history and, through selected profiles, offer exemplary analyses of the attendant changes.

Manifesto for a Post-Critical Pedagogy - Naomi Hodgson; Joris Vlieghe; Piotr Zamojski (punctum books, 2018)
The belief in the transformative potential of education has long underpinned critical educational theory. But its concerns have also been largely political and economic, using education as the means to achieve a better – or ideal – future state: of equality and social justice. Our concern is not whether such a state can be realized. Rather, the belief in the transformative potential of education leads us to start from the assumption of equality and to attend to what is “educational” about education. In Manifesto for a Post-Critical Pedagogy we set out five principles that call not for an education as a means to achieve a future state, but rather that make manifest those educational practices that do exist today and that we wish to defend. The Manifesto also acts as a provocation, as the starting point of a conversation about what this means for research, pedagogy, and our relation to our children, each other, and the world. Manifesto for a Post-Critical Pedagogy invites a shift from a critical pedagogy premised on revealing what is wrong with the world and using education to solve it, to an affirmative stance that acknowledges what is educational in our existing practices. It is focused on what we do and what we can do, if we approach education with love for the world and acknowledge that education is based on hope in the present, rather than on optimism for an eternally deferred future.

Manifesto for Living in the Anthropocene - Katherine Gibson; Deborah Bird Rose; Ruth Fincher (punctum books, 2015)
The recent 10,000 year history of climatic stability on Earth that enabled the rise of agriculture and domestication, the growth of cities, numerous technological revolutions, and the emergence of modernity is now over. We accept that in the latest phase of this era, modernity is unmaking the stability that enabled its emergence. Over the 21st century severe and numerous weather disasters, scarcity of key resources, major changes in environments, enormous rates of extinction, and other forces that threaten life are set to increase. But we are deeply worried that current responses to these challenges are focused on market-driven solutions and thus have the potential to further endanger our collective commons. Today public debate is polarized. On one hand we are confronted with the immobilizing effects of knowing “the facts” about climate change. On the other we see a powerful will to ignorance and the effects of a pernicious collaboration between climate change skeptics and industry stakeholders. Clearly, to us, the current crisis calls for new ways of thinking and producing knowledge. Our collective inclination has been to go on in an experimental and exploratory mode, in which we refuse to foreclose on options or jump too quickly to “solutions.” In this spirit we feel the need to acknowledge the tragedy of anthropogenic climate change. It is important to tap into the emotional richness of grief about extinction and loss without getting stuck on the “blame game.” Our research must allow for the expression of grief and mourning for what has been and is daily being lost. But it is important to adopt a reparative rather than a purely critical stance toward knowing. Might it be possible to welcome the pain of “knowing” if it led to different ways of working with non-human others, recognizing a confluence of desire across the human/non-human divide and the vital rhythms that animate the world? Our discussions have focused on new types of ecological economic thinking and ethical practices of living. We are interested in: Starting from the recognition that there is no “one size fits all” response to climate change, we are concerned to develop an ethics of place that appreciates the specificity and richness of loss and potentiality. While connection to earth others might be an overarching goal, it will be to certain ecologies, species, atmospheres and materialities that we actually connect. We could see ourselves as part of country, accepting the responsibility not forgotten by Indigenous people all over the world, of “singing” country into health. This might mean cultivating the capacity for deep listening to each other, to the land, to other species and thereby learning to be affected and transformed by the body-world we are part of; seeing the body as a center of animation but not the ground of a separate self; renouncing the narcissistic defense of omnipotence and an equally narcissistic descent into despair. We think that we can work against singular and global representations of “the problem” in the face of which any small, multiple, place-based action is rendered hopeless. We can choose to read for difference rather than dominance; think connectivity rather than hyper-separation; look for multiplicity — multiple climate changes, multiple ways of living with earth others. We can find ways forward in what is already being done in the here and now; attend to the performative effects of any analysis; tell stories in a hopeful and open way — allowing for the possibility that life is dormant rather than dead. We can use our critical capacities to recover our rich traditions of counter-culture and theorize them outside the mainstream/alternative binary. All these ways of thinking and researching give rise to new strategies for going forward. Think of the chapters of this book as tentative hoverings, as the fluttering of butterfly wings, scattering germs of ideas that can take root and grow.

Masks - T.H.M. Gellar-Goad (punctum books, 2024)
The mask is the classic disguise. But as alter ego, it reveals as much as it conceals. Why are masks so often creepy, even outside of horror movies? Can a mask change expression while you’re wearing it? How much of someone’s self can inhabit a mask? Why would anyone make a plaster cast of a dead person’s face? And, really, who was that masked man? Masks unmasks the answers to these frequently (m)asked questions and more. Masks are the materials for a world of make-believe, from the theater to Halloween, from masquerades to Scooby-Doo. Masks can take on magic or ritual powers. They can preserve and transmit memory. Masks are a makeover tool for appearance and identity, from spa treatments to drag to superheroes. What all these different functions have in common is the mask as physical metaphor, a mirror of the self and society. In another layer of metaphor, our words for ourselves as individuals (“person”) and for our self-presentation to society (“persona”) both derive directly from the Latin word for mask. Masks explores one of humanity’s oldest cultural objects, traveling from prehistoric remains to ancient Roman funeral processions to Mardi Gras to masked doppelgangers on stage and screen. Its examination of masks across time and the globe sheds new light on the totemic power masks have developed, especially during the COVID-19 pandemic.

Massa por Argamassa: A "Libraria de Babel" e o Sonho de Totalidade - Jonathan Basile (punctum books, 2019)
Massa por Argamassa apresenta uma exploração profunda de um dos maiores ilusionistas da literatura, Jorge Luis Borges. Seu conto “A Biblioteca de Babel” é um exemplar ilustre de sua capacidade lúdica, embora não somente devido ao mundo invertido que nele é imaginado, no qual uma biblioteca, que supostamente contém todas as combinações possíveis de todas as letras, palavras e livros, é vasculhada por bibliotecários devotos em busca de verdades divinamente pré-fabricadas. Pois também é preciso lidar com a ironia da narração de Borges, que constantemente põe em xeque as afirmações do narrador sobre a universalidade da biblioteca, incluindo a própria possibilidade de exaurir os significados possíveis através de um processo combinatório. Borges direcionava seus leitores para sua obra de não-ficção para que descobrissem o verdadeiro autor da ideia da biblioteca universal. Mas seus ensaios supostamente históricos são notoriamente repletos de referências falsas e contradições. Seja na verdade ou na ficção, Borges nunca atinge uma conclusão estável sobre as premissas atomistas da biblioteca universal – seria possível encontrar um conjunto de caracteres capaz de expressar todo o significado possível, ou estariam essas letras, assim como suas histórias e ensaios, se multiplicando e dividindo em uma incompletude incansável? Embora muitos leitores de Borges o veem como um presságio de nossas tecnologias digitais, eles muitas vezes dão crédito demais a nossas invenções ao fazê-lo. Aqueles que elidem a necessária incompletude da Biblioteca de Babel a comparam com a Internet, assumindo que ambos seriam arquivos totais de todo o pensamento e expressão possíveis. Embora as imaginações de Borges tenham contribuído para a criatividade digital (libraryofbabel.info é certamente uma evidência disto), elas o fazem demonstrando a necessária incompletude de todos os projetos totalizadores, independentemente de seu refino tecnológico. No final, Basile guia os leitores em direção à ideia de que uma exposição fictícia/imaginária possui certo poder sobre a tecnologia.

Matches: A Light Book - S.D. Chrostowska (punctum books, 2019)
The match: little stick tipped with combustible stuff, sparked by friction; typically comes in a book or a box or a bundle (the point being: never alone). The highly portable match lighting more or less when required was a great nineteenth-century innovation. Before, we had only Danger and Poison matches, and countless match-induced accidents and suicides. We still have not engineered mischief out of the match. One little lucifer, God’s little helper, lit in the company of its sisters and brothers will, if we let them, afford us a miniature inferno. Are we responsible for the recklessness of thought? There will always be match tricks to go very wrong. How many times have we amused ourselves in the schoolyard, lighting up the whole passel of ideas within our reach, getting us in trouble? And now that we are older, we can strike anywhere. We count on sparks to leap long distances virtually, to pass most swiftly from point to point instead of smouldering. No sooner do we bring a flame to something flammable than it spreads — even as its conductors are already charring and curling up. Let us congratulate ourselves for remaking the transport of ideas. And for this new refrain: What matters is what’s on fire. Through the prism of criticism, the modalities of thinking form a spectrum: on one end, systematic exposition, on the other, the fragment. It is the latter, fragmentary approach that distinguishes Matches—an investigation that does not focus on a single theme developed in all its aspects but, rather, on a constellation of themes in art, literature, philosophy, science, social and political thought, as well as the human in relation to history and nature. S.D. Chrostowska pursues here in performative fashion her research into the history of critique from the Enlightenment onward. Her choice of the fragment—in the tradition of writing represented by Gracián, Chamfort, Lichtenberg, and, closer to us, Nietzsche, Adorno, and Benjamin—does not, however, stem from an attempt to comprehend the contemporary world, which can only be done after the fact. Instead, served by an expressive and incisive style, Matches foregrounds the necessary elements for a critique of our time, capturing them in their contradictory and complementary relations. It situates itself under the sign of the future, reviving the spirit of utopia, reminding us that the last word need not belong to the present.

Matches: A Light Book - S.D. Chrostowska (punctum books, 2015)
Through the prism of criticism, the modalities of thinking form a spectrum: on one end, systematic exposition, on the other, the fragment. It is the latter, fragmentary approach that distinguishes Matches—an investigation that does not focus on a single theme developed in all its aspects but, rather, on a constellation of themes in art, literature, philosophy, science, social and political thought, as well as the human in relation to history and nature. S.D. Chrostowska pursues here in performative fashion her research into the history of critique from the Enlightenment onward. Her choice of the fragment—in the tradition of writing represented by Gracián, Chamfort, Lichtenberg, and, closer to us, Nietzsche, Adorno, and Benjamin—does not, however, stem from an attempt to comprehend the contemporary world, which can only be done after the fact. Instead, served by an expressive and incisive style, Matches foregrounds the necessary elements for a critique of our time, capturing them in their contradictory and complementary relations. It situates itself under the sign of the future, reviving the spirit of utopia, reminding us that the last word need not belong to the present.

Meaningful Flesh: Reflections on Religion and Nature for a Queer Planet - Whitney A. Bauman (punctum books, 2018)
Religion is much queerer than we ever imagined. Nature is as well. These are the two basic insights that have led to this volume: the authors included here hope to queerly go where no thinkers have gone before. The combination of queer theory and religion has been happening for at least 25 years. People such as John Boswell began to examine the history of religious traditions with a queer eye, and soon after we had the indecent theology of Marcella Althaus Ried. Jay Johnston, one of the authors in this issue, is among those who have used the queer eye to interrogate authority within Christian theological traditions. At the same time, there have been many queer interrogations of “nature,” perhaps most notably in the works of Joan Roughgarden and Ann Fausto-Sterling, and more recently in the works of Catriona Sandilands and Timothy Morton (an author in this volume). However, the intersections of religion, nature, and queer theory have been largely left untouched. With the exception of Dan Spencer, who writes the introduction for this volume and is one of the early pioneers in this realm of thought with his book Gay and Gaia (Pilgrim Press, 1996), and the work of Greta Gaard in developing a queer ecofeminist thought, religion and nature, or religion and ecology, have largely ignored the realm of queer theory. In part, the blinders to queer theory on the part of eco-thinkers (religious or otherwise) are similar to the blinders eco-thinkers have when it comes to postmodern thought in general: namely, if there are no absolute foundations, how does one create an environmental ethic and a “nature” to save? For this reason and many others, this volume on religion, nature, and queer theory is groundbreaking. Though these essays span many different disciplines and themes, they are all held together by the triple focus on religion, nature, and queer theory. Each of these essays offers a unique contribution to the intersection of religion, nature, and queer theory, and all of them challenge strict boundaries proposed in religious rhetoric and many discourses surrounding “nature.” Carol Wayne White’s essay draws from a queer reading of James Baldwin to develop an African American religious naturalism, which highlights humans as polyamorous bastards. Jacob Erickson’s essay examines Isabella Rossellini’s “Green Porno” and Martin Luther’s work to develop an irreverent theology. Jay Johnson draws from personal relationships with his late dog, and Master/Pup fetish-play, to blur the boundaries between humans and other animals, specifically within ethical and theological discourse. Whitney Bauman reflects on how the very processes of globalization and climate change queer our identities and call for a queer and versatile planetary ethic. Finally, Timothy Morton leads us through a reflection on queer green sex toys to challenge the ontology of agrologistics. Each of these essays in their own way is concerned with fleshing out more meaningful encounters with the planetary community. Without being too ambitious, we hope that these sets of essays will help to open up a new trajectory of conversations at the intersection of religion, nature, and queer theory.

Medieval Disability Sourcebook: Western Europe - Cameron Hunt McNabb (punctum books, 2020)
The field of disability studies significantly contributes to contemporary discussions of the marginalization of and social justice for individuals with disabilities. However, what of disability in the past? The Medieval Disability Sourcebook: Western Europe explores what medieval texts have to say about disability, both in their own time and for the present. This interdisciplinary volume on medieval Europe combines historical records, medical texts, and religious accounts of saints’ lives and miracles, as well as poetry, prose, drama, and manuscript images to demonstrate the varied and complicated attitudes medieval societies had about disability. Far from recording any monolithic understanding of disability in the Middle Ages, these contributions present a striking range of voices—to, from, and about those with disabilities—and such diversity only confirms how disability permeated (and permeates) every aspect of life. The Medieval Disability Sourcebook is designed for use inside the undergraduate or graduate classroom or by scholars interested in learning more about medieval Europe as it intersects with the field of disability studies. Most texts are presented in modern English, though some are preserved in Middle English and many are given in side-by-side translations for greater study. Each entry is prefaced with an academic introduction to disability within the text as well as a bibliography for further study. This sourcebook is the first in a proposed series focusing on disability in a wide range of premodern cultures, histories, and geographies.

Medieval Hackers - Kathleen E. Kennedy (punctum books, 2015)
Medieval Hackers calls attention to the use of certain vocabulary terms in the Middle Ages and today: commonness, openness, and freedom. Today we associate this language with computer hackers, some of whom believe that information, from literature to the code that makes up computer programs, should be much more accessible to the general public than it is. In the medieval past these same terms were used by translators of censored texts, including the bible. Only at times in history when texts of enormous cultural importance were kept out of circulation, including our own time, does this vocabulary emerge. Using sources from Anonymous’s Fawkes mask to William Tyndale’s Bible prefaces, Medieval Hackers demonstrates why we should watch for this language when it turns up in our media today. This is important work in media archaeology, for as Kennedy writes in this book, the “effluorescence of intellectual piracy” in our current moment of political and technological revolutions “cannot help but draw us to look back and see that the enforcement of intellectual property in the face of traditional information culture has occurred before….We have seen that despite the radically different stakes involved, in the late Middle Ages, law texts traced the same trajectory as religious texts. In the end, perhaps religious texts serve as cultural bellwethers for the health of the information commons in all areas. As unlikely as it might seem, we might consider seriously the import of an animatronic [John] Wyclif, gesturing us to follow him on a (potentially doomed) quest to preserve the information commons.”

Memoir American - Benjamin Hollander (punctum books, 2013)
In the dead letter office, you will find a Memoir American. The texts which comprise it — forms of essay, talk, dialogue — at one time saw themselves as individualists who went somewhere (to small press magazines) on their own. Now they are here, collected with the chance of going nowhere together. As it should be: since they represent the fate of language and translation in the memory of aliens living inside America — like a family going nowhere together, but at home. The philosopher Jacques Derrida and his family are part of this family in the dead letter office, and curiously they are named going nowhere together at home. Along the way, so are the poets Charles Reznikoff and William Carlos Williams and Emmanuel Hocquard and Juliette Valery and Charles Olson, as well as Horace’s Odes in translation. You will find in this Memoir what it means for an alien to search for his family in a book outside the time of its writing. You will find him discovering that translation is a personal story and that poetry might not have a home without it. You will find him wondering: whose voices are these which we hear around us as we write, as Babel turns to rumor through the fact of translation, wherein a book is being made and remade from American to French and back again? You will find him through translation like a Being in the Poetry of the Extraterritorial, an un-owned territory which is neither French nor American but is negotiated by the rumor of a poetry which emerges from both, a future condition (État) which seeks the name it could be but is not. Follow this alien Being’s trajectory: he is not of America but grows up in it. He publishes a book in French translation before it appears in the American English original. He becomes native to a writing whose eloquence is always in question, at times because it is passive, at other times because it is unpronounceable. Who, over time, finds his Memoir? In the dead letter office, we do. We find someone somewhat like ourselves, who uses language and translation as if these were a poet’s gifts in the making of history, a history which is foreign yet integral to his homeland. We find someone who uses it to return to his own people and place, so that he can “only stand more/revealed.” We find someone who will act the new basis for his identity — the consciousness whose coming into Being must be premised on his existence in another world.

Men in Aïda - David J. Melnick (punctum books, 2014)
David J. Melnick published the first book (http://eclipsearchive.org/projects/AIDA/aida.html) of Men in Aida, a homophonic, but also homoeroticized translation of Homer’s epic Iliad, in December 1983 in an edition of 450 at Tuumba Press. After appearing in many guises and fragments, Book Two was published online in 2002 as part of the Eclipse Archive (http://eclipsearchive.org/projects/AIDA/aida.html). Book Three appears for the first time in the present publication, which brings together all three books of one of the most important American avant-garde poems.

Metagestures - Carla Nappi; Dominic Pettman (punctum books, 2019)
What kinds of knowledge and understandings of the world can be generated – and shared – when we use para-academic techniques and sensibilities to decode or respond to relatively orthodox intellectual objects? And what worlds might be possible if we practiced scholarly work from a place of collaboration and pleasure, as joyful fellow explorers? In Metagestures, historian Carla Nappi and cultural theorist Dominic Pettman explore the use of fiction as a tool to write and think with works of theory. Taking Vilém Flusser’s Gestures as its point of inspiration and departure, Metagestures collects 16 pairs of short stories in which Pettman and Nappi make fictional worlds that animate and enliven each of the major gestures in Flusser’s book. Nappi and Pettman focus on Flusser’s mediations on the gestures of filming, planting, loving, smoking a pipe, turning a mask around, and much more, with their own creative explorations of each theme, in a gathering of short fictions that test, expand, and further the social scientific claims of the original text with new scenarios and occasions. Here, Flusser’s reflections on physical gesture serve as an inspiration for new ways of conceiving and conducting theory, and for thoughtful creative scholarly imagining, with and alongside one another.

Microbium: The Neglected Lives of Micro-matter - Joela Jacobs; Agnes Malinowska (punctum books, 2023)
Microbium: The Neglected Lives of Micro-matter tells the story of small matter such as bacteria, coral, fungi, lichen, pollen, protozoa, and viruses. With short entries that are organized like a herbarium or similar specimen collection, the book is a “microbium”—both the term for a single microbe and a play on “microbiome.” As such, Microbium makes visible the often overseen but huge impact of miniscule matter on human culture and the environment. Each entry is a “microscopic reading” that describes the natural history and scientific discovery of a particular form of micro-matter, while also telling a story about the cultural and artistic roles it has played over the centuries. From the poetry of Emily Dickinson to the “coralness” of coral reefs to contemporary literature about the COVID-19 pandemic, this book places micro-matter under a cultural microscope and translates the significance of the invisible interspecies social realm to the human scale, magnifying the many ways in which micro-matter matters. Ultimately, Microbium shows the potential of micro-matter to teach us how to revitalize our political and cultural systems, habits of thought, and aesthetic or representational modes.

Mineral Policies - Marko Stamenkoviç (punctum books, 2022)
Mineral Policies provides a record of an art residency organized by the ZETA Center for Contemporary Art in the mining region of Bulqiza in northeastern Albania, where four artists and activists from Albania, Blerta Hoçia, Diana Malaj, Pleurad Xhafa, and Ergin Zaloshnja, created a collective body of works in close proximity with the local miners, while still maintaining their own discrete spheres of action. This residency was followed by a public exhibition, Each Strike Leads to the Next, featuring video works produced during the residency as well as a series of objects, curated by Vincent W.J. van Gerven Oei, director of the Department of Eagles in Tirana. This book includes documentation of the residency and the exhibition, as well as the record of a public discussion between curator van Gerven Oei, former Minister of Finance Arben Malaj, mining engineer Genc Myftiu, and mining worker Bardhul Alla, moderated by cultural journalist Elsa Demo. The book also includes a conservation between cultural theorist Jonida Gashi and van Gerven Oei with the artists. Mineral Policies documents an important attempt of present-day Albanian artists to reflect on and align themselves with workers and labor activities within a political climate in which neoliberal extractivism and mafia-controlled local and national government have seriously compromised modes of solidarity and survival.

Minóy - Joseph Nechvatal (punctum books, 2014)
Minóy is a rescue operation with several life rafts. Minóy-the-book provides an introduction and overview to the important noise music artist Minóy — the pseudonym of American electronic art musician and sound artist Stanley Keith Bowsza (1951-2010). Minóy’s audio compositions, often conjuring up an enigmatic world of almost dreadful depth, earned him a key position in the homemade independent cassette culture scene of the 1980s. Minóy-the-CD (available HERE (http://amzn.to/2eI73yV)) makes available nine of Minóy’s audio compositions that span the years 1985 to 1993. These were drawn from recently discovered archival material and selected by the editor and artistic director of the project, Joseph Nechvatal, in collaboration with composer Phillip B. Klingler (PBK). Klingler (co-producer and sound engineer) houses the Minóy archive and has re-mastered the tracks, most of which have never been heard before (it was thought that Minóy stopped recording in 1992). Minóy-the-book contains two written monograms of Minóy, one by close friend Amber Sabri and one by artist and art theoretician Joseph Nechvatal. There are three additional essays by Nechvatal, the first of which, “The Obscurity of Minóy,” recounts the history of the recovery of the audio material from obscurity. In the subsequent essays (“The Aesthetics of an Obscure Monster Sacré” and “Hyper Noise Aesthetics”), Nechvatal reflects on the artistic benefits of obscurity and situates Minóy’s deep droning palimpsest soundscapes within an original aesthetic-theoretical context of an obscure monster sacré, and also examines Minóy’s legacy in terms of current aesthetic responses to the surveillance state, couching Minóy’s mysterious and excessive compositions in terms of a general art of noise. In total, Minóy’s work undergoes a critical intricacy in terms of a contemporary art practice engaged in the fragile balance between production of, and resistance to, perceptibility. Nechvatal brings a subversive reading to Minóy’s work by presenting it as a form of hyper-noise artistic gazing, based in the flipping of figure and ground. The book also contains sixty black and white portrait images from the Minóy as Haint as King Lear series that photographer Maya Eidolon (Amber Sabri) created before his death in collaboration with Minóy (then known as Haint) and Stuart Hass (Minóy’s lifetime partner).

Misinterest: Essays, Pensées, and Dreams - M.H. Bowker (punctum books, 2019)
The term “interest” lacks a precise antonym. In English, we have “disinterested” and “uninteresting,” but we want for a term that denotes robust opposition to interest. The same appears to hold true in every other language (as far as we know). Interest’s missing antonym reflects not merely a widespread lexical oversight, but a misrecognition of interest’s complete and exact meaning. More importantly, the idea that interest has no opposite expresses a certain refusal to acknowledge the power of the impulse to extinguish interest, for the self and for others. Why then do we foreclose interest’s possibility, degrade our (and others’) capacities to experience interest, and destroy interest’s objects? Why do we decline what interest proffers — which includes creative and subjective being, thinking, and relating — in favor of more primitive modes of survival, thoughtlessness, and nonbeing? Why do relationships — with ourselves, with others, with objects — toward which genuine interest draws us seem sometimes, if not often, unbearable? These questions are difficult. Their answers, even more so. Misinterest: Essays, Pensées, and Dreams attempts to approach them in an honest way, without making them fascinating, mysterious, boring, obscurantist, or fascinatingly mysteriously boringly obscurantist. Outwardly, Misinterest is concerned with dreams and forgetting and Eros and soaring dogs and groups and suicidal suburban teenagers and sex and jury duty and Nazis and fathers and hatred and holy parrots and fundamentalists and plagues and other things that may or may not be interesting. Ultimately, however, it seeks, like Jules Renard, “en restant exact” (in remaining true/real), to shed light on the establishment of misinterest, missingness, and mystery where and when they need not be, and, thus, on the psychic, familial, and political forces that compel us not to be when and where we ought.

Modernity without a Project: Essay on the Void Called Contemporary - C.B. Johnson (punctum books, 2015)
This provocative and interesting book argues that the celebratory discourse of ‘the contemporary’ is not as innocent as it seems, but is geared towards cancelling out or negating the capital-unfriendly scepticism of modernism and postmodernism. This study contributes significantly to the field of what might be termed critical cultural studies, particularly with regard to the understanding of art and architecture as they are mobilised in the first part of the 21st century. Ian Buchanan, Director of the Institute for Social Transformation Research, University of Wollongong Entering the 21st century, the postmodern succession has given way to a doom-laden, apolitical orthodoxy. This book offers suggestive readings of “the contemporary” in light of high modernity, postwar modernity, and postmodernity, as framed by the influential institutions of modern art and the spectacles of millennial architecture. Modernity without a Project critiques and connects historical avant-garde currents as they are institutionally expressed or captured, and scrutinizes the remake of New York’s Museum of Modern Art, Minoru Yamasaki’s vanished Utopias, the “anarchitecture” of Lebbeus Woods, recent work of Rem Koolhaas, delirious developments in Dubai, and the unexpected contribution to architectural debate by the late Hugo Chavez.

Moonbit - James E. Dobson; Rena J. Mosteirin (punctum books, 2019)
Moonbit is a hybrid work comprised of experimental poetry and a critical theory of the poetics and politics of computer code. It offers an extended intellectual and creative engagement with the affordances of computer software through multiple readings and re-writings of a singular text, the source code of the Apollo 11 Guidance Computer or the “AGC.” Moonbit re-marks and remixes the code that made space travel possible. Half of this book is erasure poetry that uses the AGC code as the source text, building on the premise that code can speak beyond its functional purpose. When we think about the 1960s U.S. space program and obscure scientific computer code, we might not first think about the Watts riots, Shakespeare, Winnie the Pooh, T.S. Eliot, or scatological jokes. Yet these cultural references and influences along with many more are scattered throughout the body of the code that powered the compact digital computer that successfully guided astronauts to the Moon and back and in July of 1969. Moonbit unravels and rewrites the many embedded cultural references that were braided together within the language resources of mid-century computer code. Moonbit also provides a gentle, non-expert introduction to the text of the AGC code, to digital poetics, and to critical code studies. Outlining a capacious interpretive practice, Moonbit takes up all manner of imaginative decodings and recodings of this code. It introduces some of the major existing approaches to the study of code and culture while provide multiple readings of the source code along with an explanation and theorization of the way in which the code works, as both a computational and a cultural text.

More&More: A Guide to a Harmonized System - Marina Zurkow (punctum books, 2016)
More&More is an art and research project that explores the language and mechanics of global trade, container shipping, and the exchange of goods. It questions a mercantile structure that by necessity disallows the presence of ocean as a real space in order to flatten the world into a Pangaea of capital. The project is presented in two volumes, released in conjunction with an exhibition of Marina Zurkow’s work (with collaborators Sarah Rothberg, Surya Mattu, and others) at bitforms gallery (http://www.bitforms.com/) in New York City in February 2016. This book, More&More (A Guide to the Harmonized System), is an experimental “brick” of a book that intervenes in the Harmonized Commodity Description and Coding System (also known as the HS Code). The HS Code is the internationally accepted standard of product classification, which codifies the way nations conduct import/export. All legal trade products (and illegal ones that find loopholes) are shipped using this system. More&More (A Guide to the Harmonized System) lists the astonishing variety of items that are shipped around the world, and includes instructions for using the code to ship items (both legally and illegally). It also includes poetic, personal, and scholarly annotations by Stacy Alaimo, Heather Davis, Kathleen Forde, Dylan Gauthier, Elena Glasberg, Calliope Mathios, Steve Mentz, Astrida Neimanis, Chris Piuma, Elspeth Probyn, Sarah Rothberg, Phil Steinberg, Rita Wong, and Marina Zurkow. Its companion book, More&More (The Invisible Oceans) (https://punctumbooks.com/punctum/titles/moremore-invisible-oceans/), is a catalog of the exhibition, featuring many full-color images of the art on display (including video stills, bespoke bathing suits, and fungal sculptures), as well as an introduction by Marina Zurkow and a conversation between Zurkow and international curator Kathleen Forde.

More&More: The Invisible Oceans - Marina Zurkow; Sarah Rothberg; Surya Mattu (punctum books, 2016)
More&More is an art and research project that explores the language and mechanics of global trade, container shipping, and the exchange of goods. It questions a mercantile structure that by necessity disallows the presence of ocean as a real space in order to flatten the world into a Pangaea of capital. The project is presented in two volumes, released in conjunction with an exhibition of Marina Zurkow’s work (with collaborators Sarah Rothberg, Surya Mattu, and others) at bitforms gallery (http://www.bitforms.com/) in New York City in February 2016. This book, More&More (The Invisible Oceans), is a catalog of the exhibition, featuring many full-color images of the art on display (including video stills, bespoke bathing suits, and fungal sculptures), as well as an introduction by Marina Zurkow and a conversation between Zurkow and international curator Kathleen Forde. Its companion book, More&More (A Guide to the Harmonized System) (https://punctumbooks.com/punctum/titles/moremore-a-guide-to-the-harmonized-system/), is an experimental “brick” of a book that intervenes in the Harmonized Commodity Description and Coding System (also known as the HS Code). The HS Code is the internationally accepted standard of product classification, which codifies the way nations conduct import/export. All legal trade products (and illegal ones that find loopholes) are shipped using this system. More&More (A Guide to the Harmonized System) lists the astonishing variety of items that are shipped around the world, and includes instructions for using the code to ship items (both legally and illegally). It also includes poetic, personal, and scholarly annotations by Stacy Alaimo, Heather Davis, Kathleen Forde, Dylan Gauthier, Elena Glasberg, Calliope Mathios, Steve Mentz, Astrida Neimanis, Chris Piuma, Elspeth Probyn, Sarah Rothberg, Phil Steinberg, Rita Wong, and Marina Zurkow.

Mourning the Ends: Collaborative Writing and Performance - Maria Shantelle Alexies Ambayec; Kristof van Baarle; Peter Burke; Renata Gaspar; Sozita Goudouna; Nilüfer Ovalıoğlu Gros; Adham Hafez; Jan-Tage Kühling; Eero Laine; Sarah Lucie; Juliana Martins Rodrigues de Moraes; Evan Moritz; et al. (punctum books, 2025)
Mourning the Ends: Collaborative Writing and Performance is an opening, a beginning, an attempt to rethink how we can be, think, and work together. This book, authored by a multitude, explores new methodologies of collaborative scholarship for the arts and humanities within the context of the various ecological, medical, military, and epistemic ends facing the world. The authors of Mourning the Ends performed an experimental methodology as the book was researched, written, and revised by fifteen individuals situated across the globe. The writing emerged in part from a shared sense of mourning through the global pandemic and ongoing ecological catastrophes, yet the questions and arguments that are raised are immediately relevant as the rolling crises of our contemporary moment play out and further develop. The volume challenges a number of key areas in performance studies as well as foundational expectations and assumptions of the arts and humanities more broadly—namely, that writing and scholarship should be solitary endeavors. The authors write back against the model of thinking and studying that centers the singular genius, especially against the backdrop of enduring and apparent end times. Mourning the Ends is in some ways a rehearsal for another future, a speculative engagement with performance, ecology, and academic affiliation beyond institutional bounds—a methodology for shared mourning, performance, and thinking.

Multispecies Storytelling in Intermedial Practices - Ida Bencke; Jørgen Bruhn (punctum books, 2022)
Multispecies Storytelling in Intermedial Practices is a speculative endeavor asking how we may represent, relay, and read worlds differently by seeing other species as protagonists in their own rights. What other stories are to be invented and told from within those many-tongued chatters of multispecies collectives? Could such stories teach us how to become human otherwise? Often, the human is defined as the sole creature who holds language, and consequently is capable of articulating, representing, and reflecting upon the world. And yet, the world is made and remade by ongoing and many-tongued conversations between various organisms reverberating with sound, movement, gestures, hormones, and electrical signals. Everywhere, life is making itself known, heard, and understood in a wide variety of media and modalities. Some of these registers are available to our human senses, while some are not. Facing a not-so-distant catastrophe, which in many ways and for many of us is already here, it is becoming painstakingly clear that our imaginaries are in dire need of corrections and replacements. How do we cultivate and share other kinds of stories and visions of the world that may hold promises of modest, yet radical hope? If we keep reproducing the same kind of languages, the same kinds of scientific gatekeeping, the same kinds of stories about “our” place in nature, we remain numb in the face of collapse. Multispecies Storytelling in Intermedial Practices offers steps toward a (self)critical multispecies philosophy which interrogates and qualifies the broad and seemingly neutral concept of humanity utilized in and around conversations grounded within Western science and academia. Artists, activists, writers, and scientists give a myriad of different interpretations of how to tell our worlds using different media, and possibly gives hints as to how to change it, too.

The Unnaming of Aliass - Karin Bolender (punctum books, 2020)
The Unnaming of Aliass performs a paradoxical quest for wildly “untold” stories in the company of one special donkey companion, a femammal of the species Equus asinus and, significantly, a registered “American Spotted Ass.” Beast of burden that she is, this inscrutable companion helped carry a ridiculous load of human longings and quandaries into a maze of hot, harrowing miles, across the US South from Mississippi to Virginia, in the summer of 2002 – all the while carrying her own onerous and unreckoned burdens and histories. Over two decades, the original journey evolved – from the cracking-open of a quasi-Western novel-that-never-was by an implosive pun, into an ongoing philosophical and assthetic adventure: a hybrid roadside- and barnyard-based living-art practice, wherein “Aliass” un/names something much harder to grasp than the body of a lovely little ass: protagonist, setting, and traditional Western narratives turn inside-out around this “name-that-ain’t.” Through a deeply dug-in questioning of its own authorial assumptions, The Unnaming of Aliass makes space for untold autobiographies and bright dusty lacunae, tracing ineffable tales through the tangled shapes and shadows that interweave in any environment.

The Viscous: Slime, Stickiness, Fondling, Mixtures - Freddie Mason (punctum books, 2020)
Slime, goo, gunge, gloop, gels, sols, globules, jellies, emulsions, greases, soaps, syrups, glues, lubricants, liquid crystals, moulds, plasmas, and protoplasms – the viscous is not one thing, but rather a quality of resistance and flow, of stickiness and slipperiness. It is a state of matter that oozes into the gaps of our everyday existence, across age groups, between cultures and disciplines. Since the large-scale extraction of petroleum in the 19th century, the viscous has witnessed a proliferation in the variety of its forms. Mechanized industry required lubricants and oil distillation produced waste products that were refined to form Vaseline. From this age, new viscous forms and technologies emerged: products from plastic (and plastic explosives) to cosmetics, glycerine, asphalt, sexual lubrication, hydro- and aero-gels, and even anti-climb paint. Based on unique and wide-ranging research, The Viscous is the first major investigation of encounters with and possibilities of the viscous over the course of the last century, not simply as a material state, but also as an imaginative event. We enter into a story of matter at its most wayward, deviant, hesitant, and resistant. From asphalt lakes to industrial molasses tanks, from liquid crystals squirming in our screens to milk fetishes, The Viscous discloses gooeyness as a peculiarly modern phase of matter. “Everything oozes,” as Beckett’s Estragon famously proclaims in Waiting for Godot. Viscous dynamics are exposed as not only hugely various in a post-industrial age, but particularly useful ways of thinking, feeling, writing, and making in a time of ecological anxiety.

The Way Things Go - Louis Bury (punctum books, 2023)
The Way Things Go contains a mix of poetry, art writing, and life writing about anticipatory grief, or mourning someone or something before it’s gone. Each successive chapter in the book decreases in length by exactly one sentence, from a 71-sentence-long opening chapter, to a 70-sentence-long second chapter, to 69 sentences, 68 sentences, and so on down to 1 (a book-length Oulipian “melting snowball”). This shrinking form enacts the book’s concerns with loss, climate change, and the passage of time. At the level of its content, however, The Way Things Go is not fatalistic. Its title comes from a cult classic 1987 Fischli and Weiss film, in which objects such as bags of trash, car tires, and oil drums knock into one another in a Rube Goldberg-esque chain reaction. Moving through both personal history (his sister’s lupus and heroin addiction, his grandmother’s experience as a Holocaust survivor) and more global concerns (the Sixth Mass Extinction, COVID-19, the war in Ukraine), Bury considers the disruptions that occur as “things go,” as well as the continuity that remains. The book suggests that recent negotiations between optimism and pessimism with respect to the future reflect people’s feelings of vulnerability, particularly people who are used to taking their life’s stability for granted, in a world that seems increasingly precarious.

The Wind An Unruly Living - Jeremy Bendik-Keymer (punctum books, 2018)
Barely moving a solid thesis, the creative essay is atmospheric. Yet the wind, although it slips through fingers, grasps at them, a fluid hand on our hands. A process begun in Pisa, Italy in April of 2016 during a workshop on political theory in the Anthropocene, The Wind An Unruly Living is a philosophical exercise (askêsis, translated, following Ignatius of Loyola, as “spiritual exercise”). In his exercise, Bendik-Keymer throws to the void: the ideology of self-ownership from a society of possession. By using the Stoic kanôn, the rule of living by phûsis, he follows an element. Unhappily for the Stoic and happily for us, the wind is unruly. A swerve of currents through a social fabric, it’s full of holes, all holely. Stretch and stitch as you want, it might settle more shapely tattered into light, but it will never become whole. The wind’s only holesome.

The Witch and the Hysteric: The Monstrous Medieval in Benjamin Christensen's Häxan - Alexander Doty; Patricia Clare Ingham (punctum books, 2014)
Benjamin Christensen’s 1922 Swedish/Danish film Häxan (http://en.wikipedia.org/wiki/H%C3%A4xan) (known under its English title as Witchcraft Through the Ages) has entranced, entertained, shocked, and puzzled audiences for nearly a century. The film mixes documentary with fantasy, history with theatrics, religion and science, the medieval past and modern culture. This uncanny content is compounded by the film’s formal strangeness, a mixture of quasi-documentary with fictional episodes, illustrated lectures alongside docudrama recreations and dreamscapes. Is this a documentary, a horror flick, or both? In this chapbook, authors Doty and Ingham argue that the puzzle of Christensen’s Häxan might be unraveled by attending to the film’s provocative and paradoxical medievalism, its fantasmatic rendering of the witch as a medieval monster. Such monstrous medievalism, moreover, sheds considerable light on the politics of gender and culture once the witch is rendered a female figure in a time out-of-joint.

The(y)ology: Mythopoetics for Queer/Trans Liberation - Max Yeshaye Brumberg-Kraus (punctum books, 2023)
Every body contains multitudes, but no body is immune to the ideology of oneness: one true self, one sexuality, one gender, one vision of the world, one true God. For many who identify (or who have been named by others) as transgender, queer, and nonbinary, the refusal to fit within the illusion of one set of sex and gender expectations has been met with violence and suppression. While the myth of oneness is a powerful story that shapes the contours of our societies and our selves, it is not the only myth. Performances, fictions, rituals, and theologies can transform current realities. The(y)ology: Mythopoetics for Queer/Trans Liberation is a manifesto for artists, teachers, theologians, clergy, and activists looking for ways to resist rigid paradigms of gender, sexuality, self, and the sacred. In these pages, we are called to tell new stories about who we are and how we relate to each other within our ecosystems. The myths discussed wrestle with and transform the complex mytho-histories that have birthed and, often, harmed us. No story comes from nothing, and, more radically, perhaps no story is fully irredeemable. In The(y)ology, feminist philosophies join with trans poetics, literary theory with liberation theologies, drag performance with kabbalah, ecologies with pornographies, and ancient theater with queer autobiographies. However ambitious its scope might be, The(y)ology is fundamentally about encouraging us all to think playfully and to play thoughtfully with the mythologies that define our lives.

Thinking with the Sleeping Body: A Feminist Reimagination of Human–Earth Relations - Anu Valtonen (punctum books, 2026)
In times of Earthly crises, habituated Euro-Western vocabularies and imaginaries—dichotomist and human-centric—need to be questioned, and radically different ones developed. Thinking with the Sleeping Body: A Feminist Reimagination of Human-Earth Relations employs the sleeping body as a theoretically informed and politically motivated figure to open novel imaginaries and relationalities—ones that are not based on wakeful rationality, or the possessive quest for controlling and managing everything. The book does not explore the sleeping body as such but is interested in its potential to generate an intellectual space for rethinking and experimenting with Earthly relations creatively and critically, with the aim of paving the way for more caring relations. Valtonen draws from feminist new materialist and post-humanist scholarship, and employs relational feminist methodologies for studying multispecies life. Based on long-term (auto)ethnographic fieldwork in the Northern context, the book discusses the aerial, vulnerable, and temporal relations that are articulated through a breathing body, a (dis)connecting sleeping body, and a sleeping body that slows down. The sleeping body can thus also be seen as a rebellious body in the world of stories occupied by wakeful heroic-masculine protagonists. Ultimately, Valtonen argues, creative thinking on the sleeping body opens up new spaces for imagining and enacting more caring, and more-than-human, relations with a fragile Earth.

thN Lng Folk 2go: Investigating Future Premoderns™ - Norman Hogg; Neil Mulholland (punctum books, 2013)
Neomedievalisms are cultural practices that breathe a bouquet of premoderns as permanent rehearsals of coming events. Where medievalists may be prone to police the post-medieval weald for inauthentic medievalisms, neomedievalists embrace the articulation and mobilisation of metahistorical anachronisms. To the medievalist, medievalisms provide powerful indexes that reveal how post-medieval societies have variously imagined ‘little middle ages’ to suit modern agendas. To the neomedievalist, medievalisms are theory-fictions that facilitate ludic speculation on non-modern futurities. While neomedievalist theories have emerged in a variety of fields since the early 1970s — notably in cultural studies of medievalisms, international relations and literary theory — there are few applications that synthesise and put the methodologies of these diverse fields into practice. thN Lng folk 2go applies this extant scholarship as an extradisciplinary practice, dramatising the neomedieval turn in (quasi)objects, persons, work, education, travel, food, ethnicity, media, art, hypereconomics and technology. This speculative journey is ghost authored by a trinity of neomedievalist narrators — Journeyman, Anchorite and Host — each relic-ing their own curious neomedieval futurities. Drawing its heterogeneous approaches from studies in medievalisms, international relations, literary theory, actor-network theory, anthropology, hypereconomics, art history, aesthetics, ecology, cultural theory, cultural geography, ambience, speculative realism and future studies — thN Lng folk 2go is both an investigation of and a benefaction to a murmuration of neomedievalisms.

Thoughtrave: An Interdimensional Conversation with Lady Gaga - Robert Craig Baum (punctum books, 2016)
Thoughtrave is the immediate and most detailed archive of Lady Gaga’s emotional, intellectual, philosophical, and spiritual evolution, a reclaiming of her art (and humanity) from within the center of her celebrity during one of the most difficult transitions of her career: Summer 2013–Fall 2014. Thoughtrave marks perhaps the most important (and unconditional, unpublished, unencumbered) insights into the music industry, as well as into the personal battles that accompanied Lady Gaga’s transition from Stefani to Gaga. “It’s one of those rare moments in life when you ask a question of someone you’ve admired for many years and receive the most honest of answers leading both people into a relationship that was and remains one of the most important of my life,” says Baum. As Baum explains to Stefani in one of the many interviews published here for the first time, "It’s uncanny for me to look back at 2008–2011 — when I was intensely meditating on the problem 'Why is there any being at all?' — to find evidence of your intervention here with me…to find you, back then…before I knew you. It was almost as if I was playing the Bruce Willis character in Twelve Monkeys, overshooting my mark in time/space, aiming for this particular conversation but speaking through Ereignis (life gives) to a moment I (and many others) call 'headphones on.'"

To Be, or Not to Be: Paraphrased - Bardsley Rosenbridge (punctum books, 2016)
To Be, or Not to Be: Paraphrased is an expanding deconstruction of Hamlet’s famous existential question, achieved by putting the line through paraphrasing software 50 times. With each permutation, the quotation grows longer and its meaning is distorted, causing the question to question its own existence by acting as a faulty self-replicator, a nonsensical self-affirmation that destroys itself in the process of becoming. This controlled explosion of a sentence was performed by Bardsley Rosenbridge as part of his work with the Dark Meaning Research Institute (http://www.darkmeaningresearchinstitute.org), a group of parasemantic experimenters developing innovative ways to extract hidden meaning from the world around us.

Topie Impitoyable: The Corporeal Politics of the Cloth, the Wall, and the Street / Les politiques corporelles du vêtement, du mur et la rue - Léopold Lambert (punctum books, 2016)
What is a body? This book is more attached to raising the question than in offering a definitive answer. Instead, Lambert proposes to make more complex certain commonplaces located at various degrees of proximity to the body’s material assemblage, allowing a better integration of the surrounding objects, atmosphere and other bodies and proposing a political reading of their relationship to the body, whether deliberate or accidental. From the hoodie that Trayvon Martin wore when he was killed in the suburbs of Miami Gardens, Florida, to the streets of New York City during Occupy Wall Street and the apartheid wall in Palestine, this book moves through a series of episodes that illustrate how bodies and objects of all sizes are enmeshed in deeply entangled political relationships.

Toward a Radical Metaphysics of Socialism: Marx and Laruelle - Katerina Kolozova (punctum books, 2015)
Departing from the conventional readings of Karl Marx’s Capital and other of his works, by way of François Laruelle’s “radicalization of concepts,” Katerina Kolozova identifies a theoretical kernel in Marx’s thought whose critical and interpretative force can be employed without reference to its subsequent interpretations in the philosophical mainstream. The latter entails a process of abstracting a philosophical legacy — or rather, of putting it in brackets — and then codifying a history of a learned interpretation established in supposed fidelity to the theoretical project of a “master.” Interpreting the master implies a mastery of doctrinal tools, which results in establishing a catechism of the Logos of the Master. And this catechism interferes, Kolozova argues, with more direct encounters with Marx’s writings. As we know, Marx’s rigorously descriptive language unravels the radical core of capitalist economic processes and, through that unraveling, also reveals capitalism’s necessary exploitation and subjugation of human labor. Toward a Radical Metaphysics of Socialism attempts to recuperate and emancipate the notion of metaphysics in this scenario by virtue of radicalizing thought’s encounter with the Real. Kolozova argues that this metaphysical drama is at the origin of the social and economic injustices of contemporary global economic-political realities, and she illustrates this state of affairs in discussions of the problem of wage labor, automated speculation as the core of late capitalism, the post-2008 financial crisis, the status of technology in late capitalism, sexual difference and gender, and the human and non-human body’s subjugation capitalist automation.

Traffic Jams: Analysing Everyday Life through the Immanent Materialism of Deleuze & Guattari - David R. Cole (punctum books, 2013)
This dead letter presents an exploration of the immanent materialism of Deleuze & Guattari as theorised in A Thousand Plateaus as a means to analysing everyday life. The evidence consists of art, film and objects from life that relate to and suggest the complex ways in which we are affected by traffic jams. Reciprocating substrata of everyday life build upon the unconscious, and show how the abstract turbulence of everyday life forms eddies and flows that may be followed and understood. The immanent materialism of Deleuze & Guattari is a philosophical construction that leads to the formation of ‘plateaus’ as they were executed in A Thousand Plateaus. The plateau of this dead letter is [21 October 2011: the Petro-Citizen] and is populated with traffic jams, car crashes, global environmental concerns and the psychological and sociological contingencies that accompany the petro-citizen. Connections between the strata that make up the plateau of the petro-citizen will deliberately be left as open-ended and speculative to show how the petro-citizen functions as a flagrant construct in everyday life, which includes the desire for petrol and explains the resulting panpsychic petro-political landscape. The double-articulation of the plateau depends upon the ways in which the petro-citizen and petro-politics create reciprocating realms of motivation and drive that tend towards contemporary double-articulation, paradox and contradiction with respect to the usages of oil. This double-articulation results in a multiple chequered flag or illusionary global end-game that designates the current human relationships with oil.

Transfer Queen - A.W. Strouse (punctum books, 2018)
Cruising the New York City subway, the Transfer Queen is on the prowl! These voyeuristic figure drawings—both poetic and visual—sketch the men of Gotham’s transportation system. A.W. Strouse and Patty Barth spy on strangers with a special kind of anonymous intimacy. Transfer Queen is ideal reading material for kinky commuters. But remember: “A crowded subway car is no excuse for unlawful sexual conduct!”

Transparent Things: A Cabinet - Maggie M. Williams; Karen Eileen Overbey (punctum books, 2013)
Inspired by a passage in Vladmir Nabokov’s Transparent Things (1972), and also compiled as a future love letter to The Material Collective (http://thematerialcollective.org/), the essays collected here play with the transparency of pedagogy, scholarship, and writing, as well as with objects that can be seen through, such as crystals and stained glass. As Nabokov wrote, For the art and literary historians gathered together in this volume (Angela Bennett Segler, Jennifer Borland, Karen Eileen Overbey, Nancy Thompson, and Maggie M. Williams), all students of medieval material, these tensions between surface and depth, present and past, concentration and skimming are all too familiar. The inherent contradictions of medieval objects, their irreducibility to either the purely intellectual or the merely physical, are at once the delights and the dangers of the art historian’s work. This book thus offers a dialogue on the question of how our encounters with physical things spark a process and how objects might allow unique collisions between the past and the present, the human and the inanimate, the practice of history and lived experience. As works of medieval studies or art history, these essays are incomplete, awkward, and provisional. Some of them may even read like embarrassing teenage poetry. This collection is like that dusty box in the basement: it is full of raw, unedited, transparent expressions of affect, of the sort we have learned to hide.

Tribulations of a Westerner in the Western World - Vincent Dachy (punctum books, 2024)
Someone has taken a trip and taken photographs of that trip and someone else has been invited to watch a slideshow of the trip taken. There is a road, there is an abstract painting, there is a viewer who wishes he could live in a televised loop of a sunset, and another who wonders why people are obese. Tribulations of a Westerner in the Western World is a stunner of a first book, a narrated slideshow of inner and outer geographies complete with fifty-two black-and-white photographs taken by the author. This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

Trickbox of Memory: Essays on Power and Disorderly Pasts - Felicitas Macgilchrist; Rosalie Metro (punctum books, 2020)
Reach into this trickbox of memory and rummage around: you may find a tiny spaceship, or perhaps a signpost, a parade, a raised fist, or an entire museum. The essays in Trickbox of Memory: Essays on Power and Disorderly Pasts draw on literary criticism, post-qualitative inquiry, new materialisms, and political activism to dismember and reanimate the field of memory studies. In the trickbox, concepts rub up against each other, pieces chip off, things leak, and glitter gets everywhere. Things are damaged, their edges are ragged. Some show the potential for repair in the future. Collectively, the contributors to Trickbox of Memory cross from Israel and Palestine to aboriginal culture in Australia and New Zealand to black student protests in Mississippi to outer space and beyond, responding to the observation that in today’s moment of political danger, “expected” pasts can easily be instrumentalized in the service of fascism. Trickbox of Memory interrupts the “expected” to throw history into disarray by focusing on the subtlety of how power relations are enacted and contested in reference to the past, assembling a transnational constellation of scholars and practitioners who offer new tricks for working critically with disorderly pasts.

Trouble Songs: A Musicological Poetics - Jeff T. Johnson (punctum books, 2018)
Trouble Songs is a hybrid serial work that tracks the appearance of the word “trouble” in 20th- and 21st-century American music. It reads (and sings) songs and poems, with reference to cultural events ranging from the death of a pop singer to the growth of popular resistance movements. The trouble singer invokes the word “trouble” in place of actual trouble—the song is a spell that conjures trouble (from bad luck and disaffection to infidelity, impotence, destitution, and the specter of death) in a temporary form that can be dis-spelled, if only for the length of the song. Singer and song also open a critical space for making trouble, for stirring the heart and mind. This space is a disjunction in time (and a superimposition of events) where singer and listener collaborate on meaning (un/)making as they temporarily transform trouble. Trouble Songs enacts its poetics with the use of footnote and body text as modular, contiguous, and porous fields of writing and imagination, a corollary for overlapping singer/listener roles. In effect, the footnotes sing along with (and trouble) each chapter, providing chorus and counterpoint to these Trouble Songs, as the compositional horizon between body and notes rises and falls. These cultural investigations suggest that the way we sing about trouble, and the way we receive those songs and cultural transmissions, says much about what preoccupies us spiritually and intellectually—what moves us and disturbs us, brings us together even as we keep some things to ourselves.

Truth and Fiction: Notes on (Exceptional) Faith in Art - Milcho Manchevski (punctum books, 2012)
Reflecting upon his experience making his 2010 feature film Mothers (http://www.imdb.com/title/tt1588880/), a cinematic triptych interweaving three narratives that are each, in their own way, about the often tenuous lines between truth and fiction, and one of which actually morphs into a documentary about the aftermath in a small Macedonian town where three retired cleaning women were found raped and killed in 2008 and the murderer turned out to be the journalist covering the story for a major Macedonian newspaper, the Oscar-nominated Macedonian-born and New York-based writer-director Milcho Manchevski (http://www.manchevski.com/default.htm) writes that, “Most of us look at films differently or accept stories in a different way if we believe that they are true. We watch a documentary film in a different way from the way we watch a drama. We read a magazine article in a different way from the way in which we read a short story. Sometimes, we even treat a film that employs actors differently than a regular drama because we were told that it is based on something that really happened. We treat these works based on truth or reporting on the truth in different ways.” Further, he asks, “What is it in our relation to reality or in our relation to what we perceive to be reality that makes us value a work of artifice (an art piece) differently depending on our knowledge or conviction of whether that work of artifice is based on events that really took place?” In this extended essay, or letter, Manchevski ruminates the different ways in which both filmmakers and audiences create, experience, and absorb the cinematic narrative with a certain trust and faith in the artwork to render, not the factual truth, per se, but the importantly shared experience of trusting “the plane of reality created by the work itself,” such that “we trust its inner logic and integrity, we have faith in what happens while we give ourselves to this work of art.” Truth becomes a question of what artist and audience can see and feel together: what feels real becomes the world we inhabit.

What Is Philosophy? - Michael Munro (punctum books, 2012)
“Every written work,” Giorgio Agamben opens the preface to Infancy and History, “can be regarded as the prologue (or rather, the broken cast) of a work never penned, and destined to remain so.” Although that observation applies to any work of writing, the exemplary case is that of a work of philosophy. While every written work is put to work in its nonexistent successor, a work of philosophy is bereft of even that recourse: philosophy is written in the breakdown of destiny, so that every work of philosophy must first and foremost confront the absolute abandonment of its writing. At work in each and every work of philosophy is the question, “What is a work of philosophy?” More concretely, although well-formed and rigorously structured, What is Philosophy? abstains from work. On even a quick reading that fact must be palpable. A seminar paper? An article, or book chapter? Not in the least. Nor, essentially, may the individual pieces that compose it be so developed. Fragments unrecognizable as at one time a cast, inconceivable at a future time as anything else, the position of each piece with respect to the others thwarts development in order to preserve, in its place, the tension of its absence. As such, the articulations internal to each of the three divisions, and between them, are essential. The first division — What is Philosophy? — takes seriously Deleuze and Guattari’s contention in their book of the same title that “The nonphilosophical is perhaps closer to the heart of philosophy than philosophy itself, and this means that philosophy cannot be content to be understood only philosophically or conceptually, but is essentially addressed to nonphilosophers as well” — including the nonphilosopher in every philosopher. The second division — On Argument — interrogates the status and value of evidence, and self-evidence. The third division — On Not Knowing — generalizes a parenthetical observation of Agamben’s on Heidegger, “If we may attempt to identify something like the characteristic Stimmung of every thinker, perhaps it is precisely this being delivered over to something that refuses itself that defines the specific emotional tonality of Heidegger’s thought”: Might not philosophy be defined, the phil of sophia, precisely, as what it is to be delivered over to something that refuses itself? The first contours of a darkling shape, What is Philosophy? is none other than these—and nothing beyond their glimmer.

Where the Tiny Things Are: Feathered Essays - Nicole Walker (punctum books, 2017)
In this collection of longer essays nested within brief, lyrical meditations, each piece focuses on some micro aspect of everyday life as a means of exploring complex macro systems—families, dinner parties, vineyards, deserts, nations. For example, Walker’s own experience as the mother of a micropreemie (a baby born weighing less than one pound, twelve ounces, or before twenty-six weeks gestation), “the smallest thing in the world,” spurs an exploration of, among other things, the economics of health care, the causes of premature births, and the ethics of extreme interventions. Where the Tiny Things Are is a book of ideas and an exploration of science. It is of the world and of the heart – both intensely personal and expansively empathetic.

Who Killed the Berkeley School? Struggles over Radical Criminology - Herman Schwendinger; Julia Schwendinger (punctum books, 2014)
The Berkeley School of Criminology stands, to this day, as one of the most significant developments in criminological thought and action. Its diverse participants, students and faculty, were true innovators, producing radical social analyses (getting to the roots causes) of institutions of criminal justice as part of broader relations of inequality, injustice, exploitation, patriarchy, and white supremacy within capitalist societies. Even more they situated criminology as an active part of opposition to these social institutions and the relations of harm they uphold. Their criminology was directly engaged in, and connected with, the struggles of resistance that emerged in the late 1960s and early 1970s. Not surprisingly perhaps, they became a target of regressive and reactionary forces that sought to quiet those struggles. Notably the Berkeley School of Criminology was targeted by key players in the US military-industrial complex such as Ronald Reagan himself, then Governor of California and Regent of UC-Berkeley. Who Killed the Berkeley School? by Julia and Herman Schwendinger, key players in the Berkeley School, is the first full-length, in-depth analysis, of the Berkeley School of Criminology, its participants, and the attack against it. It tells the story of an important infrastructure of resistance, a resource of struggle, and how it was dismantled. It lays bare the role not only of conservatives but of liberal academics and false critical theorists, who failed to stand up in defense of the School and its work when called upon. This is a story with profound lessons in the current period of corporatization of campuses, neoliberal education, and market-driven curricula. It will be of interest to anyone concerned with developing resistance to the corporate campus and seeking critical alternatives. It also stands as a challenge to social science disciplines, including criminology, to develop a practice that identifies the roots of social injustice and organizes to confront it.

Why the Center Can't Hold: A Diagnosis of Puritanized America - Tom O’Neill (punctum books, 2016)
“Things fall apart; the centre cannot hold.” These words from Yeats’s poem “The Second Coming” provide Why the Center Can’t Hold with its organizing theme. And although Yeats was describing the grim atmosphere of post-World War I Europe, O’Neill regards the poem’s pronouncements as eerily predictive of the state of the world as we are currently observing it. O’Neill takes them as predictive of the agency in particular of the United States—the “Center”—in bringing about in the world the more general chaos we are now observing (relative to various refugee and migrant crises, the emergence of sophisticated and even postmodern forms of militant and cyber terrorism, banking and other monetary crises, environmental catastrophes under the aegis of climate change, the defunding of public higher education, the persistence of virulent forms of racism and other types of intolerance, the concentration of wealth in fewer and fewer hands, the marginalisation and even outright elimination of human labor forces, etc.). O’Neill provides historical analyses that illuminate why this is the case, and he also asks what changes in the United States — in its politics, in its socio-cultural formations, and in its beliefs and (supposedly common) values — might help us to avoid the inevitable (and lamentable) destruction that seems ahead. In the first section of the book, O’Neill begins with a survey of destructive trends in education, finance, and military policy, and the intent here is to show how these trends work together to produce a negative synergy of great momentum. This section also looks at the systemic abuse and mismanagement of natural resources and the environmental destruction all of that has also wrought: “The war-making tendencies feed off the accumulative tendencies; the accumulative tendencies feed off the war-making tendencies. Both depress education. In the negative synergy of all this, injury to habitat is consistently written off as unintended — therefore unimportant — collateral damage.” Further, O’Neill takes an unvarnished look at Max Weber’s thesis that the Protestant ethic provides the animating force of the “spirit” of capitalism, and he finds in this ethic the common source of the destructive trends we are currently experiencing. More specifically, O’Neill accepts Weber’s claim that the doctrine of predestination, particularly as articulated by John Calvin and his immediate disciples, is not just a handy rationalization for capitalism, but is the actual motivating principle operating at its roots. Further, O’Neill agrees with Weber that while capitalism has organized the western world, it has been especially forceful in shaping America. While most everyone will acknowledge that Calvinist Puritanism functioned as the foundation for colonization in New England, it is quite a bit more to claim that Puritanism is the organizing ethos of the entire (and contemporary) United States, and it is O’Neill’s intent to trace the processes and various routes by which this surprising eventuality took place. People will kill and be killed sooner than change their minds. In fact, this resistance to mind-change seems especially strong among us children of Puritans. And so the final question: Can we, in the face of a manifest need to do so, change our minds? Can we abandon an unexamined and bankrupt ideology? In the second section of his book, O’Neill works to unveil the epistemological maneuvers whereby Americans attempt to deny there’s anything systematically wrong with America. He argues that various forms of skepticism provide convenient paths of evasion that allow us to dodge fairly self-evident indications of trouble. In the third section, he addresses those who acknowledge there is indeed notable, deep-rooted trouble, but who have found ways to shrug it off. In his conclusion, O’Neill suggests that the civil rights struggles of the 1950s onward (relative to race, gender, sexuality, able-ness, etc.) offer a paradigm for an alternative to our present self-destructive way of life, and that the core principles of the Enlightenment embedded in our Constitution — principles to which we have always paid lip-service — could even now lead us to a reconstitution of a better and more just American polis.

Widening Scripts: Cultivating Feminist Care in Academic Labor - Mariana Prandini Assis; Michelle Forrest; Angela Henderson; Lindsey MacCallum; Ian Reilly; Ellen Shaffner; Scott Stoneman (punctum books, 2023)
Widening Scripts: Cultivating Feminist Care in Academic Labor is addressed to scholars, educators, and students devoted to the struggle against precarity, atomization, and the commodification of knowledge. Through shared reading, discussion, and reflection, and gathered around a shared interest in feminist theory and politics, the authors discovered a model of care within academia that helped them to sustain their opposition to dominant academic practices that are diminishing, competitive, and exploitative. In this book, the authors narrate that discovery and the realization of a desire to share in the assembling of a collective feminist survival kit. In Living a Feminist Life, Sara Ahmed offers a wide-ranging killjoy survival kit that includes books, things, tools, time, life, permission notes, other killjoys, humor, feelings, and bodies. As a response to the stress, strain, and profound grief produced by the COVID-19 pandemic, with its viral acceleration of crises already endemic to neoliberal capitalism, the authors mined an evolving cluster of decolonial feminist texts in an attempt to find meaning, encounter moving premonitions, and engage with radical instigations to thought. By co-creating a survival kit through sustained collaboration during the pandemic, they develop a sense of the value of experimentation and risk-taking and learn how to cultivate an inclusive space that allows them to express their views, reclaim accountability, and learn confidently from each other. Widening Scripts combines collaborative feminist theory, acts of care, and critical dialogue in an effort to open up decelerated, altruistic, and connected ways of doing academic work together.

Wilhelm Reich versus the Flying Saucers: An American Tragedy - James Reich (punctum books, 2024)
The convenient myth of Wilhelm Reich is that he “lost his mind” in the early 1950s, if not before, and that the last seven years of his life and work—the orgone and radiation experiments, the cloudbuster, and flying saucer intrigues—present an embarrassment. Even the counterculture that embraced Reich, not least William S. Burroughs, Norman Mailer, and filmmaker Dušan Makavejev, tended to distort his theory. The psychosis attached to Reich by his detractors was the culmination of decades of scapegoating by psychoanalysts, Nazis, communists, and conservatives. But Reich’s environmental and Cold War preoccupations and his slow-burning fascination with UFO phenomena were not signs of a madness incipient since his break with Sigmund Freud. They anticipated and reflected much in the American psyche. Defining the presence of a “cinematic self” in the misunderstood analyst once considered an heir to Freud, Wilhelm Reich versus the Flying Saucers rejects orthodox portrayals of Reich’s final years as merely pathological. Combining original analysis and evidence from the Wilhelm Reich Archive, James Reich uncovers the fatal moments in the psychologist’s uncanny identification with the “spaceman,” and the myth of a scientist lost to his own grandiosity and paranoia. Taking seriously the influence of The Day the Earth Stood Still, Bad Day at Black Rock, and other pop cultural narratives on Reich, this “psychoanalytic detective story” concerns existential traps, conscious and unconscious collaborations and betrayals by disciples, and unidentified flying object-relations. Reich’s is an atomic-age passion narrative. Vitally, Reich’s story could be ours. The author is not related to his subject.

Winter Light: On Late Life's Radiance - Douglas J. Penick (punctum books, 2025)
In the contemporary West, the elderly are regarded as somehow “other,” no longer who they used to be, no longer full members of the worlds they once inhabited. Being old is seen as a medical management issue. But old age is not a defective version of what preceded it; it is—like childhood, adolescence, and middle age—its own time of life with its own challenges and gifts. It is an unexpected experience and largely unknown terrain. Winter Light: On Late Life’s Radiance is an exploration of old age as a time when sudden and uncontrollable losses reveal and clarify patterns of existence formerly obscured. In this context, Penick tells of the lives of artists, musicians, and others who, in old age, changed radically through visionary modes of experience that otherwise would not have been possible. Near the end of their lives, Titian, Michelangelo, Beethoven, Rabindranath Tagore, Jean Rhys, Andrea Palladio, Paul Cézanne, Leoš Janáček, Igor Stravinsky, and others found unforeseen paths and articulated subtleties and beauties never before encountered. Their visions are now woven into our culture and the stories of their lives are signposts for us. As Thoreau once said: “Not ’til we are lost… not ’til we have lost the world, do we begin to find ourselves and realize where we are and the infinite extent of our relations.” In five essays, concerned respectively with body, connection, pattern, loss, and vision, Winter Light explores irretrievable losses and dawning possibilities. Penick gives voice to aspects of the inner life that in old age unfold with unanticipated depth, breadth, strangeness, and light.

Wonder, Horror, Mystery: Letters on Cinema and Religion in Malick, Von Trier, and Kieślowski - J.M. Tyree; Morgan Meis (punctum books, 2021)
Wonder, Horror, Mystery is a dialogue between two friends, both notable arts critics, that takes the form of a series of letters about movies and religion. One of the friends, J.M. Tyree, is a film critic, creative writer, and agnostic, while the other, Morgan Meis, is a philosophy PhD, art critic, and practicing Catholic. The question of cinema is raised here in a spirit of friendly friction that binds the personal with the critical and the spiritual. What is film? What’s it for? What does it do? Why do we so intensely love or hate films that dare to broach the subjects of the divine and the diabolical? These questions stimulate further thoughts about life, meaning, philosophy, absurdity, friendship, tragedy, humor, death, and God. The letters focus on three filmmakers who challenge secular assumptions through various modes of cinematic re-enchantment: Terrence Malick, Lars von Trier, and Krzysztof Kieślowski. The book works backwards in time, giving intensive analysis to Malick’s To The Wonder (2012), Von Trier’s Antichrist (2009), and Kieślowski’s Dekalog (1988), respectively, in each of the book’s three sections. Meis and Tyree discuss the filmmakers and their films as well as related ideas about philosophy, theology, and film theory in an accessible but illuminating way. The discussion ranges from the shamelessly intellectual to the embarrassingly personal. Spoiler alert: No conclusions are reached either about God or the movies. Nonetheless, it is a fun ride.

Workers Leaving the Studio: Looking Away from Socialist Realism - Vincent W.J. van Gerven Oei (punctum books, 2015)
Workers Leaving the Studio. Looking Away from Socialist Realism. catalogs the exhibition “Workers leaving the studio. Looking away from socialist realism.,” curated by Mihnea Mircan in the National Gallery of Arts in Tirana, Albania in 2015. According to Mircan, “The […] exhibition reflects on another projection machine, whose history and consequences, unlike cinema, are circumscribed by national boundaries, specific histories, and ideological configurations. The regime of production and representation of socialist realism radicalizes the violence that the creation of a new image does to its subject: it intensifies the fraught relation between refashioned representation and that which is represented. Its insistence on a particular, projective notion of reality is commensurate with the coercion of daily — cultural, social, emotional — life into a grid whose perspective lines and vanishing points carry heavy ideological charges. It enforces what it represents onto that which it represents, so that representation would replace reality.” Apart from a full documentation of the exhibition by photographer Marco Mazzi, the catalogue also features theoretical and art-historical contributions, both in English and in Albanian, on socialist realist art as developed in Albania under the communist regime, as well as texts highlighting contemporary attempts to display political realities through progressive artistic practices.

Works for Works - Gavin Keeney (punctum books, 2022)

Works for Works, Book 1: Useless Beauty - Gavin Keeney (punctum books, 2022)
Works for Works, Book 1: Useless Beauty tackles “legacy” issues of intellectual property rights (IPR) in artistic production and academic scholarship and proposes a category or class of works that has no relation to IPR nor to proprietary regimes of copyright and academic privilege. Keeney’s book is a structuralist argument for establishing new forms of artistic scholarship that operate in direct opposition to established norms in both the art world and neoliberal academia, and is also rigorously contextualized within past and present-day arguments for and against patrimonial and paternalistic, avant-garde and normative forms of censure and conformity across cultural production. Works for Works, Book 1: Useless Beauty privileges an iterative, generative, and aleatory methodology for artistic scholarship, with transmedia proposed as a “tutelary form” of editioning works against the dictates of the art-academic complex. This focus on generativity also invokes the dialectical operations historically associated with past avant-gardes as they have negotiated an elective nihilism as an avenue for exiting established and authorized forms of conceptual and intellectual inquiry in the Arts and Humanities.

Works for Works, Book 2: "No Rights" - Gavin Keeney (punctum books, 2026)
Works for Works, Book 2: “No Rights,” privileges works-based agency (praxis) in literary-artistic scholarship. The principal focus of the Franciscan-inspired embrace of a “no rights” status for works of literary-artistic scholarship is toward freeing both author and works from forms of technocratic determinism and neo-utilitarianism associated with regimes of intellectual property rights law and platform cultures. Engaging, and then dispensing with, the concept of “the artistic exception,” a holdover from modernist justifications for art in/for itself, Works for Works nonetheless restores the primacy of the work itself through disconnecting author and work toward a transfiguration of both author and work and the substantiation of a new ecosystem for radical works of artistic-critical inquiry. Works for Works, Book 2: “No Rights,” follows upon Works for Works, Book 1: Useless Beauty (https://punctumbooks.com/titles/works-for-works-book-1-useless-beauty/) (2022), a structuralist-inspired survey and exposé of the immanentist paradox artist-scholars inhabit in the post-contemporary transition from modernist and post-modernist reflexivity to forms of cultural production that favor no singular raison d’être nor socio-cultural, socio-economic, or socio-political bias.

Wound Building: Dispatches from the Latest Disasters in UK Poetry - Danny Hayward (punctum books, 2021)
I want to hate more and more graphically the devastation of the concepts that now collapse into resentful anxiety about borders and the impoverished people who die on the wrong sides of them, and I want the sickness to be historical, a lesson learned in the nerves from the intricate history in which the desire for communism pursued through struggle led to so many accomplishments beyond our power of anticipation. I want the sickness to flare up in the communism that sickens me by virtue of its exclusion of exactly that sensation, along with so much else of what happened in the period that separates the present from its decades-old doppelganger. What is there now besides bad options? Danny Hayward, Wound Building Wound Building is a volume of essays, with digressions, on one group of contemporary poets active in a self-organizing political poetry scene in the UK, most of whom have little to no audience outside of the little magazines that they publish and the reading series they put on. This book is a front-line report on the rapid development of this poetry in the period between 2015 and 2020, with a particular focus on the relationship of poetry to violence and its representation. The poets discussed here write violent love poems and violent elegies as well as violent fantasies composed in stabs of violent verse and violet prose. The poems themselves comprise fantasies of killing David Cameron, dreams of being split open along a seam, basement songs, hundreds of pages of notes on working life in a privatized care home in Hove, East Sussex, a four-line slogan about the Cologne groping scandal of New Year 2016, variations on the Refugees Medical Phrasebook, a life wasted in a factory in Guangzhou, an autobiographical sci-fi internet fever dream, an anarchist elegy, and a refusal to argue. Ultimately, Hayward suggests that the lessons this poetry teaches is never to write a “worthy” narrative when a fucked up collage will do. Rather than a cohesive “account” of a “school” of poets, or a “contribution” to the boring tittle-tattle of aesthetic debates over British poetry as an institution, Wound Building is a front-line report on the local disasters of a contemporary UK poetry caught in the grip of the historical cataclysm of capitalist culture. Wound Building is further concerned with aesthetic problems related to Marxism, anarchism, contemporary trans politics, and class, though its “theoretical” preoccupations are subordinated to its desire to provide a ground-level view on the writing itself, its production, its intellectual aporia, and the ways it finds itself outstripped by the ongoing “march of events.” The book will be of interest not only for those concerned with contemporary British political and experimental poetry, but also more generally for anyone who wishes to think carefully about what it means to make art about present-day history and its many horrible enormities. The book’s title is derived from the idea of a sublime woundedness that subtends the context of the poets discussed here: the impressions of wounds opening up like LED-lit shopfronts in the night, in a parallel universe in which injury is intoxicatingly impersonal and structural, and which forms the environment in which the poems fight to absolutize the value of every last breath, or face into the reality of extravagantly violent wish fulfillment, or dissolve themselves in a search for new ways of professing love, or transform into a kind of expressionism of vomiting up medical-diagnostic categories found in abstract social labor, or pump their verses full of the convulsive rhythms of surprise and sudden relief, without any guarantee that this is the right thing to do or that anyone will even fucking hear. Wound Building does not historicize this state of affairs as much as it attempts to live alongside the immediacy of this work, in order to see what is still possible for poetry, and criticism, to make and do.

Writing Art - Jeremy Fernando (punctum books, 2015)
Writing Art is an attempt to respond to the possibilities of art, the potentialities in art, to the possible event that art is. Keeping in mind that events are always already potentially beyond us, are quite possibly unknown, unknowable. In this book, Jeremy Fernando meditates on art through a response to specifics works, to the specificity of the craft, tekhnē, of each work; offering a reading of specific works of photography (Photovoice sg), poetry (Tammy Ho Lai-Ming), installation art (Charles Lim), film (Tan Chui Mui), conceptual art (ZXEROKOOL), and charcoal drawings (Yanyun Chen). For, to write is always also to scribble, to scratch, tear, quite possibly open — and perhaps more importantly, to open the possibility of a relation with another, to the unknowability that is the other. At the risk that this writing causes one to writhe, to be torn, to cry out; even if the very one is himself.

Writing Death - Jeremy Fernando (punctum books, 2011)
Writing Death opens a meditation on the possibility of mourning; of whether there is a subject, or even object, that one mourns—of whether one is mourning, can only mourn, the very impossibility of mourning itself. The manuscript is framed by two attempts at mourning—Avital Ronell’s “The Tactlessness of an Unending Fadeout” and Jeremy Fernando’s “adieu.” In-between—for this is where both pieces posit the possibility of attending to the passing, the memory, the fading of the person—is an attempt to think this impossibility. The text is continually haunted by the question of whether one is mourning the person as such, or a particular version of the person, a reading of the person. And in reading another, in attempting to respond to the other, one can never have the metaphysical comfort that one is reading accurately, correctly; in fact, one may always already be re-writing the person. Thus, all one can do is attempt to mourn the name of that person, whilst never being certain of whether her name even refers to her any longer.

Writing in the Kitchen with Martha Rosler and Carrie Mae Weems: From Reproductive Labor to the Affective Labor of the Image - Kimberly Lamm (punctum books, 2026)
What do images have to do with the stubborn perception that women are naturally and fundamentally mothers? How can artwork aligned with feminism teach us to see women differently? In Writing in the Kitchen with Martha Rosler and Carrie Mae Weems: From Reproductive Labor to the Affective Labor of the Image, Kimberly Lamm explores these questions by examining two artworks from the canon of feminist art: Martha Rosler’s video Semiotics of the Kitchen (1975) and Carrie Mae Weems’s photo-text installation Kitchen Table Series (1990). Drawing on psychoanalytic feminism, Lamm demonstrates how these artworks challenge dominant images of women in the American cultural imagination, reveal the fantasies of maternal care we bring to those images, and expose the expectation that women will craft images of their bodies that transmit comforting, easily consumable affects. Lamm calls the work of meeting this expectation the affective labor of the image and follows the interrelated ways Rosler and Weems work through this deep-seated expectation, expressing ambivalence about the idea that women can—and should—naturally care for others for free, without complaint, and in the name of love. By reading Semiotics and Kitchen Table in tandem, Lamm shows how the two works of art evoke the interrelated ways white and Black women in the United States have been called into the affective labor of the image, and by limning their distinct themes and stylistic features, Lamm also illuminates the differences the history of US racism has made in those affective conscriptions.

Xenoflesh: Vegan Poetics and Capitalocene Meat - Simon Ryle (punctum books, 2026)
In Xenoflesh: Vegan Poetics and Capitalocene Meat, Simon Ryle considers the representation of flesh and meat in an eclectic range of literary texts, artworks, and films produced incipient to and across capitalocene modernity, from Hesiod’s Theogony and Rembrandt’s The Slaughtered Ox to Tobe Hooper’s The Texas Chainsaw Massacre and Olga Tokarczuk’s Drive Your Plow Over the Bones of the Dead. Encompassing sensational genre pieces alongside high-brow canonical works, Xenoflesh explores a diverse array of affective, sensational, uncanny, and weird meat and flesh aesthetics. Centrally, the book seeks to understand these representations in the context of industrial models of production and resource extraction, and explores how these artworks trouble or contest normative modes of affect, sensation, and consumption promulgated by the Capitalocene’s creation of surplus value from industrially farmed animal flesh, one of the key drivers of land degradation, mass extinction, and climate breakdown. The central concept “xenoflesh” describes aesthetic forms and motifs that produce a sudden awareness of uncanny embodiment. Prefixing the flesh of creaturely being with the Greek xeno- (from xenos, meaning “stranger,” “other,” “foreigner,” “alien,” and “guest”), xenoflesh conceptualizes the strange and obscured continuum of our own fleshy alterity-to-ourselves with that of other flesh creatures. Xenoflesh involves the aesthetic production of discomfiting bodily solidarity – a sensation of weirdness that impels praxes of mutuality and veganism. Constituting a multi-disciplinary account of philosophical, ecological, psychological, and economic flesh, the book engages with canonical and contemporary literary criticism and theory, ecocriticism, ecofeminism, vegan studies, animal studies, posthumanism, phenomenology, cognitive theory, black studies, and animal liberation theory.

Zen for Record - Ken Friedman (punctum books, 2026)
Zen for Record gathers five essays around Ken Friedman’s 1966 Fluxus event score instructing the production of “a phonograph record with no sound on it.” Originating as a found object, the work has migrated across six decades and multiple incarnations, from an unrealized concept to the LP edition that occasions this volume. These essays accompany Friedman’s account of the Fluxus origins of the work, but they approach the silent record from radically different angles. Craig Dworkin situates Zen for Record within a broader aesthetics of negation and conceptual art’s engagement with the zero-degree of content. Christof Migone spirals through the paradoxes of inscribing nothing and the impossibility of a truly soundless playback. Robin McGinley traces a remarkable counter-history of the silent record as pop artifact, from 1950s jukebox novelties and Vulfpeck’s album Sleepify. Finally, Hanna B. Hölling reads the work through sonic materialism, preservation theory, and the politics of silencing, asking what it means for a concept to survive the obsolescence of its successive carriers. Touching on Fluxus event scores and Cagean silence, the political economy of streaming platforms and the conservation of time-based media, these essays stage a sustained interdisciplinary meditation on silence as material, medium, commodity, and philosophical provocation.

ρan-ρan - Norman Hogg; Neil Mulholland (punctum books, 2021)
With the peristaltic gurglings of this gastēr-investigative procedural – a soooo welcomed addition to the ballooning corpus of slot-versatile bad eggs The Confraternity of Neoflagellants (CoN) – [users] and #influencers everywhere will be belly-joyed to hold hands with neomedieval mutter-matter that literally sticks and branches, available from punctum in both frictionless and grip-gettable boke-shaped formats. A game-changer in Brownian temp-controlled phoneme capture, ρan-ρan’s writhing paginations are completely oxygen-soaked, overwriting the flavour profiles of 2013’s thN Lng folk 2go (https://punctumbooks.com/titles/thn-lng-folk-2go/) with no-holds-barred argumentations on all voice-like and lung-adjacent functions. Rumoured by experts to be dead to the World™, CoN has clearly turned its ear canal arrays towards the jabbering OMFG feedback signals from their scores of naive listeners, scrapping all lenticular exegesis and content profiles to construct taped-together vernacular dwellings housing ‘shrooming atmospheric awarenesses and pan-dimensional cross-talkers, making this anticipatory sequel a serious competitor across ambient markets, and a crowded kitchen in its own right. An utterly mondegreen-infested deep end may deter would-be study buddies from taking the plunge, but feet-wetted Dog Heads eager to sniff around for temporal folds and whiff past the stank of hastily proscribed future fogs ought to ©k no further than the roll-upable-rim of ρan-ρan’s bleeeeeding premodern lagoon. Arrange yerself cannonball-wise or lead with the #gut and you’ll be kersplashing in no times.

Remote Vision (poetry 1999–2015) - Alessandro De Francesco (punctum books, 2016)
Remote Vision represents, in English and Italian, the most significant works in poetry and conceptual writing produced by Alessandro De Francesco to date. It is both a coherent book and the most exhaustive collection of his poetry ever published in any language. All sections have been rearranged for this publication, with each one containing the complete English text followed by the complete Italian version. The texts have been beautifully translated by poets and Brown University alumni Belle Cushing and Dusty Neu, under the coordination of the acclaimed poet and Comparative Literature scholar Forrest Gander. Remote Vision condenses and presents under a new light the conceptual and emotional intensity of Alessandro De Francesco’s poetry.

Repetitions - Scott Abbott; Žarko Radaković (punctum books, 2013)
In 1994, after following a character in Peter Handke’s novel Repetition into what is now Slovenia and after traveling in landscapes of Handke’s youth, Žarko Radaković and Scott Abbott published a two-headed text in Belgrade, Ponavljane, now published in English by punctum as Repetitions. The possibility of narration in two voices, complicated by the third voice that is Peter Handke’s own narrator, is the main focus of deliberation while traveling and reading and writing. Repetitions begins with Abbott’s text, a fairly straightforward travel narrative. It ends with Radaković’s account of the same events, much less straightforward, more repetitious, more adventuresome. Two aspects make the double-book unique. First, it represents experiences shared by two authors whose native languages are Serbian and English respectively (German is their only common language). The authors’ perspectives contrast with and supplement one another: Radaković grew up in Tito’s Yugoslavia and Abbott comes from the Mormon American West; Radaković is the translator of most of Peter Handke’s works into Serbo-Croatian and Abbott translated Handke’s provocative A Journey to the Rivers: Justice for Serbia for Viking Press and his play Voyage by Dugout: The Play of the Film of the War for PAJ (Performing Arts Journal); Radaković was a journalist for Deutsche Welle in Cologne and Abbott is a professor of German literature at Utah Valley University; Radaković is the author of several novels and Abbott has published mostly literary-critical work; and so on. Two sets of eyes. Two pens. Two visions of the world.

Requiem - Teresa Carmody (punctum books, 2025)
Requiem by Teresa Carmody is a “folk opera, a lament for the unexamined life,” writes editor and author David Ulin in his Introduction. In this short collection of fiction, a lonely man plainchants for the waitress he once stalked, a sonless father serenades a fatherless son, and a bereft family gathers to bury a parent, providing an aching chorus of what is left. Carmody uses Biblical language to pierce the callous and bruised souls of these lost, and sometimes found, small-town Michiganders. In her raw spare stories, novelist, essayist, and poet Carol Muske-Dukes writes that Carmody creates in her raw, spare stories, “a voice out of the backyard burning bush, a Midwest scriptural mist: frank, fierce and fidgety, and most emphatically her own.” This title is a second edition, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

Rescuing Democracy - Paul E. Smith (punctum books, 2016)
This book proposes a new institution — the "People’s Forum" — to enable democratic governments to effectively address long-running issues like global warming and inequality. It would help citizens decide what strategic problems their government must fix, especially where this requires them to suffer some inconvenience or cost. The People’s Forum is first based on a new diagnosis of government failure in democracies. The book tests its own analyses of government failure by seeing whether these might help us to explain the failures of particular democracies to address (and in some cases, to even recognize) several crucial environmental problems. The essential features of a new design for democracy are described and then compared with those of previous institutional designs that were also intended to improve the quality of democratic government. In that comparison, the People’s Forum turns out to be not only the most effective design for developing and implementing competent policy, but also the easiest to establish and run. The latter advantage is crucial as there has been no success in getting previous designs into actual trial practice. It is hoped that this book may inspire a small group to raise the money to set up and run the People’s Forum. Then, as citizens see it operating and engage with it, they may come to regard the new Forum as essential in helping them to deliberate long-running issues and to get their resulting initiatives implemented by government. Smith also discusses how the People’s Forum must be managed and how groups with different political ideologies may react to it. An Afterword sets out the method by which this design was produced, to help those who might want to devise an institution themselves. The new concepts in environmental science that the book develops to test its diagnosis are applied in an Appendix to outline crucial options for the future of Tasmania. Similar options apply to many countries, states and provinces. As indicated above, those choices are currently beyond the capacity of democratic governments to address and in some cases, even to recognize. But the People’s Forum may lift them out of that morass.

Resistance - Marko Stamenkoviç (punctum books, 2021)
Resistance features a selection of overtly non-conformist positions in the contemporary visual arts scene of Albania vis-à-vis the most recent social, political, and economic turmoils in the Western Balkans—a region marked by the dark side of political governances that have remained “democratic” in their outward appearance only (especially toward the European Union), while dramatically leaning toward autocratic regimes in the eyes of their own citizens. Regardless of their citizens’ primary interests, and despite some positive signals surfacing in the international media, almost every attempt to establish lasting conditions for democratic governance in the Western Balkans has been shrouded in the veil of profit-driven political scandals, personal greed for more and more power over the people’s rights, and the extinction of public property in pursuit of the social elite’s corporate and private interests. Additionally, and more specifically related to Tirana, artists and citizens have, over the years, been involved in various types of revolt, expressing their disagreements with the ongoing destruction of public property in the name of “modernization and development”: a movement led by local political powers through financially and strategically motivated processes of architectural cannibalism—not only at the expense of erasing Albanian cultural heritage or long-term residents’ habitats, but also at the expense of taking human lives under the pretext of “urbanization.” The most obvious instance of this economy of destruction was the complex of buildings linked to the National Theater of Albania in downtown Tirana that has served as a symbolic and material place of citizens’ resistance: for more than two years, together with local artists, they have been opposing the government’s plans to demolish the old complex in order to build a new one, until this finally happened in Spring 2020, in the midst of the ongoing COVID19 pandemic. Rooted in the atmosphere of the National Theater Protests in Tirana, RESISTANCE was conceived in Summer 2019 by the ZETA Center for Contemporary Art as the International Artists-in-Residence Program, in cooperation with three partner organizations from Kosovo, Serbia, and North Macedonia (Stacion Center for Contemporary Art in Prishtina; Ilija & Mangelos Foundation in Novi Sad; and Faculty of Things That Can’t Be Learned in Bitola) and supported by the Swiss Cultural Fund in Albania, a project of the Swiss Agency for Development and Cooperation. Gradually, the project expanded into an exhibition (Heterotopias of Resistance, curated by Blerta Hoçia and featuring works by Lori Lako, Fatlum Doçi, Edona Kryeziu, Nina Galiç, Darko Vukiç, Nikola Slavevski, and Natasha Nedelkova) and a series of interviews and panel discussions (with contributions by Lindita Komani, Edmond Budina, Ervin Goci, Ergin Zaloshnja, Pleurad Xhafa, Gentian Shkurti, Stefano Romano, Luçjan Bedeni, HAVEIT, Leonard Qylafi, Jonida Gashi, and Fatmira Nikolli). The results of both projects have been collected in this book which, besides serving as an indispensable reading material concerning visual arts and politics in contemporary Albania, especially to those abroad, also functions as a form of resistance against contagious cultural policies in weak post-socialist “democracies” in southeastern Europe.

Resistant Form: Aristophanes and the Comedy of Crisis - Mario Telò (punctum books, 2023)
Can attending to poetic form help us imagine a radical politics and bridge the gap between pressing contemporary political concerns and an ancient literature that often seems steeped in dynamics of oppression? The corpus of the fifth-century Athenian playwright Aristophanes includes some of the funniest yet most disturbing comedies of Western literature. His work’s anarchic experimentation with language invites a radically “oversensitive” hyperformalism, a formalistic overanalysis that disrupts, disables, or even abolishes a range of normativities (government, labor, reproduction, gender). Exceeding not just historicist contextualism, but also conventional notions of laughter and the logic of the joke, Resistant Form: Aristophanes and the Comedy of Crisis uses Aristophanes to fully embrace, in the practice of close or “too-close” reading, the etymological and conceptual nexus of crisis, critique, and literary criticism. These exuberant readings of Birds, Frogs, Lysistrata, and Women at the Thesmophoria, together with the first attempt ever to grapple with the comic style of critical theorists Gilles Deleuze, Achille Mbembe, and Jack Halberstam, connect Aristophanes with contemporary discourses of biopolitics, necrocitizenship, care, labor, and transness, and at the same time disclose a quasi- or para-Aristophanic mode in the written textures of critical theory. Here is a radically new approach to the literary criticism of the premodern—one that materializes the circuit of crisis and critique through a restless inhabitation of the becomings and unbecomings of comic form.

Rhetorical Agency: Mind, Meshwork, Materiality, Mobility - Les Belikian (punctum books, 2017)
In recent accounts of rhetoric’s storied productivity, commentators have implied, along systematically Kantian lines, albeit with the occasional protestation, that agency must be coextensive with subjectivity. But is that all there is (to 2,500 years’ worth of hypothesizing about the ways in which communication might promote social change)? Les Belikian’s answer, drawing not only on traditional and contemporary rhetorical studies but also on Deleuzean thinking, actor-network theory, and object-oriented ontology, takes the form of a quadruply contrarian thesis: Rhetorical agency inheres, irreducibly so, in subjectivity, in conventionality, in transcendence, and in materiality, all of which are themselves always under production.

Rituals for Climate Change: A Crip Struggle for Ecojustice - Naomi Ortiz (punctum books, 2023)
Disability justice and ecojustice are rarely considered together but are in constant conversation in our world. Rituals for Climate Change: A Crip Struggle for Ecojustice, combining poetry and the lyrical essay, doesn’t contain just one point of view but encompasses dialectical perspectives which often exist in contradiction to each other. A disabled person is in need of plastic cups and concerned about the overwhelming plastic in our ecosystems. Ortiz expands on and complicates who is seen as an environmentalist and what being in relationship with the land can look like. This book is an offering to explore the spiritual question of how to witness. It serves as a companion to those also grappling with the difficult and often unanswerable questions posed by climate change in the borderlands. By exploring the ways body, mind, and cultures both clash with and long for ecojustice, Rituals for Climate Change offers an often-overlooked perspective on climate-grief, interdependence, and resilience. Disabled people know how to adapt to a world that is ever changing without considering them.

Romance Studies: Manifesto and Method: Twenty-Eight Lectures, with Drinks Pairings - Jon Beasley-Murray (punctum books, 2027)
What is Romance Studies? What could it be? This book is a sustained attempt to define—indeed, invent—the field, both in theory and in practice. It is therefore both a manifesto for Romance Studies as a discipline that may be an antidote to bureaucratic reason and, more broadly, a provocative but accessible introduction to methods of reading literature beyond national boundaries. Romance Studies: Manifesto and Method is thus both a disciplinary provocation as well as a set of actual “lessons” that have been designed for the uninitiated. Romance Studies proceeds via a tasting menu of representative novels from the twentieth and twenty-first centuries originally written in the Romance languages: French, Spanish, Italian, Portuguese, Catalan, and Romanian. From Marcel Proust to Georges Perec, María Luisa Bombal to Javier Cercas, Clarice Lispector to Elena Ferrante, it argues that these texts betray and exceed tradition, as well as constitute an assemblage that is also a minor literature, a war machine set against the neo-imperial tendencies of contemporary culture. The book opens up a world of difference in which new concepts, new habits may arise. Ultimately, Beasley-Murray intends not to construct a discipline like others, but to come up with something different and distinctive, something beyond discipline. The book outlines a Romance Studies that is a vector of deterritorialization, flight, and betrayal that subverts the hegemony of a perverse global monolingualism for which “world literature” can only come into being in English. Romance Studies: Manifesto and Method is thus also an intellectual history that calls for its own deconstruction so that something else can emerge, offered in the form of twenty-eight lectures with drinks pairings. What happens when you read a novel (or poem) with an eye to the beverages it contains? There is a history to be told in the objects taken for granted, the things we absent-mindedly consume, and the minor details of the material world that a text conjures up. Enjoy!

Rough Notes to Erasure: White Male Privilege, My Senses, and the Story I Cannot Tell - Dolsy Smith (punctum books, 2020)
We are living through the wrack of the White Male. As the compact between social hierarchy, inherited privilege, and race (reinforced by gender and other normative categories) shows signs of buckling, his rage and resentment threaten us all. For he is a thing possessed: possessed by his own love of possession, and born to a sense that the world belongs to him and him alone. The spoils of oppression lie coiled inside him, a glut he can’t digest, and murder beckons behind the respect that he conceives of as his due. A hybrid of critical essay and memoir, and Rough Notes to Erasure contributes to a growing body of work that wrestles with the tacit and embodied nature of privilege and prejudice, and it contributes not only via argument but also through style. Taking inspiration from feminist/queer poetics and what Fred Moten calls “the black avant-garde,” these rough notes address the remainder that gets lost in explicit argument, which is the flesh. Where privilege roils through history, and empire whets the appetites. But also where the world catches on its own fractalization by thought, feeling, and desire; and language recovers, for a moment or two, the power to entangle us with our mother tongue.

Rumba under Fire: The Arts of Survival from West Point to Delhi - Irina Dumitrescu (punctum books, 2016)
A professor of poetry uses a deck of playing cards to measure the time until her lover returns from Afghanistan. Congolese soldiers find their loneliness reflected in the lyrics of rumba songs. Survivors of the siege of Sarajevo discuss which book they would have never burned for fuel. A Romanian political prisoner writes her memoir in her head, a book no one will ever read. These are the arts of survival in times of crisis. Rumba under Fire proposes we think differently about what it means for the arts and liberal arts to be “in crisis.” In prose and poetry, the contributors to Rumba under Fire explore what it means to do art in hard times. How do people teach, create, study, and rehearse in situations of political crisis? Can art and intellectual work really function as resistance to power? What relationship do scholars, journalists, or even memoirists have to the crises they describe and explain? How do works created in crisis, especially at the extremes of human endurance, fit into our theories of knowledge and creativity?

Sacred Views of Saint Francis: The Sacro Monte di Orta - Cynthia O. Ho; Kathleen W. Peters; John McClain (punctum books, 2020)
Overlooking Lago di Orta in the foothills of the Northern Italian Alps, the Renaissance-era Sacro Monte di Orta (a UNESCO World Heritage site) is spectacle and hagiography, theme park and treatise. Sacro Monte di Orta is a sacred mountain complex that extolls the life of St. Francis of Assisi through fresco, statuary, and built environment. Descending from the vision of the 16th-century Archbishop Carlo Borromeo, the design and execution of the chapels express the Catholic Church’s desire to define, or, perhaps redefine itself for a transforming Christian diaspora. And in the struggle to provide a spiritual and geographical front against the spread of Protestantism into the Italian peninsula, the Catholic Church mustered the most powerful weapon it had: the widely popular native Italian saint, Francis of Assisi. Sacred Views of Saint Francis: The Sacro Monte di Orta examines this important pilgrimage site where Francis is embraced as a ne plus ultra saint. The book delves into a pivotal moment in the life of the Catholic Church as revealed through the artistic program of the Sacro Monte’s twenty-one chapels, providing a nuanced understanding of the role the site played in the Counter-Reformation. The Sacro Monte di Orta was, in its way, a new hagiographical text vital to post-Tridentine Italy. Sacred Views provides research and analysis of this popular, yet critically neglected Franciscan devotional site. Sacred Views is the first significant scholarly work on the Sacro Monte di Orta in English and one of the very few full-length treatments in any language. It includes a catalogue of artists, over one hundred photographs, maps, short essays on each chapel, and longer essays that examine some of the most significant chapels in greater detail.

Sappho: ]fragments - Jonathan Goldberg (punctum books, 2018)
In Sappho, Jonathan Goldberg takes as his model the fragmentary state in which this sublime poet’s writing survives, a set of compositional and theoretical resources for living and thinking in more fully erotic ways in the present and the future. This book thus offers fragmentary commentary on disparate (Sapphic) works, such as the comics of Alison Bechdel, the paintings and cartoons of Leonardo da Vinci, Robert Reid-Pharr’s “Living as a Lesbian,” Madeleine de Scudéry’s Histoire de Sapho, John Donne’s “Sapho to Philaenis,” Todd Haynes and Patricia Highsmith’s Carol, Virginia Woolf’s Orlando, writings by Willa Cather, and the paintings and writings of Simeon Solomon, among other works. Goldberg challenges readers to imagine and experience what Sarah Orne Jewett named the “country of our friendship,” a love both exceedingly strange and compellingly familiar. Just as Sappho’s coinage “bitter-sweet” describes eros as inextricably contradictory — two things at once, one thing after another, each interrupting, complicating, each other — the juxtapositions in this book mean to continually call into question categories of identity and identification in the wake of a quintessential woman writer from Lesbos. Over and over again, Goldberg’s Sappho: ]fragments inquires into how race, sexuality, and gender cross each other. The theoretical genius of Eve Kosofsky Sedgwick presides over this set of meditations and mediations on likeness and desire. Rather than homogenizing its many subjects, it invites the reader to explore and inhabit new transits within and through what Audre Lorde called “the very house of difference.”

Sea Monsters: Things from the Sea, Volume 2 - Thea Tomaini; Asa Simon Mittman (punctum books, 2017)
Beaches are places that give and take, bringing unexpected surprises to society, and pulling essentials away from it. Through monsters, we confront our tiny time between catastrophes and develop a recognition of Otherness by which an ethical understanding of difference becomes possible. Learning to read the monster’s environmental signs often helps humans determine the scope of the monster’s place in the eco/cosmic timeline and defeat it—until the epic cycle inevitably repeats; monsters live and live and live. Even so; when humans identify and confront monsters we do so at the risk of exposing our own monstrosity. When a massive creature is pushed into human proximity by the ocean’s wide shoulders, the waves deposit and erode human assumptions about itself and its environment; words, sounds, breath, water, wind, flesh, blood, and bones wash in and out. Chance encounters reveal us to ourselves anew. When we look into the inky backs of whales, or deep into vortices, what do we see? In October 2014, the BABEL Working Group (http://babel-meeting.org) headed to the beach. The 3rd Biennial Meeting (https://babel-meeting.org/2014-meeting/2014-program/) of the BABEL Working Group was held at The University of California, Santa Barbara, where the Pacific Ocean laid her face against the sand and experienced the conference panels exploring, examining, and exalting the margins of sea and shore, of earth and water. This volume of essays represents MEARCSTAPA (https://www.mearcstapa.org/)’s panel, entitled, “The Nature of the Beast/Beasts of Nature: Monstrous Environments.” These essays explore what the environment reveals via monster theory, what monsters—here, whales and whirlpools—make visible or accessible to humanity and what they draw away from it. Things from the Sea is a queer companion to Walk on the Beach (https://punctumbooks.com/punctum/titles/walk-on-the-beach/), which emerged from another session at the same conference.

Selected Essays 2019–2023 - Peter Valente (punctum books, 2026)
“There are floods that destroy entire contents of a library or publishing house; libraries and museums bombed during wartime; authors themselves demanding certain works or letters be burned at their death; those who attempt at their own risk to save what they can of a manuscript; manuscripts left in taxis and never to be found again; there are distracted painters who paint over an artwork not realizing what they are doing; finally, there are those works that never came to fruition for one reason or another, never to be known. We are given the misfires, the aborted works, the destroyed works, the mishandled works; the book is a catalogue of brutality, desperation, anger, shame and failure. It is like the negative of a photo, not the bright image we expect; it is the lack seething behind our feeling of abundance; it is a catalogue of the unfinished, the unknown, the unknowable. The effect of all the statements is quite devastating, and it reads like a kind of book of the dead. But it is also a magical book where the dead will live again in its pages.” So writes translator and cultural critic Peter Valente, in an essay about Henri LeFebvre’s The Missing Pieces, a catalogue of lost and never realized artworks. Selected Essays, 2019-2023 collects Valente’s thinking and writings about books, films, poetry, digital art, dance, music, and other cultural objects that were important to him during the last decade. The essays cover a wide array of topics, from an examination of the new styles of music and dance in the UK to Gavin Douglas’s 16th-century translation of the Aeneid, from Bernadette Mayer’s Memory to John Ruskin’s work, from an in-depth analysis of John Wieners’s “A Poem for Painters” to an exploration of Maya Deren’s experimental filmmaking. In these essays, Valente explores books by contemporary experimental poets such as Will Alexander and Adeena Karasick as well as prose writers such as Cookie Mueller and David Wojnarowicz. Valente’s essays are not limited nor bound by current fashions in the poetry or prose worlds. His readings remain, as can be seen in his previous collection, Essays on the Peripheries (https://punctumbooks.com/titles/essays-on-the-peripheries/), open ended and adventurous.

Shadowing the Anthropocene: Eco-Realism for Turbulent Times - Adrian Ivakhiv (punctum books, 2018)
A spectre is haunting humanity: the spectre of a reality that will outwit and, in the end, bury us. “The Anthropocene,” or The Human Era, is an attempt to name our geological fate – that we will one day disappear into the layer-cake of Earth’s geology – while highlighting humanity in the starring role of today’s Earthly drama. In Shadowing the Anthropocene, Adrian Ivakhiv proposes an ecological realism that takes as its starting point humanity’s eventual demise. The only question for a realist today, he suggests, is what to do now and what quality of compost to leave behind with our burial. The book engages with the challenges of the Anthropocene and with a series of philosophical efforts to address them, including those of Slavoj Žižek and Charles Taylor, Graham Harman and Timothy Morton, Isabelle Stengers and Bruno Latour, and William Connolly and Jane Bennett. Along the way, there are volcanic eruptions and revolutions, ant cities and dog parks, data clouds and space junk, pagan gods and sacrificial altars, dark flow, souls (of things), and jazz. Ivakhiv draws from centuries old process-relational thinking that hearkens back to Daoist and Buddhist sages, but gains incisive re-invigoration in the philosophies of Charles Sanders Peirce and Alfred North Whitehead. He translates those insights into practices of “engaged Anthropocenic bodymindfulness” – aesthetic, ethical, and ecological practices for living in the shadow of the Anthropocene. Check out the “Reader’s Guide” to Shadowing the Anthropocene (https://blog.uvm.edu/aivakhiv/2018/10/13/shadowing-the-anthropocene-a-readers-guide/)

Turkish Voices - Murat Nemet-Nejat (punctum books, 2022)
Turkish Voices, written during 1989/90, is initially based on the Second New Turkish poet Cemal Süreya’s first book of poetry, Üvercinka (Pigeon English), which he wrote during the 1950s, in his twenties. In this book, striking erotic passages of uncanny psychological insight, where a nexus between pleasure and power is revealed through the lyric persona of a male seducer, are mixed with cute refrains or half-digested surrealist lines which blur the text, sentimentalizing that insight by turning the poems into general appeals for freedom, completely overlooking the victimization of the female persona, who never speaks. A work of deconstructive translation, Turkish Voices offers a reworking of Üvercinka, containing fragments from different poems in Süreya’s book, some ending in mid-sentence, with other fragments isolated, spliced together, and altered. Fragments from other Turkish poets have also been added, splitting the lyric persona and opening up its unity to let in other personae. Finally, poems written earlier by the author himself join the text. The result is a series of eighty-four fragments where any idea of ownership or originality or source—what poem, that is, comes from whom or where—disappears, is completely blurred. In other words, what starts with the ego and power-centered persona of the male seducer is dissolved and splintered through a dialectic or critical confrontation with Süreya’s resistant text, into multiple points of view, often of a sufferer, a victim. What one ends up with is a multiplicity of voices, an erotic poem which becomes its own critique of power.

Último día cada día: Y otro escrito sobre cine y filosofía - Adrian Martin (punctum books, 2013)
This edition has been produced jointly with: FICUNAM (http://www.ficunam.unam.mx/en/) (International Film Festival of the National Autonomous University of Mexico) Where is the film analysis today? What are you doing, in the dark, the theory of cinema? This field, as it has been professionally defined (at least in the Anglo-American academic world), is currently divided between historians interested in the social context that examine the great formations of modernity, and experts in the style that They demand the return of outmoded things such as authorial vision, tone, and staging. But there are also other currents, vital and inventive, of which we are hardly hearing anything in any of the official channels. Last day each day , which for this edition has been extended with the essay “Avatars of the meeting”, shines a light on one of these new and exciting ways.

Último Dia Todos os Dias: E Outros Escritos sobre Cinema e Filosofia - Adrian Martin (punctum books, 2015)
Onde se encontra a análise fílmica hoje? O que é que a teoria de cinema anda a desenvolver na obscuridade? Este campo, tal como foi definido profissionalmente (pelo menos no mundo académico anglo-saxónico), encontra-se actualmente dividido entre historiadores interessados no contexto das grandes formações da modernidade e connoisseurs que reclamam o regresso estilístico de coisas antiquadas como a visão autoral, o tom ou a mise-en-scène. Mas há também outras correntes, vitais e inventivas – na crítica, na internet, em pequenas revistas, em conferências renegadas um pouco por todo o lado –, que não estamos a conseguir escutar em nenhum dos canais oficiais. Último Dia Todos os Dias, de Adrian Martin – nesta edição acompanhado do ensaio “Avatares do Encontro” –, lança uma luz sobre estas novas e excitantes avenidas. Publicado originalmente como Last Day Every Day: (https://punctumbooks.com/punctum/titles/last-day-every-day/)Figural Thinking from Auerbach and Kracauer to Agamben and Brenez (https://punctumbooks.com/punctum/titles/last-day-every-day/), em 2012, por Dead Letter Office, uma série da editora punctum books. Esta edição foi produzida conjuntamente por Centro de Estudos Comparatistas | Faculdade de Letras da Universidade de Lisboa e punctum books, 2015.

Unexpected Flourishing: Growth from Decay in the Mycelial University - Katina L. Rogers (punctum books, 2027)
Unexpected Flourishing is a book about rotting logs, higher education, and critical hope. Katina L. Rogers draws on the hope and possibility of mycorenewal to ask what possibilities for unexpected flourishing we can find within higher education’s decay, and how we can cultivate conditions where these possibilities can thrive: a mycelial university. In a forest, the mycorrhizal network connects fungal mycelia and plant roots to pipe nutrients among species, fostering a complex and interdependent ecosystem. These multispecies ecologies thrive even (or especially) in less-than-pristine conditions. What if that kind of collectivitism were a baseline for understanding and sharing scholarly work? Just as mushrooms spring up from the rot of the forest floor and return nutrients to depleted soil, perhaps something new might emerge in higher education from the decomposing remnants of what came before. Higher education in the US is a ravaged landscape of diminished public funding and even governmental hostility, exploitative labor practices, students crippled by debt, and endless stories of racism, ableism, and sexual harassment—and yet, beauty and curiosity continue to emerge. Unexpected Flourishing surveys the decay of the higher education landscape as it is now while offering a speculative consideration of what might be possible if we—scholars, practitioners, administrators, teachers of all kinds—adopted different value structures and different ways of making meaning in community. The underlying focal point is one of abundance, sustenance, and joy.

Unless As Stone Is - Sam Lohmann (punctum books, 2014)
The sestina is a form in which words repeat regularly, intricately, appearing and reappearing in new contexts with new meanings. Sam Lohmann’s Unless As Stone Is emerged from a few years of living with Dante’s sestina, “Al poco giorno e al gran cerchio d’ombra (https://ethpress.com/dante/).” He allowed the text to appear in its own new — if irregularly scheduled — contexts. New translations, new scenery, new meanings; new phrases entered the poem (from García Lorca, from Sappho, from strangers and from loved ones) and found their own patterns. What resulted is a serial poem in seven movements, incorporating several strategies of reincorporation. “Quandunque i colli fanno più nera ombra” — “All our oddity operates / on changing verity.”

Unvoicing Migraine: A Study of the Failing Voice - Mariske Broeckmeyer (punctum books, 2026)
These writings spring from an observation: When migraine arises, the voice fails. It does so on many levels, ranging from a vocal-technical disintegration to migraine-specific symptoms like dysarthria and aphasia, up to the muteness forced upon the sufferer by stigmatization. As a migraine-suffering singer, Mariske Broeckmeyer witnesses and experiences these alterations. Frequently, routinely, and almost faithfully, she retreats to the blackened bedroom when migraine manifests. Lying in silence, she notices how little of her vocal instrument remains intact and how distorted our relations become under these circumstances. Migraine mutes—it occupies the body and leaves muscles, lungs, larynx, and tongue under its command. In the attempt to describe these sufferings, Broeckmeyer has indeed stammered and fallen silent, unable to name the pain. But could it be that this failure holds some sort of potential? What might vocal failure reveal about the nature of the voice? To these questions, Unvoicing Migraine lends an ear. Shuttling between theoretical findings and artistic practice, the book turns to concepts provided by voice theory, disability studies, and queer theory to engage in an artistic research that studies the devocalizing impact of migraine. The book also attempts to redefine the artistic practice of a singer, the author, when her vocal apparatus falters: it questions the singer’s relation to the stage and challenges the boundaries of performance. These aspects of vocality were not merely approached through an autotheoretical discourse, but through the creation of music and sound art that capture the failing voice and amplify it. Ultimately, Unvoicing Migraine looks at what lies beyond migraine, and makes note of its consequences and residues: stains the acid left on the carpet that transform into a woolly eye whose gaze morphs into a mouth that raves in a language we cannot always understand, but which Broeckmeyer transforms into migraine opera.

Urban Interactions: Communication and Competition in Late Antiquity and the Early Middle Ages - Michael J. Kelly; Michael Burrows (punctum books, 2020)
This volume is dedicated to eliciting the interactions between localities across late antique and early medieval Europe and the wider Mediterranean. Significant research has been done in recent years to explore how late “Roman” and post-“Roman” cities, towns and other localities communicated vis-à-vis larger structural phenomena, such as provinces, empires, kingdoms, institutions and so on. This research has contributed considerably to our understanding of the place of the city in its context, but tends to portray the city as a necessarily subordinate conduit within larger structures, rather than an entity in itself, or as a hermeneutical object of enquiry. Consequently, not enough research has been committed to examining how local people and communities thought about, engaged with, and struggled against nearby or distant urban neighbors. Urban Interactions addresses this lacuna in urban history by presenting scholarship that applies a diverse spectrum of approaches, from archaeological investigation to critical analyses of historiographical and historical biases and developmental consideration of antagonisms between ecclesiastical centers. Through these avenues of investigation, this volume elucidates the relationship between the urban centers and their immediate hinterlands and neighboring cities with which they might vie or collaborate. This entanglement and competition, whether subterranean or explicit across overarching political, religious or other macro categories, is evaluated through a broad geographical range of late “Roman” provinces and post-“Roman” states to maintain an expansive perspective of developmental trends within and about the city.

Urban Liquefaction: Rethinking the Relationship between Land and Sea - Cristián Simonetti; Michel Lussault; Tim Ingold (punctum books, 2026)
From classical times until today, cities have been conceived in the western imagination as ideally confined to the fixities of the land, a space defined in opposition to the fluxes of the sea. Whereas solid land afforded a durable platform for the establishment of property and citizenship, the fluid sea allowed markets—isolated within the secure boundaries of cities—to be connected across the globe though navigation. Urban Liquefaction: Rethinking the Relationship between Land and Sea attends to the concurrent tensions between solidity and fluidity, permanence and impermanence, and substance and change that remain at the core of the western intellectual tradition, often dividing what is perceived as social from what is perceived as natural in life. Sea level rise poses unprecedented threats to this oppositional relationship, forcing us to reconsider the tension between solidity and fluidity in the design of the built environment. Nearly ten percent of all major cities are likely to be impacted by sea level rise in the coming decades, compromising the necessary infrastructure on which urban life depends. In reality, urban landscapes have been continually in flux, which becomes dramatically visible to urban dwellers mostly in catastrophic events such as earthquakes, tsunamis, alluvions, sinkholes, and, above all, soil liquefaction. Urban Liquefaction gathers contributions from scholars and practitioners working across continents and fields interested in urban life in (and after) the Anthropocene, including anthropology, archaeology, art, architecture, design, human geography, and science studies, to open up an inquiry into these categorical tensions and to speculate on alternative futures for the built environment.

Urban Re-Industrialization - Krzysztof Nawratek (punctum books, 2017)
Urban re-industrialisation could be seen as a method of increasing business effectiveness in the context of a politically stimulated ‘green economy’; it could also be seen as a nostalgic mutation of a creative-class concept, focused on 3D printing, ‘boutique manufacturing’ and crafts. These two notions place urban re-industrialisation within the context of the current neoliberal economic regime and urban development based on property and land speculation. Could urban re-industrialisation be a more radical idea? Could urban re-industrialization be imagined as a progressive socio-political and economic project, aimed at creating an inclusive and democratic society based on cooperation and a symbiosis that goes way beyond the current model of a neoliberal city? In January 2012, against the backdrop of the 2008 financial crisis, Krzysztof Nawratek published a text in opposition to the fantasy of a ‘cappuccino city,’ arguing that the post-industrial city is a fiction, and that it should be replaced by ‘Industrial City 2.0.’ Industrial City 2.0 is an attempt to see a post-socialist and post-industrial city from another perspective, a kind of negative of the modernist industrial city. If, for logistical reasons and because of a concern for the health of residents, modernism tried to separate different functions from each other (mainly industry from residential areas), Industrial City 2.0 is based on the ideas of coexistence, proximity, and synergy. The essays collected here envision the possibilities (as well as the possible perils) of such a scheme.

Útrásarvíkingar! The Literature of the Icelandic Financial Crisis (2008–2014) - Alaric Hall (punctum books, 2020)
As the global banking boom of the early twenty-first century expanded towards implosion, Icelandic media began calling the country’s celebrity financiers útrásarvíkingar: “raiding vikings.” This new coinage encapsulated the macho, medievalist nationalism which underwrote Iceland’s exponential financialisation. Yet within a few days in October 2008, Iceland saw all its main banks collapse beneath debts worth nearly ten times the country’s GDP. Hall charts how Icelandic novelists and poets grappled with the Crash over the ensuing decade. As the first English-language monograph devoted to twenty-first-century Icelandic literature, it provides Anglophone readers with an introduction to one of the world’s liveliest literary scenes. It also contributes a key case study for understanding global artistic responses to the early twenty-first century crisis of runaway, unregulated capitalism, exploring the struggles of writers to adapt realist forms of art to surreal times. As Iceland’s biggest crisis since their independence from Denmark in 1944, the effect of the Crash on the national self-image was as seismic as its effects on the economy. This study analyses the centrality of whiteness and the abjection of the “developing world” in Iceland’s post-colonial identity, and shows how Crash-writing explores the collisions of Iceland’s traditional, nationalist medievalism with a dystopian, Orientalist medievalism associated with the Islamic world. The Crash in Iceland was instantly recognised as offering important economic insights. This book shows how Iceland also helps us to understand the cultural convulsions that have followed the Financial Crisis widely in the West.

Vampires & A Reasonable Dictionary - Scott Abbott; Žarko Radaković (punctum books, 2014)
As a follow-up to their first collaboration Repetitions (https://punctumbooks.com/punctum/titles/repetitions/) (published in Belgrade in 1994, and in English by punctum in 2013), in 2008 the authors published, also in Belgrade, Vampiri & Razumni recnik, published here by punctum as Vampires & A Reasonable Dictionary. Vampires is Radaković’s fictionalized account of a Serb living in Cologne, Germany while his former country disintegrates. He travels in the American West, ostensibly looking for the vampires causing chaos in his own country, and then returns to Europe, having found no vampires. It is a dark text, a story of destruction told in a narrative that refuses all the solaces narrative has traditionally afforded. A Reasonable Dictionary is Abbott’s personally troubled account of his and Radaković’s trip up the Drina River between the civil wars, a journey made with the novelist Peter Handke, a trip during which some of Abbott’s specifically American stories lost their moral structure. Both works examine generic distinctions and question storytelling in general, all in the context of travel in Yugoslavia, in the former Yugoslavia, and in western America. Two aspects make the books unique. First, they are written about experiences shared by two authors whose native languages are Serbian and English respectively (German is their only common language). The authors’ perspectives contrast with and supplement one another: Radaković grew up in Tito’s Yugoslavia and Abbott comes from the Mormon American West; Radaković is the translator of most of Peter Handke’s works into Serbo-Croatian and Abbott translated Handke’s provocative A Journey to the Rivers: Justice for Serbia for Viking Press and his play Voyage by Dugout: The Play of the Film of the War for PAJ (Performing Arts Journal); Radaković was a journalist for Deutsche Welle in Cologne and Abbott is a professor of German literature at Utah Valley University; Radaković is the author of several novels and Abbott has published mostly literary-critical work; and so on. Two sets of eyes. Two pens. Two visions of the world. Further, the years 1994 and 2008 (publication dates for Repetitions (https://punctumbooks.com/punctum/titles/repetitions/) and Vampires & A Reasonable Dictionary in Belgrade, respectively) bracket a horrendous period in the history of Yugoslavia. The authors changed during that period as well — divorces, new partners, new jobs; and Peter Handke, while metamorphosing into the bête noir of the press after his attacks on media portrayals of the Yugoslav wars, became the authors’ friend and entered their second text as a fellow traveler.

Vera Lex Historiae? Constructions of Truth in Medieval Historical Narrative - Catalin Taranu; Michael J. Kelly (punctum books, 2022)
In his Historia Ecclesiastica Gentis Anglorum (circa 731 CE), Bede says that he will write his account of the past of the English following only vera lex historiae (“the true law of history”). Whether explicitly or implicitly, historians narrate the past according to conceptions of what constitutes historical truth that emerge in the use of narrative strategies, formulae, and other textual forms, in establishing one’s ideological authority or that of one’s informants, and in faithfulness to a cultural, narrative, or poetic tradition. But what if we extend the scope of what we understand by history (especially in premodern settings) to include not just the writings of historians legitimated by the Latinate matrix of Christianized classical history writing, but also collective narratives, practices, rituals, oral poetry, liturgy, artistic representations, and acts of identity? In these genres of re-enacting the past as, or as representation of, the present, we find a plethora of modes of constructions of historical truth, narrative authority, and reliability. Vera Lex Historiae? comprises contributions that reveal the variety of evental strategies by which historical truth was constructed in late antiquity and the earlier Middle Ages, and the range of procedures by which such narratives were first established as being historical and then as “true” histories. This is not only a matter of narrative strategies, but also of habitus—ways of living and acting in the world that are deeply imbricated with the commemoration and re-enactment of the past by communities and by individuals. In doing this, Vera Lex Historiae? aims to recover something of the plurality of modes of preserving and reenacting the past available in late antiquity and the earlier middle ages which we often overlook because of preconceived notions of what constitutes history writing.

Visceral: Essays on Illness Not as Metaphor - Maia Dolphin-Krute (punctum books, 2017)
Memoirs about being sick are popular and everywhere and only ever contribute to pop narratives of illness as a single event or heroic struggle or journey. Visceral: Essays on Illness as Metaphor is not that. Visceral, to the extent that it is a memoir, is a record not of illness but of the research project being sick became. While rooted firmly in critical disability and queer practices, the use of personal narratives opens these approaches up to new ways of writing the body—ultimately a body that is at once theoretical and unavoidably physical. A body where everything is visceral, so theory must be too. From the gothic networks of healthcare bureaucracy and hospital philanthropy to the proliferation of wellness media, off-label usage of drugs, and running off to live a life with, these essays move fluidly through theoretical and physical anger, curiosity and surprise. Arguing for disability rights that attend to the theoretical as much as the physical, this is Illness Not As Metaphor, Being Sick and Time, and The Body in Actual Pain as one. A sick body of text that is—and is not—in direct correspondence to an actual sick body, Visceral is an unrelenting examination of chronic illness that turns towards the theoretical only to find itself in the realms of the biological and autobiographical: because how much theory can a body take?

Vital Reenchantments: Biophilia, Gaia, Cosmos, and the Affectively Ecological - Lauren Greyson (punctum books, 2019)
Not all charms fly at the touch of cold philosophy. Vital Reenchantments examines so-called cold philosophy, or science, that does precisely the opposite — rather than mercilessly emptying out and unweaving, it operates as a philosophy that animates. More specifically, this book closely examines how a specific group of “poet-in-scientists” of the late 1970s and 1980s directed attention to the “wondrous” unfolding of life, at a time when the counter-culture had made the institution of science synonymous with technologies of alienation and destruction. Vital Reenchantments takes up E.O. Wilson’s Biophilia (1984), James Lovelock’s Gaia (1979), and Carl Sagan’s Cosmos (1980), in order to show how each work fleshes out scientific concepts with a unique attention to “affective wonder.” These works reenchanted the scientific world without pandering to what Richard Dawkins would later term “cosmic sentimentality.” Carl Sagan may have said “We are made of starstuff,” but he would never insist, as Joni Mitchell did in 1969, that “we’ve got to get ourselves back to the garden.” Instead, Wilson, Lovelock, and Sagan insisted on a third way that does not rely on the idea of an ecological Eden — a vigorously vital materialism in which the affective trumps the sentimental. Further, the historical emergence of these works, all published within 5 years of each other, was no accident: each book responded to an ever deepening sense of environmental crisis, as well as to the large-scale disenchantment brought on by modernity. Greyson argues that the persistence of these works and their affectively-charged scientific concepts in contemporary popular culture and ecological thought is no accident. As such, these works deserve recognition as far more than “popular science” and can be seen as essential contributions to more contemporary vital materialist thought and ecological theory. No doubt this talk of enchantment and wonder, so tied to immediate experience, can seem trivial in the face of any number of environmental crises (global warming first among these). The first task of this book is thus to pose the same question that Jane Bennett does at the end of her own work on enchantment: “How can someone write a book about enchantment in such a world?” Does this approach really provide, as Latour phrases it, “a way to bridge the distance between the scale of the phenomena we hear about and the tiny Umwelt inside which we witness, as if it were a fish inside its bowl, an ocean of catastrophes that are supposed to unfold”? Ultimately, Vital Reenchantments argues that affective ecologies, properly attended to, point toward an open present, one that broadens the horizons of the “fish bowl” and allows us to imagine engendering futures that are neither naively hopeful nor hopelessly apocalyptic.

Voices from Nubia: Critical Essays on Contemporary Nubian Literature from Egypt - Amal Mazhar; Faten I. Morsy; Mona M. Radwan (punctum books, 2024)
The Nubians, the largest ethnic community in Egypt, saw their ancestral homelands disappear beneath the waters of the Nile from the dawn of the 20th century through to 1964. The massive displacement of this population has been the subject of numerous literary works by Nubian writers who seek to save their heritage from oblivion and to preserve their Nubian collective memory. Despite the renewal of socio-political interest in Nubia in post-2011 Egypt, the authors of Voices from Nubia, all non-Nubian Egyptians, claim that art in general and literature in particular remain the domain in which the problematics of what has been called the Nubian Question can be primarily vocalized. Only through a thorough reading and analysis of the literary output of Egyptian Nubians can the complexities of Nubia, its people, and culture can find full expression. The rich literary heritage of contemporary Nubian literature allows for a multiplicity of critiques that makes possible a reading of this literature that crosses the borderlines between literature, history, geography, politics, gender, and ethnicity. The diversity of themes and tropes in Voices from Nubia reflects a hallmark of Nubian literary output which is generally marked by a common feeling of solidarity around the Nubian cause. The array of critical studies included in the volume’s eight chapters covers a multiplicity of approaches: cultural, postcolonial, ecofeminist, and critical race theory. Voices from Nubia constitutes an attempt to go beyond the dichotomy between the activist Nubian writer who views the Nubian Question as a human rights issue and Arab-Egyptian nationalists who consider the discussion of Nubians as a distinct ethnic group or minority a threat to societal cohesion and national security. The editors conclude the book with interviews with three Egyptian Nubian writers belonging to different generations and expressing different positions with regards to the Nubian Question. It is thus hoped that this book will introduce the English-speaking reader to the rich tradition of contemporary Nubian literature from Egypt, written in Arabic. On the other hand, the book also forces the Egyptian-Arab reader to question some of the most cherished assumptions and ingrained ideas about the nature of culture, history, and identity. As such, Voices from Nubia has far-reaching implications for how we think about the diverse nature of our societies and nations.

Voix de Glace / Voice of Ice - Alta Ifland (punctum books, 2025)
Voix de Glace/Voice of Ice is a series of prose poems about the estranged self living outside of one’s native land and away from one’s native tongue. Romanian poet Alta Ifland writes first in French, then translates her work into English, before returning to the original French for further revisions, a process of linguistic reconciliation as much as translation. Published in a bilingual, French–English edition, Ifland repeatedly turns to remembered images of her unnamed homeland to animate her unfamiliar home, creating, what poet Gary Young calls “a brilliant collection of prose poems document[ing] the quest for a coherent self, an authentic identity born out of the chaos of language and history.” He continues, “Ifland’s poems trace a radical process of de-creation—dismemberment of the body, dissolution of the ego, abandonment of the self—and the reinvention of a new identity, purified by the acid of tears. This new creation—tentative and rarified, ‘a child’s body of light’—earns a tenuous existence, but it proves to be enough to withstand the omnipresent threat of oblivion.” Voix de Glace/Voice of Ice won the 2008 Prix Louis Guillaume du Poème en Prose/Louis Guillaume Prize for Prose Poetry. This title is a second revised and expanded edition with a new introduction by John Taylor, released as part of punctum’s Special Collections (https://punctumbooks.pubpub.org/pub/punctum-introduces-special-collections-les-figues/) project.

Walk on the Beach: Things from the Sea, Volume 1 - Maggie M. Williams; Karen Eileen Overbey (punctum books, 2016)
This volume brings together writing and imagery from the experimental “beachwalk” session(s) at the Third Biennial Meeting of the BABEL Working Group, On the Beach: Precariousness, Risk, Forms of Life, Affinity, and Play at the Edge of the World (https://babel-meeting.org/2014-meeting/). We began with conversations about the sea. We meditated together on chance, discovery, agency, beauty, and material ecology. We talked about the delicate care of treading the world, the confluence of the personal and the professional, and the possibilities of storytelling. We thought about what happens when we encounter stuff, when we take it, change it, do something with it. When we display it, or sculpt it, or collect it. When we make something an object, and an object of looking. Then we met on the beach. We walked and talked about loss, home, agency, and liminality. We collected things: We picked up stones, feathers, seaweed. We pointed to stuff, gathered it, let it strike our fancy. Every shell nurtured a conversation among the artists, scientists, historians, poets, archivists, surfers, philosophers, and pirates who had joined the walk. We brought the sea-things back, manipulated them, and displayed them as works of art. Walk on the Beach is a souvenir of that project, a record of our bounty. It emerges from the process at the heart of art historical work: close looking. Thinking through objects, thinking with objects. Letting the things help us tell their stories. This is a tiny collection of looking, together.

Warez: The Infrastructure and Aesthetics of Piracy - Martin Paul Eve (punctum books, 2021)
When most people think of piracy, they think of Bittorrent and The Pirate Bay. These public manifestations of piracy, though, conceal an elite worldwide, underground, organized network of pirate groups who specialize in obtaining media–music, videos, games, and software–before their official sale date and then racing against one another to release the material for free. Warez: The Infrastructure and Aesthetics of Piracy is the first scholarly book about this underground subculture, which began life in the pre-internet era Bulletin Board Systems and moved to internet File Transfer Protocol servers (“topsites”) in the mid- to late-1990s. “The Scene,” as it is known, is highly illegal in almost every aspect of its operations. The term “Warez” itself refers to pirated media, a derivative of “software.” Taking a deep dive into the documentary evidence produced by the Scene itself, Warez describes the operations and infrastructures of an underground culture with its own norms and rules of participation, its own forms of sociality, and its own artistic forms. Even though forms of digital piracy are often framed within the positive ideological terms of equal access to knowledge and culture, Eve uncovers in the Warez Scene a culture of competitive ranking and one-upmanship that is at odds with the often communalist interpretations of piracy. Broad in scope and novel in its approach, Warez is indispensible reading for anyone interested in recent developments in digital culture, access to knowledge and culture, and the infrastructures that support our digital age.

War Machine - Richard A. Carter (punctum books, 2026)
War Machine is a speculative sounding of the myriad entanglements of technology, ecology, discourse, politics, and conflict shaping the contemporary environment. Taking the tools of geopolitical competition and control as its formal and conceptual basis—wargame simulations, artificial intelligence, weaponised drones, territorial enclosure, and extractivist economics—War Machine presents a series of digitally simulated conflicts over the most ecologically vulnerable areas of the Earth, using the data gathered to generate hybrid visual poems that stand in for the multitude of political, conceptual, and economic battles that are presently raging across the face of a profoundly endangered planet. A hybrid work of generative criticism and poetry, War Machine depicts the intensive complexities of the present moment through conducting an experimental textual performance, attempting to enfold and perform, rather than simply describe, challenging conjunctions of competing discourses and activities. The resulting stream of outputs and interpretive potentials preclude the ascendency of any “definitive” critical narrative, refusing any straightforward integration with existing canons of worldly diagnosis, but also illustrating opportunities for resistant play and critical-creative possibility within the uncertainty. The consciously unconventional gesture at the heart of War Machine is in attempt at modelling an adventurous, forward-facing approach, in both thought and practice, that refuses inaction when dealing with otherwise devastating scenarios. It is an approach that acknowledges head-on myriad worldly harms, seemingly insurmountable, while still contributing to the aesthetic, affective, and conceptual foundations from which alternative modes of knowing, being, and meaning are developed and justified.

Waste: Capitalism and the Dissolution of the Human in Twentieth-Century Theater - Jessica Rizzo (punctum books, 2020)
If at its most elemental, the theater is an art form of human bodies in space, what becomes of the theater as suicide capitalism pushes our world into a posthuman age? Waste: Capitalism and the Dissolution of the Human in Twentieth-Century Theater traces the twentieth-century theater’s movement from dramaturgies of efficiency to dramaturgies of waste, beginning with the observation that the most salient feature of the human is her ability to be ashamed of herself, to experience herself as excess, the waster and the waste of the world. By examining theatrical representations of capitalism, war, climate change, and the permanent refugee crisis, Waste traces the ways in which these human-driven events signal a tendency toward prodigality that terminates with self-destruction. Defying its promise of abundance for all, capitalism poisons all relationships with competition and fear. The desire to dominate in war is revealed to be the desire to obliterate the self in collective conflagration. The refugee crisis raises the urgent question of our responsibility to the other, but the climate crisis renders the question of anthropocentric obligations moot. Waste proposes that the theater is the form best suited to confronting the human’s perverse relationship to its finitude. Everything about the theater is suffused with existential shame, with an acute awareness of its provisionality. Unlike the dominant narrative of the human, which is bound up with a fantasy of infinite growth, the theater is not deluded about its nature, origins, and destiny. At its best, the theater gathers artist and audience in one space to die together for a little while, to consciously waste, and not spend, their time.

Weaponising Speculation - Caoimhe Doyle (punctum books, 2014)
This book contains the proceedings from Weaponising Speculation (http://dublindust.wordpress.com/2013/01/16/weaponising-speculation-schedule/), a two-day conference and exhibition that took place in Dublin in March 2013. Weaponising Speculation was organised by D.U.S.T. (Dublin Unit for Speculative Thought) and aimed to be an exploration of the various expressions of DIY theory operative in the elsewheres, the shafts and tunnels of the para-academy. The topics covered all come under the welcoming embrace of speculation, spanning a broad range: from art, philosophy, nature, fiction, and computation to spiders, culinary cosmology, and Oscar the Grouch. The book itself aims to be more than just a collection of essays and catalogue of artworks, but also a documentation of the event as a whole. An object that both those present at the event and those who missed it would want to own — bringing something new to both sets of readers. The range of topics covered in this collection, along with the added elements of design and photography, result in a book that appeals beyond the (para)academic circle within which the Speculative Realist community currently resides. One of the original aims of the Weaponising Speculation conference, and by extension, the book, is to expand what might be considered the expected reach of the subject, bringing Speculation to a new audience — artists, designers, fans of fiction, photographers, biologists, film theorists, comedians, culinary artists, illustrators, computer programmers, and individuals from any number of fields. Before the storms the para-academic needs to equip herself. Not only with tools, but weapons. In this way this collection is not only a book to read, an object to own, or a tool for learning, but a weapon with which to break open academic discourse, to invade and conquer as yet unknown territory, and to aid thinkers in the siege to reclaim the real.